Gloeotrichia echinulata genomes from the United States are nontoxigenic and likely geosmin producers - Theo W. Dreher; Robin Sleith; Edward W. Davis; Ryan S. Mueller; Peter D. Countway (Harmful Algae, 2026)

Multi-level biomarker responses to potentially toxic elements (PTEs) contamination in a coastal bivalve from the Maharashtra coast, India - Shubra Singh; Diganta Dey; M. Harshavarthini; Edward Inpent Campal; Saurav Kumar; Nalini Poojary; Manoj Pandit Brahmane; Ashok Kumar Jaiswar; Naresh S. Nagpure (Marine Pollution Bulletin, 2026)

Beyond the dung heap: the reliability of spores of the ascomycete fungal genus Sporormiella (incl. Preussia) as a proxy indicator of dung and grazing animals - David L. Hawksworth; Patricia E.J. Wiltshire; K. Anupama; M.B. Govinda Rajulu; N. Thirunavukkarasu; S. Prasad; Kevin J. Edwards; T.S. Suryanarayanan (Review of Palaeobotany and Palynology, 2026)

Triploid sablefish (Anoplopoma fimbria) display marked inhibition of female reproductive development and female skewed sex ratios through sex reversal of genotypic males - Jamie L. Mankiewicz; Edward S. Hayman; William T. Fairgrieve; J. Adam Luckenbach (Aquaculture, 2026)

Corrigendum to “Mapping long-term soil organic carbon stocks across the conterminous United States with machine learning” [Environ Res. 306 (2026) 125271] - Hannah J. Rubin; Xinxin Zhang; Joshua S. Fu; T. Edward Yu (Environmental Research, 2026)

Mapping long-term soil organic carbon stocks across the conterminous United States with machine learning - Hannah J. Rubin; Xinxin Zhang; Joshua S. Fu; T. Edward Yu (Environmental Research, 2026)

Multiphysics modeling of high-surface area carbon supports for polymer electrolyte fuel cells - Alper Can Ince; Mustafa Fazil Serincan; Siddharth Komini Babu; Jacob S. Spendelow; Edward F. Holby; Ugur Pasaogullari; Wilton J.M. Kort-Kamp (Chemical Engineering Journal, 2026)

Animal responses and physiological indicators of stress in late pregnant alpacas on cultivated pastures in the High Peruvian Andes - Diannett Benito López; Laura B. Gualdrón-Duarte; Rassiel Macedo Sucari; Guadalupe Orellana Ligas; Yemi Sanca Uscamayta; Feliciano Rivera Pachiño; Nancy F. Huanca-Marca; Francisco E. Franco; Rubén García-Ticllacuri; Joel Pacheco Curie; Bernardo Roque Huanca; Víctor M. Vélez-Marroquín; et al. (Tropical Animal Health and Production, 2026)

Probiotic Characterization of Honey Bee-Associated Lactic Acid Bacteria and Their Impact on Colony Growth - Subramanian Pradeep; Y. S. Johnson Thangaraj Edward; Vangili Ramasamy Saminathan; Angappan Suganthi; Murugaiyan Senthilkumar; Narayanan Manikanda Boopathi; Venkatachalam Karthik; Bimal Kumar Sahoo; Mohammad Ikram (Probiotics and Antimicrobial Proteins, 2026)

Climate-driven regime shift associated with range contraction at warm range edge of Macrocystis pyrifera forests - Marisol Atela; Jeremie Bauer; Rodrigo Beas-Luna; Alicia Abadía-Cardoso; Mark H. Carr; Dillon Dolinar; Matthew S. Edwards; Luis Malpica-Cruz; Nemer E. Narchi; Kyle Cavanaugh; Julio Lorda (Marine Biology, 2026)

Cyanide-Triggered Fluorescence Turn-On in an Indole-Based Chemodosimeter - V. Raju; J. Edward Jeyakumar; Gujuluva Gangatharan Vinoth Kumar; Anil Kumar Thandlam; Baburao Gaddala; S. Ayyanaar; Anjaneyulu Mamindla (Journal of Fluorescence, 2026)

Simulation modelling as a tool to guide control strategies for foot and mouth disease in an endemic country: Nusa Tenggara Barat, Indonesia 2023–2024 - Y. Yupiana; M.A. Stevenson; M. Edwards; R.V. Ekowati; Ermawanto; I. Permatasari; R. Morita; S. Yulianti; Nurhayati; T.D. Utami; D. Nugroho; H.P. Kurniawan; et al. (Preventive Veterinary Medicine, 2026)

Novel sustainable graphitic carbon nitride (g-C3N4) photocatalytic approach for treatment of saxitoxin contaminated water - Diana S Moura; Indira Menezes; Nuruddin Mahadik; Christine Edwards; Linda A Lawton (Harmful Algae, 2026)

Shoulder Kinematic and Muscle Activity Compensations to Scapular Stabilizer Weakness: An Optimal Control Framework - Matthew S. Russell; Daanish M. Mulla; Peter J. Keir; Edward K. Chadwick; Dimitra Blana; Janessa D. M. Drake; Jaclyn N. Chopp-Hurley (Annals of Biomedical Engineering, 2026)
Purpose Shoulder kinematic and muscular redundancy promotes considerable variability, obscuring possible insights into neuromuscular control and compensation mechanisms for muscle weakness or fatigue. The current study harnessed recent advancements in optimal control formulations for computational musculoskeletal models to determine potential neuromuscular control strategies to compensate for isolated muscle weakness. Methods A computational shoulder model characterized by independent clavicular, scapular, and humeral kinematics and 138 muscle elements was used. Optimal control-predicted thoracohumeral elevation kinematics were validated against published empirical kinematics. Force-generating capacity of the upper trapezius, middle trapezius, and lower trapezius, and serratus anterior were individually limited to 75%, 50%, and 25% maximal capacity to generate subsequent optimal control predictions of scapulothoracic kinematic changes associated with muscle weakness. Combined limited maximal force-generating capacity of lower trapezius and serratus anterior was also explored. Results Model-predicted scapulothoracic kinematics showed good agreement with reference data, yet some significant differences were identified below 55° thoracohumeral elevation. Fatigue-mediated kinematic changes were most apparent during sagittal plane elevation. Serratus anterior weakness displayed the largest scapulothoracic kinematic changes at all thresholds of limited force-generating capacity. It also prompted the largest compensatory muscle activity changes from other shoulder muscles, while upper trapezius weakness prompted very little compensatory changes in muscle activity. Conclusion Optimal control simulations were used to identify potential compensation mechanisms for shoulder muscle weakness and predict their effects on scapular kinematics. Findings suggest that thoracohumeral elevation in the scapular plane displayed less trapezius coactivity, both when ‘weakened’ and ‘unweakened.’ Thus, scapular plane tasks may isolate serratus anterior, while frontal plane tasks may achieve more balanced coactivation.

Emergence of heartbeat frailty in advanced age II: individual cardiovascular aging trajectories revealed by lifelong echocardiography in male mice - Ismayil Ahmet; Nolan M. Winicki; Jacob S. Roberts; Christopher H. Morrell; Edward G. Lakatta (GeroScience, 2026)

Managing brackish water to boost wheat and barley yield, water productivity, and maintain soil solute potential in the Ganges Delta - Khokan Kumer Sarker; Mohammed Mainuddin; Richard W. Bell; Edward G. Barrett-Lennard; Mark R. Glover; M. A. Hossain; S. S. A. Kamar; M. M. R. Sarker; Priya Lal Chandra Paul (Irrigation Science, 2026)

Correction: Structure–Function Parameters Over Different Surface Footprints in Coastal Zones - Andrey A. Grachev; Harindra J. S. Fernando; Stef L. Bardoel; Robb M. Randall; Christopher M. Hocut; Edward D. Creegan; Laura S. Leo (Boundary-Layer Meteorology, 2026)

Mixed Support for Pleistocene Sea‐Level Fluctuations in Promoting the Diversification of Anole Lizards in the Northern Lesser Antilles - Ayanna J. Browne; Edward A. Myers; S. Blair Hedges; Kevin de Queiroz; Robert Powell; Lauren A. Esposito; Rayna C. Bell; Michael L. Yuan (Molecular Ecology, 2026)
In the Pleistocene, climatic changes resulted in cycles of sea‐level fluctuation that periodically fragmented islands into aggregate island complexes. These temporary saltwater barriers between islands within an island bank had the potential to decrease migration between populations on separate islands, resulting in increased genetic divergence and potentially speciation. In the Lesser Antilles, Anolis lizards (anoles) are distributed across island banks that vary in distance and water depth between islands, making them excellent candidates for studying how different barriers shape patterns of genetic diversity. Here, we focused on anoles found across the St. Kitts Bank ( A. bimaculatus , A . schwartzi ), Anguilla Bank ( A. gingivinus ), and Barbuda Bank ( A. leachii , A. wattsi ) to test the hypothesis that populations separated by narrower and shallower marine barriers are more genetically similar to one another than populations on more distant islands or those separated by deeper water. Using a combination of mitochondrial and nuclear genomic DNA, we found a spectrum of population genetic structure ranging from weak but detectable structure ( A. gingivinus , Anguilla Bank and A. leachii , Barbuda Bank) to pronounced ( A. bimaculatus and A. schwartzi , St. Kitts Bank) and even species divergence ( A. wattsi complex, Barbuda Bank). The extent of genetic divergence, however, did not consistently correspond to island bathymetry. Our demographic analyses for each currently recognized species supported a model of divergence with gene flow, consistent with a history of intermittent migration between present‐day islands. Collectively, these results support a partial role for sea‐level fluctuations in the Pleistocene structuring current patterns of genetic diversity in Lesser Antillean anoles.

Promoting Research Excellence in Down Syndrome: Proceedings of the 5th International Conference of the Trisomy 21 Research Society - Fabio Di Domenico; Marzia Perluigi; Antonella Tramutola; Maria Giulia Bacalini; Daniella Balduino Victorino; Isabel Barroeta; Renata Bartesaghi; Angelo Carfi; Maria Carmona-Iragui; Ann D. Cohen; Alberto C. S. Costa; Floriana Costanzo; et al. (NeuroMolecular Medicine, 2026)
Down syndrome (DS), or trisomy 21 (T21), represents the most common genetic cause of intellectual disability worldwide and is associated with a wide range of medical, developmental, and neurodegenerative conditions, including a universal predisposition to early-onset Alzheimer’s disease (AD). Since its establishment in 2014, the Trisomy 21 Research Society (T21RS) has provided a global forum for advancing DS research across disciplines and promoting translational efforts to improve health and quality of life. Every two years, T21RS hosts an international scientific meeting that brings together researchers, clinicians, self-advocates, families, and industry stakeholders. In 2024, the 5th T21RS International Conference was held in Rome, Italy, from June 5 to 8, under the theme “Promoting Research Excellence in Down Syndrome.” The meeting brought together about 500 scientists from 26 countries across five continents, and more than 900 attendees overall, including families and caregivers. The scientific program featured 5 keynote lectures, 2 satellite meetings, 17 symposia, 7 nano symposia, 2 workshops, and 1 industry-focused session, totaling more than 150 oral presentations. More than 230 abstracts were presented as posters. The conference covered research across the lifespan of individuals with DS, spanning genomic and epigenetic regulation, molecular and cellular mechanisms, preclinical and experimental models, cognition and behavior, neurodevelopment, aging and neurodegeneration, co-occurring medical conditions, and therapeutic interventions. Dedicated sessions focused on capacity-building in DS research and societal engagement were established. Significantly, T21RS promoted inclusivity by supporting 60 young investigator fellowships, providing childcare awards, and organizing a two-day program for families and caregivers in collaboration with Italian DS associations. This proceeding summarizes the main scientific highlights of the 5th T21RS International Conference, reflecting the latest advances in DS biology, clinical research, biomarker development, and therapeutic innovation.

From the deep sea to the shore: Source fingerprinting and weathering of spilled oil following the 2023 MT Princess Empress oil spill (Oriental Mindoro, Philippines) - Jay Rumen U. Maglupay; Edward S. Yeo; Gerald L. Cordero; Rachel Zioness O. Diputado; Kim Christopher C. Aganda; Rodolfo A. Romarate; Julien Guyomarch; Chin-Chang Hung; Hernando P. Bacosa (Marine Pollution Bulletin, 2026)

Lung function and inflammation in healthy young adults after 6.6 hours of 0.07 ppm ozone exposure - Edward R. Pennington; Jairus C. Pulczinski; Martin W. Case; Jacob S. Griffin; Neil E. Alexis; Ilona Jaspers; Carole Robinette; Ann Chelminski; Andrea Davis; Neena Miller; David B. Peden; Andrew J. Ghio; et al. (Environmental Research, 2026)

Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Cattle habitat selection in response to weather extremes within a native Aspen Parkland rangeland - Sydney G. Lopes; Francisco J. Novais; Cameron N. Carlyle; Carolyn J. Fitzsimmons; John S. Church; Edward W. Bork (International Journal of Biometeorology, 2026)

The Circular Economy has High Potential to Mitigate the Global Biodiversity Crisis - Jianan Xie; Yingtong Zhu; Chloe Yun Yi Tan; Cengiz Akandil; Joanna. L. Coleman; David P. Edwards; Wanggi Jaung; Kelvin S.-H. Peh; Linjun Xie; Shweta Yadav; L. Roman Carrasco (Circular Economy and Sustainability, 2026)

Oases of endemism: Regional aquifer desert springs serve as biodiversity hotspots preserving vulnerable endemic taxa in the Great Basin and Mojave Desert regions - Matthew J. Forrest; Donald W. Sada; Matthew S. Edwards; Robert K. Burton; Richard D. Norris (Limnology and Oceanography, 2026)
Spring ecosystems in arid regions often serve as crucial biodiversity hotspots by providing some of the only reliable sources of surface water. However, anthropogenic activities and climate change have severely degraded spring ecosystems worldwide, emphasizing the need for large‐scale multidisciplinary studies informing conservation efforts. Here, we analyzed characteristics of 1121 widely dispersed springs within the Great Basin and Mojave Desert regions, USA to assess the distribution of endemic animal taxa relative to hydrological, geochemical, and ecological parameters. To our knowledge this is the largest original dataset of springs that has been examined in this manner. Our results revealed that the three broad classes of springs: regional aquifer thermal springs, local aquifer cold springs, and local aquifer geothermal springs can be distinguished by their environmental and physicochemical parameters, taxa present, persistence, and natural and human perturbations. Notably, regional aquifer thermal springs support disproportionate numbers of endemic taxa, likely reflecting their stability and longevity. These patterns are particularly striking considering that these springs have been subjected to extreme anthropogenic exploitation and modifications for centuries and frequently support non‐native taxa. Conversely, local aquifer cold springs, which are often highly disturbed and less persistent, support proportionately fewer endemic taxa. The high abundance of endemic taxa in regional aquifer thermal springs indicates that they represent critical biodiversity hotspots, and efforts to conserve and restore these important ecosystems should be major priorities.

Petrogenesis and Provenance of Unique Amphibole-Bearing Carbonaceous Chondrite Almahata Sitta 202: Further Evidence for a Ceres-Sized, Water-Rich Parent Body - Cyrena A. Goodrich; Victoria E. Hamilton; Michael E. Zolensky; Noriko Kita; Issaku Kohl; Lauren Tafla; Robert J. Macke; Takahiro Hiroi; Yoko Kebukawa; Wayne Buckley; Jacob B. Setera; Justin I. Simon; et al. (Geochimica et Cosmochimica Acta, 2026)

Structure–Function Parameters Over Different Surface Footprints in Coastal Zones - Andrey A. Grachev; Harindra J. S. Fernando; Stef L. Bardoel; Robb M. Randall; Christopher M. Hocut; Edward D. Creegan; Laura S. Leo (Boundary-Layer Meteorology, 2026)
High frequency turbulent data from sonic anemometers and other ancillary information collected at multiple levels on several meteorological flux towers located at two coastal sites are used to study velocity and scalar (temperature and humidity) structure–function parameters over heterogeneous surfaces in an area of complex coastal terrains. Understanding of such parameters has important applications for studies on wave propagation in a turbulent atmosphere. One observational site was located on the Outer Banks near the town of Duck, North Carolina, with data from the CASPER-East Program (October–November 2015). The second site was located near the town of Ferryland, Newfoundland, Canada, with data from the C-FOG (Coastal-Fog) field campaign (September–October 2018). These measurements allowed studies of structure parameters and other statistics for different footprints, including relatively smooth sea surface conditions and aerodynamically rough dry inland areas for both stable and unstable stratifications. The coastal land cover discontinuity for onshore and offshore winds leads to a thin internal boundary layer (IBL) that could often be resolved by the instrumented towers. The drag coefficient, Bowen ratio, and diurnal variation of sensible heat flux were found to be coastal IBL markers. Our study shows that lower values of the dimensional structure parameters are associated with higher altitudes, smooth surfaces (i.e., over water, outside onshore IBL) and stable stratification (e.g., nocturnal boundary layer), ceteris paribus. In particular, observations showed that the structure parameters over land footprint areas (inside the onshore IBL) can be an order of magnitude larger than over the sea surface due to the change of aerodynamic and thermal properties of the surface. This study also discusses the applicability of Monin–Obukhov similarity theory (MOST) for the velocity and scalar structure parameters in the coastal environment for both stable and unstable conditions. While surface inhomogeneities and the complexity of the coastal landforms nominally violate assumptions underlying MOST, our observations show that the nondimensional structure parameters obey MOST reasonably well for all measurement levels, stability condition, and wind direction. In addition, we suggest a new variance-based hybrid scaling for the structure parameters that overcomes some of the shortcomings of the traditional approach (e.g., self-correlation and ambiguity of the dimensionless temperature structure parameter for near-neutral conditions).

Evaluation of siRNA-mediated knockdown of heat shock protein 16.2 in adult Acropora cervicornis - Edward P. Gniffke; Benjamin D. Young; Keir J. Macartney; Michael S. Studivan; Ian C. Enochs; Erin E. Easton (Frontiers in Marine Science, 2026)
Acropora cervicornis is a critically endangered Caribbean coral species facing a precipitous decline due to disease and thermal bleaching. To combat the loss of ecologically important reef-building corals, novel molecular approaches can be used to understand mechanisms of resilience and ultimately provide a means to modulate coral performance. In this study, we tested a recently developed method for gene knockdown in adult corals that utilizes short interfering RNAs (siRNAs) and the RNA interference pathway. The Heat Shock Protein 16.2 (HSP16.2) gene in fragments of adult A. cervicornis was targeted for knockdown using a single siRNA construct. RT-qPCR analysis of HSP16.2 gene expression was performed between filtered seawater, no template control siRNA (NTC), and siRNA targeting HSP16.2 across four genotypes of A. cervicornis with known differences in thermal susceptibility (two heat-tolerant and two heat-susceptible genotypes). There was no significant difference in HSP16.2 gene expression due to the treatment of HSP16.2 siRNAs versus controls, but we did identify a single genotype-driven effect that corroborates evidence that A. cervicornis heat tolerance is driven largely by genotype. No difference in photophysiological performance or mortality was observed between experimental and control treatments. There were, however, some differences in mortality and HSP16.2 expression among genotypes. Our results reveal that siRNA-mediated knockdown was not successful for this species and gene and thus further optimization is needed prior to broader applicability of siRNA-mediated knockdown in corals. We provide an assessment of potential methodological improvements to support the development of future reverse-genetics studies in corals.

Lake sturgeon ( Acipenser fulvescens ) growth and longevity estimated from adult capture–mark–recapture data - Edward A. Baker; Scott F. Colborne; Nancy A. Auer; Kim T. Scribner; Douglas L. Larson; Andrew S. Briggs; Ronald M. Bruch; Margaret H. Stadig; Michael C. Donofrio (Journal of Fish Biology, 2026)
Effective fishery management policy depends on accurate life‐history data, particularly for harvested species. Longevity is a core life‐history trait that is directly related to annual survival and lifetime reproductive potential, but fish longevity is generally not well documented, particularly for long‐lived species. We used capture–mark–recapture data spanning 44 years as an alternative method to estimate sex‐specific adult lake sturgeon ( Acipenser fulvescens ) average annual growth and longevity for five populations in the Laurentian Great Lakes. We determined individual fish average annual growth and fit population and sex‐specific exponential lines for average annual growth as a function of fish length at initial capture. We used the exponential equations to estimate age for 180 cm fork length (FL) female and 160 cm FL male lake sturgeon from each population by sequential subtraction of annual growth increments and assuming age at onset of sexual maturity of 24 and 15 years for females and males, respectively. Average annual growth estimates varied between sexes and among populations and ranged from 0.26 to 1.15 cm year −1 . Estimated ages also varied among populations. Age estimated for a 160 cm FL male lake sturgeon across the five populations ranged from 90 to 279 years. Age for a 180 cm FL female across populations ranged from 99 to 427 years. Our data suggest lake sturgeons live much longer than currently believed. High longevity and inferentially higher adult survival have important implications for sturgeons in general and support conservative harvest regulations for lake sturgeon fisheries.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Just a good thing to have: Stakeholder support for a long-running marine stock enhancement program is based on broad criteria and only weakly contingent on biological outcomes - Susana Hervas; Theresa S. Talley; Ashleigh Palinkas; Edward V. Camp; Joy Hazell; Kai Lorenzen (Fisheries Research, 2026)

Age of the Acraman impact ejecta layer in the adelaide superbasin and Implications on clay-mineral provenance from the Rb–Sr systematics of middle Ediacaran shales - Alan S. Collins; Morgan L. Blades; Darwinaji Subarkah; Holly Cooke; Lesley Edwards; Chelsea Forbister; Jake Jolly; Jarred C. Lloyd; Sarah E. Gilbert; Stefan Löhr; Juraj Farkaš; Victor Gostin (Precambrian Research, 2026)

A laboratory-based spectrometer intercomparison for the measurement of snow spectra - Benjamin M. Roberts-Pierel; Christopher J. Crawford; Steven W. Brown; Raymond F. Kokaly; Kelly E. Gleason; Anne W. Nolin; Edward H. Bair; Brenton A. Wilder; Anton J. Surunis; S. McKenzie K. Skiles; Joachim Meyer; Allyson E. Fitts; et al. (Cold Regions Science and Technology, 2026)

Particulate nitrate over the Northwest Atlantic: Insights gained by comparing airborne AMS and PILS measurements - Soodabeh Namdari; Taiwo Ajayi; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Eva-Lou Edwards; Johnathan W. Hair; Christopher A. Hostetler; Simon Kirschler; John B. Nowak; Michael Shook; et al. (Atmospheric Environment, 2026)

A permeating threat of microplastics on insects and their ecological roles - Keerthana Alagesan; Logeshwaran Panneerselvan; Murugan Marimuthu; Sivasubramanian Karuppusamy; Y. S. Johnson Thangaraj Edward; Jayakanthan Mannu; Balasubramani Venkatasamy; Thava Palanisami (International Journal of Environmental Research, 2026)

Drivers of aquatic zoosporic parasites in natural and artificial environments - Maya Stoyneva-Gärtner; Hans-Peter Grossart; Thijs Frenken; Dirk S. Schmeller; Laura Garzoli; Serena Rasconi; Elżbieta Wilk-Woźniak; Albert Reñé; Slawek Cerbin; Cécile Lepère; Caio César Pires de Paula; Adeline Loyau; et al. (Aquatic Sciences, 2026)

Integrated Immunogenicity Assessment of a Novel, First-in-Class TrenibotulinumtoxinE Across 5 Clinical Trials for Glabellar Lines - Steve Yoelin; Edward Lain; Marion Moers-Carpi; Michael Gold; David Wirta; Wayne Lam; Amy S. Weitzenfeld; Jie Shen; Mitalee Tamhane (Toxicon, 2026)

First record of Cassiopea xamachana ephyrae from the wild in India, with insights into its life history and development - L. Ranjith; Raju Saravanan; K.S. Sobhana; I. Jagadis; S. Ramkumar; C. Kalidas; D. Linga Prabu; M. Kavitha; P. Nevathitha; A. Mathan Babu; D. Sarathapriya; L. Loveson Edward; et al. (Regional Studies in Marine Science, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Delta-X: An airborne remote sensing framework to calibrate hydrodynamic and ecogeomorphic processes responsible for land building in coastal deltas - Marc Simard; Cathleen E. Jones; Robert R. Twilley; Edward Castañeda-Moya; Sergio Fagherazzi; Cédric G. Fichot; Michael P. Lamb; Paola Passalacqua; Tamlin M. Pavelsky; David R. Thompson; Saoussen Belhadj-aissa; Pradipta Biswas; et al. (Remote Sensing of Environment, 2026)

Extracellular enzyme activities under adaptive multi-paddock and conventional grazing in grassland soils of western Canada - Dauren Kaliaskar; Edward W. Bork; Cameron N. Carlyle; Bharat M. Shrestha; Timm F. Döbert; Cole D. Gross; Upama Khatri-Chhetri; Mark S. Boyce; Scott X. Chang (Pedobiologia, 2026)

Associations between exposure to environmental pollutants, metabolic syndrome risk, and obesity-related anthropometric indices - Iman Al-Saleh; Rola Elkhatib; Reem Alswayeh; Reem Al-Rouqi; Mawadah Baali; Yara Aljerayed; Sophia S. De Padua; Hissah Alnuwaysir; Ghada Hussein; Habiba Sultana; Naveed Yousaf; Abass Waqar; et al. (International Journal of Hygiene and Environmental Health, 2026)

Earlier transplanting increases Boro rice yield and water productivity by minimizing exposure to high temperature and salinity in the coastal Ganges Delta - Priya Lal Chandra Paul; Richard W. Bell; Edward G. Barrett-Lennard; Mohammed Mainuddin; Donald S. Gaydon; Mark Glover; Marta Monjardino; Debjit Roy; Md. Belal Hossain; Md. Nazrul Islam; Sukamal Sarkar (Field Crops Research, 2026)

Performance evaluation and methods comparison of transcriptomic-based approaches for the characterization of wastewater treatment effluent - Adam D. Biales; Morgan S. Hu; David C. Bencic; Mary Jean See; Susan T. Glassmeyer; Edward T. Furlong; Julia M. Stelman; Weichun Huang; Dana W. Kolpin; Marc A. Mills; Laura D. Brunelle; Angela L. Batt; et al. (Environmental Pollution, 2026)

Acoustic Indices Reveal Fundamental Differences in Daily Phenology of Tropical and Temperate Forest Soundscapes - Laura M. Berman; Santiago Perea; H. S. Sathya Chandra Sagar; Maia Persche; Grace Ingram; Tatiana Maeda; Natalie Yoh; Jorg Müller; Jens Schlüter; Nicolas Zapata; Ciara Wirth; Gonzalo Rivas‐Torres; et al. (Global Ecology and Biogeography, 2026)
Aim Forests support the majority of the planet's terrestrial biodiversity, and in recent years the characterisation of soundscapes has emerged as a powerful tool for understanding forest ecosystems, both in terms of ecology and for the purpose of conservation. But it is still poorly understood to what extent generalisations can be made about soundscapes in different parts of the world, and to what extent we should expect soundscapes to differ regionally. Here, we characterise the dominant acoustic features of forest soundscapes on a global scale and establish baseline expectations for how acoustic indices vary among biogeographic realms and biomes. Location Forests in Brunei, Ecuador, Gabon, Germany, Peru, Singapore, Sierra Leone and the USA, a dataset spanning two biomes and five out of six global biogeographic realms where forests occur. Time Period Two to five weeks of continuous audio data from each site collected between 2020 and 2024. Major Taxa Birds, amphibians, insects and mammals. Methods Stratifying data by time and frequency, we calculated four acoustic indices. Principal components analysis was used to compare the similarity of soundscapes across sites. Results Temperate and tropical forest soundscapes clustered separately in principal component analysis. Temperate forests had soundscapes which were uniformly loud during the day across all frequencies and were generally quiet at night. In contrast, all tropical locations had complex soundscapes during both day and night and had banding patterns suggestive of a high diversity of soniferous insects. These banding patterns were created by the unique soniferous community at each site, causing the ‘acoustic fingerprint’ of each site to be most similar to other sites in the same ecoregion and in the same biogeographic realm. The ‘acoustic fingerprints’ of temperate forest differentiated between ecoregions only when dawn was considered separately. Main Conclusions Our results stress the importance of using regional specific baseline data, as soundscapes are not necessarily comparable. Ecoacoustics is growing in popularity as an ecosystem monitoring tool, and understanding how forest soundscapes vary naturally across the globe can provide much needed context for studies that seek to understand factors that may disrupt or alter those soundscapes.

Endoluminal Catheter Pulsed Field Ablation for the Treatment of Atherosclerotic Vascular Disease - Zaid S. Salameh; Edward J. Jacobs; Rafael V. Davalos (Annals of Biomedical Engineering, 2026)
Purpose Atherosclerotic vascular disease remains a leading cause of morbidity and mortality worldwide. Current treatments such as angioplasty, stenting, and atherectomy are invasive and limited by restenosis, thrombosis, and incomplete long-term efficacy. Pulsed field ablation (PFA), a nonthermal electroporation-based modality, has demonstrated safety in other cardiovascular applications, but it has not been applied for the treatment of endoluminal vascular diseases. We investigated whether pulsed electric fields could be delivered within the coronary artery and if PFA could selectively ablate the cellular components of atherosclerotic plaques. Methods An endoluminal bipolar PFA probe was fabricated using a balloon catheter with flexible electrodes and evaluated in potato and ex vivo porcine hearts. The electrical conductivities of human atherosclerotic plaques were derived from previous impedance measurements for patient-specific multi-tissue and single-cell electroporation modeling. PFA was then evaluated for selective decellularization within an electrical conductivity-matched 3D fibrotic atherosclerosis tissue mimic using high concentrations of human macrophages and aggregated oxidized low-density lipoproteins, encapsulated within a collagen matrix. Results Endoluminal probe positioning and high-voltage pulsed electric field delivery feasibility was established within the porcine left coronary arteries, with susequent potato lesions experiments demonstrating maximum ablations (6.99 cm 2 ) and current (13 A) with equal treatment parameters. The multi-tissue model then indicated that endoluminal PFA can effectively cover > 95% of severe and thick plaques with irreversible electroporation, with single-cell modeling supporting the electroporation of foam cells within the plaque. The 3D atherosclerosis mimic validated the ability of PFA to completely ablate the foam cells with fibrotic tissue at > 1000 V/cm. Conclusions This study provides practical demonstration of PFA for the treatment of atherosclerotic vascular disease. By combining experimental validation with computational modeling, we establish proof-of-concept that endoluminal PFA can selectively ablate diseased cells while preserving extracellular architecture, laying the groundwork for future translational development of this therapy.

Cardiovascular risk factors and vascular neuropathological findings in primary age-related tauopathy versus Alzheimer’s disease - Lisa Y. Xiong; Myuri Ruthirakuhan; Si Won Ryoo; Che-Yuan Wu; Jodi D. Edwards; Jennifer S. Rabin; Maria Carmela Tartaglia; Sandra E. Black; Julia Keith; Walter Swardfager (GeroScience, 2026)

A Sensitive Schiff Base Probe for UV-visible Spectral and Colorimetric Detection of Cu2+, Al3+, and Fe3+: Spectroscopic and DFT Studies - Gujuluva Gangatharan Vinoth Kumar; Munusamy Settu; J. Edward Jeyakumar; Hari Kumar S; V. Raju (Journal of Fluorescence, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Label-free non-destructive spectroscopic detection of mixed microplastic uptake and differential effects on intestinal epithelial cells - Charlotte E. Sofield; Edward Attenborough; Ryan S. Anderton; Anastazja M. Gorecki; Li Shan Chiu; Chidozie C. Anyaegbu; Kamila Kochan (Journal of Hazardous Materials, 2026)

An updated transketolase activity assay to probe thiamine utilization in fish - Katie A. Edwards; Dennis Kleiner; Banshika M. Mangal; Bhavna S. Sonare (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Revealing the Impact of Polystyrene Nanoplastics on Gill Tissues of the Intertidal Clam, Gafrarium Divaricatum (Gmelin, 1791) using Transcriptomics Approach - Edward Inpent Campal; Ezekiel Targain; M. Harshavarthini; Shubra Singh; Kiran D. Rasal; Arvind Sonwane; Rupam Sharma; Mukunda Goswami; Naresh S. Nagpure; Manoj Pandit Brahmane (Marine Biotechnology, 2026)

Effects of action instruction source on the sense of agency: humans vs. artificial agents - Salina Edwards; Sukhvinder S. Obhi (Experimental Brain Research, 2026)

Emerging organic pollutants in sediments from Lake Victoria: Spatial patterns, sources and ecological risks - Merolyne Natuhwera; Patrick Ssebugere; Kenneth Arinaitwe; Peter Oswald; Edward Mubiru; Florence Nantaba; Zaccheus Shehu; Krištof Urban; Liudmyla Khvalbota; Nikiforos A. Alygizakis; Nikolaos S. Thomaidis; Dimitrios Triantafyllos Gerokonstantis; et al. (Science of The Total Environment, 2026)

The history of Martian water during the Hesperian and Amazonian epochs - Bruce M. Jakosky; Noora R. Alsaeed; Eryn M. Cangi; Michael S. Chaffin; Justin Deighan; Margaret E. Landis; Michael T. Mellon; Edward M.B. Thiemann (Icarus, 2026)

Iono non-hydrothermal (INH) method for synthesis of highly ordered mesoporous silica materials - Hosein Ghaedi; Jiawen Fu; Xin Meng; Yang Liu; Yeshui Zhang; Shakil Ahmed Jiskani; Abdul Raheem; Ming Zhao; Paul S. Fennell; Edward J. Anthony (Chemical Engineering Journal, 2026)

High-temperature CO2 capture and in-situ conversion over bifunctional Na2ZrO3 self-catalyst/sorbent for circular CO production - Ke Wang; Pengfei Zhao; Ting Zhou; Yanjun Wu; Tianyu Wang; Paul S. Fennell; Edward J. Anthony (Chemical Engineering Journal, 2026)

Subsaturated aerosol hygroscopicity over the northwest Atlantic: Impacts of seasonal factors, offshore location, and clouds - Genevieve Rose Lorenzo; Luke D. Ziemba; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Richard A. Ferrare; Simon Kirschler; John B. Nowak; Michael A. Shook; Kenneth L. Thornhill; Christiane Voigt; et al. (Atmospheric Environment, 2026)

Correction to: Granulopoietic Dysregulation in a Patient-Tailored Mouse Model of Barth Syndrome - Elizabeth A. Sierra Potchanant; Maegan L. Capitano; Donna M. Edwards; Baskar Ramdas; Scott Cooper; James Ropa; S. Louise Pay; Aditya Sheth; Paige L. Snider; Hilary J. Vernon; Ngoc-Tung Tran; Reuben Kapur; et al. (Stem Cell Reviews and Reports, 2026)

Epiphytic microbes induced defensive phytochemicals against insects - M. Jayaveni; Y. S. Johnson Thangaraj Edward; A. Suganthi; M. Kannan; R. Anandham; R. Kannan (Phytochemistry Reviews, 2026)

Correction to: Lipopolysaccharide and Morphine-3-Glucuronide-Induced Immune Signalling Increases the Expression of Polysialic Acid in PC12 Cells (PMID- 31646464) - Sameera Iqbal; Lindsay M. Parker; Arun V. Everest-Dass; Edward S. X. Moh; Nima Sayyadi; Mark R. Hutchinson; Nicolle H. Packer (Molecular Neurobiology, 2026)

Achieving the once-unthinkable: Successful Rabi cropping via technology integration in coastal saline Bengal - Donald S. Gaydon; Sukamal Sarkar; Mohammed Mainuddin; Edward G. Barrett-Lennard; Richard W. Bell; Koushik Brahmachari; Md. Maniruzzaman; Buddheswar Maji; Md. Alimur Rahman; Md. Enamul Kabir; Md.Harunor. Rashid; Md. Shahidul Islam Khan; et al. (Agricultural Systems, 2026)

Integration of Multiple Data Types to Document Spatial Effort in a Recreational Fishery for Highly Migratory Species in Relation to Offshore Wind Development - Jeff Kneebone; Matthew Davis; Ryan Knotek; Connor Capizzano; Edward Kim; Camilla T. McCandless; Peter Chaibongsai; Wessley Merten; Eric S. Orbesen (Fisheries Oceanography, 2026)
The expansion of offshore wind interests in US waters has raised concern over potential adverse impacts to fisheries activity and productivity. Yet evidence‐based platforms for assessing those impacts are lacking for many recreational fisheries. We demonstrate how data from a federal fishery survey (Large Pelagics Intercept Survey [LPIS]), cooperative tagging programs, and the direct survey of recreational fishermen can be used to characterize the spatial extent of baseline (pre‐construction) effort in a recreational fishery that targets highly migratory fishes (HMS) in US territorial waters of the Atlantic, Gulf of Mexico, and Caribbean. To document the location of effort, LPIS catch data and tag, release, and recapture (CTR) records from four cooperative tagging programs were independently aggregated onto a grid of offshore wind lease blocks. An online survey of recreational fishermen was also executed to assess the spatial extent of effort in relation to a Draft Call Area (DCA) in the Gulf of Maine region. Collectively, the LPIS and CTR data described widespread recreational fishing effort for HMS, including within and around the majority of existing and planned offshore wind lease areas. Responses to the online survey revealed more widespread effort within the Gulf of Maine DCA than both the LPIS and CTR data, but some respondents may have overrepresented true levels of fishing effort. Our results demonstrate the need for multiple data types to comprehensively assess offshore wind impacts on the recreational HMS fishery and to inform marine spatial planning in regions into which offshore wind energy development may be expanded.

Correction: Importance of near-bottom oceanographic data in modeling the distribution of eulachon bycatch in the U.S. West Coast shrimp trawl fishery - Leif K. Rasmuson; Scott D. Groth; Christopher A. Edwards; Eric S. Anderson; Matthew T.O. Blume; Kendall R. Smith (Frontiers in Marine Science, 2025)

Effects of salinity stress on Acropora sp. and Stylophora pistillata in the Red Sea: A pre-construction risk assessment for desalination plants - Micaela S.S. Justo; Laura Beenham; João Cúrdia; Marta Cunha; Fern Lyne; Rita Bartossek; Carla Leite; Edwin Palmer; Edward Oldmeadow; Raquel S. Peixoto; Rosa Freitas; Michael L. Berumen; et al. (Desalination, 2025)

Fertilizer price hikes, farmers’ willingness to pay and crop switching decision in Ghana - William Adzawla; Oumou Camara; Prem S. Bindraban; Edward Martey; Amadou Gouzaye; Emmanuel Eshun; Emmanuel W. Rachid Zida (Nutrient Cycling in Agroecosystems, 2025)

Regional Genomic and Phylogenomic Insights into Multidrug and Colistin-Resistant Klebsiella pneumoniae Strains from Tanzania, Kenya, Uganda, and Ethiopia - Samweli Y. Bahati; Edward Moto; Abdalah Makaranga; Joseph I. Massawe; Reuben S. Maghembe (Current Microbiology, 2025)

Linking crystal shape and dynamic undercooling: a new framework for inferring magmatic crystallization histories - Amanda Lindoo; Madeleine C. S. Humphreys; Charlotte Gordon; Martin F. Mangler; Edward W. Llewellin; Richard A. Brooker; Fabian B. Wadsworth; Eshbal Geifman (Contributions to Mineralogy and Petrology, 2025)
Magmas contain crystals exhibiting diverse shapes and sizes, yet the relationship between crystal shape (specifically aspect ratio) and undercooling ( $$Δ T$$ ), the driving force for crystallization, remains poorly constrained. Crystal shape should correlate with undercooling because undercooling governs the growth regime (interface-controlled versus diffusion-controlled) and thus the resulting crystal form. Prior experiments confirm that large nominal undercoolings drive transitions from polyhedral to hopper, skeletal, or dendritic forms. Large undercoolings reflect rapid decompression or cooling, differing from slower cooling rates typical of magmatic intrusions and storage systems. In such slowly cooled environments, crystals remain polyhedral, exhibiting subtle shape variations. Accurately quantifying crystal shape evolution at relatively low undercoolings could provide critical insights into crystallization histories, improving interpretations of the timescales and processes governing magma storage and eruption dynamics. Experimental verification of correlations between aspect ratios of polyhedral crystals and cooling rates remains inconclusive, possibly because nominal undercooling neglects the dynamic evolution of undercooling throughout crystallization. To address this, we introduce average instantaneous undercooling ( $$\overline{{Δ T_{I} }}$$ ), a metric capturing dynamic undercooling history during crystallization. Through controlled cooling experiments and numerical modelling, we demonstrate that higher $$\overline{{Δ T_{I} }}$$ histories produce tabular, high aspect ratio plagioclase crystals, whereas lower $$\overline{{Δ T_{I} }}$$ produces more prismatic crystals with lower aspect ratios. These variations in shape reflect undercooling-driven shifts in the predominant growth mechanism operating on different crystal faces. By quantitatively linking crystal shape to $$\overline{{Δ T_{I} }}$$ , our study provides a new approach for reconstructing crystallization histories in magmas under varying pH2O-T-t conditions.

Importance of near-bottom oceanographic data in modeling the distribution of eulachon bycatch in the U.S. West Coast shrimp trawl fishery - Leif K. Rasmuson; Scott D. Groth; Christopher A. Edwards; Eric S. Anderson; Matthew T.O. Blume; Kendall R. Smith (Frontiers in Marine Science, 2025)
Introduction Species distribution models (SDMs) are increasingly used in fisheries science to understand species’ spatial patterns and improve stock assessments. Method This study developed SDMs for eulachon smelt ( Thaleichthys pacificus ), a threatened, demersal forage fish often caught as bycatch in the United States West Coast ocean shrimp trawl fishery. Using ten years of observer data (2012–2021, n=19,749 with 25.4% being zeros), the study assessed the influence of static (e.g., substrate) and dynamic (e.g., ocean temperature, currents) environmental variables on eulachon abundance. Results The best-performing SDM included near-bottom temperature and current data, outperforming SDMs using only surface variables. Eulachon abundance peaked at ~150 m depth, especially over gravel substrates, and during nighttime. Although none of the SDM-based abundance indices significantly correlated with the Columbia River stock assessment index, bottom-based SDMs showed stronger alignment with the stock assessment (R=0.61, p=0.08 & R=0.62, p=0.07). Discussion Management implications are significant. Rock habitats were associated with higher eulachon bycatch, and vessels can use bottom-typing tools to avoid them. Also, delaying the season opener could reduce bycatch, as eulachon catch was reduced by 0.0109 mt per trawl over the interquartile range of day of the year. These findings can inform Best Management Practices (BMPs), which have historically led to regulatory changes such as the adoption of excluder grates and LED lights. Overall, incorporating near-bottom oceanographic data greatly enhanced predictive performance, especially for demersal species like eulachon. These mechanistic SDMs can be projected forward, aiding future management amid changing ocean conditions. While some discrepancies remain, this approach offers promising insights for adaptive fishery management and conservation of imperiled species like eulachon.

Development and application of the Illinois Buckle Risk Model (IBRM) using multi-source track condition data - Neeraj Thakur; Arthur de O. Lima; Marcus S. Dersch; J.Riley Edwards (Transportation Geotechnics, 2025)

Hydrological variability in the Black Sea region during the last 670,000 years recorded in multi-proxy speleothem records from northern Türkiye - F. Held; H. Cheng; R.L. Edwards; T. Kipfer; O. Tüysüz; K. Koç; S. Affolter; D. Fleitmann (Quaternary Science Reviews, 2025)

Heat stress analysis using RTMA over heatwave regions in India - Ch. Sridevi; M. V. S. Ramarao; Ashish Routray; B. Tarakesh Lakshman; K. B. R. R. Hari Prasad; Suryakanti Dutta; D. Srinivas; Edward Colón; Annette Gibbs; Manuel Pondeca; V. S. Prasad (Theoretical and Applied Climatology, 2025)

Functions and clinical implications of the liver microenvironment in hepatic uveal melanoma metastases - Camille J. Cunanan; Alyssa B. Sanders; Kayla C. Gallant; Rino S. Seedor; Edward J. Hartsough (Cancer and Metastasis Reviews, 2025)
Uveal melanoma (UM) is an aggressive intraocular malignancy in adults arising from the melanocytes of the uveal tract. While primary UM lesions can be successfully treated, ~ 50% of UM patients develop metastases primarily in the liver. Patients with liver metastatic UM (LMUM) have poor prognosis and few therapeutic options. LMUM lesions are unresponsive to standard chemotherapies, targeted therapies, and immune checkpoint inhibitors — an effect at least in part associated with the detoxification function of the liver and the diverse hepatic immunological landscape. Here, we recount the etiology and molecular mechanisms in the development of LMUM, examine the influences of the hepatic tumor microenvironment (TME) on UM liver tropism, and review how the innate and peripheral immune response contributes to LMUM progression and therapeutic efficacy. The unique immunological properties of the liver coupled with the distinct growth patterns of LMUM lesions present significant challenges for developing effective treatments that can overcome this specialized microenvironment. Improved understanding of the interplay between the liver and LMUM is essential for the development of more effective diagnostic techniques and improved therapeutic outcomes.

Proof-of-concept for sterility induction in sablefish (Anoplopoma fimbria) via a scalable immersion-based gene silencing approach - Yuzo R. Yanagitsuru; Edward S. Hayman; William T. Fairgrieve; Yonathan Zohar; Ten-Tsao Wong; J. Adam Luckenbach (Aquaculture, 2025)

Granulopoietic Dysregulation in a Patient-Tailored Mouse Model of Barth Syndrome - Elizabeth A. Sierra Potchanant; Maegan L. Capitano; Donna M. Edwards; Baskar Ramdas; Scott Cooper; James Ropa; S. Louise Pay; Aditya Sheth; Paige L. Snider; Hilary J. Vernon; Ngoc-Tung Tran; Reuben Kapur; et al. (Stem Cell Reviews and Reports, 2025)
Barth syndrome (BTHS) is an X-linked recessive disorder characterized by cardiomyopathy, skeletal muscle myopathy and fatigue, growth restriction, and neutropenia. Neutropenia increases the risk of life-threatening bacterial infections, a major cause of death in individuals with BTHS. Currently, there is no curative treatment for BTHS or associated neutropenia. The development of therapeutic strategies to correct BTHS-associated neutropenia has been hindered by a limited understanding of the underlying molecular mechanisms involved. BTHS is caused by a mutation in the Tafazzin gene encoding a transacylase required for the maturation of cardiolipin, an inner mitochondrial membrane phospholipid crucial for mitochondrial structure and function. We introduced a BTHS patient’s point mutation ( TAZ D75H ) into the mouse Tafazzin enzyme’s critical acyltransferase site using CRISPR/Cas9 -mediated genome editing, resulting in a patient-tailored point mutant knock-in BTHS model ( Taz D75H ) that expresses a stable mutant Taz D75H protein lacking transacylase activity. Taz D75H mice were then used to investigate how loss of Tafazzin enzymatic activity impacts hematopoiesis. Male Taz D75H mice exhibited impaired granulopoiesis and neutropenia secondary to impaired function of hematopoietic progenitors. Furthermore, they demonstrated age-dependent neutrophil maturation impairment reflecting the variable neutropenia observed in BTHS patients. Additionally, male Taz D75H mice exhibit chronic lymphopenia that persists post Taz D75H bone marrow transplantation. Mechanistically, the TAZ D75H point mutation caused hematopoietic cell mitochondrial dysfunction in patient-derived immortalized TAZ D75H lymphoblasts, increasing reactive oxygen species production and mitochondrial membrane depolarization. Likewise, Cyclosporine A treatment rescued these mitochondrial phenotypes in vitro, confirming TAZ D75H mitochondrial dysfunction. Overall, our findings demonstrate that mitochondrial dysfunction secondary to TAFAZZIN loss of enzymatic function underlies BTHS-associated neutropenia and lymphopenia.

Unveiling the role of lactic acid bacteria (LAB)-induced volatile in the tritrophic interaction for the management of Plutella xylostella (L.) in cauliflower - M. Jayaveni; Y. S. Johnson Thangaraj Edward; A. Suganthi; M. Kannan; R. Anandham; R. Kannan; J. Kousika (Journal of Plant Diseases and Protection, 2025)

Unveiling the Biocidal Effect of Giant Milkweed, Calotropis gigantea (L.) W.T. Aiton On the Cassava Mealybug, Phenacoccus manihoti Matile-Ferrero - K. Mounisha; Y. S. Johnson Thangaraj Edward; M. Kannan; S. Vellaikumar; D. Uma (Journal of Crop Health, 2025)

Perceived discrimination, trust in physicians, and their associations with ovarian cancer mortality among women in the African American Cancer Epidemiology Study - Lindsay J. Collin; Courtney E. Johnson; Maxwell Akonde; Mary Kan; Elisa V. Bandera; Lauren C. Peres; Bo Qin; Michele L. Cote; Anthony Alberg; Edward S. Peters; Theresa A. Hastert; Joellen M. Schildkraut (Cancer Causes & Control, 2025)
Purpose Black women are 30% more likely to die of ovarian cancer than White women. Discrimination may affect cancer health disparities through pathways including socioeconomic disadvantage, chronic stress, and access to care. In this study, we evaluated associations of discrimination and trust in physicians with all-cause mortality among Black women with ovarian cancer. Methods Using data from the African American Cancer Epidemiology Study (AACES), we included 592 Black ovarian cancer patients who completed an interview. Discrimination and trust in physicians were measured using the Everyday Discrimination, Major Experiences of Discrimination, and Trust in Physicians scales, respectively. We used Cox proportional hazard models to compute multivariable-adjusted hazard ratios (HR) and 95% confidence intervals (CIs) associating everyday discrimination, major experiences of discrimination, and trust in physicians with all-cause mortality. Results Approximately 43% reported experiencing at least one major experience of discrimination, 16% reported high everyday experiences of discrimination, and the median trust in physician score was 35. The association between higher experiences of everyday discrimination was HR = 0.84 (95% CI: 0.63, 1.11), compared with low experiences of everyday discrimination. We observed that more major experiences of discrimination had 1.25-times the mortality rate compared with low experiences of major discrimination (95% CI: 0.84, 2.20). Higher trust in physicians was associated with slightly lower mortality rates (HR = 0.91, 95% CI: 0.74, 1.14). Conclusion We observed complexities in the relationships of everyday discrimination, major experiences of discrimination, and trust in physicians with mortality among Black women with ovarian cancer. Future work to understand the these relationships is likely warranted.

P18-65 Advancing the Grouping and Harmonization of Similar Key Events in the AOP Wiki: Ontology-Based Key Event Component Combinations as Catalysts for Integration - J. Filipovska; K. Audouze; J. Blum; L.-A. Clerbaux; E. Coerek; E. Demuynck; S. Edwards; E. Fritsche; L. Gerner; K. Groh; G. Hench; N. Jeliazkova; et al. (Toxicology Letters, 2025)

P28-16 Assessment of Motor Activity in Rodents: Positive Control Validation using the VivaMARS Mobile Activity Rack System (MARS) - S. Beck; D. Myers; D. Stannard; S. Edwards; A. Hedge; S. Renaut (Toxicology Letters, 2025)

Association of oil spill cleanup-related hydrocarbon exposure with hypertension and blood pressure in the Gulf Long-term Follow-up Study - Opal P. Patel; Jessie K. Edwards; Anna M. Kucharska-Newton; Eric A. Whitsel; W. Braxton Jackson; Kaitlyn G. Lawrence; Patricia A. Stewart; Mark R. Stenzel; Lawrence S. Engel; Dale P. Sandler (Science of The Total Environment, 2025)

Opportunities to better integrate inland fish and fisheries in multilateral environmental agreements - Abigail J. Lynch; Devin Bartley; T. Douglas Beard, Jr.; Gabriel Borba; Steven J. Cooke; Ian G. Cowx; Vittoria Elliott; Holly Embke; Edith Gondwe; Zeb Hogan; Jonathan G. Low; Jamie C. Madden; et al. (Environmental Science & Policy, 2025)

Spatially resolved X-ray imaging and molecular characterisation of sulfur and iron in organic- and sulfur-rich hydrocarbon source mudstones - Yusuf Abubakar; Roy A. Wogelius; Victoria S. Coker; Kevin G. Taylor; Nicholas P. Edwards; Bart E. van Dongen (Chemical Geology, 2025)

Integration of crop modeling and sensing into molecular breeding for nutritional quality and stress tolerance - Jonathan Berlingeri; Abelina Fuentes; Earl Ranario; Heesup Yun; Ellen Y. Rim; Oscar Garrett; Alexander Howard; Mary-Francis LaPorte; Sassoum Lo; Duke Pauli; Jenna Hershberger; Mason Earles; et al. (Theoretical and Applied Genetics, 2025)
Integrating innovative technologies into plant breeding is critical to bolster food and nutritional security under biotic and abiotic stresses in changing climates. While breeding efforts have focused primarily on yield and stress tolerance, emerging evidence highlights the need to also prioritize nutritional quality. Advanced molecular breeding approaches have enhanced our ability to develop improved crop varieties and could be substantially informed by the routine integration of crop modeling and remote sensing technologies. This review article discusses the potential of combining crop modeling and sensing with molecular breeding to address the dual challenge of nutritional quality and stress tolerance. We provide overviews of stress response strategies, challenges in breeding for quality traits, and the use of environmental data in genomic prediction. We also describe the status of crop modeling and sensing technologies in grain legumes, rice, and leafy greens, alongside the status of -omics tools in these crops and the use of AI with directed evolution to identify novel resistance genes. We describe the pairwise and three-way integration of AI-enabled sensing and biophysically and empirically constrained crop modeling into breeding to enable prediction of phenotypic and breeding values and dissection of genotype-by-environment-by-management interactions with increasing fidelity, efficiency, and temporal/spatial resolution to inform selection decisions. This article highlights current initiatives and future trends that focus on leveraging these advancements to develop more climate-resilient and nutritionally dense crops, ultimately enhancing the effectiveness of molecular breeding.

Failure of efficient cardiac proteostatic adaptations to chronic cAMP-stress is associated with accelerated heart aging - Maria Grazia Perino; Miguel Calvo-Rubio Barrera; Daniel R. Riordon; Giulio Agnetti; Alexander Maltsev; Admira Parveen; Christopher H. Morrell; Ismayil Ahmet; Khalid Chakir; Yelena S. Tarasova; Jia-Hua Qu; Kirill V. Tarasov; et al. (GeroScience, 2025)

Origins and Diversification of the Caatinga Dry Forest Endemic Avifauna - Hevana S. Lima; Gustavo A. Bravo; Diego Astúa; Daniele Mariz; Scott V. Edwards; Luciano N. Naka (Journal of Biogeography, 2025)
Aim Understanding the geographic origin of lineages is critical to comprehending their biogeographical and evolutionary histories and the historical connections among biomes. In northeastern Brazil, the Caatinga dry forest represents the largest and most biologically diverse patch of Seasonally Dry Tropical Forest in the Neotropics. Here, using the endemic avian taxa of the Caatinga, we aim to (i) infer their biogeographical origins and timing of diversification, (ii) investigate the relationships with taxa from other Neotropical domains and (iii) understand the processes driving the evolution and diversification of the Caatinga endemic avifauna. Location Neotropical Region. Taxon Birds. Methods We obtained previously published calibrated phylogenies of 40 bird species endemic to the Caatinga to reconstruct their ancestral geographic ranges through the R package BioGeoBEARS to infer and highlight the origins, mode and tempo of evolution of the Caatinga avian endemics. Results Our results suggest that most avian endemics (21 taxa) are related to lineages from open habitats, including other dry forests or savannas; less than a quarter of the species (9 taxa) likely colonised the Caatinga from adjacent humid forests; we also highlight in situ origins (6 taxa), and cladogenetic events playing an important role in the colonisation of the domain. Although most of the endemics seem to represent new arrivals from adjacent habitats, we also detected relatively old lineages that likely occupied these dry landscapes since the Miocene. A correlation between the age, origins of Caatinga birds and their degree of threat was also found. Main Conclusions We provide a much needed framework for the evolution and biogeographic diversification of the Caatinga Dry Forest. The spatio‐temporal patterns recovered here suggest an evolutionary history influenced not only by strict vicariance events but also by episodes of dispersal that likely played an important role in the origin of its avifauna. These events were likely influenced by major climatic and geological events that formed ancient corridors, allowing connections between the Caatinga and both dry and humid forests in South America.

Assessment of methods for mapping snow albedo from MODIS - Ross T. Palomaki; Karl Rittger; Sebastien J.P. Lenard; Edward Bair; Jeff Dozier; S. McKenzie Skiles; Thomas H. Painter (Remote Sensing of Environment, 2025)

A novel control volume methodology to constrain ecosystem nutrient cycling within a tidal freshwater river - D.R. Mackenzie; D.R. Tait; J. Sippo; A. Ferguson; Rao S; C. Ralph; B. Stewart; M. Call; M. Reading; M. Andskog; D. Laicher-Edwards; D.T. Maher (Estuarine, Coastal and Shelf Science, 2025)

An economical and rapid method of comet assay and micronucleus cytome assay for genotoxicity biomonitoring using clam, Gafrarium divaricatum (Gmelin, 1791) - M. Harshavarthini; Edward Inpent Campal; Shubra Singh; Nalini Poojary; Martin Xavier; Kiran D. Rasal; Madhuri S. Pathak; Naresh S. Nagpure (DNA Repair, 2025)

Lactic Acid Bacteria: A Probiotic to Mitigate Pesticide Stress in Honey Bee - Subramanian Pradeep; Johnson Thangaraj Edward Y. S.; Suganthi Angappan; Senthilkumar Murugaiyan; Saminathan Vangili Ramasamy; Narayanan Manikanda Boopathi (Probiotics and Antimicrobial Proteins, 2025)

Nitrogen addition alters interactions between ectomycorrhizal host trees and fungal communities in a mixed mycorrhizal tropical rainforest - Georgia S. Seyfried; Joseph D. Edwards; James W. Dalling; Angela D. Kent; Wendy H. Yang (Plant and Soil, 2025)

Pathways to Recovery: Genomics and Resistance Assays for Tree Species Devastated by the Myrtle Rust Pathogen - Stephanie H. Chen; Jia‐Yee S. Yap; Veronica Viler; Craig Stehn; Karanjeet S. Sandhu; Julie Percival; Geoff S. Pegg; Tracey Menzies; Ashley Jones; Karina Guo; Fiona R. Giblin; Joel Cohen; et al. (Molecular Ecology, 2025)
Myrtle rust is a plant disease caused by the invasive fungal pathogen Austropuccinia psidii (G. Winter) Beenken, which has a global host list of 480 species. It was detected in Australia in 2010 and has caused the rapid decline of native Myrtaceae species, including rainforest trees Rhodamnia rubescens (Benth.) Miq. (scrub turpentine) and Rhodomyrtus psidioides (G.Don) Benth. (native guava). Ex situ collections of these species have been established, with the goal of preserving remaining genetic variation. Analysis of reduced representation sequencing (DArTseq; n = 444 for R. rubescens and n = 301 for R . psidioides ) showed genetic diversity is distributed along a latitudinal gradient across the range of each species. A panel of samples of each species ( n = 27 for R. rubescens and n = 37 for R . psidioides ) was resequenced at genome scale, revealing large historical effective population sizes, and little variation among individuals in inferred levels of deleterious load. In Rhodamnia rubescens , experimental assays ( n = 297) identified individuals that are putatively resistant to myrtle rust. This highlights two important points: there are tangible pathways to recovery for species that are highly susceptible to rust via a genetically informed breeding programme, and there is a critical need to act quickly before more standing diversity is lost.

The Southern Ocean Time Series: a climatological view of hydrography, biogeochemistry, phytoplankton community composition, and carbon export in the Subantarctic Zone - Elizabeth H. Shadwick; Cathryn A. Wynn-Edwards; Ruth S. Eriksen; Peter Jansen; Xiang Yang; Gemma Woodward; Diana Davies (Ocean Science, 2025)
The Southern Ocean Time Series (SOTS) provides highly temporally resolved observations of the physical, chemical, and biological variability in the upper ocean, as well as the export of particulate organic and inorganic carbon to the ocean interior, in the subantarctic region south of Australia. The SOTS observatory focuses on the subantarctic region because of its importance in the formation of mode water and the associated uptake and storage of anthropogenic heat and carbon. The region is also critical for the supply of oxygen to the ocean interior and the export of nutrients to fuel primary production in broad areas of the low-latitude global ocean. The SOTS observatory is the longest running multidisciplinary initiative in the open Southern Ocean and has delivered high-quality observations from the surface to the seafloor for more than a decade and, for some parameters, for over two decades, using two deep-water moorings. The moorings are serviced annually, providing additional opportunities for shipboard sampling and sensor validation and calibration. Using observations collected at the SOTS site between 1997 and 2022, we present the seasonal variability in upper-ocean hydrography, biogeochemistry, phytoplankton and microplankton community composition, and diversity, along with particulate organic and particulate inorganic carbon export to the deep ocean. This climatological view of the region is complemented by a review of recent findings underpinned by observations collected by the SOTS observatory and highlighting the ongoing need for long time series to better understand the Subantarctic Ocean and its response to a changing climate.

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

Corrigendum to FTIR spectra from grass pollen: A quest for species-level resolution of Poaceae and Cerealia-type pollen grains [Review of Palaeobotany and Palynology, 321 (2024): 105039] - F. Katsi; M.S. Kent; M. Jones; W.T. Fraser; P.E. Jardine; W. Eastwood; M. Mariani; C. Osborne; S. Edwards; B.H. Lomax (Review of Palaeobotany and Palynology, 2025)

Sea-level rise and freshwater management are reshaping coastal landscapes - Amanda Richey; Steven F. Oberbauer; Edward Castañeda-Moya; Tiffany Troxler; John S. Kominoski; Paulo Olivas; Sparkle L. Malone (Journal of Environmental Management, 2025)

Integrating multi-omics and machine learning for disease resistance prediction in legumes - Shameela Mohamedikbal; Hawlader A. Al-Mamun; Mitchell S. Bestry; Jacqueline Batley; David Edwards (Theoretical and Applied Genetics, 2025)
Key message Multi-omics assisted prediction of disease resistance mechanisms using machine learning has the potential to accelerate the breeding of resistant legume varieties. Abstract Grain legumes, such as soybean ( Glycine max (L.) Merr.), chickpea ( Cicer arietinum L.), and lentil ( Lens culinaris Medik.) play an important role in combating micronutrient malnutrition in the growing human population. However, plant diseases significantly reduce grain yield, causing 10–40% losses in major food crops. The genetic mechanisms associated with disease resistance in legumes have been widely studied using genomic approaches. Multi-omics data encompassing various biological layers such as the transcriptome, epigenome, proteome, and metabolome, in addition to the genome, enables researchers to gain a deeper understanding of these complementary layers and their roles in complex legume-pathogen interactions. Genomic prediction, used to select the best genotypes with desirable traits for breeding, has largely relied on genome-wide markers and statistical approaches to estimate the breeding values of individuals. Integrating multi-omics data into genomic prediction can be achieved using machine learning models, which can capture nonlinear relationships prevalent in high-dimensional data better than traditional statistical methods. This integration may enable more accurate predictions and identification of resistance mechanisms for breeding resistant legumes. Despite its potential, multi-omics integration for disease resistance prediction in legumes has been largely unexplored. In this review, we explore omics studies focusing on disease resistance in legumes and discuss how machine learning models can integrate multi-omics data for disease resistance prediction. Such multi-omics assisted prediction has the potential to reduce the breeding cycle for developing disease-resistant legume varieties.

Tsunami hazard assessment along the US East Coast from extreme sources in the North Atlantic Ocean: a limited probabilistic analysis - Stephan T. Grilli; Lauren Schambach; Maryam Mohammadpour; Annette R. Grilli; James T. Kirby; Edward S. Fratto; Fengyan Shi (Natural Hazards, 2025)
Coastal hazard is assessed along the US East Coast (USEC) through model simulation of 14 probable maximum tsunamis (PMTs) from sources located in the North Atlantic Ocean basin, in terms of: (i) standard inundation maps and other hazard products, and (ii) a limited probabilistic tsunami hazard analysis (PTHA) based on these. Tsunami sources are based on historical records or are hypothetical, including extreme seismic events in the Puerto Rico Trench (PRT)/Caribbean Arc area and in the Açores Convergence Zone (ACZ), near-field submarine mass failures (SMF) on or near the continental shelf break, and large scale volcanic flank collapses of the Cumbre Vieja Volcano (CVV), on La Palma in the Canary Archipelago. Various state-of-the-art models are used to simulate tsunami generation from these sources and propagation to the USEC, in a series of nested grids, by one-way coupling. Based on these results, hazard metrics are computed for each PMT and their envelope as: (i) a synoptic representation along the entire USEC (with results interpolated on the 5 m isobath in coarse 450 m grids), and (ii) high-resolution (10–30 m) inundation maps, for about 30% of the USEC to date, prioritizing the most exposed areas. While existing maps can be accessed in a repository, in this paper, we focus on assessing the synoptic tsunami hazard using 4 hazard metrics (surface elevation, flow velocity, momentum force and arrival time) and their combination into a Tsunami Intensity Index ( TII ) introduced in earlier work. A comparison of metrics for each PMT shows similar alongshore patterns of higher/lower impact, due to wave focusing and defocusing effects induced by the shelf bathymetry; on this basis, 14 focusing areas are identified from Maine to southern Florida, where tsunami hazard for any PMT is always relatively larger. The limited PTHA is then performed based on the PMT metrics, using estimated return period ranges for each source (in the $$T_r\in [500; 50,000]$$ T r ∈ [ 500 ; 50 , 000 ] year interval), from the literature and/or educated guesses. This analysis yields return periods along the USEC for 5 classes of metrics and the TII . The PTHA results are then interpolated to provide the same metrics along the USEC for $$T_r = 500$$ T r = 500 and 2,500 years, which are standard in geohazard assessment. PTHA results show, depending on low-high estimates of PMT return periods that: (i) up to $$T_r = 137-261$$ T r = 137 - 261 years, there is no probable tsunami hazard; (ii) for $$T_r =500$$ T r = 500 years, tsunami hazard would be expected to be low-medium and only larger near some focusing sites, with flooding metrics at par with a severe coastal storm; and (iii) for $$T_r =2,500$$ T r = 2 , 500 years, which is commensurate with the longest return periods considered on the US west Coast for large Cascadia events, the USEC would face high tsunami hazard, with widespread destruction near the focusing areas and severe impact elsewhere. As uncertainties are large on the estimated return period ranges used and, hence, on the results of this limited PTHA, while raising awareness for the potential tsunami hazard facing the USEC, this work stresses the need for conducting a more in-depth and comprehensive PTHA, including using a larger selection of tsunami sources and further supporting and refining the range of return periods selected for each of those. Such work has been initiated and will be the object of future papers.

Contrasting grazing practices alter plant community trajectories across western Canada’s grasslands with implications for ecosystem function - Timm F. Döbert; Lysandra A. Pyle; Carter Case; Edward W. Bork; Cameron N. Carlyle; Scott X. Chang; Laio Silva Sobrinho; Majid Iravani; Mark S. Boyce (Agriculture, Ecosystems & Environment, 2025)

Clearance of particles from regular-flavored little cigar smoke across lung lobes in female Sprague-Dawley rats - Kaisen Lin; Christopher Wallis; Patricia Edwards; Austin Cole; Laura Van Winkle; Anthony S. Wexler (Journal of Aerosol Science, 2025)

Quantifying explosive processes of the 2022 Meradalir eruption of the Fagradalsfjall Fires, Iceland - Caroline M. Tisdale; Bruce F. Houghton; Thorvaldur Thorsdarson; Edward W. Llewellin; Jóna S. Pálmadóttir (Bulletin of Volcanology, 2025)

Corrigendum to “Large sardine resource discovered off south-eastern Australia: Potential risks, challenges and benefits of establishing a new fishery” [Mar. Policy 155 (2023) 105739] - Tim M. Ward; Barrett W. Wolfe; Gretchen L. Grammer; Alex R. Ivey; Edward King; Andreas Schiller; Karlie S. McDonald; Jeffrey M. Dambacher (Marine Policy, 2025)

Detecting patches of invasive shrubs using high-density airborne LiDAR data and spectral imagery - Dennis Heejoon Choi; Isaac S. Morton; Lindsay E. Darling; Jianmin Wang; Bina Thapa; Edward P.F. Price; David N. Zaya; Songlin Fei; Brady S. Hardiman (Urban Forestry & Urban Greening, 2025)

Evaluating virtual fencing as a tool to manage beef cattle for rotational grazing across multiple years - Alexandra J. Harland; Francisco J. Novais; Carolyn J. Fitzsimmons; John S. Church; Gleise M. da Silva; Maria C. Londono-Mendez; Edward W. Bork (Journal of Environmental Management, 2025)

Effects of heat load on beef cattle activity budgets in a northern temperate grazing system - Temitope O. Oloyede; Francisco J. Novais; Carolyn J. Fitzsimmons; John S. Church; Cameron N. Carlyle; Changxi Li; Edward W. Bork (International Journal of Biometeorology, 2025)

Temporal trends and patterns for early- and late-onset adult liver cancer incidence vary by race/ethnicity, subsite, and histologic type in the United States from 2000 to 2019 - Mei-Chin Hsieh; Kendra L. Ratnapradipa; Laura Rozek; Shengdi Wen; Yu-Wen Chiu; Edward S. Peters (Cancer Causes & Control, 2025)
Purpose To examine incidence trends and patterns for early- and late-onset liver cancer. Methods Liver and intrahepatic bile duct (IBD) cancers diagnosed between 2000 and 2019 were acquired from 22 SEER registries. Variables included early-onset (20–49) vs. late-onset (50+), anatomic subsite, histologic type (hepatocellular carcinoma [HCC] and IBD cholangiocarcinoma [ICC]), sex, and race/ethnicity. Age-standardized incidence rates were calculated using SEER*Stat. Jointpoint regression analysis was employed to estimate the annual percent change (APC) and the average APC (AAPC) with pairwise comparisons for trend by sex and by race/ethnicity stratified by age and subsite. Results Liver cancer incidence decreased among early-onset (AAPC [95% CI] − 2.39 [− 2.74, − 2.07]) but increased among late-onset patients (2.85 [2.71, 3.01]), primarily driven by HCC (3.60 [3.50, 3.71]). IBD incidence increased for both ages with ICC incidence annually increasing 7.92% (6.84, 9.26) for early-onset and 6.32% (5.46, 8.86) for late-onset patients. Early-onset liver cancer displayed comparable trends across racial/ethnic groups; however, late-onset liver cancer showed more variation, particularly among American Indian/Alaska Native/Asian Pacific Islander (AI/AN/API) populations, which experienced a significant decrease in incidence, thereby narrowing the gap with other racial/ethnic groups. For IBD, an identical pattern of early-onset IBD among non-Hispanic Blacks (NHBs) compared to Hispanics was showed with coincidence test p = 0.1522, and a parallel pattern was observed among late-onset patients for both sexes ( p = 0.5087). Conclusion Late-onset HCC continues to rise, except for NHB and AI/AN/API, where incidence rates have started to decrease over the past 4–5 years. Early and late-onset ICC incidence continues to increase across all racial/ethnic groups.

Unveiling the diversity of gut microbes in green lacewings (Chrysopidae: Neuroptera) and their role as protagonist in nutrition - N. Karkuzhali; Y. S. Johnson Thangaraj Edward; N. Chitra; M. Senthilkumar; J. Ramalingam (Archives of Microbiology, 2025)

Transient Lymphatic Remodeling Follows Sub-Ablative High-Frequency Irreversible Electroporation Therapy in a 4T1 Murine Model - Savieay Esparza; Edward Jacobs; Jennifer H. Hammel; Sharon K. Michelhaugh; Nastaran Alinezhadbalalami; Margaret Nagai-Singer; Khan Mohammad Imran; Rafael V. Davalos; Irving C. Allen; Scott S. Verbridge; Jennifer M. Munson (Annals of Biomedical Engineering, 2025)
High-frequency irreversible electroporation (H-FIRE) is a minimally invasive local ablation therapy known to activate the adaptive immune system and reprogram the tumor microenvironment. Its predecessor, irreversible electroporation (IRE), transiently increases microvascular density and immune cell infiltration within the surviving non-ablated and non-necrotic tumor region, also known as the viable tumor region. However, the impact of pulse electric field therapies on lymphatic vessels, crucial for T-cell fate and maturation, remains unclear. This study investigates how sub-ablative H-FIRE (SA-HFIRE) affects lymphatic and blood microvascular remodeling in the 4T1 mammary mouse model. We conducted a temporal and spatial analysis to evaluate vascular changes in the viable tumor, peritumoral fat pad, and tumor-draining lymph node post-treatment. Histological examination showed a transient increase in blood vessel density on Day 1 post-treatment, followed by a spike in lymphatic vessel density in the viable tumor region on Day 3 post-treatment, increased lymphatic vessel density in the peripheral fat pad, and minimal remodeling of the tumor-draining lymph node within 3 days following treatment. Gene expression analysis indicated elevated levels of CCL21 and CXCL2 on Day 1 post-treatment, while VEGFA and VEGFC did not appear to contribute to vascular remodeling. Likewise, CCL21 protein content in tumor-draining axillary lymph nodes correlated with gene expression data from the viable tumor region. These findings suggest a dynamic shift in lymphatic and blood microvascular structures post-SA-HFIRE, potentially enhancing the adaptive immune response through CCL21-mediated lymphatic homing and subsequent lymph node microvascular remodeling. Future work will assess the immune and transport function of the microvasculature to inform experiments aimed at the application of adjuvant therapies during scenarios of tumor partial ablation.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

The Volcanoes of the World database - Benjamin J. Andrews; Edward Venzke; Elizabeth Cottrell; Sally S. K. Sennert; Kadie L. Bennis; A. E. J. Crafford (Bulletin of Volcanology, 2025)

Ingestive behaviour, performance, and methane emissions of pregnant alpacas grazing cultivated pastures in the high Peruvian Andes - Laura B. Gualdrón-Duarte; Cecilia Loza; José I. Gere; Nancy F. Huanca-Marca; Francisco E. Franco; Yemi Sanca Uscamayta; Rubén García‐Ticllacuri; Guadalupe Orellana Ligas; Diannett Benito López; Feliciano Rivera Pachiño; Juan E. Moscoso-Muñoz; Medardo A. Díaz-Céspedes; et al. (Livestock Science, 2025)

Ultraviolet radiation vs air filtration to mitigate virus laden aerosol in an occupied clinical room - Shane A. Landry; Milan Jamriska; Vinay J. Menon; Leo Yi Yang Lee; Isabelle Magnin-Bougma; Dinesh Subedi; Jeremy J. Barr; Jason Monty; Kevin Kevin; Ajith Gunatilaka; Michelle Delaire; Guy B. Marks; et al. (Journal of Hazardous Materials, 2025)

John Raven, FRS, FRSE: a truly great innovator in plant physiology, photosynthesis and much more - A. W. D. Larkum; P. G. Falkowski; Dianne Edwards; C. B. Osmond; H. Lambers; P. Sanchez-Baracaldo; R. J. Ritchie; J. W. Runcie; P. J. Ralph; M. Westoby; S. Maberly; H. Griffiths; et al. (Photosynthesis Research, 2025)
This is a tribute to a truly inspirational plant biologist, Prof. John A. Raven, FRS, FRSE (25th June 1941– 23rd May 2024), who died at the age of 82. He was a leader in the field of evolution and physiology of algae and land plants. His research touched on many areas including photosynthesis, ion transport, carbon utilisation, mineral use, such as silicon, iron and molybdenum, the evolution of phytoplankton, the evolution of root systems, the impact of global change, especially on the acidification of the oceans, carbon gain and water use in early land plants, and ways of detecting extraterrestrial photosynthesis. Beginning his research career in the Botany School, University of Cambridge, John studied ion uptake in a giant algal cell. This was at the time of great strides brought about by Peter Mitchell (1920–1992) in elucidating the role of energy generation in mitochondria and chloroplasts and the coupling of ion transport systems to energy generation. With Enid MacRobbie and Andrew Smith, John pioneered early work on the involvement of ion transport in the growth and metabolism of plant cells.On leaving Cambridge John took up a lectureship at the University of Dundee in 1971, where he was still attached upon his death. His primary focus over the years, with one of us (Paul Falkowski), was on phytoplankton, the photosynthetic microalgae of the oceans. Still, his publication list of 5 books and over 600 scientific papers spans a very broad range. The many highly cited papers (see Table 1) attest to an outstanding innovator, who influenced a multitude of students and coworkers and a very wide readership worldwide. At the personal level, John Raven was a wonderful human being; he had an extraordinary memory, dredging up facts and little-known scientific papers, like a scientific magician, but at the same time making humorous jokes and involving his colleagues in fun and sympathetic appreciation. Table 1 Ten best cited articles (from google scholar) Citations Date Aquatic Photosynthesis, 3rd EditionP.G. Falkowski & J.A. RavenPrinceton University Press, 2013 3854 2013 The evolution of modern eukaryotic phytoplanktonP.G. Falkowski, M.E. Katz, A.H. Knoll, A. Quigg, J.A. Raven, et alScience 305 , 354–360 1790 2004 C O 2 concentrating mechanisms in algae:mechanisms, environmental modulation, and evolutionM. Giordano, J. Beardall & J.A. RavenAnnu. Rev. Plant Biol. 56 (1), 99–131 1648 2005 Algae as nutritional food sources: revisiting our understandingM.L. Wells, P. Potin, J.S. Craigie, J.A. Raven, S.S. Merchant, et alJournal of applied phycology 29 , 949–982 1527 2017 Plant Nutrient acquisition strategies change with soil ageH. Lambers, J.A. Raven, G.R. Shaver & S.E. SmithTrends in ecology & evolution 23 , 95–103 1488 2008 Ocean acidification due to increasing atmospheric carbon dioxideJ. Raven, K. Caldeira, H. Elderfield, O. Hoegh-Guldberg, P. Liss, et alThe Royal Society, Policy Document, June 2005 1470 2005 Phytoplankton in a changing world: cell size and elemental stoichiometryZ.V. Finkel, J. Beardall, K.J. Flynn, A. Quigg, T.A.V. Rees & J.A. RavenJournal of plankton research 32 , 119–137 1198 2010 Opportunities for improving phosphorus efficiency in crop plantsE.J. Veneklaas, H. Lambers, J. Bragg, P.M. Finnegan, C.E. Lovelock, et alNew phytologist 195 , 306–320 951 2012 Adaptation of unicellular algae to irradiance: an analysis of strategiesK. Richardson, J. Beardall & J.A. RavenNew Phytologist 93 , 157–191 914 1983 N itrogen assimilation and transport in vascular land plants in relation to Intracellular pH regulationJ.A. Raven & F.A. SmithNew Phytologist 76 , 415–431 893 1976 Temperature and algal growth J.A. Raven & R.J. GeiderNew phytologist 110 , 441–461 867 1988 The role of trace metals in photosynthetic electron transport in O 2 -evolving organismsJ.A. Raven, M.C.W. Evans & R.E. KorbPhotosynthesis Research 60 , 111–150 840 1999

Giant milkweed: a comprehensive review of chemical constituents and their insecticidal properties - K. Mounisha; Y. S. Johnson Thangaraj Edward; M. Kannan; S. Vellaikumar; D. Uma; P. Indiragandhi (Phytochemistry Reviews, 2025)

Bonobo (Pan paniscus) Density and Distribution in Central Africa's Largest Rainforest Reserve: Long-term Survey Data Show Pitfalls in Methodological Approaches and Call for Vigilance - Mattia Bessone; Hjalmar S. Kühl; Ilka Herbinger; Gottfried Hohmann; Kouamé Paul N’Goran; Papy Asanzi; Stephen Blake; Michel Basele; Martin Bofeko; Nono Bondjengo; Pitshou Wangongo Bondo; Rigobert Booto; et al. (International Journal of Primatology, 2025)
Conservation measures require accurate estimates of density and abundance and population trend assessments. The bonobo ( Pan paniscus ) is considered Endangered in the IUCN Red List. This classification assumes that available population data are representative. However, with only 30% of the bonobo’s historic geographical range surveyed, reliable information is needed to assess the species' population status. Here, we use information from 13 surveys conducted between 2002 and 2018 in an area of 42,000 km 2 , representing ~27% of bonobo-suitable habitat: Salonga National Park and its corridor, Democratic Republic of the Congo (DRC). Using 8310 km of reconnaissance and transect walks and 27,045 days of camera trapping, we: (1) provide updated estimates of bonobo population density and distribution (42,000 km 2 ; ~5,000 km 2 of which, to the best of our knowledge, have not been surveyed before by scientists), (2) assess population trends (15,758 km 2 ; 2002–2008 vs 2012–2018), (3) compare estimates obtained with different methods, and (4) assess the factors driving bonobo density and distribution. Although we detected a non-significant population decline, our study suggests that Salonga is a bonobo stronghold, with a population ranging between 8244 and 18,308 mature individuals (density: 0.31 individuals/km 2 ). Standing crop nest counts returned non-significantly lower density estimates than camera trap distance sampling. Nest count-estimates were higher in areas with Marantaceae understorey and those farther away from rivers, while camera trap-estimates were higher in areas with lower human presence. Regardless of the method, bonobos were rarer in proximity to villages. They occurred more often in areas of dense forest cover and in proximity to ranger posts. Our results point towards a declining bonobo population in Salonga, but do not provide sufficient evidence to confirm this statistically. Consequently, the continued monitoring of the bonobo population and preservation of the integrity of Salonga, considering its biological and cultural heritage, will be crucial in the preservation of this stronghold of wild bonobos.

Skeletal muscle hypertrophy and enhanced mitochondrial bioenergetics following electrical stimulation exercises in spinal cord injury: a randomized clinical trial - Ashraf S. Gorgey; Refka E. Khalil; William Carter; Jeannie Rivers; Qun Chen; Edward J. Lesnefsky (European Journal of Applied Physiology, 2025)
We examined the combined effects of neuromuscular electrical stimulation-resistance training (NMES-RT) and functional electrical stimulation-lower extremity cycling (FES-LEC) compared to passive movement training (PMT) and FES-LEC on mitochondrial electron transport chain (ETC) complexes and citrate synthase (CS) in adults with SCI . Thirty-two participants with chronic SCI were randomized to 24 weeks of NMES-RT + FES [n = 16 (14 males and 2 females) with an age range of 20–54 years old] or PMT + FES [n = 16 (12 males and 4 females) with an age range of 21–61 years old]. The NMES-RT + FES group underwent 12 weeks of surface NMES-RT using ankle weights followed by an additional 12 weeks of FES-LEC. The PMT + FES performed 12 weeks of passive leg extension movements followed by an additional 12 weeks of FES-LEC. Using repeated measures design, muscle biopsies of the vastus lateralis were performed at baseline (BL), post-intervention 1 (P1) and post-intervention 2 (P2). Spectrophotometer was used to measure ETC complexes (I-III) and CS using aliquots of the homogenized muscle tissue. Magnetic resonance imaging was used to measure skeletal muscle CSAs. A time effect was noted on CS (P = 0.001 ) with an interaction between both groups (P = 0.01 ). 46% of the participants per group had zero activities of CI without any changes following both interventions. A time effect was noted in CII ( P = 0.023 ) following both interventions. Finally, NMES-RT + FES increased CIII at P1 compared to BL ( P = 0.023) without additional changes in P2 or following PMT + FES intervention. Skeletal muscle hypertrophy may potentially enhance mitochondrial bioenergetics after SCI. NMES-RT is likely to enhance the activities of complex III in sedentary persons with SCI. Clinical trials # NCT02660073.

Investigating stocking density, culture duration, and the combination ratio of artificial feed and fresh feed for mangrove crab Scylla serrata megalopae reared in pond-based net cages - Pedrita A. Caballero; Veronica R. Alava; Kyle Dymer L. Regatalio; Rheniel Dayrit; Joseph P. Faisan; Roger Edward P. Mamauag; Mercedes M. Pates; Gaudioso S. Pates (Aquaculture International, 2025)

Warming Disrupts Plant–Fungal Endophyte Symbiosis More Severely in Leaves Than Roots - Joseph D. Edwards; Melanie R. Kazenel; Yiqi Luo; Joshua S. Lynn; Rebecca L. McCulley; Lara Souza; Carolyn Young; Jennifer A. Rudgers; Stephanie N. Kivlin (Global Change Biology, 2025)
Disruptions to functionally important symbionts with global change will negatively impact plant fitness, with broader consequences for species' abundances, distribution, and community composition. Fungal endophytes that live inside plant leaves and roots could potentially mitigate plant heat stress from global warming. Conversely, disruptions of these symbioses could exacerbate the negative impacts of warming. To better understand the consistency and strength of warming‐induced changes to fungal endophytes, we examined fungal leaf and root endophytes in three grassland warming experiments in the US ranging from 2 to 25 years and spanning 2000 km, 12°C of mean annual temperature, and 600 mm of precipitation. We found that experimental warming disrupted symbiosis between plants and fungal endophytes. Colonization of plant tissues by septate fungi decreased in response to warming by 90% in plant leaves and 35% in roots. Warming also reduced fungal diversity and changed community composition in plant leaves, but not roots. The strength, but not direction, of warming effects on fungal endophytes varied by up to 75% among warming experiments. Finally, warming decoupled fungal endophytes from host metabolism by decreasing the correlation between endophyte community and host metabolome dissimilarity. These effects were strongest in the shorter‐term experiment, suggesting endophyte‐host metabolome function may acclimate to warming over decades. Overall, warming‐driven disruption of fungal endophyte community structure and function suggests that this symbiosis may not be a reliable mechanism to promote plant resilience and ameliorate stress responses under global change.

Stochastic investigation of the relationship between track geometry and ballast degradation rates - Jose Augusto V.S. Ramos; Arthur de O. Lima; Marcus S. Dersch; J. Riley Edwards (Transportation Geotechnics, 2025)

Performance evaluation of longer crossties in railroad track transition zone: Finite element analysis and laboratory experimentation - Jaeik Lee; Arthur de O. Lima; Marcus S. Dersch; J.Riley Edwards (Transportation Geotechnics, 2025)

Corrigendum to “Incorporating heterogeneity in farmer disease control behaviour into a livestock disease transmission model” Preventive Vet. Med. 219 (2023) 106019 - Edward M. Hill; Naomi S. Prosser; Paul E. Brown; Eamonn Ferguson; Martin J. Green; Jasmeet Kaler; Matt J. Keeling; Michael J. Tildesley (Preventive Veterinary Medicine, 2025)

The function of love: A signaling-to-alternatives account of the commitment device hypothesis - Benjamin Gelbart; Kathryn V. Walter; Daniel Conroy-Beam; Casey Estorque; David M. Buss; Kelly Asao; Agnieszka Sorokowska; Piotr Sorokowski; Toivo Aavik; Grace Akello; Mohammad Madallh Alhabahba; Charlotte Alm; et al. (Evolution and Human Behavior, 2025)

Quantifying impacts of seabird bycatch using genetic assignment: A case study of black-footed albatross in U.S. fisheries - Jessie N. Beck; Diana S. Baetscher; Claire Tobin; Scott V. Edwards; Simon Yung Wa Sin; Shannon Fitzgerald; Vanessa J. Tuttle; John Peschon; Wesley A. Larson (Biological Conservation, 2025)

Behavioral evidence that repetitive responses in a free-movement pattern Y-maze are associated with ageing-related deficit in working memory - Edward S. Redhead; Jude Rolfe-Tarrant; Antony Wood; Matthew O. Parker (Behavioural Processes, 2025)

Comparative Transcriptomics Reveals the Molecular Mechanisms of Maize in Response to Downy Mildew Disease Caused by Peronosclerospora philippinensis (Weston) Shaw - Edward Cedrick J. Fernandez; Eliza Vie M. Simon-Ada; Jay-Vee S. Mendoza; Anand Noel C. Manohar; Roanne R. Gardoce; Tonette P. Laude; Fe M. Dela Cueva; Darlon V. Lantican (Plant Molecular Biology Reporter, 2025)

CT scatter spectra transmission data of 80, 100, 120 and 140 kVp primary beams for various shielding materials - S. M. Edwards (Physical and Engineering Sciences in Medicine, 2025)

Dust transport pathways from The Great Basin - Ronald S. Treminio; Nicholas P. Webb; Saroj Dhital; Akasha Faist; Beth Newingham; Colby Brungard; David DuBois; Brandon L. Edwards; Emily Kachergis (Aeolian Research, 2025)

Achieving multifunctionality in green infrastructure projects: a fuzzy evaluation and Gini index of Key drivers in developing countries - S. Seidu; D. J. Edwards; D. Owusu-Manu; D. W. M. Chan; S. F. Abdulai; J. I. T. Buertey (Environment, Development and Sustainability, 2025)
While many developed countries are well advanced in green infrastructure (GI), more efforts are needed to bring less developed regions to speed. Existing evidence shows that GI understanding differs significantly among stakeholders due to the multifunctionality concept. As key technical stakeholders in GI implementation, there is little empirical knowledge of the multifunctional attributes of GI systems among built environment professionals in developing regions. This study provides an in-depth analysis to fill this knowledge gap through a combination of the Gini coefficient and fuzzy synthetic evaluation toward understanding the multifunctionality concept of GI among built environment professionals in developing regions. As a measure of dispersion, the stationary driver points to a constant factor that underpins the implementation of GI across several geographic regions. The need to mitigate urban heat islands and enhance ecosystem services were revealed as the anchors among built environment professionals in supporting GI development; hence, specific attention needs to be accorded to these dimensions in GI policies. Ecosystem services, water resources management, and thermal regulation were identified as the three broad multifunctional drivers of GI in developing nations. For effective water management in GI projects, integrated green-grey infrastructure systems are recommended. To achieve thermal objectives, insulation materials are pivotal. The ecosystem properties are more passive as compared to thermal and water management; hence, specific considerations must be accorded to ensure GI success. The key contribution of the study was the delineation of the key multifunctional factors that support GI adoption and implementation success in developing regions.

In silico design of multi-epitope vaccine candidate based on structural proteins of porcine reproductive and respiratory syndrome virus - Ella Mae Joy S. Sira; Edward C. Banico; Lauren Emily Fajardo; Nyzar Mabeth O. Odchimar; Kristina Marie Dela Cruz; Fredmoore L. Orosco (Veterinary Immunology and Immunopathology, 2025)

Fate of a toxic Microcystis aeruginosa bloom introduced into a subtropical estuary from a flow-managed canal and management implications - Edward J. Phlips; Susan Badylak; Eric C. Milbrandt; Benjamin Stelling; Mauricio Arias; Cassondra Armstrong; Thomas Behlmer; Amanda Chappel; Amanda Foss; David Kaplan; Leslie Landauer; Peter Landauer; et al. (Journal of Environmental Management, 2025)

Synthesis of encapsulated nanofertilizer from biogas plant digestate - Edward D. Nasser; Joel Kenneth M. Ngojo; Ramiro Emerson C. Amon; Jayvee Moore S. Dy; Julius J. Rosalia; Chosel P. Lawagon (Bioresource Technology Reports, 2025)

Derivation of toxicity parameters from field data: Analysis of lake zooplankton species responses to metals and acidity - E. Tipping; W. Keller; B.A. Edwards; S. Lofts (Aquatic Toxicology, 2025)

Sphingomyelin Inhibits Hydrolytic Activity of Heterodimeric PLA2 in Model Myelin Membranes: Pharmacological Relevance - Anwaar S. Chaudary; Yanglin Guo; Yuri N. Utkin; Maryam Barancheshmeh; Ruben K. Dagda; Edward S. Gasanoff (The Journal of Membrane Biology, 2025)

Ecosystem Changes Caused by Hydrological Change are Associated with Population Decline in a Formerly-Common Grazing Herbivore - W. J. Blaser-Hart; G. K. Shanungu; P. J. Edwards; J. Harms; S. P. H. Hart; G. A. Ellenbroek; H. A. M. J. van Gils; C. Simukonda; H. Olde Venterink (Ecosystems, 2025)
Few ecosystems are more sensitive to hydrological change than seasonally-flooded wetlands. Here, we investigate how changes in hydrological regimes caused by the construction of two dams have contributed to large changes in the structure and dynamics of the Kafue Flats, an internationally-important, partially-protected wetland ecosystem in Zambia. We use historical (1970) and contemporary (2013) data to describe changes in hydrology due to dam operations, and to compare the areal extent, distribution, and composition of the major wetland and dryland habitats in the pre- and post-dam periods. To understand the seasonal dynamics of the ecosystem and how these dynamics influence the seasonal movement and use of the ecosystem by the dominant grazing herbivore, the endangered Kafue lechwe, we combine data on annual hydrological variation with spatially- and/or temporally-explicit quantitative estimates of: (1) grass biomass and nutrient stocks, (2) distribution of lechwe across habitats, and (3) lechwe nutritional status. The operation of the dams has reduced hydrological variation, causing a loss of more than 50% of seasonally-flooded grasslands and probably promoting woody encroachment in some habitats. Our results demonstrate that Kafue lechwe is highly dependent on these seasonally-flooded grasslands during the dry season, when their nutritional status is otherwise critically low. In combination, we hypothesize that changes in the flooding regime driven by dam construction precipitated ecosystem-level changes that—together with other factors—may have contributed to a rapid historic, as well as ongoing decline in the lechwe population. Our study highlights potential consequences of the spatio-temporal homogenization of a previously highly variable ecosystem.

Coral reef attributes associated with microplastic exposure - Cheryl Hankins; Danielle Lasseigne; Sarah M. Davis; Kimberly Edwards; Jenny S. Paul (Coral Reefs, 2025)
Coral reef declines have been documented since the 1980’s from a variety of global and local stressors. Management resource tools are needed to preserve these fragile ecosystems from stressors, both known and unknown. Laboratory studies have shown microplastics (MP) to have negative effects on coral physiology, but their effects in a natural environment are not well understood. Thus, our primary objectives were to explore associations between MPs and coral reef attributes. We measured MP concentrations from sub-surface water and coral tissue samples from two Caribbean/Atlantic scleractinian coral species, Montastraea cavernosa and Orbicella faveolata, from St. John, U.S. Virgin Islands and Florida’s Coral Reef in 2017 and 2018, respectively. Polymer identification yielded mostly cotton or polyester fibers for both water and coral tissue samples. This study is the first to document MPs in coral tissues from either the U.S. Virgin Islands or Florida’s Coral Reef and is the first to explore how MPs relate to coral reef attributes. Significant, positive relationships were seen between MPs in coral tissue and coral density, rugosity, and percent coral cover, indicating MPs may not have immediate adverse effects on coral reef health.

Inhibition of chondroitin sulphate-degrading enzyme Chondroitinase ABC by dextran sulphate - Sagar Dalal; Rachana Pathak; Edward X. S. Moh; Nicolle H. Packer (Glycoconjugate Journal, 2025)
Chondroitin sulphate (CS) is a sulphated glycosaminoglycan (GAG) polysaccharide found on proteoglycans (CSPGs) in extracellular and pericellular matrices. Chondroitinase ABC (CSase ABC) derived from Proteus vulgaris is an enzyme that has gained attention for the capacity to cleave chondroitin sulphate (CS) glycosaminoglycans (GAG) from various proteoglycans such as Aggrecan, Neurocan, Decorin etc. The substrate specificity of CSase ABC is well-known for targeting various structural motifs of CS chains and has gained popularity in the field of neuro-regeneration by selective degradation of CS GAG chains. Within this context, our investigation into the biochemistry of CSase ABC led us to a previously unreported inhibition of CSase ABC activity by Dextran Sulphate (DexS). To understand the inhibitory effects of DexS, we compared its inhibition of CSase ABC to that of other polysaccharides such as Heparan Sulphate, Heparin, Colominic Acid, Fucoidan, and Dextran. This analysis identified key structural factors such as monosaccharide composition and linkage, sulphation degree and overall charge as influencing CSase ABC inhibition. Remarkably, DexS emerged as a unique inhibitor of CSase ABC, with distinctive inhibitory effects that correlate with its chain length. DexS has been used to reliably induce ulcerative colitis in mice, effectively mimicking inflammatory bowel diseases in humans, and has been previously shown to inhibit both RNA polymerase and reverse transcriptase. Our investigation emphasizes the interplay between the properties of DexS and CSase ABC, providing significant insights into the utilization of polysaccharide-based inhibitors for modulating enzyme activity.

Weekend Backpack Program Tailored for Ethnic and Dietary Food Preferences: Nutrition Quality, Program Usage, and Parent Satisfaction - Jiwoo Lee; Lisa J. Harnack; Lindsey Torkilsen; Rose Bauer; Rebecca L. Freese; Winnie Yip; Maryah S. Fram; Edward A. Frongillo (Journal of Nutrition Education and Behavior, 2025)

Influence of regulated water discharges on phytoplankton composition and biomass in a subtropical canal - Susan Badylak; Edward J. Phlips; Eric C. Milbrandt; Elise S. Morrison; Benjamin D. Stelling; Shin-Ah Lee; Thomas A. Frankovich; David Kaplan (Journal of Environmental Management, 2025)

On the impact of the vertical structure of Martian water ice clouds on nadir atmospheric retrievals from simultaneous EMM/EXI and TGO/ACS-MIR observations. - Aurélien Stcherbinine; Michael J. Wolff; Christopher S. Edwards; Oleg Korablev; Anna Fedorova; Alexander Trokhimovskiy (Icarus, 2025)

Numeric ring-reconstructions based on massifs favor a non-oblique south pole-Aitken-forming impact event - Hannes Bernhardt; Jessica M. Walsh; Leon M. Schröder; Jaclyn D. Clark; Megan R. Henriksen; Christopher S. Edwards (Earth and Planetary Science Letters, 2025)

Divergence in Regulatory Regions and Gene Duplications May Underlie Chronobiological Adaptation in Desert Tortoises - N. Jade Mellor; Timothy H. Webster; Hazel Byrne; Avery S. Williams; Taylor Edwards; Dale F. DeNardo; Melissa A. Wilson; Kenro Kusumi; Greer A. Dolby (Molecular Ecology, 2025)
Many cellular processes and organismal behaviours are time‐dependent, and asynchrony of these phenomena can facilitate speciation through reinforcement mechanisms. The Mojave and Sonoran desert tortoises ( Gopherus agassizii and G. morafkai respectively) reside in adjoining deserts with distinct seasonal rainfall patterns and they exhibit asynchronous winter brumation and reproductive behaviours. We used whole genome sequencing of 21 individuals from the two tortoise species and an outgroup to understand genes potentially underlying these characteristics. Genes within the most diverged 1% of the genome ( F ST ≥ 0.63) with putatively functional variation showed extensive divergence in regulatory elements, particularly promoter regions. Such genes related to UV nucleotide excision repair, mitonuclear and homeostasis functions. Genes mediating chronobiological (cell cycle, circadian and circannual) processes were also among the most highly diverged regions (e.g., XPA and ZFHX3 ). Putative promoter variants had significant enrichment of genes related to regulatory machinery (ARC‐Mediator complex), suggesting that transcriptional cascades driven by regulatory divergence may underlie the behavioural differences between these species, leading to asynchrony‐based prezygotic isolation. Further investigation revealed extensive expansion of respiratory and intestinal mucins (MUC5B and MUC5AC) within Gopherus , particularly G. morafkai . This expansion could be a xeric‐adaptation to water retention and/or contribute to differential Mycoplasma agassizii infection rates between the two species, as mucins help clear inhaled dust and bacterial. Overall, results highlight the diverse array of genetic changes underlying divergence, adaptation and reinforcement during speciation.

Challenges to and importance of considering early and intermediate ontogenetic stages in mangrove forest recovery and restoration - Taylor M. Sloey; Sean P. Charles; Lin Xiong; Edward Castañeda-Moya; Erik S. Yando; David Lagomasino (Marine Pollution Bulletin, 2024)

Controls on spatial variation in porewater methane concentrations across United States tidal wetlands - Erika L. Koontz; Sarah M. Parker; Alice E. Stearns; Brian J. Roberts; Caitlin M. Young; Lisamarie Windham-Myers; Patricia Y. Oikawa; J. Patrick Megonigal; Genevieve L. Noyce; Edward J. Buskey; R. Kyle Derby; Robert P. Dunn; et al. (Science of The Total Environment, 2024)

Investigating the chemical space coverage of multiple chromatographic and ionization methods using non-targeted analysis on surface and drinking water collected using passive sampling - Angela L. Batt; Laura D. Brunelle; Natalia S. Quinete; Eva K. Stebel; Brian Ng; Piero Gardinali; Alex Chao; Anna K. Huba; Susan T. Glassmeyer; David A. Alvarez; Dana W. Kolpin; Edward T. Furlong; et al. (Science of The Total Environment, 2024)

Pneumocephalus due to temporohyoid osteoarthropathy in a 16-year-old Friesian mare - P. Witt; E.K.L. Stas; L.C. Hardeman; E.R. van Proosdij; E.A.W.S. Weerts; R.A. Lloyd-Edwards; S. Veraa; L.C. Kranenburg; R. van den Boom (Journal of Equine Veterinary Science, 2024)

Investigating the enzymatic response of Plutella xylostella L. (Lepidoptera: Plutellidae) to Metarhizium anisopliae (Metschnikoff) Sorokin (Ascomycota: Hypocreales) Infection: A Comprehensive study - Abarna V.P.; Muthuswami M.; Jeyarajan Nelson S; Johnson Thangaraj Edward Y.S.; Manikanda Boopathi N.; Anita B.; Jeya Sundara Sharmila D. (Journal of Asia-Pacific Entomology, 2024)

Global survey of paleo-bedforms on Mars - Matthew Chojnacki; Lori K. Fenton; Lauren A. Edgar; Mackenzie Day; Christopher S. Edwards; Aaron R. Weintraub; Amber L. Gullikson; Matt W. Telfer (Geomorphology, 2024)

A comprehensive analysis of new particle formation across the northwest Atlantic: Analysis of ACTIVATE airborne data - Soodabeh Namdari; Taiwo Ajayi; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Simon Kirschler; Hongyu Liu; John B. Nowak; Michael A. Shook; Cassidy Soloff; Kenneth L. Thornhill; et al. (Atmospheric Environment, 2024)

A Transcriptomic Comparative Study of Cranial Vasculature - Jianing Zhang; Jee-Yeon Ryu; Selena-Rae Tirado; Lawrence D. Dickinson; Aviva Abosch; M. Ali Aziz-Sultan; Alan S. Boulos; Daniel L. Barrow; H. Hunt Batjer; Tamar R. Binyamin; Spiros L. Blackburn; Edward F. Chang; et al. (Translational Stroke Research, 2024)

New perspectives on ice forcing in continental arc magma plumbing systems - Brad S. Singer; Pablo Moreno-Yaeger; Meredith Townsend; Christian Huber; Joshua Cuzzone; Benjamin R. Edwards; Matias Romero; Yasmeen Orellana-Salazar; Shaun A. Marcott; Rachel E. Breunig; Ken L. Ferrier; Kathryn Scholz; et al. (Journal of Volcanology and Geothermal Research, 2024)

Quantifying the effect of fixed structures on rail stress management: A numerical investigation - Kamyar Kosarneshan; Marcus S. Dersch; J. Riley Edwards (Engineering Structures, 2024)

Upgraded syngas through selective partial oxidation of tar using Ni-doped LaFeO3 with tuned oxidation potential - Hang Yang; Ming Zhao; Yi Lv; Ghulam Tariq; Paul S. Fennell; Edward J. Anthony (Chemical Engineering Journal, 2024)

Automated assessment of cardiac morphological variation in Atlantic salmon (Salmo salar L.) - Lisa-Victoria Bernhardt; Andreas Hafver; Nafiha Usman; Edward Yi Liu; Jørgen Andreas Åm Vatn; André Ødegårdstuen; Heidi S. Mortensen; Ida Beitnes Johansen (Aquaculture, 2024)

High resolution luminescence and radiocarbon dating of Holocene Aeolian silt (loess) in west Greenland - D. Sechi; T. Stevens; P. Hällberg; R.H. Smittenberg; M. Molnár; G.T. Kertész; J.P. Buylaert; R. Schneider; C. Edward; Keld Romer Rasmussen; Niels Aage Tvis Knudsen; S. Andreucci; et al. (Quaternary Geochronology, 2024)

Manipulation of Farmed Wetlands Increases use by Migrating Shorebirds and Ducks - Dustin L. Toy; Michael J. Anteau; Aaron T. Pearse; Edward S. DeKeyser; David C. Roberts (Wetlands, 2024)
The Drift Prairie, in central North America, has been largely converted from grasslands to croplands, but still contains thousands of wetlands used by shorebirds and waterfowl during breeding and migration periods. Consequently, many of the remaining wetlands are situated within cropland where disturbance regimes (i.e., fire, grazing, and water-level dynamics), which occurred naturally prior to agricultural development, have been highly altered by landscape fragmentation from agriculture practices. Currently, smaller wetlands within crop fields are subject to disturbances stemming from agricultural practices (i.e., manipulations), such as burning, disking, harvesting, and mowing. We evaluated vegetation structure of idled (i.e., not recently manipulated by farming practices) and manipulated agricultural wetlands to investigate whether management method or resulting vegetation structure had greater influence on occurrence probabilities and densities of dabbling ducks and shorebirds during spring. All manipulation methods reduced vegetation heights compared to idled wetlands and most manipulations reduced the proportion of vegetation cover in inundated areas. Wetland manipulations generally increased shorebird occurrence compared to idled wetlands, whereas vegetation variables better explained duck occurrence probabilities. Duck occurrence peaked in wetlands with lower vegetation coverage (32%), and duck densities decreased as vegetation coverage increased beyond 10%. While more studies are needed to understand underlying mechanisms driving these outcomes, our results indicate that including periodic disturbances that reduce dense vegetation within wetlands in agricultural fields would increase their use by migrating and breeding shorebirds and dabbling ducks.

Moths are less attracted to light traps than they used to be - Ian Battles; Eric Burkness; Michael S. Crossley; Collin B. Edwards; Kristian Holmstrom; William Hutchison; Joseph Ingerson-Mahar; David Owens; Avalon C.S. Owens (Journal of Insect Conservation, 2024)
As evidence of global insect declines continues to mount, insect conservationists are becoming increasingly interested in modeling the demographic history of at-risk species from long-term survey data. However, certain entomological survey methods may be susceptible to temporal biases that will complicate these efforts. Entomological light traps, in particular, may catch fewer insects today than they once did due solely to increases in anthropogenic light pollution. Here we investigate this possibility by comparing the demographic histories of corn earworm moths ( Helicoverpa zea ) estimated from pairs of blacklight and pheromone traps monitored at the same farms. We find a stark decline in blacklight trap efficacy over 25 years of monitoring in Delaware, USA, mirrored over 10 years of monitoring in New Jersey, USA. While the precise causes of this decline remain a subject for discussion, the practical consequences are clear: insect conservationists cannot fully rely on long-term trends from entomological light traps.

Mutagenesis on a complex mouse genetic background by site-specific nucleases - Benjamin Davies; Lucy Trelfa; Victoria S. Rashbrook; Edward Drydale; Rachel Martin; Boyan Bai; Jedrzej Golebka; Daniel Stephen Biggs; Keith M. Channon; Shoumo Bhattacharya; Gillian Douglas (Transgenic Research, 2024)
Mouse models with complex genetic backgrounds are increasingly used in preclinical research to accurately model human disease and to enable temporal and cell-specific evaluation of genetic manipulations. Backcrossing mice onto these complex genetic backgrounds takes time and leads to significant wastage of animals. In this study, we aimed to evaluate whether site-specific nucleases could be used to generate additional genetic mutations in a complex genetic background, using the REVERSA mouse model of atherosclerosis, a model harbouring four genetically altered alleles. The model is comprised of a functional null mutation in the Ldlr gene in combination with a ApoB100 allele, which, after high-fat diet, leads to the rapid development of atherosclerosis. The regression of the pathology is achieved by inducible knock-out of the Mttp gene. Here we report an investigation to establish if microinjection of site-specific nucleases directly into zygotes prepared from the REVERSA could be used to investigate the role of the ATP binding cassette transporter G1 (ABCG1) in atherosclerosis regression. We show that using this approach we could successfully generate two independent knockout lines on the REVERSA background, both of which exhibited the expected phenotype of a significant reduction in cholesterol efflux to HDL in bone marrow-derived macrophages. However, loss of Abcg1 did not impact atherosclerosis regression in either the aortic root or in aortic arch, demonstrating no important role for this transporter subtype. We have demonstrated that site-specific nucleases can be used to create genetic modifications directly onto complex disease backgrounds and can be used to explore gene function without the need for laborious backcrossing of independent strains, conveying a significant 3Rs advantage.

A temperature snapshot from MIS 5c in southeastern Alaska - PAUL S. Wilcox; Christoph Spötl; R.L. Edwards (Journal of Quaternary Science, 2024)
Marine Isotope Stage (MIS) 5c, between ~106 000 and ~93 000 years ago, represents an important warm period in which the current anthropogenic warming can be contextualized. Although viewed as a pronounced interstadial, its climate expression is regionally disparate, with different regions on Earth showing evidence of either cooler or warmer conditions than modern‐day. It is therefore important to expand temperature reconstructions to different regions on Earth to gain a better picture of climate dynamics during MIS 5c. In Alaska, there are no quantitative temperature reconstructions for MIS 5c, limiting our knowledge of temperature changes in this climatically sensitive high‐latitude region. Here, we fill this gap by providing the first quantitative temperature estimates from MIS 5c in Alaska using hydrogen isotopes of fluid inclusions in precisely dated speleothems. We find that regional temperatures during MIS 5c were within error of the modern‐day reference period (1929–1989 ce ) temperatures, possibly representing the most recent time period that regional temperatures were as high as modern‐day.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

A data-driven approach to quantify track buckling strength through the development and application of a Track Strength Index (TSI) - Sadaf Shafie Zadeh A.; J. Riley Edwards; Arthur de O. Lima; Marcus S. Dersch; Paula Palma (Transportation Geotechnics, 2024)

Proximity Labelling Confirms the Involvement of Papain-Like Cysteine Proteases and Chaperones in Cyclotide Biosynthesis - Meng-Han Lee; Mark A. Jackson; Fabian B. H. Rehm; Deborah S. Barkauskas; Wing L. Ho; Kuok Yap; David J. Craik; Edward K. Gilding (Plant Molecular Biology Reporter, 2024)
Cyclotides are disulfide-rich insecticidal peptides from plants that harbour a cyclic cystine knot motif that imparts them with high stability. Like most ribosomally encoded peptides, cyclotides are produced as precursor proteins that are subsequently processed to maturity through proteolytic activity. Although the final maturation of the prototypic cyclotide kalata B1 (kB1) is known to involve asparaginyl endopeptidases, the role of the in planta folding machinery is less well characterized, as is also the case for in planta N-terminal processing enzyme(s). Here, we used proximity labelling to identify proteins involved in the biosynthesis of kB1 in both a cyclotide-bearing plant species, Petunia × hybrida [Regel], and in Nicotiana benthamiana [Domin] that does not naturally produce cyclotides. Together, several ER resident chaperones, protein disulfide isomerases, a papain-like cysteine protease, and an asparaginyl endopeptidase were identified in the kB1 interactome. We found that overexpression of the identified papain-like cysteine protease resulted in an improvement in the yield of cyclic kB1, while this was not the case for the overexpression of protein disulfide isomerases, despite their interaction being verified using bimolecular fluorescence complementation. Together, these results provide a significant advance in our understanding of the role of auxiliary biosynthetic elements for heterologous cyclotide production in plants.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Remote sensing-based mangrove blue carbon assessment in the Asia-Pacific: A systematic review - Abhilash Dutta Roy; Pavithra S. Pitumpe Arachchige; Michael S. Watt; Apoorwa Kale; Mollie Davies; Joe Eu Heng; Redeat Daneil; G.A. Pabodha Galgamuwa; Lara G. Moussa; Kausila Timsina; Ewane Basil Ewane; Kerrylee Rogers; et al. (Science of The Total Environment, 2024)

Spatial and temporal variability of martian water-ice cloud effective radius in EMIRS thermal infrared observations - Samuel A. Atwood; Michael D. Smith; Michael J. Wolff; Khalid Badri; Christopher S. Edwards; Philip R. Christensen; Alain S.J. Khayat; M.R. El-Maarry (Icarus, 2024)

Pyrrhotites in asteroid 162173 Ryugu: Records of the initial changes on their surfaces with aqueous alteration - Hiroharu Yui; Shu-hei Urashima; Morihiko Onose; Mayu Morita; Shintaro Komatani; Izumi Nakai; Yoshinari Abe; Yasuko Terada; Hisashi Homma; Kazuko Motomura; Kiyohiro Ichida; Tetsuya Yokoyama; et al. (Geochimica et Cosmochimica Acta, 2024)

Effect of the mitochondrial membrane potential on the absorbance of the reduced form of cytochrome c oxidase - Raul Covian; Lanelle O. Edwards; Robert S. Balaban (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Adaptive multi-paddock grazing increases mineral associated soil carbon in Northern grasslands - Upama Khatri-Chhetri; Karen A. Thompson; Sylvie A. Quideau; Mark S. Boyce; Scott X. Chang; Edward W. Bork; Cameron N. Carlyle (Agriculture, Ecosystems & Environment, 2024)

Longitudinal relationships between depressive symptoms, functional impairment, and physical activity in later late life - Lisa Y. Xiong; Madeline Wood Alexander; Hugo Cogo-Moreira; Che-Yuan Wu; Michael Eid; Nathan Herrmann; Damien Gallagher; Jodi D. Edwards; Krista L. Lanctôt; Susan Marzolini; David A. Bennett; Jennifer S. Rabin; et al. (GeroScience, 2024)

Resistance response of yellow maize inbreds and F1 crosses against Philippine downy mildew [Peronosclerospora philippinensis (Weston) C.G. Shaw] - Eliza Vie M. Simon-Ada; Jay-Vee S. Mendoza; Edward Cedrick J. Fernandez; John Paolo P. Nuñez; Fe M. Dela Cueva; Anand Noel C. Manohar; Roanne R. Gardoce; Tonette P. Laude; Darlon V. Lantican (Crop Protection, 2024)

Estimating the scope, scale, and contribution of direct seafood marketing to the United States seafood sector - Sahir Advani; Jeffrey K. O’Hara; Sarah M. Shoffler; Patricia Pinto da Silva; Juan Agar; JuliAnna Arnett; Lilian Brislen; Matthew Cutler; Abigail Harley; Justin Hospital; Karma Norman; Edward Ragland; et al. (Marine Policy, 2024)

Impact of chickpea hummus on postprandial blood glucose, insulin and gut hormones in healthy humans combined with mechanistic studies of food structure, rheology and digestion kinetics - Rasha A. Alshaalan; Maria N. Charalambides; Cathrina H. Edwards; Peter R. Ellis; Shatha H. Alrabeah; Gary S. Frost (Food Research International, 2024)

Development of validated sandwich ELISA for detecting peanut allergen Ara h 3 in food - Jia-Fong Lin; Kee-Lung Chang; Bau-Shan Hsieh; Yu-Chen Hu; Edward S. Huang; Hsu-Sheng Yu (Food Chemistry, 2024)

Female foragers sometimes hunt, yet gendered divisions of labor are real: a comment on Anderson et al. (2023) The Myth of Man the Hunter - Vivek V. Venkataraman; Jordie Hoffman; Kyle Farquharson; Helen Elizabeth Davis; Edward H. Hagen; Raymond B. Hames; Barry S. Hewlett; Luke Glowacki; Haneul Jang; Robert Kelly; Karen Kramer; Sheina Lew-Levy; et al. (Evolution and Human Behavior, 2024)

Deliberately introduced dung beetles in A ustralia: 12 years of occurrence and abundance records from 2001 to 2022 - Jacob D. Berson; Penelope B. Edwards; T. James Ridsdill‐Smith; Christopher K. Taylor; Daniel J. Anderson; Nigel R. Andrew; Russell A. Barrow; David A. Cousins; Robert N. Emery; Laura L. Fagan; Rhiannon M. Foster; Lucas G. Harwood; et al. (Ecology, 2024)
Since 1968, the Australian Dung Beetle Project has carried out field releases of 43 deliberately introduced dung beetle species for the biological control of livestock dung and dung‐breeding pests. Of these, 23 species are known to have become established. For most of these species, sufficient time has elapsed for population expansion to fill the extent of their potential geographic range through both natural and human‐assisted dispersal. Consequently, over the last 20 years, extensive efforts have been made to quantify the current distribution of these introduced dung beetles, as well as the seasonal and spatial variation in their activity levels. Much of these data and their associated metadata have remained unpublished, and they have not previously been synthesized into a cohesive dataset. Here, we collate and report data from the three largest dung beetle monitoring projects from 2001 to 2022. Together, these projects encompass data collected from across Australia, and include records for all 23 species of established dung beetles introduced for biocontrol purposes. In total, these data include 22,718 presence records and 213,538 absence records collected during 10,272 sampling events at 546 locations. Most presence records (97%) include abundance data. In total, 1,752,807 dung beetles were identified as part of these data. The distributional occurrence and abundance data can be used to explore questions such as factors influencing dung beetle species distributions, dung beetle biocontrol, and insect‐mediated ecosystem services. These data are provided under a CC‐BY‐NC 4.0 license and users are encouraged to cite this data paper when using the data.

Photogrammetry scans for neuroanatomy education - a new multi-camera system: technical note - André S. B. Oliveira; Luciano C. P. C. Leonel; Megan M. J. Bauman; Alessandro De Bonis; Edward R. LaHood; Stephen Graepel; Michael J. Link; Carlos D. Pinheiro-Neto; Nirusha Lachman; Jonathan M. Morris; Maria Peris-Celda (Neuroinformatics, 2024)

Impact of aging and ergothioneine pre-treatment on naphthalene toxicity in lung - Veneese JB Evans; Xiangmeng Wu; Kyle K Tran; Shanlea K Tabofunda; Liang Ding; Lei Yin; Patricia Edwards; Qing-Yu Zhang; Xinxin Ding; Laura S. Van Winkle (Toxicology Letters, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Temporal and spatial drivers of the structure of macroinvertebrate assemblages associated with Laminaria hyperborea detritus in the northeast Atlantic - Adam Gouraguine; Dan A. Smale; Arwyn Edwards; Nathan G. King; Mathilde Jackson-Bué; Sean Kelly; Hannah S. Earp; Pippa J. Moore (Marine Environmental Research, 2024)

Catalytic production of light Olefins: Perspective and prospective - Naif S. Almuqati; Afrah M. Aldawsari; Khalid N. Alharbi; Sergio González-Cortés; Mohammed F. Alotibi; Fawaz Alzaidi; Jonathan R. Dilworth; Peter P. Edwards (Fuel, 2024)

Correction to: Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon‑Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)

Addressing Cardiovascular Toxicity Risk of Electronic Nicotine Delivery Systems in the Twenty-First Century: “What Are the Tools Needed for the Job?” and “Do We Have Them?” - Mark Chandy; Thomas Hill; Nerea Jimenez-Tellez; Joseph C. Wu; S. Emma Sarles; Edward Hensel; Qixin Wang; Irfan Rahman; Daniel J. Conklin (Cardiovascular Toxicology, 2024)

Damage to tropical forests caused by cyclones is driven by wind speed but mediated by topographical exposure and tree characteristics - Thomas Ibanez; David Bauman; Shin‐ichiro Aiba; Thomas Arsouze; Peter J. Bellingham; Chris Birkinshaw; Philippe Birnbaum; Timothy J. Curran; Saara J. DeWalt; John Dwyer; Thierry Fourcaud; Janet Franklin; et al. (Global Change Biology, 2024)
Each year, an average of 45 tropical cyclones affect coastal areas and potentially impact forests. The proportion of the most intense cyclones has increased over the past four decades and is predicted to continue to do so. Yet, it remains uncertain how topographical exposure and tree characteristics can mediate the damage caused by increasing wind speed. Here, we compiled empirical data on the damage caused by 11 cyclones occurring over the past 40 years, from 74 forest plots representing tropical regions worldwide, encompassing field data for 22,176 trees and 815 species. We reconstructed the wind structure of those tropical cyclones to estimate the maximum sustained wind speed (MSW) and wind direction at the studied plots. Then, we used a causal inference framework combined with Bayesian generalised linear mixed models to understand and quantify the causal effects of MSW, topographical exposure to wind (EXP), tree size (DBH) and species wood density ( ρ ) on the proportion of damaged trees at the community level, and on the probability of snapping or uprooting at the tree level. The probability of snapping or uprooting at the tree level and, hence, the proportion of damaged trees at the community level, increased with increasing MSW, and with increasing EXP accentuating the damaging effects of cyclones, in particular at higher wind speeds. Higher ρ decreased the probability of snapping and to a lesser extent of uprooting. Larger trees tended to have lower probabilities of snapping but increased probabilities of uprooting. Importantly, the effect of ρ decreasing the probabilities of snapping was more marked for smaller than larger trees and was further accentuated at higher MSW. Our work emphasises how local topography, tree size and species wood density together mediate cyclone damage to tropical forests, facilitating better predictions of the impacts of such disturbances in an increasingly windier world.

A half-cell reaction approach for pH calculation using a solid-state chloride ion-selective electrode with a hydrogen ion-selective ion-sensitive field effect transistor - S. Fisher Gonski; George W. Luther; Amanda L. Kelley; Todd R. Martz; Elliott G. Roberts; Xinyu Li; Bo Dong; Jordan A. Watson; Taylor S. Wirth; Najid Hussain; Randy J. Feris Serrano; Edward Hale; et al. (Marine Chemistry, 2024)

CAUSES AND INCIDENCE OF FAILURE TO LITTER IN CONTROL ratS FROM EXTENDED ONE-GENERATION REPRODUCTIVE TOXICITY STUDIES - O. Greville-Heygate; P. Edwards; S. Renaut; P. Scott; M. Levi (Journal of Comparative Pathology, 2024)

Consequences of ecological aggregation in general equilibrium analysis of perturbed ecosystems - Stephanie Brockmann; David C. Finnoff; Doran M. Mason; Edward S. Rutherford; Hongyan Zhang (Ecological Economics, 2024)

Nth-plant scenario for blended pellets of Miscanthus, Switchgrass, and Corn Stover using multi-modal transportation: Biorefineries and depots in the contiguous U.S. - Tasmin Hossain; Daniela S. Jones; Edward Godfrey; Daniel Saloni; Mahmoud Sharara; Damon S. Hartley (Biomass and Bioenergy, 2024)

An assessment and characterization of pharmaceuticals and personal care products (PPCPs) within the Great Lakes Basin: Mussel Watch Program (2013–2018) - Edwards M. A.; Kimbrough K.; Fuller N.; Davenport E.; Rider M.; Freitag A.; Regan S.; Leight A; K.; Burkart H.; Jacob A.; Johnson E. (Environmental Monitoring and Assessment, 2024)
Defining the environmental occurrence and distribution of chemicals of emerging concern (CECs), including pharmaceuticals and personal care products (PPCPs) in coastal aquatic systems, is often difficult and complex. In this study, 70 compounds representing several classes of pharmaceuticals, including antibiotics, anti-inflammatories, insect repellant, antibacterial, antidepressants, chemotherapy drugs, and X-ray contrast media compounds, were found in dreissenid mussel (zebra/quagga; Dreissena spp.) tissue samples. Overall concentration and detection frequencies varied significantly among sampling locations, site land-use categories, and sites sampled proximate and downstream of point source discharge. Verapamil, triclocarban, etoposide, citalopram, diphenhydramine, sertraline, amitriptyline, and DEET (N,N-diethyl-meta-toluamide) comprised the most ubiquitous PPCPs (> 50%) detected in dreissenid mussels. Among those compounds quantified in mussel tissue, sertraline, metformin, methylprednisolone, hydrocortisone, 1,7-dimethylxanthine, theophylline, zidovudine, prednisone, clonidine, 2-hydroxy-ibuprofen, iopamidol, and melphalan were detected at concentrations up to 475 ng/g (wet weight). Antihypertensives, antibiotics, and antidepressants accounted for the majority of the compounds quantified in mussel tissue. The results showed that PPCPs quantified in dreissenid mussels are occurring as complex mixtures, with 4 to 28 compounds detected at one or more sampling locations. The magnitude and composition of PPCPs detected were highest for sites not influenced by either WWTP or CSO discharge (i.e., non-WWTPs), strongly supporting non-point sources as important drivers and pathways for PPCPs detected in this study. As these compounds are detected at inshore and offshore locations, the findings of this study indicate that their persistence and potential risks are largely unknown, thus warranting further assessment and prioritization of these emerging contaminants in the Great Lakes Basin. Graphical Abstract

Accuracy of patient race and ethnicity data in a central cancer registry - Rachel R. Codden; Carol Sweeney; Blessing S. Ofori-Atta; Kimberly A. Herget; Kacey Wigren; Sandra Edwards; Marjorie E. Carter; Rachel D. McCarty; Mia Hashibe; Jennifer A. Doherty; Morgan M. Millar (Cancer Causes & Control, 2024)

Soil microbial community response to ectomycorrhizal dominance in diverse neotropical montane forests - Joseph D. Edwards; Alexander H. Krichels; Georgia S. Seyfried; James Dalling; Angela D. Kent; Wendy H. Yang (Mycorrhiza, 2024)
Ectomycorrhizal (EM) associations can promote the dominance of tree species in otherwise diverse tropical forests. These EM associations between trees and their fungal mutualists have important consequences for soil organic matter cycling, yet the influence of these EM-associated effects on surrounding microbial communities is not well known, particularly in neotropical forests. We examined fungal and prokaryotic community composition in surface soil samples from mixed arbuscular mycorrhizal (AM) and ectomycorrhizal (EM) stands as well as stands dominated by EM-associated Oreomunnea mexicana (Juglandaceae) in four watersheds differing in soil fertility in the Fortuna Forest Reserve, Panama. We hypothesized that EM-dominated stands would support distinct microbial community assemblages relative to the mixed AM-EM stands due to differences in carbon and nitrogen cycling associated with the dominance of EM trees. We expected that this microbiome selection in EM-dominated stands would lead to lower overall microbial community diversity and turnover, with tighter correspondence between general fungal and prokaryotic communities. We measured fungal and prokaryotic community composition via high-throughput Illumina sequencing of the ITS2 (fungi) and 16S rRNA (prokaryotic) gene regions. We analyzed differences in alpha and beta diversity between forest stands associated with different mycorrhizal types, as well as the relative abundance of fungal functional groups and various microbial taxa. We found that fungal and prokaryotic community composition differed based on stand mycorrhizal type. There was lower prokaryotic diversity and lower relative abundance of fungal saprotrophs and pathogens in EM-dominated than AM-EM mixed stands. However, contrary to our prediction, there was lower homogeneity for fungal communities in EM-dominated stands compared to mixed AM-EM stands. Overall, we demonstrate that EM-dominated tropical forest stands have distinct soil microbiomes relative to surrounding diverse forests, suggesting that EM fungi may filter microbial functional groups in ways that could potentially influence plant performance or ecosystem function.

Differential advances in budburst timing among black spruce, white spruce and balsam fir across Canada - Diego S. Podadera; Lorena Balducci; Sergio Rossi; Fabrizio Cartenì; Valérie Néron; Rémi Saint-Amant; Stefano Mazzoleni; Jacques Régnière; Eric R.D. Moise; Joseph J. Bowden; Jean-Noël Candau; Alain Dupont; et al. (Agricultural and Forest Meteorology, 2024)

Associating white matter microstructural integrity and improvements in reactive stepping in people with Parkinson’s Disease - Andrew S Monaghan; Edward Ofori; Brett W Fling; Daniel S Peterson (Brain Imaging and Behavior, 2024)

The structural–functional-connectivity coupling of the aging brain - Hui Zhang; Peng Cao; Henry K. F. Mak; Edward S. Hui (GeroScience, 2024)
Aging primarily affects memory and executive functions, a relationship that may be underpinned by the fact that almost all adults over 60 years old develop small vessel disease (SVD). The fact that a wide range of neuropathologies could only explain up to 43% of the variation in age-related cognitive impairment suggests that other factors, such as cognitive reserve, may play a role in the brain’s resilience against aging-related cognitive decline. This study aims to examine the relationship between structural–functional-connectivity coupling (SFC), and aging, cognitive abilities and reserve, and SVD-related neuropathologies using a cohort of n = 176 healthy elders from the Harvard Aging Brain Study. The SFC is a recently proposed biomarker that reflects the extent to which anatomical brain connections can predict coordinated neural activity. After controlling for the effect of age, sex, and years of education, global SFC, as well as the intra-network SFC of the dorsolateral somatomotor and dorsal attention networks, and the inter-network SFC between dorsolateral somatomotor and frontoparietal networks decreased with age. The global SFC decreased with total cognitive score. There were significant interaction effects between years of education versus white matter hyperintensities and between years of education versus cerebral microbleeds on inter-network SFC. Enlarged perivascular space in basal ganglia was associated with higher inter-network SFC. Our results suggest that cognitive ability is associated with brain coupling at the global level and cognitive reserve with brain coupling at the inter-functional-brain-cluster level with interaction effect from white matter hyperintensities and cerebral microbleed in a cohort of healthy elderlies.

New whole-genome alignment tools are needed for tapping into plant diversity - Baoxing Song; Edward S. Buckler; Michelle C. Stitzer (Trends in Plant Science, 2024)

Abundant incongruence in a clade endemic to a biodiversity hotspot: Phylogenetics of the scrub mint clade (Lamiaceae) - Andre A. Naranjo; Christine E. Edwards; Matthew A. Gitzendanner; Douglas E. Soltis; Pamela S. Soltis (Molecular Phylogenetics and Evolution, 2024)

Modelling of Salmonella Enteritidis inactivation in liquid whole egg under dynamic manothermosonication treatments - Enrique Beitia; Edward Ebert; Matthias Plank; Panagiotis Chanos; Christian Hertel; Satyajeet S. Bhonsale; Jan F.M. Van Impe; Volker Heinz; Kemal Aganovic; Vasilis Valdramidis (Innovative Food Science & Emerging Technologies, 2024)

Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon-Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)
Recent extremes of flood and drought across Australia have raised questions about the recurrence of such rare events and highlighted the importance of understanding multi-decadal climate variability. However, instrumental records over the past century are too short to adequately characterise climate variability on multi-decadal and longer timescales or robustly determine extreme event frequencies and their duration. Palaeoclimate reconstructions can provide much-needed information to help address this problem. Here, we use the 600-year hydroclimate record captured in the eastern Australian and New Zealand Drought Atlas (ANZDA) to analyse drought and pluvial frequency trends for East Australian Natural Resource Management (NRM) clusters. This partitioning of the drought atlas grid points into recognised biophysical areas (i.e. NRM clusters) revealed their differences and similarities in drought intensity and pluvial events over time. We find sustained multi-decadal periods of a wet–dry geographic 'seesaw' between eastern to central and southern NRMs (e.g. 1550–1600 CE and 1700–1750 CE). In contrast, other periods reveal spatially consistent wetting (e.g. 1500–1550 CE) or drying (e.g. 1750–1800 CE). Emerging hot spot analysis further shows that some areas that appear naturally buffered from severe drought during the instrumental period have a greater exposure risk when the longer 600-year record is considered. These findings are particularly relevant to management plans when dealing with the impacts of climate extremes developed at regional scales. Our results demonstrate that integrating and extending instrumental records with palaeoclimate datasets will become increasingly important for developing robust and locally specific extreme event frequency information for managing water resources.

Blood flow rate to the femur of extinct kangaroos implies a higher locomotor intensity compared to living hopping macropods - Qiaohui Hu; Roger S. Seymour; Edward P. Snelling; Rod T. Wells (Journal of Mammalian Evolution, 2024)
The stocky skeletons and post-cranial anatomy of many extinct kangaroos indicate that they might have engaged in varied locomotor behaviors, rather than bipedal hopping, as their primary mode of locomotion. This study investigates support for this idea by estimating femoral bone perfusion, which is a correlate of locomotor intensity, in extinct kangaroos compared to living hopping species. Femur blood flow rates can be estimated from the sizes of nutrient foramina on the femur shaft of living and extinct species, without preservation of soft tissue. Estimated femur blood flow rates among the extinct Macropus , Protemnodon and Sthenurinae ( Sthenurus , Simosthenurus and Procoptodon ) are not significantly different from one another but are significantly greater than in living hopping macropods after accounting for the effect of body mass, consistent with their purportedly different locomotor style. The giant sthenurines have more robust femora than extrapolated from data of living hopping macropods, possibly due to the larger sthenurines requiring relatively stronger leg bones to support their heavier body weights, especially if loaded onto a single limb during bipedal striding.

Red Drum Salinity Tolerance: Comments on Ackerly et al. “Short-Term Salinity Stress During Early Development Impacts the Growth and Survival of Red Drum (Sciaenops ocellatus)” - A. Conway; S. Pauwels; M. Edwards; L. Fontenot; R. Palachek (Estuaries and Coasts, 2024)

Saltwater intrusion and sea level rise threatens U.S. rural coastal landscapes and communities - Kiera L. O’Donnell; Emily S. Bernhardt; Xi Yang; Ryan E. Emanuel; Marcelo Ardón; Manuel T. Lerdau; Alex K. Manda; Anna E. Braswell; Todd K. BenDor; Eric C. Edwards; Elizabeth Frankenberg; Ashley M. Helton; et al. (Anthropocene, 2024)

Cattle grazing management affects soil microbial diversity and community network complexity in the Northern Great Plains - Upama Khatri-Chhetri; Samiran Banerjee; Karen A. Thompson; Sylvie A. Quideau; Mark S. Boyce; Edward W. Bork; Cameron N. Carlyle (Science of The Total Environment, 2024)

FTIR spectra from grass pollen: A quest for species-level resolution of Poaceae and Cerealia-type pollen grains - F. Katsi; M.S. Kent; M. Jones; W.T. Fraser; P.E. Jardine; W. Eastwood; M. Mariani; C. Osborne; S. Edwards; B.H. Lomax (Review of Palaeobotany and Palynology, 2024)

Pervasive aqueous alteration in the early Solar System revealed by potassium isotopic variations in Ryugu samples and carbonaceous chondrites - Yan Hu; Frédéric Moynier; Wei Dai; Marine Paquet; Tetsuya Yokoyama; Yoshinari Abe; Jérôme Aléon; Conel M. O'D. Alexander; Sachiko Amari; Yuri Amelin; Ken-ichi Bajo; Martin Bizzarro; et al. (Icarus, 2024)

Land‐use change from market responses to oil palm intensification in Indonesia - Felix K. S. Lim; Luis Roman Carrasco; David P. Edwards; Jolian McHardy (Conservation Biology, 2024)
Oil palm is a major driver of tropical deforestation. A key intervention proposed to reduce the footprint of oil palm is intensifying production to free up spare land for nature, yet the indirect land‐use implications of intensification through market forces are poorly understood. We used a spatially explicit land‐rent modeling framework to characterize the supply and demand of oil palm in Indonesia under multiple yield improvement and demand elasticity scenarios and explored how shifts in market equilibria alter projections of crop expansion. Oil palm supply was sensitive to crop prices and yield improvements. Across all our scenarios, intensification raised agricultural rents and lowered the effectiveness of reductions in crop expansion. Increased yields lowered oil palm prices, but these price‐drops were not sufficient to prevent further cropland expansion from increased agricultural rents under a range of price elasticities of demand. Crucially, we found that agricultural intensification might only result in land being spared when the demand relationship was highly inelastic and crop prices were very low (i.e., a 70% price reduction). Under this scenario, the extent of land spared (∼0.32 million ha) was countered by the continued establishment of new plantations (∼1.04 million ha). Oil palm intensification in Indonesia could exacerbate current pressures on its imperiled biodiversity and should be deployed with stronger spatial planning and enforcement to prevent further cropland expansion.

Closing the gap between existing large‐area imaging research and marine conservation needs - Orion S. McCarthy; Kanisha Contractor; Will F. Figueira; Arthur C. R. Gleason; T. Shay Viehman; Clinton B. Edwards; Stuart A. Sandin (Conservation Biology, 2024)
Emerging technology has immense potential to increase the scale and efficiency of marine conservation. One such technology is large‐area imaging (LAI), which relies on structure‐from‐motion photogrammetry to create composite products, including 3‐dimensional (3‐D) environmental models, that are larger in spatial extent than the individual images used to create them. Use of LAI has become widespread in certain fields of marine science, primarily to measure the 3D structure of benthic ecosystems and track change over time. However, the use of LAI in the field of marine conservation appears limited. We conducted a review of the coral reef literature on the use of LAI to identify research themes and regional trends in applications of this technology. We also surveyed 135 coral reef scientists and conservation practitioners to determine community familiarity with LAI, evaluate barriers practitioners face in using LAI, and identify applications of LAI believed to be most exciting or relevant to coral conservation. Adoption of LAI was limited primarily to researchers at institutions based in advanced economies and was applied infrequently to conservation, although conservation practitioners and survey respondents from emerging economies indicated they expect to use LAI in the future. Our results revealed disconnect between current LAI research topics and conservation priorities identified by practitioners, highlighting the need for more diverse, conservation‐relevant research using LAI. We provide recommendations for how early adopters of LAI (typically Global North scientists from well‐resourced institutions) can facilitate access to this conservation technology. These recommendations include developing training resources, creating partnerships for data storage and analysis, publishing standard operating procedures for LAI workflows, standardizing methods, developing tools for efficient data extraction from LAI products, and conducting conservation‐relevant research using LAI.

Surface ocean warming near the core of hurricane Sam and its representation in forecast models - Andrew M. Chiodi; Hristina Hristova; Gregory R. Foltz; Jun A. Zhang; Calvin W. Mordy; Catherine R. Edwards; Chidong Zhang; Christian Meinig; Dongxiao Zhang; Edoardo Mazza; Edward D. Cokelet; Eugene F. Burger; et al. (Frontiers in Marine Science, 2024)
On September 30, 2021, a saildrone uncrewed surface vehicle intercepted Hurricane Sam in the northwestern tropical Atlantic and provided continuous observations near the eyewall. Measured surface ocean temperature unexpectedly increased during the first half of the storm. Saildrone current shear and upper-ocean structure from the nearest Argo profiles show an initial trapping of wind momentum by a strong halocline in the upper 30 m, followed by deeper mixing and entrainment of warmer subsurface water into the mixed layer. The ocean initial conditions provided to operational forecast models failed to capture the observed upper-ocean structure. The forecast models failed to simulate the warming and developed a surface cold bias of ~0.5°C by the time peak winds were observed, resulting in a 12-17% underestimation of surface enthalpy flux near the eyewall. Results imply that enhanced upper-ocean observations and, critically, improved assimilation into the hurricane forecast systems, could directly benefit hurricane intensity forecasts.

The underwater soundscape of the North Sea - F. Basan; J.-G. Fischer; R. Putland; J. Brinkkemper; C.A.F. de Jong; B. Binnerts; A. Norro; D. Kühnel; L.-A. Ødegaard; M. Andersson; E. Lalander; J. Tougaard; et al. (Marine Pollution Bulletin, 2024)

Habitat modelling of native freshwater mussels distinguishes river specific differences in the Detroit and St. Clair rivers of the Laurentian Great Lakes - Shay S. Keretz; Daelyn A. Woolnough; Todd J. Morris; Edward F. Roseman; David T. Zanatta (Ecological Modelling, 2024)

Fine-mapping of a major locus for Fusarium wilt resistance in flax (Linum usitatissimum L.) - S. Cloutier; T. Edwards; C. Zheng; H. M. Booker; T. Islam; K. Nabetani; H. R. Kutcher; O. Molina; F. M. You (Theoretical and Applied Genetics, 2024)
Key message Fine-mapping of a locus on chromosome 1 of flax identified an S-lectin receptor-like kinase (SRLK) as the most likely candidate for a major Fusarium wilt resistance gene. Abstract Fusarium wilt, caused by the soil-borne fungal pathogen Fusarium oxysporum f. sp. lini , is a devastating disease in flax. Genetic resistance can counteract this disease and limit its spread. To map major genes for Fusarium wilt resistance, a recombinant inbred line population of more than 700 individuals derived from a cross between resistant cultivar ‘Bison’ and susceptible cultivar ‘Novelty’ was phenotyped in Fusarium wilt nurseries at two sites for two and three years, respectively. The population was genotyped with 4487 single nucleotide polymorphism (SNP) markers. Twenty-four QTLs were identified with IciMapping, 18 quantitative trait nucleotides with 3VmrMLM and 108 linkage disequilibrium blocks with RTM-GWAS. All models identified a major QTL on chromosome 1 that explained 20–48% of the genetic variance for Fusarium wilt resistance. The locus was estimated to span ~ 867 Kb but included a ~ 400 Kb unresolved region. Whole-genome sequencing of ‘CDC Bethune’, ‘Bison’ and ‘Novelty’ produced ~ 450 Kb continuous sequences of the locus. Annotation revealed 110 genes, of which six were considered candidate genes. Fine-mapping with 12 SNPs and 15 Kompetitive allele-specific PCR (KASP) markers narrowed down the interval to ~ 69 Kb, which comprised the candidate genes Lus10025882 and Lus10025891 . The latter, a G-type S-lectin receptor-like kinase (SRLK) is the most likely resistance gene because it is the only polymorphic one. In addition, Fusarium wilt resistance genes previously isolated in tomato and Arabidopsis belonged to the SRLK class. The robust KASP markers can be used in marker-assisted breeding to select for this major Fusarium wilt resistance locus.

Temperature Thresholds for Leaf Damage from Two Extreme Freeze Events (2018 and 2021) Near the Northern Range Limit of Black Mangroves (Avicennia germinans) in Southeastern North America - Simen Kaalstad; Michael J. Osland; Donna J. Devlin; C. Edward Proffitt; Laura C. Feher; Anna R. Armitage; Richard H. Day; Kathleen M. Swanson; Gordon H. Anderson; Brigid Berger; Just Cebrian; Karen L. Cummins; et al. (Estuaries and Coasts, 2024)

Indigenous Peoples' Lands are critical for safeguarding vertebrate diversity across the tropics - Jocelyne S. Sze; Dylan Z. Childs; L. Roman Carrasco; Álvaro Fernández‐Llamazares; Stephen T. Garnett; David P. Edwards (Global Change Biology, 2024)
Indigenous Peoples are long‐term custodians of their lands, but only recently are their contributions to conservation starting to be recognized in biodiversity policy and practice. Tropical forest loss and degradation are lower in Indigenous lands than unprotected areas, yet the role of Indigenous Peoples' Lands (IPL) in biodiversity conservation has not been properly assessed from regional to global scales. Using species distribution ranges of 11,872 tropical forest‐dependent vertebrates to create area of habitat maps, we identified the overlap of these species ranges with IPL and then compared values inside and outside of IPL for species richness, extinction vulnerability, and range‐size rarity. Of assessed vertebrates, at least 76.8% had range overlaps with IPL, on average overlapping ~25% of their ranges; at least 120 species were found only within IPL. Species richness within IPL was highest in South America, while IPL in Southeast Asia had highest extinction vulnerability, and IPL in Dominica and New Caledonia were important for range‐size rarity. Most countries in the Americas had higher species richness within IPL than outside, whereas most countries in Asia had lower extinction vulnerability scores inside IPL and more countries in Africa and Asia had slightly higher range‐size rarity in IPL. Our findings suggest that IPL provide critical support for tropical forest‐dependent vertebrates, highlighting the need for greater inclusion of Indigenous Peoples in conservation target‐setting and program implementation, and stronger upholding of Indigenous Peoples' rights in conservation policy.

Fungal community dissimilarity predicts plant–soil feedback strength in a lowland tropical forest - Camille S. Delavaux; Janika K. Angst; Hilario Espinosa; Makenna Brown; Daniel F. Petticord; John W. Schroeder; Kirk Broders; Edward A. Herre; James D. Bever; Thomas W. Crowther (Ecology, 2024)
Soil microbes impact plant community structure and diversity through plant–soil feedbacks. However, linking the relative abundance of plant pathogens and mutualists to differential plant recruitment remains challenging. Here, we tested for microbial mediation of pairwise feedback using a reciprocal transplant experiment in a lowland tropical forest in Panama paired with amplicon sequencing of soil and roots. We found evidence that plant species identity alters the microbial community, and these changes in microbial composition alter subsequent growth and survival of conspecific plants. We also found that greater community dissimilarity between species in their arbuscular mycorrhizal and nonpathogenic fungi predicted increased positive feedback. Finally, we identified specific microbial taxa across our target functional groups that differentially accumulated under conspecific settings. Collectively, these findings clarify how soil pathogens and mutualists mediate net feedback effects on plant recruitment, with implications for management and restoration.

Reinstatement and expansion of the genus Anatherum (Andropogoneae, Panicoideae, Poaceae) - Maria S. Vorontsova; Kurt B. Petersen; Patrick Minx; Taylor M. Aubuchon-Elder; M. Cinta Romay; Edward S. Buckler; Elizabeth A. Kellogg (Systematics and Biodiversity, 2023)

Nutricline adjustment by internal tidal beam generation enhances primary production in idealized numerical models - Jasen R. Jacobsen; Christopher A. Edwards; Brian S. Powell; John A. Colosi; Jerome Fiechter (Frontiers in Marine Science, 2023)
When the barotropic tide encounters variable bathymetry, fluctuating flow along a topographic slope generates baroclinic tides, or internal tides. There is growing evidence that these internal tides can affect primary production in the euphotic zone, though the dominant mechanisms are unclear. Internal tides move passive phytoplankton through an exponentially varying light field, enhancing primary production near the base of the euphotic zone. In addition internal tides also increase primary production through vertical nutrient advection into the euphotic zone. Topographically generated internal tides can be separated into two regimes: 1) the often highly nonlinear near-field regime where tidal beams are observed and 2) the more linear far-field regime. This study examines the primary production response to these internal tide processes using the Regional Ocean Modeling System (ROMS) coupled to a simple Nutrient, Phytoplankton, Zooplankton, Detritus (NPZD) model configured for an oligotrophic system with the nutricline positioned below 50 m depth. These idealized simulations generate internal tide beams with an oscillating, horizontal body force at the M 2 tidal frequency that is applied to domains with a bathymetric step and uniform stratification. Sensitivity of the primary production response to the energy content of the tidal beam is obtained by adjusting the height and slope of the bathymetric step. Simulation results reveal that primary production intensifies along tidal beams due to the local enhancement of parcel vertical displacement (light effect) and nutrient advective flux divergence (nutrient effect). In the near-field regime across the range of step heights and slopes in this study, the nutrient effect is an order of magnitude larger and explains 92% of the variance in primary production versus only 14% for the light effect. The geometry of the generating feature sets the kinematics of the tidal beam. The light effect is limited in the euphotic zone across our domains because realized changes in light experienced over a tidal cycle are small relative to the amount of light available at a particular depth. In contrast, the magnitude of the nutrient effect increases more substantially with tidal beam energy.

Utility of wastewater genomic surveillance compared to clinical surveillance to track the spread of the SARS-CoV-2 Omicron variant across England - Franziska S. Brunner; Alexander Payne; Edward Cairns; George Airey; Richard Gregory; Natalie D. Pickwell; Myles Wilson; Matthew Carlile; Nadine Holmes; Verity Hill; Harry Child; Jasmine Tomlinson; et al. (Water Research, 2023)

A globally integrated structure of taxonomy to support biodiversity science and conservation - Emily L. Sandall; Aurore A. Maureaud; Robert Guralnick; Melodie A. McGeoch; Yanina V. Sica; Matthew S. Rogan; Douglas B. Booher; Robert Edwards; Nico Franz; Kate Ingenloff; Maisha Lucas; Charles J. Marsh; et al. (Trends in Ecology & Evolution, 2023)

Valuing bioeconomic impacts of regulation on nutrient loads mediated by invasive mussels in Lake Michigan - Stephanie Brockmann; David Finnoff; Nicholas Boucher; Doran M. Mason; Edward S. Rutherford; Hongyan Zhang (Journal of Environmental Management, 2023)

Sampling method drives differing detection of responses to land-use change in small mammals - Mariana F. Rocha; Luiz Fernando S. Magnago; Marcelo Passamani; Vinicius Chaga Lopes; Sergio Barbiero Lage; David P. Edwards (Journal for Nature Conservation, 2023)

Fungal diversity in homes and asthma morbidity among school-age children in New York City - Samuel J. Cochran; Luis Acosta; Adnan Divjan; Angela R. Lemons; Andrew G. Rundle; Rachel L. Miller; Edward Sobek; Brett J. Green; Matthew S. Perzanowski; Karen C. Dannemiller (Environmental Research, 2023)

An acoustic-optic comparison of fish assemblages at a Rigs-to-Reefs habitat and coral reef in the Gulf of Thailand - Edward C.P. Sibley; Alethea S. Madgett; Travis S. Elsdon; Michael J. Marnane; Euan S. Harvey; Se Songploy; Jes Kettradad; Paul G. Fernandes (Estuarine, Coastal and Shelf Science, 2023)

Cationic Proteins Rich in Lysine Residue Trigger Formation of Non-bilayer Lipid Phases in Model and Biological Membranes: Biophysical Methods of Study - Meiyi Li; Edward S. Gasanoff (The Journal of Membrane Biology, 2023)

Atmospheric Small-Scale Turbulence from Three-Dimensional Hot-film Data - Livia S. Freire; Marcelo Chamecki; Edward G. Patton (Boundary-Layer Meteorology, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Reply to Discussion of Yule, C. T. G., Daniell, J., Edwards, D. S., Rollet, N., & Roberts, E. M. (2023). Reconciling the onshore/offshore stratigraphy of the Canning Basin and implications for petroleum prospectivity. Australian Journal of Earth Sciences , 70 (5), 691–715 - C. T. G. Yule; J. Daniell; D. S. Edwards; N. Rollet; E. M. Roberts (Australian Journal of Earth Sciences, 2023)

Total infectome investigation of diphtheritic stomatitis in yellow-eyed penguins (Megadyptes antipodes) reveals a novel and abundant megrivirus - Janelle R. Wierenga; Rebecca M. Grimwood; Harry S. Taylor; Stuart Hunter; Lisa S. Argilla; Trudi Webster; Lauren Lim; Rebecca French; Hendrik Schultz; Fátima Jorge; Mihnea Bostina; Laura Burga; et al. (Veterinary Microbiology, 2023)

Early-life ozone exposure modulates region-specific gene expression in the developing rat lung - Nathanial C. Stevens; Patricia C. Edwards; Laura S. Van Winkle (Toxicology Letters, 2023)

Building an inclusive wave in marine science: Sense of belonging and Society for Women in Marine Science symposia - Katherine N. Canfield; Alexa R. Sterling; Christina M. Hernández; Sophie N. Chu; Bethanie R. Edwards; Diana N. Fontaine; Jillian M. Freese; Marissa S. Giroux; Aubree E. Jones; Alexandra J. McCarty; Hannah K. Morrissette; Hilary I. Palevsky; et al. (Progress in Oceanography, 2023)

Isopropyl alcohol inhalation versus 5-HT3 antagonists for treatment of nausea: a meta-analysis of randomised controlled trials - James S. Kimber; Joshua G. Kovoor; John M. Glynatsis; Samuel J. West; Thi Thien Nhi Mai; Jonathan Henry W. Jacobsen; Christopher D. Ovenden; Stephen Bacchi; Joseph N. Hewitt; Aashray K. Gupta; Suzanne Edwards; Fiona J. Taverner; et al. (European Journal of Clinical Pharmacology, 2023)
Purpose Nausea is a common and unpleasant sensation for which current therapies such as serotonin (5-HT 3 ) antagonists are often ineffective, while also conferring a risk of potential adverse events. Isopropyl alcohol (IPA) has been proposed as a treatment for nausea. We aimed to compare IPA with 5-HT 3 antagonists for the treatment of nausea across all clinical settings. Methods MEDLINE, EMBASE, PubMed, CENTRAL and CINAHL were searched from inception to 17 July 2023 for randomised controlled trials (RCTs) comparing inhaled IPA and a 5-HT 3 antagonist for treatment of nausea. Severity and duration of nausea, rescue antiemetic use, adverse events and patient satisfaction were the outcomes sought. Risk of bias (RoB) was assessed using Cochrane RoB 2. Random-effects model was used for meta-analysis. Combination of meta-analyses and narrative review was used to synthesise findings. The evidence was appraised using GRADE. Results From 1242 records, 4 RCTs were included with 382 participants. Participants receiving IPA had a significantly lower mean time to 50% reduction in nausea (MD − 20.06; 95% CI − 26.26, − 13.85). Nausea score reduction at 30 min was significantly greater in the IPA group (MD 21.47; 95% CI 15.47, 27.47). IPA led to significantly reduced requirement for rescue antiemetics (OR 0.60; 95% CI 0.37, 0.95; p = 0.03). IPA led to no significant difference in patient satisfaction when compared with a 5-HT 3 antagonist. The overall GRADE assessment of evidence quality ranged from very low to low. Conclusion IPA may provide rapid, effective relief of nausea when compared with 5-HT 3 antagonists.

Free-water imaging reveals unique brain microstructural deficits in hispanic individuals with Dementia - Edward Ofori; David E. Vaillancourt; Maria T Greig-Custo; Warren Barker; Kevin Hanson; Steven T. DeKosky; Cynthia S. Garvan; Malek Adjouadi; Todd Golde; David A. Loewenstein; Chad Stecher; Rylan Fowers; et al. (Brain Imaging and Behavior, 2023)

Reproductive quality evaluation of male Indian white prawn Penaeus indicus broodstock fed diets supplemented with polychaete extracts ( Marphysa sp.) - Sheryll S. Santander-Avanceña; Rex Ferdinand M. Traifalgar; Erish G. Estante-Superio; Steve P. Janagap; Roger Edward P. Mamauag; Harold M. Monteclaro; Liberato V. Laureta; Gerald F. Quinitio (Invertebrate Reproduction & Development, 2023)

Microplastic contamination in Indian rural and urban lacustrine ecosystems - R.L. Laju; M. Jayanthi; K. Immaculate Jeyasanta; Jamila Patterson; Deepak S. Bilgi; Narmatha Sathish; J.K. Patterson Edward (Science of The Total Environment, 2023)

Incorporating heterogeneity in farmer disease control behaviour into a livestock disease transmission model - Edward M. Hill; Naomi S. Prosser; Paul E. Brown; Eamonn Ferguson; Martin J. Green; Jasmeet Kaler; Matt J. Keeling; Michael J. Tildesley (Preventive Veterinary Medicine, 2023)

Mitochondrial dysfunction and oxidative stress contribute to cross-generational toxicity of benzo(a)pyrene in Danio rerio - Jordan S. Kozal; Nishad Jayasundara; Andrey Massarsky; Casey D. Lindberg; Anthony N. Oliveri; Ellen M. Cooper; Edward D. Levin; Joel N. Meyer; Richard T. Di Giulio (Aquatic Toxicology, 2023)

Interactions among Sodalis, Glossina pallidipes salivary gland hypertrophy virus and trypanosomes in wild Glossina pallidipes - Deusdedit J. Malulu; Hamisi S. Nyingilili; Delphina Edward; Peter Lucas; Ismail W. R. Taifa; Imna I. Malele; Adly M. M. Abd-Alla (International Journal of Tropical Insect Science, 2023)

Large sardine resource discovered off south-eastern Australia: Potential risks, challenges and benefits of establishing a new fishery - Tim M. Ward; Barrett W. Wolfe; Gretchen L. Grammer; Alex R. Ivey; Edward King; Andreas Schiller; Karlie S. McDonald; Jeffrey M. Dambacher (Marine Policy, 2023)

Inclusion of live mud polychaete (Marphysa iloiloensis) in the feeding regime improved the hatchery performance of domesticated Indian white shrimp (Penaeus indicus) - Erish G. Estante-Superio; Mary Anne E. Mandario; Sheryll S. Santander-Avanceña; Therese Marie M. Geanga; Fe Dolores Parado-Estepa; Roger Edward P. Mamauag (Regional Studies in Marine Science, 2023)

Biogeography and evolution of social parasitism in Australian Myrmecia bulldog ants revealed by phylogenomics - Daniela Mera-Rodríguez; Hervé Jourdan; Philip S. Ward; Steven Shattuck; Stefan P. Cover; Edward O. Wilson; Christian Rabeling (Molecular Phylogenetics and Evolution, 2023)

Sound sees more: A comparison of imaging sonars and optical cameras for estimating fish densities at artificial reefs - Edward C.P. Sibley; Travis S. Elsdon; Michael J. Marnane; Alethea S. Madgett; Euan S. Harvey; Thomas Cornulier; Damon Driessen; Paul G. Fernandes (Fisheries Research, 2023)

Evaluation in a porcine wound model and long-term clinical assessment of an autologous heterogeneous skin construct used to close full-thickness wounds - Nicholas Baetz; Pratima Labroo; Marytheresa Ifediba; Devin Miller; Kendall Stauffer; Michael Sieverts; Jessie Nicodemus-Johnson; Eric Chan; Ian Robinson; James Miess; Stephanie Roth; Jenny Irvin; et al. (Tissue and Cell, 2023)

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Complement component C1q is an immunological rheostat that regulates Fc:Fc$$γ$$R interactions - Edward C. So; Hua Zhou; Ariana Greenwell; Erin E. Burch; Yaping Ji; Emmanuel Y. Mérigeon; Henrik S. Olsen; Søren M. Bentzen; David S. Block; Xiaoyu Zhang; Scott E. Strome (Immunogenetics, 2023)

Reconciling the onshore/offshore stratigraphy of the Canning Basin and implications for petroleum prospectivity - C. T. G. Yule; J. Daniell; D. S. Edwards; N. Rollet; E. M. Roberts (Australian Journal of Earth Sciences, 2023)

Seasonal and spatial variations in the distribution pattern, sources and impacts of microplastics along different coastal zones of Tamil Nadu, India - K. Immaculate Jeyasanta; M. Jayanthi; R.L. Laju; Jamila Patterson; Deepak S. Bilgi; Narmatha Sathish; J.K. Patterson Edward (Marine Pollution Bulletin, 2023)

Assessment of selected pharmaceuticals in Riyadh wastewater treatment plants, Saudi Arabia: Mass loadings, seasonal variations, removal efficiency and environmental risk - Obaid A. Alharbi; Edward Jarvis; Aikaterini Galani; Nikolaos S. Thomaidis; Maria-Christina Nika; Deborah V. Chapman (Science of The Total Environment, 2023)

An improved method for determining frequency of multiple variants of SARS-CoV-2 in wastewater using qPCR assays - Meghan Fuzzen; Nathanael B.J. Harper; Hadi A. Dhiyebi; Nivetha Srikanthan; Samina Hayat; Leslie M. Bragg; Shelley W. Peterson; Ivy Yang; J.X. Sun; Elizabeth A. Edwards; John P. Giesy; Chand S. Mangat; et al. (Science of The Total Environment, 2023)

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

Vegetation changes over time in Prairie Pothole Region reference wetlands - Christina L. M. Hargiss; Savannah Fritz Metz; Edward S. DeKeyser; Jack Norland; Breanna Kobiela; Deirdre A. Prischmann-Voldseth (Environmental Monitoring and Assessment, 2023)

Woronichinia naegeliana: A common nontoxigenic component of temperate freshwater cyanobacterial blooms with 30% of its genome in transposons - Theo W. Dreher; Robin Matthews; Edward W. Davis; Ryan S. Mueller (Harmful Algae, 2023)

Long-term trends in nitrate and chloride in streams in an exurban watershed - Emma S. Castiblanco; Peter M. Groffman; Jonathan Duncan; Lawrence E. Band; Edward Doheny; Gary T. Fisher; Emma Rosi; Amanda K. Suchy (Urban Ecosystems, 2023)

The benefits of regular aerobic exercise training on cerebrovascular function and cognition in older adults - Edward S. Bliss; Samia M. Biki; Rachel H. X. Wong; Peter R. C. Howe; Dean E. Mills (European Journal of Applied Physiology, 2023)
We compared the differences in cerebrovascular and cognitive function between 13 aerobic exercise trained, older adults and 13 age-, height- and sex-matched sedentary, untrained controls. We determined whether other measures accounted for differences in cerebrovascular and cognitive function between these groups and examined the associations between these functions. Participants undertook anthropometric, mood, cardiovascular, exercise performance, strength, cerebrovascular, and cognitive measurements, and a blood collection. Transcranial Doppler ultrasonography determined cerebrovascular responsiveness (CVR) to hypercapnia and cognitive stimuli. The trained group had a higher CVR to hypercapnia (80.3 ± 7.2 vs 35.1 ± 6.7%, P < 0.001), CVR to cognitive stimuli (30.1 ± 2.9 vs 17.8 ± 1.4%, P = 0.001) and total composite cognitive score (117 ± 2 vs 98 ± 4, P < 0.001) than the controls. These parameters no longer remained statistically different between the groups following adjustments for covariates. There were positive correlations between the total composite cognitive score and CVR to hypercapnia ( r = 0.474, P = 0.014) and CVR to cognitive stimuli ( r = 0.685, P < 0.001). We observed a relationship between cerebrovascular and cognitive function in older adults and an interaction between regular lifelong aerobic exercise training and cardiometabolic factors that may directly influence these functions.

Effects of Environmental Variation in Structuring Population Genetic Variation in the False-Water Cobras (Xenodontinae: Hydrodynastes) - Priscila S. Carvalho; Diego J. Santana; Hussam Zaher; Edward A. Myers (Evolutionary Biology, 2023)

Multi-year landscape-scale efficacy analysis of fluridone treatment of invasive submerged aquatic vegetation in the Sacramento–San Joaquin Delta - Shruti Khanna; Jereme W. Gaeta; J. Louise Conrad; Edward S. Gross (Biological Invasions, 2023)
Invasive aquatic macrophytes are a major threat to estuarine ecosystems globally, posing difficult control challenges for resource managers. This study examined the efficacy of a fluridone treatment program to control invasive submerged aquatic vegetation (SAV). We leveraged four datasets to examine efficacy of fluridone treatment in the Sacramento–San Joaquin Delta, a freshwater tidal estuary in California, from 2014 to 2018. Annual SAV coverage maps derived from spectroscopy data were used in conjunction with fluridone application data and water current speed predicted by a 3-D hydrodynamic model of the study system. Our objective was to determine if the probability of SAV occurrence in treated sites was significantly different from untreated sites. We examined whether efficacy was influenced by the amount of herbicide applied at a site, the local current speed, and the treatment history of the site. We found that treatment efficacy was positively associated with the amount of herbicide applied per unit area, but this effect was mediated by a negative association with current speed. The efficacy of treatment did not improve when a site was treated for multiple consecutive years. Finally, we did not detect legacy effects one year after cessation of treatment. Our results suggest the need for careful selection of treatment sites to ensure that the amount of fluridone applied is likely to have significant impact given local current speeds. Our study underscores the need for development of additional treatment methodologies for hydrologically dynamic systems such as estuaries, particularly when control is needed year-round and for multiple years.

Coral adaptive capacity insufficient to halt global transition of coral reefs into net erosion under climate change - Christopher Edward Cornwall; Steeve Comeau; Simon D. Donner; Chris Perry; John Dunne; Ruben van Hooidonk; James S. Ryan; Cheryl A. Logan (Global Change Biology, 2023)
Projecting the effects of climate change on net reef calcium carbonate production is critical to understanding the future impacts on ecosystem function, but prior estimates have not included corals' natural adaptive capacity to such change. Here we estimate how the ability of symbionts to evolve tolerance to heat stress, or for coral hosts to shuffle to favourable symbionts, and their combination, may influence responses to the combined impacts of ocean warming and acidification under three representative concentration pathway (RCP) emissions scenarios (RCP2.6, RCP4.5 and RCP8.5). We show that symbiont evolution and shuffling, both individually and when combined, favours persistent positive net reef calcium carbonate production. However, our projections of future net calcium carbonate production (NCCP) under climate change vary both spatially and by RCP. For example, 19%–35% of modelled coral reefs are still projected to have net positive NCCP by 2050 if symbionts can evolve increased thermal tolerance, depending on the RCP. Without symbiont adaptive capacity, the number of coral reefs with positive NCCP drops to 9%–13% by 2050. Accounting for both symbiont evolution and shuffling, we project median positive NCPP of coral reefs will still occur under low greenhouse emissions (RCP2.6) in the Indian Ocean, and even under moderate emissions (RCP4.5) in the Pacific Ocean. However, adaptive capacity will be insufficient to halt the transition of coral reefs globally into erosion by 2050 under severe emissions scenarios (RCP8.5).

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Uranus ring occultation observations: 1977–2006 - Richard G. French; Colleen A. McGhee-French; Mitchell Gordon; Richard L. Baron; Amanda S. Bosh; Marc W. Buie; Nancy Chanover; Mary Ann Clark; Edward W. Dunham; Linda M. French; Ian S. Glass; Jay D. Goguen; et al. (Icarus, 2023)

Spectroscopic identification of the catalytic intermediates of cytochrome c oxidase in respiring heart mitochondria - Raul Covian; Lanelle O. Edwards; Bertrand M. Lucotte; Robert S. Balaban (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2023)

Updated guidelines for gene nomenclature in wheat - S. A. Boden; R. A. McIntosh; C. Uauy; S. G. Krattinger; J. Dubcovsky; W. J. Rogers; X. C. Xia; E. D. Badaeva; A. R. Bentley; G. Brown-Guedira; M. Caccamo; L. Cattivelli; et al. (Theoretical and Applied Genetics, 2023)
Key message Here, we provide an updated set of guidelines for naming genes in wheat that has been endorsed by the wheat research community. Abstract The last decade has seen a proliferation in genomic resources for wheat, including reference- and pan-genome assemblies with gene annotations, which provide new opportunities to detect, characterise, and describe genes that influence traits of interest. The expansion of genetic information has supported growth of the wheat research community and catalysed strong interest in the genes that control agronomically important traits, such as yield, pathogen resistance, grain quality, and abiotic stress tolerance. To accommodate these developments, we present an updated set of guidelines for gene nomenclature in wheat. These guidelines can be used to describe loci identified based on morphological or phenotypic features or to name genes based on sequence information, such as similarity to genes characterised in other species or the biochemical properties of the encoded protein. The updated guidelines provide a flexible system that is not overly prescriptive but provides structure and a common framework for naming genes in wheat, which may be extended to related cereal species. We propose these guidelines be used henceforth by the wheat research community to facilitate integration of data from independent studies and allow broader and more efficient use of text and data mining approaches, which will ultimately help further accelerate wheat research and breeding.

Why human rights matter for marine conservation - Patrick Smallhorn-West; Edward Allison; Georgina Gurney; Divya Karnad; Heidi Kretser; Aaron Savio Lobo; Sangeeta Mangubhai; Helen Newing; Kamille Pennell; Sushil Raj; Alexander Tilley; Haley Williams; et al. (Frontiers in Marine Science, 2023)
Human rights matter for marine conservation because people and nature are inextricably linked. A thriving planet cannot be one that contains widespread human suffering or stifles human potential; and a thriving humanity cannot exist on a dying planet. While the field of marine conservation is increasingly considering human well-being, it retains a legacy in some places of protectionism, colonialism, and fortress conservation. Here, we i) provide an overview of human rights principles and how they relate to marine conservation, ii) document cases where tensions have occurred between marine conservation goals and human rights, iii) review the legal and ethical obligations, and practical benefits, for marine conservation to support human rights, and iv) provide practical guidance on integrating human rights principles into marine conservation. We argue that adopting a human rights-based approach to marine conservation, that is integrating equity as a rights-based condition rather than a charitable principle, will not only help meet legal and ethical obligations to respect, protect, and fulfil human rights, but will also result in greater and more enduring conservation impact.

Seawater from Bergen harbor is a reservoir of conjugative multidrug-resistance plasmids carrying genes for virulence - Nachiket P. Marathe; Didrik H. Grevskott; Francisco Salvà-Serra; Priyank S. Nimje; Cecilie S. Svanevik; Bjørn Tore Lunestad; Edward R.B. Moore (International Journal of Hygiene and Environmental Health, 2023)

Thalamus sends information about arousal but not valence to the amygdala - Chris A. Leppla; Laurel R. Keyes; Gordon Glober; Gillian A. Matthews; Kanha Batra; Maya Jay; Yu Feng; Hannah S. Chen; Fergil Mills; Jeremy Delahanty; Jacob M. Olson; Edward H. Nieh; et al. (Psychopharmacology, 2023)
Rationale The basolateral amygdala (BLA) and medial geniculate nucleus of the thalamus (MGN) have both been shown to be necessary for the formation of associative learning. While the role that the BLA plays in this process has long been emphasized, the MGN has been less well-studied and surrounded by debate regarding whether the relay of sensory information is active or passive. Objectives We seek to understand the role the MGN has within the thalamoamgydala circuit in the formation of associative learning. Methods Here, we use optogenetics and in vivo electrophysiological recordings to dissect the MGN-BLA circuit and explore the specific subpopulations for evidence of learning and synthesis of information that could impact downstream BLA encoding. We employ various machine learning techniques to investigate function within neural subpopulations. We introduce a novel method to investigate tonic changes across trial-by-trial structure, which offers an alternative approach to traditional trial-averaging techniques. Results We find that the MGN appears to encode arousal but not valence, unlike the BLA which encodes for both. We find that the MGN and the BLA appear to react differently to expected and unexpected outcomes; the BLA biased responses toward reward prediction error and the MGN focused on anticipated punishment. We uncover evidence of tonic changes by visualizing changes across trials during inter-trial intervals (baseline epochs) for a subset of cells. Conclusion We conclude that the MGN-BLA projector population acts as both filter and transferer of information by relaying information about the salience of cues to the amygdala, but these signals are not valence-specified.

Freshwater Flow Affects Subsidies of a Copepod (Pseudodiaptomus forbesi) to Low-Salinity Food Webs in the Upper San Francisco Estuary - Jason L. Hassrick; Josh Korman; Wim J. Kimmerer; Edward S. Gross; Lenny F. Grimaldo; Calvin Lee; Andrew A. Schultz (Estuaries and Coasts, 2023)
Productivity of the food web supporting small pelagic fishes in the upper San Francisco Estuary is chronically low, and some of the native fish species are in a long-term decline. The low-salinity (oligohaline) zone (LSZ) is particularly depauperate in phytoplankton and zooplankton. Based on prior empirical studies, it is hypothesized that freshwater flow increases the subsidy of a key copepod prey species ( Pseudodiaptomus forbesi ) from its freshwater population center into the LSZ. We combined hydrodynamic and particle-tracking modeling with Bayesian analysis in a box-model approach to estimate the magnitude of this subsidy and its dependence on freshwater flow rates. Net gains of P. forbesi into the LSZ came mostly from freshwater, landward regions of higher copepod abundance. The subsidy increased with freshwater flow, a finding that supports previous empirical analyses. However, in the context of persistent drought and ongoing climate change, the levels required to achieve a detectable net gain may be difficult and costly to achieve.

Survival of epithelial ovarian cancer in Black women: a society to cell approach in the African American cancer epidemiology study (AACES) - Joellen M. Schildkraut; Courtney Johnson; Lauren F. Dempsey; Bo Qin; Paul Terry; Maxwell Akonde; Edward S. Peters; Hannah Mandle; Michele L. Cote; Lauren Peres; Patricia Moorman; Ann G. Schwartz; et al. (Cancer Causes & Control, 2023)
Purpose The causes for the survival disparity among Black women with epithelial ovarian cancer (EOC) are likely multi-factorial. Here we describe the African American Cancer Epidemiology Study (AACES), the largest cohort of Black women with EOC. Methods AACES phase 2 (enrolled 2020 onward) is a multi-site, population-based study focused on overall survival (OS) of EOC. Rapid case ascertainment is used in ongoing patient recruitment in eight U.S. states, both northern and southern. Data collection is composed of a survey, biospecimens, and medical record abstraction. Results characterizing the survival experience of the phase 1 study population (enrolled 2010–2015) are presented. Results Thus far, ~ 650 patients with EOC have been enrolled in the AACES. The five-year OS of AACES participants approximates those of Black women in the Surveillance Epidemiology and End Results (SEER) registry who survive at least 10-month past diagnosis and is worse compared to white women in SEER, 49 vs. 60%, respectively. A high proportion of women in AACES have low levels of household income (45% < $25,000 annually), education (51% ≤ high school education), and insurance coverage (32% uninsured or Medicaid). Those followed annually differ from those without follow-up with higher levels of localized disease (28 vs 24%) and higher levels of optimal debulking status (73 vs 67%). Conclusion AACES is well positioned to evaluate the contribution of social determinants of health to the poor survival of Black women with EOC and advance understanding of the multi-factorial causes of the ovarian cancer survival disparity in Black women.

Prediction of near‐term climate change impacts on UK wheat quality and the potential for adaptation through plant breeding - Nick S. Fradgley; James Bacon; Alison R. Bentley; Germano Costa‐Neto; Andrew Cottrell; Jose Crossa; Jaime Cuevas; Matthew Kerton; Edward Pope; Stéphanie M. Swarbreck; Keith A. Gardner (Global Change Biology, 2023)
Wheat is a major crop worldwide, mainly cultivated for human consumption and animal feed. Grain quality is paramount in determining its value and downstream use. While we know that climate change threatens global crop yields, a better understanding of impacts on wheat end‐use quality is also critical. Combining quantitative genetics with climate model outputs, we investigated UK‐wide trends in genotypic adaptation for wheat quality traits. In our approach, we augmented genomic prediction models with environmental characterisation of field trials to predict trait values and climate effects in historical field trial data between 2001 and 2020. Addition of environmental covariates, such as temperature and rainfall, successfully enabled prediction of genotype by environment interactions (G × E), and increased prediction accuracy of most traits for new genotypes in new year cross validation. We then extended predictions from these models to much larger numbers of simulated environments using climate scenarios projected under Representative Concentration Pathways 8.5 for 2050–2069. We found geographically varying climate change impacts on wheat quality due to contrasting associations between specific weather covariables and quality traits across the UK. Notably, negative impacts on quality traits were predicted in the East of the UK due to increased summer temperatures while the climate in the North and South‐west may become more favourable with increased summer temperatures. Furthermore, by projecting 167,040 simulated future genotype–environment combinations, we found only limited potential for breeding to exploit predictable G × E to mitigate year‐to‐year environmental variability for most traits except Hagberg falling number. This suggests low adaptability of current UK wheat germplasm across future UK climates. More generally, approaches demonstrated here will be critical to enable adaptation of global crops to near‐term climate change.

Composition and Patterns of Taxa Assemblages in the Western Channel Assessed by 18S Sequencing, Microscopy and Flow Cytometry - Rowena Stern; Kathryn Picard; Jessica Clarke; Charlotte E. Walker; Claudia Martins; Clare Marshall; Ana Amorim; E. Malcolm S. Woodward; Claire Widdicombe; Glen Tarran; Martin Edwards (Journal of Marine Science and Engineering, 2023)
Plankton monitoring by microscopy offers a long-term ecological perspective of plankton communities, but detection approaches are uniquely biased. Genetic identification of marine plankton has become standard but is still not used in routine monitoring. This study assesses the value that genetic methods bring to microscopic and flow cytometry monitoring methods in the Western (English) Channel. An 18S high throughput sequencing (HTS) diversity survey of plankton taxa was performed on samples collected from an automated Water and Microplankton Sampler (WaMS) deployed on the Continuous Plankton Recorder platform (CPR) from 2011–2012. This survey detected contrasting but complementary taxa assemblages to that of microscopic surveys, mostly composed of smaller or naked or thin-walled plankton taxa, with most phytoplankton being under 10 µm infrequently recorded by other surveys. Most genetically-detected taxa in the survey were mixotrophic or heterotrophic. In comparison with microscopic phytoplankton counts from the CPR survey and Western Channel Observatory station L4, only 8–12 taxonomic families were common to all three surveys, most of them dinoflagellates, with a bias towards larger diatoms and dinoflagellate taxa in microscopy surveys. Additional quantitative real-time PCR detection of two potentially harmful taxa, the pelagophyte, Aureococcus anophagefferens and four Pseudo-nitzschia from 2011–2013. This revealed that growth of A. anophagefferens was elevated in the summer of 2011, whilst the appearance of Pseudo-nitzschia delicatissima in February of that year contrasted with it’s timing at a coastal station. Smaller phytoplankton measured by flow cytometry had distinct seasonality and abundance in the mid-Atlantic compared to coastal regions reflecting distinct conditions.

Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - Michelle M. McClure; Melissa A. Haltuch; Ellen Willis-Norton; David D. Huff; Elliott L. Hazen; Lisa G. Crozier; Michael G. Jacox; Mark W. Nelson; Kelly S. Andrews; Lewis A.K. Barnett; Aaron M. Berger; Sabrina Beyer; et al. (Frontiers in Marine Science, 2023)
Introduction Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. Methods This study applies the NOAA (National Oceanic and Atmospheric Administration) Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Results Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans and low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with Low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. Discussion As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information can inform near-term advice for prioritizing species-level data collection and research on climate impacts, help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially effective to protect or restore.

Microplastic pollution and its implicated risks in the estuarine environment of Tamil Nadu, India - K. Immaculate Jeyasanta; R.L. Laju; Jamila Patterson; M. Jayanthi; Deepak S. Bilgi; Narmatha Sathish; J.K. Patterson Edward (Science of The Total Environment, 2023)

Integrated bio- and chemo-stratigraphy for Early Cretaceous strata offshore Gabon: Additional constraints on the timing of salt deposition and rifting of the South Atlantic - James S. Eldrett; Steven C. Bergman; Christian Heine; Paul Edwards; Marcus Jakeman; Nick Miles; Bastian Hambach; Steven M. Bohaty; Megan R. Wilding (Marine and Petroleum Geology, 2023)

SCIP: software for efficient clinical interpretation of copy number variants detected by whole-genome sequencing - Qiliang Ding; Cherith Somerville; Roozbeh Manshaei; Brett Trost; Miriam S. Reuter; Kelsey Kalbfleisch; Kaitlin Stanley; John B. A. Okello; S. Mohsen Hosseini; Eriskay Liston; Meredith Curtis; Mehdi Zarrei; et al. (Human Genetics, 2023)
Copy number variants (CNVs) represent major etiologic factors in rare genetic diseases. Current clinical CNV interpretation workflows require extensive back-and-forth with multiple tools and databases. This increases complexity and time burden, potentially resulting in missed genetic diagnoses. We present the Suite for CNV Interpretation and Prioritization (SCIP), a software package for the clinical interpretation of CNVs detected by whole-genome sequencing (WGS). The SCIP Visualization Module near-instantaneously displays all information necessary for CNV interpretation (variant quality, population frequency, inheritance pattern, and clinical relevance) on a single page—supported by modules providing variant filtration and prioritization. SCIP was comprehensively evaluated using WGS data from 1027 families with congenital cardiac disease and/or autism spectrum disorder, containing 187 pathogenic or likely pathogenic (P/LP) CNVs identified in previous curations. SCIP was efficient in filtration and prioritization: a median of just two CNVs per case were selected for review, yet it captured all P/LP findings (92.5% of which ranked 1st). SCIP was also able to identify one pathogenic CNV previously missed. SCIP was benchmarked against AnnotSV and a spreadsheet-based manual workflow and performed superiorly than both. In conclusion, SCIP is a novel software package for efficient clinical CNV interpretation, substantially faster and more accurate than previous tools (available at https://github.com/qd29/SCIP , a video tutorial series is available at https://bit.ly/SCIPVideos ).

Nutrient function over form: Organic and inorganic nitrogen additions have similar effects on lake phytoplankton nutrient limitation - Sabrina N. Volponi; Heather L. Wander; David C. Richardson; Clayton J. Williams; Denise A. Bruesewitz; Shelley Arnott; Jennifer A. Brentrup; Hailee L. Edwards; Holly A. Ewing; Kristen Holeck; Lauren Johnson; Brian S. Kim; et al. (Limnology and Oceanography, 2023)
The concentration of dissolved organic nitrogen (DON) is increasing in many northern hemisphere lakes, yet its use by phytoplankton and fate in the environment seldom have been quantified. We conducted 1 week, in situ, microcosm incubations across 25 lakes in northeastern North America to understand how DON, dissolved inorganic nitrogen (DIN), and dissolved inorganic phosphorus (P) affected phytoplankton biomass. In addition, we tested whether lakes were limited by single macronutrients (N or P) or colimited by both. Phytoplankton biomass in 80% of lakes responded similarly to DON and DIN additions. Of the lakes where N form produced differential responses, the majority of phytoplankton communities exhibited greater biomass accumulation with DON than DIN. Colimitation was the most common type of nutrient limitation among the study lakes, followed by P limitation. Limitation type shifted with N form in 40% of the study lakes, but without consistent patterns explaining how shifts occurred. Regardless of N form, lakes with watersheds more dominated by agriculture and higher total dissolved nitrogen (TDN) tended to show P‐limited phytoplankton responses, while lakes with less agricultural watersheds and lower TDN tended to show colimited phytoplankton responses. Finally, ambient TDN and total phosphorus (TP) nutrient concentrations were stronger predictors of limitation type than ambient TDN : TP ratios. The different contributions of DON and DIN to phytoplankton biomass in some of our study lakes suggest that DON loading from surrounding watersheds may be an overlooked component in predicting phytoplankton productivity and nutrient limitation dynamics in freshwater ecosystems.

Effect of Microalgal Diets on Sunray Venus Clam (Macrocallista nimbosa) Production and Fatty Acid Profile - Edward Perri; Leslie Sturmer; Paul S. Wills; John Baldwin; Susan Laramore (Fishes, 2023)
The sunray venus (sunray) clam, Macrocallista nimbosa, is an alternative clam species reared in hard clam hatcheries in Florida. Current feeding practices follow those used for hard clam culture. This study aimed to identify whether a hard clam bi-algal Tisochrysis lutea and Chaetoceros neogracile diet was an optimal diet for post-set sunray clams or whether other microalgal dietary combinations could improve production. Six dietary bi-, tri-, or tetra-algal combinations consisting of four microalgae species (Tisochrysis lutea, Diacronema lutheri, Chaetoceros neogracile, and Thalassiosira weissflogii) were fed for 6 weeks; the growth, survival, and fatty acid profiles of post-set clams were evaluated. Clams fed equal proportions of T. lutea, D. lutheri, C. neogracile, and T. weissflogii had higher growth, while those fed equal proportions of T. lutea and C. neogracile had higher survival. The poorest-performing diet consisted solely of diatoms. A contrasting polyunsaturated fatty acid (PUFA) profile was found in post-set clams fed flagellate- or diatom-only diets. Clams fed the bi-algal flagellate diet had a higher percentage of docosahexaenoic acid (DHA) but a lower percentage of (n-6) PUFA, whereas those fed the bi-algal diatom diet had a higher percentage of arachidonic acid (ARA) and eicosapentaenoic acid (EPA) but a lower percentage of DHA. The percentages were similar and neither very high nor very low in clams fed the remaining dietary treatments. The results of this study show that sunray venus post-set clams can be successfully produced when fed a typical hard clam bi-algal flagellate and diatom diet, but they indicate that growth may be accelerated by the addition of other microalgae species.

Coral disease outbreak at the remote Flower Garden Banks, Gulf of Mexico - Michelle A. Johnston; Michael S. Studivan; Ian C. Enochs; Adrienne M. S. Correa; Nicole Besemer; Ryan J. Eckert; Kimberly Edwards; Ryan Hannum; Xinping Hu; Marissa Nuttall; Kelly O’Connell; Ana M. Palacio-Castro; et al. (Frontiers in Marine Science, 2023)
East and West Flower Garden Bank (FGB) are part of Flower Garden Banks National Marine Sanctuary (FGBNMS) in the northwest Gulf of Mexico. This geographically-isolated reef system contains extensive coral communities with the highest coral cover (>50%) in the continental United States due, in part, to their remoteness and depth, and have historically exhibited low incidence of coral disease and bleaching despite ocean warming. Yet in late August 2022, disease-like lesions on seven coral species were reported during routine monitoring surveys on East and West FGB (2.1–2.6% prevalence). A series of rapid response cruises were conducted in September and October 2022 focused on 1) characterizing signs and epidemiological aspects of the disease across FGB and within long-term monitoring sites, 2) treating affected coral colonies with Base 2B plus amoxicillin, and 3) collecting baseline images through photostations and photomosaics. Marginal and/or multi-focal lesions and tissue loss were observed, often associated with substantial fish and invertebrate predation, affecting the dominant coral species Pseudodiploria strigosa (7–8% lesion prevalence), Colpophyllia natans (11–18%), and Orbicella spp. (1%). Characterizing this disease event during its early epidemic phase at East and West FGB provides a critical opportunity to observe how coral disease functions in a relatively healthy coral ecosystem versus on reefs chronically affected by various stressors (e.g., Caribbean reefs adjacent to urban centers). Insights into the etiology, spread, and impacts of the disease can ultimately inform efforts to mitigate its effects on coral communities.

Bio-oil and biochar from the pyrolytic conversion of biomass: A current and future perspective on the trade-off between economic, environmental, and technical indicators - Arun Krishna Vuppaladadiyam; Sai Sree Varsha Vuppaladadiyam; Abhisek Sahoo; S. Murugavelh; Edward Anthony; Thallada Bhaskar; Ying Zheng; Ming Zhao; Huabo Duan; Yan Zhao; Elsa Antunes; Ajit K. Sarmah; et al. (Science of The Total Environment, 2023)

Constant-temperature predictions underestimate growth of a fungal amphibian pathogen under individual host thermal profiles - Sasha E. Greenspan; Elizabeth A. Roznik; Lexie Edwards; Richard Duffy; Lee Berger; Deborah S. Bower; David A. Pike; Lin Schwarzkopf; Ross A. Alford (Journal of Thermal Biology, 2023)

Peeling the Onion! What are the drivers and barriers of cleaner production? A case of the Kenyan manufacturing SMEs - Edward Mungai; S. Wagura Ndiritu (Journal of Cleaner Production, 2023)

Fine particulate matter and incident coronary heart disease events up to 10 years of follow-up among Deepwater Horizon oil spill workers - Dazhe Chen; Dale P. Sandler; Alexander P. Keil; Gerardo Heiss; Eric A. Whitsel; Gregory C. Pratt; Patricia A. Stewart; Mark R. Stenzel; Caroline P. Groth; Sudipto Banerjee; Tran B. Huynh; Jessie K. Edwards; et al. (Environmental Research, 2023)

Lipid Nanoparticles for Nucleic Acid Delivery to Endothelial Cells - Gary W. Liu; Edward B. Guzman; Nandita Menon; Robert S. Langer (Pharmaceutical Research, 2023)
Endothelial cells play critical roles in circulatory homeostasis and are also the gateway to the major organs of the body. Dysfunction, injury, and gene expression profiles of these cells can cause, or are caused by, prevalent chronic diseases such as diabetes, cardiovascular disease, and cancer. Modulation of gene expression within endothelial cells could therefore be therapeutically strategic in treating longstanding disease challenges. Lipid nanoparticles (LNP) have emerged as potent, scalable, and tunable carrier systems for delivering nucleic acids, making them attractive vehicles for gene delivery to endothelial cells. Here, we discuss the functions of endothelial cells and highlight some receptors that are upregulated during health and disease. Examples and applications of DNA, mRNA, circRNA, saRNA, siRNA, shRNA, miRNA, and ASO delivery to endothelial cells and their targets are reviewed, as well as LNP composition and morphology, formulation strategies, target proteins, and biomechanical factors that modulate endothelial cell targeting. Finally, we discuss FDA-approved LNPs as well as LNPs that have been tested in clinical trials and their challenges, and provide some perspectives as to how to surmount those challenges.

Reproductive sterility in aquaculture: A review of induction methods and an emerging approach with application to Pacific Northwest finfish species - Lan Xu; Mingli Zhao; Jun Hyung Ryu; Edward S. Hayman; William T. Fairgrieve; Yonathan Zohar; J. Adam Luckenbach; Ten‐Tsao Wong (Reviews in Aquaculture, 2023)
Aquaculture is the fastest‐growing food‐production sector and is striving to become a long‐term sustainable approach to meet the rising global demand for seafood. During the expansion and advancement of aquaculture, minimizing ecological impacts should occur concomitantly with maximizing production. Farmed fish, often genetically distinct from their natural conspecifics, may pose significant risks of genetic contamination and ecological imbalance to wild populations if they escape from aquaculture confinement. Growing reproductively sterile fish is the most effective way to genetically contain farmed fish. Atlantic salmon ( Salmo salar ) escape events in the ‘Pacific Northwest’ region of the United States and Canada have raised alarms over potential ecological impacts and led to legislation in Washington State phasing out the culture of non‐native finfish species. Farming sterile native species such as coho salmon ( Oncorhynchus kisutch ) and sablefish ( Anoplopoma fimbria ) in the Pacific Northwest would ease public concerns and promote environmentally and economically sustainable aquaculture. Sterile fish also can mitigate the challenge of precocious maturation, a prominent issue associated with culture of salmonids and many other species, to improve somatic growth, flesh quality and fish health and welfare. Here, we review methods having potential applications for producing sterile fish and introduce our novel immersion‐based technology that temporarily silences the dead end ( dnd ) gene using Morpholino oligonucleotides to produce sterile coho salmon and sablefish for the first time. The successful induction of sterility in these two iconic Pacific Northwest species without introducing genetic modifications would promote the use of this immersion‐based sterilization technology for more aquaculture finfish worldwide.

Caught red handed: modeling and confirmation of the myeloperoxidase ceruloplasmin alpha-thrombin complex - Yana A. Zabrodskaya; Vladimir V. Egorov; Alexey V. Sokolov; Alexey V. Shvetsov; Yulia E. Gorshkova; Oleksandr I. Ivankov; Valeria A. Kostevich; Nikolay P. Gorbunov; Edward S. Ramsay; Natalya D. Fedorova; Andrey B. Bondarenko; Vadim B. Vasilyev (BioMetals, 2022)

Streptomyces spiramenti sp. nov., isolated from a deep-sea microbial mat - Rachel M. Loughran; Caitlin M. Diefendorf; Jassmine R. Reill-VanSise; Edward A. Mitchell; Oliver B. Vining; David A. Gallegos; Gregory Miller; Marc J. Koyack; David K. Oline; Orion S. Rivers; Blake Ushijima; Jimmy H. Saw; et al. (Archives of Microbiology, 2022)

Uterine fibroid polygenic risk score (PRS) associates and predicts risk for uterine fibroid - Jacqueline A. Piekos; Jacklyn N. Hellwege; Yanfei Zhang; Eric S. Torstenson; Gail P. Jarvik; Ozan Dikilitas; Iftikhar J. Kullo; Daniel J. Schaid; David R. Crosslin; Sarah A. Pendergrass; Ming Ta Michael Lee; Dan Roden; et al. (Human Genetics, 2022)

Lowering water table reduces carbon sink strength and carbon stocks in northern peatlands - Min Jung Kwon; Ashley Ballantyne; Philippe Ciais; Chunjing Qiu; Elodie Salmon; Nina Raoult; Bertrand Guenet; Mathias Göckede; Eugénie S. Euskirchen; Hannu Nykänen; Edward A. G. Schuur; Merritt R. Turetsky; et al. (Global Change Biology, 2022)
Peatlands at high latitudes have accumulated >400 Pg carbon (C) because saturated soil and cold temperatures suppress C decomposition. This substantial amount of C in Arctic and Boreal peatlands is potentially subject to increased decomposition if the water table (WT) decreases due to climate change, including permafrost thaw‐related drying. Here, we optimize a version of the Organizing Carbon and Hydrology In Dynamic Ecosystems model (ORCHIDEE‐PCH4) using site‐specific observations to investigate changes in CO 2 and CH 4 fluxes as well as C stock responses to an experimentally manipulated decrease of WT at six northern peatlands. The unmanipulated control peatlands, with the WT −2 year −1 ; including 6 ± 7 g C–CH 4 m −2 year −1 emission). We found, however, that lowering the WT by 10 cm reduced the CO 2 sink by 13 ± 15 g C m −2 year −1 and decreased CH 4 emission by 4 ± 4 g CH 4 m −2 year −1 , thus accumulating less C over 100 years (0.2 ± 0.2 kg C m −2 ). Yet, the reduced emission of CH 4 , which has a larger greenhouse warming potential, resulted in a net decrease in greenhouse gas balance by 310 ± 360 g CO 2‐eq m −2 year −1 . Peatlands with the initial WT close to the soil surface were more vulnerable to C loss: Non‐permafrost peatlands lost >2 kg C m −2 over 100 years when WT is lowered by 50 cm, while permafrost peatlands temporally switched from C sinks to sources. These results highlight that reductions in C storage capacity in response to drying of northern peatlands are offset in part by reduced CH 4 emissions, thus slightly reducing the positive carbon climate feedbacks of peatlands under a warmer and drier future climate scenario.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Development of the invasive candidiasis discharge [I Can discharge] model: a mixed methods analysis - Jinhee Jo; Truc T. Tran; Nicholas D. Beyda; Debora Simmons; Joshua A. Hendrickson; Masaad Saeed Almutairi; Faris S. Alnezary; Anne J. Gonzales-Luna; Edward J. Septimus; Kevin W. Garey (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Patients with invasive candidiasis (IC) have complex medical and infectious disease problems that often require continued care after discharge. This study aimed to assess echinocandin use at hospital discharge and develop a transition of care (TOC) model to facilitate discharge for patients with IC. This was a mixed method study design that used epidemiologic assessment to better understand echinocandin use at hospital discharge TOC. Using grounded theory methodology focused on patients given echinocandins during their last day of hospitalization, a TOC model for patients with IC, the invasive candidiasis [I Can] discharge model was developed to better understand discharge barriers. A total of 33% (1405/4211) echinocandin courses were continued until the last day of hospitalization. Of 536 patients chosen for in-depth review, 220 (41%) were discharged home, 109 (20%) were transferred, and 207 (39%) died prior to discharge. Almost half (46%, 151/329) of patients discharged alive received outpatient echinocandin therapy. Independent predictors for outpatient echinocandin use were osteomyelitis (OR, 4.1; 95% CI, 1.1–15.7; p = 0.04), other deep-seated infection (OR, 4.4; 95% CI, 1.7–12.0; p = 0.003), and non-home discharge location (OR, 3.9, 95% CI, 2.0–7.7; p < 0.001). The I Can discharge model was developed encompassing four distinct themes which was used to identify potential barriers to discharge. Significant echinocadin use occurs at hospital discharge TOC. The I Can discharge model may help clinical, policy, and research decision-making processes to facilitate smoother and earlier hospital discharges.

Cancer clinical trials in the Philippines - Michelle Ann B. Eala; Patricia Anne S. Basilio; Edward Christopher Dee; Reno Eufemon P. Cereno; Christian Daniel Ang; Nikko J. Magsanoc; Frederic Ivan L. Ting; Dennis L. Sacdalan (Cancer Causes & Control, 2022)

No butts about it: using urogenital disparity in a deep‐water snapper, Etelis carbunculus (Lutjanidae), for field‐based sexual identification - Ryan S. Nichols; Edward E. DeMartini; Erik C. Franklin (Journal of Fish Biology, 2022)
In this study, the authors describe a process that consistently identified sex based on differences in the length and characteristics of the urogenital papilla septum of Etelis carbunculus , a deep‐water snapper (Lutjanidae, Etelinae). These characteristics, regardless of fish size, were found to be accurate for 96% of 157 specimens evaluated . The application of this external sex determination technique expedites the collection of sex‐specific data and may perform well for other morphologically similar lutjanid snappers. The non‐invasive method also minimizes damage to the fish, thereby allowing either its return to the ocean or landing as a valuable whole fish.

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Comparative analysis of patient scatter to phantom scatter for computed tomography systems - S. M. Edwards; D. Schick (Physical and Engineering Sciences in Medicine, 2022)

Total Dental Occlusal Area as a Feeding Constraint Feature in Extant Walruses (Odobenus rosmarus), and Implications for the Evolution of Molluscivory in Odobenidae - Win N. F. McLaughlin; Caitlyn J. Boatman; Edward B. Davis; Samantha S. B. Hopkins (Journal of Mammalian Evolution, 2022)

Fusarium langsethiae and mycotoxin contamination in oat grain differed with growth stage at inoculation - Heidi Udnes Aamot; Hesam Mousavi; Jafar Razzaghian; Guro Brodal; Michael Sulyok; Rudolf Krska; Simon G. Edwards; Ingerd S. Hofgaard (European Journal of Plant Pathology, 2022)
High levels of mycotoxins are occasionally observed in Norwegian oat grain lots. Mycotoxins of primary concern in Norwegian oats are deoxynivalenol (DON) produced by Fusarium graminearum and HT2- and T2-toxins (HT2 + T2) produced by Fusarium langsethiae . Improved understanding of the epidemiology of Fusarium spp. is important for the development of measures to control mycotoxins. We studied the susceptibility to F. langsethiae after inoculation at early (booting, heading, flowering) or late (flowering, milk, dough) growth stages in three oat varieties in greenhouse experiments. The varieties had previously shown different levels of resistance to F. graminearum : Odal, Vinger (both moderately resistant), and Belinda (susceptible). The level of F. langsethiae DNA and HT2 + T2 were measured in harvested grain. In addition, we observed differences in aggressiveness (measured as the level of F. langsethiae DNA in grain) between F. langsethiae isolates after inoculation of oats at flowering. Substantial levels of F. langsethiae DNA (mean ≥ 138 pg per μg plant DNA) and HT2 + T2 (≥348 μg/kg) were detected in grain harvested from oats that were spray-inoculated at heading or later stages, but not at booting (mean ≤ 10 pg/μg and ≤ 25 μg/kg, respectively), suggesting that oats are susceptible to F. langsethiae from heading and onwards. Vinger was the most resistant variety to F. langsethiae /HT2 + T2, whereas Odal and Belinda were relatively susceptible. We observed that late inoculations yielded high levels of other trichothecene A metabolites (mean sum of metabolites of 35–1048 μg/kg) in addition to HT2 + T2, in harvested grain, an indication that infections close to harvest may pose a further risk to food and feed safety.

Predicting larval alewife transport in Lake Michigan using hydrodynamic and Lagrangian particle dispersion models - Mark D. Rowe; Sara E. Prendergast; Karen M. Alofs; David B. Bunnell; Edward S. Rutherford; Eric J. Anderson (Limnology and Oceanography, 2022)
Several species of fish in large lakes and marine environments have a pelagic larval stage, and are subject to variable transport that can ultimately regulate survival and recruitment success. Alewife, Alosa pseudoharengus , are subject to transport by complex coastal currents during their pelagic larval stage (~ 30 d). We assessed backward‐trajectory simulations, consisting of a Lagrangian particle dispersion model linked to the Finite Volume Community Ocean Model, to estimate likely hatch locations of aged larval alewife collected from locations on both the eastern and western sides of Lake Michigan during July 2015. We used four deployments of three satellite‐tracked drifter buoys in coastal waters to assess model skill in estimating the origin of a drifter from its final location. We found that the trajectories of drifters varied greatly, depending on wind events and associated coastal transport processes, including upwelling/downwelling and coastal jet currents. In 2 of 12 cases, the backward trajectory simulations failed to predict the drifter origin, associated with transport of 170 km in a narrow coastal jet current. In the remaining 10 cases, the known drifter origin was within 3.5 km of the spatial patch of predicted possible origins for a scenario of horizontal diffusivity (188 m 2 s −1 ) consistent with the offshore model grid resolution. Modeled backward trajectories estimated that alewife originated from the same side of the lake where they were collected, within ~ 100 km of the collection site. Our paper demonstrates the utility of hydrodynamic models to estimate a region of origin for aged larval fish.

Shifts in root dynamics along a hillslope in a mixed, mesic temperate forest - Edward J. Primka; Thomas S. Adams; Alexandra S. Buck; David M. Eissenstat (Plant and Soil, 2022)

A New Insight Into Amicula, a Genus of Tiny Marine Benthic Diatoms With the Description of Two New Tropical Species and the Largest Mitogenome Known for a Stramenopile - Romain Gastineau; Chunlian Li; Matt P. Ashworth; Andrzej Witkowski; Monique Turmel; Ewa Górecka; Thomas A. Frankovich; Anna Wachnicka; Christopher S. Lobban; Edward C. Theriot; Christian Otis; Przemysław Dąbek; et al. (Frontiers in Marine Science, 2022)
The current article focuses on the morphological and molecular characterization of the often inconspicuous genus Amicula. This recently erected genus from brackish and marine sediments was monotypic but here we describe two new tropical species: Amicula micronesica sp. nov. and Amicula vermiculata sp. nov. Once considered an incertae sedis genus regarding its higher rank taxonomy, its position among the family Diploneidaceae is proposed here by molecular phylogenetics. The complete plastid and mitochondrial genomes of Amicula micronesica sp. nov. are also presented here. It appears that the 177614-bp long mitogenome is the biggest yet recorded among stramenopiles, due to its invasion by 57 introns. Moreover, it utilizes the genetic code 4 for translation instead of the code 1 usually found among diatoms.

A stable isotope record of late Quaternary hydrologic change in the northwestern Brooks Range, Alaska (eastern Beringia) - Amanda L. King; Lesleigh Anderson; Mark Abbott; Mary Edwards; Matthew S. Finkenbinder; Bruce Finney; Matthew J. Wooller (Journal of Quaternary Science, 2022)
A submillennial‐resolution record of lake water oxygen isotope composition (δ 18 O) from chironomid head capsules is presented from Burial Lake, northwest Alaska. The record spans the Last Glacial Maximum (LGM; ~20–16k cal a bp ) to the present and shows a series of large lake δ 18 O shifts (~5‰). Relatively low δ 18 O values occurred during a period covering the LGM, when the lake was a shallow, closed‐basin pond. Higher values characterize deglaciation (~16–11.5k cal a bp ) when the lake was still closed but lake levels were higher. A rapid decline between ~11 and 10.5k cal a bp indicates that lake levels rose to overflowing. Lake δ 18 O values are interpreted to reflect the combined effects of changes in lake hydrology, growing season temperature and meteoric source water as well as large‐scale environmental changes impacting this site, including opening of the Bering Strait and shifts in atmospheric circulation patterns related to ice‐sheet dynamics. The results indicate significant shifts in precipitation minus evaporation across the late Pleistocene to early Holocene transition, which are consistent with temporal patterns of vegetation change and paludification. This study provides new perspectives on the paleohydrology of eastern Beringia concomitant with human migration and major turnover in megafaunal assemblages.

Rapid climate changes during the Lateglacial and the early Holocene as seen from plant community dynamics in the Polar Urals, Russia - Anne E. Bjune; Inger Greve Alsos; Jo Brendryen; Mary E. Edwards; Haflidi Haflidason; Maren S. Johansen; Jan Mangerud; Aage Paus; Carl Regnéll; John‐Inge Svendsen; Charlotte L. Clarke (Journal of Quaternary Science, 2022)
A detailed, well‐dated record of pollen and sedimentary ancient DNA ( sed aDNA) for the period 15 000–9500 cal a bp describes changes at Lake Bolshoye Shchuchye in the Polar Ural Mountains, located far east of the classical Lateglacial sites in western Europe. Arctic tundra rapidly changed to lusher vegetation, possibly including both dwarf ( Betula nana ) and tree birch ( B. pubescens ), dated in our record to take place 14 565 cal a bp , coincident with the onset of the Bølling in western Europe; this was paralleled by increased summer temperatures. A striking feature is an early decline in Betula pollen and sed aDNA reads 300 years before the onset of the Younger Dryas (YD) in western Europe. Given the solid site chronology, this could indicate that the YD cooling started in Siberia and propagated westwards, or that the vegetation reacted to the inter‐Allerød cooling at 13 100 cal a bp and did not recover during the late Allerød. During the YD, increases in steppe taxa such as Artemisia and Chenopodiaceae suggest drier conditions. At the onset of the Holocene, the vegetation around the lake reacted fast to the warmer conditions, as seen in the increase of arboreal taxa, especially Betula , and a decrease in herbs such as Artemisia and Cyperaceae.

Managing fisheries for maximum nutrient yield - James P.W. Robinson; Kirsty L. Nash; Julia L. Blanchard; Nis S. Jacobsen; Eva Maire; Nicholas A.J. Graham; M. Aaron MacNeil; Jessica Zamborain‐Mason; Edward H. Allison; Christina C. Hicks (Fish and Fisheries, 2022)
Wild‐caught fish are a bioavailable source of nutritious food that, if managed strategically, could enhance diet quality for billions of people. However, optimising nutrient production from the sea has not been a priority, hindering development of nutrition‐sensitive policies. With fisheries management increasingly effective at rebuilding stocks and regulating sustainable fishing, we can now begin to integrate nutritional outcomes within existing management frameworks. Here, we develop a conceptual foundation for managing fisheries for multispecies Maximum Nutrient Yield (mMNY). We empirically test our approach using size‐based models of North Sea and Baltic Sea fisheries and show that mMNY is predicted by the relative contribution of nutritious species to total catch and their vulnerability to fishing, leading to trade‐offs between catch and specific nutrients. Simulated nutrient yield curves suggest that vitamin D, which is deficient in Northern European diets, was underfished at fishing levels that returned maximum catch weights. Analysis of global catch data shows there is scope for nutrient yields from most of the world's marine fisheries to be enhanced through nutrient‐sensitive fisheries management. With nutrient composition data now widely available, we expect our mMNY framework to motivate development of nutrient‐based reference points in specific contexts, such as data‐limited fisheries. Managing for mMNY alongside policies that promote access to fish could help close nutrient gaps for coastal populations, maximising the contribution of wild‐caught fish to global food and nutrition security.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The Diel and Seasonal Heterogeneity of Carbonate Chemistry and Dissolved Oxygen in Three Types of Macroalgal Habitats - Huiru Li; Hanbi Moon; Eun Ju Kang; Ja-Myung Kim; Miok Kim; Kitack Lee; Cheol-Woo Kwak; Haryun Kim; Il-Nam Kim; Ki Yeol Park; Young Kweon Lee; Ji Woong Jin; et al. (Frontiers in Marine Science, 2022)
As concerns about ocean acidification continue to grow, the importance of macroalgal communities in buffering coastal seawater biogeochemistry through their metabolisms is gaining more attention. However, studies on diel and seasonal fluctuations in seawater chemistry within these communities are still rare. Here, we characterized the spatial and temporal heterogeneity in diel and seasonal dynamics of seawater carbonate chemistry and dissolved oxygen (DO) in three types of macroalgal habitats (UAM: ulvoid algal mat dominated, TAM: turf algal mat dominated, and SC: Sargassum horneri and coralline algae dominated). Our results show that diel fluctuations in carbonate parameters and DO varied significantly among habitat types and seasons due to differences in their biological metabolisms (photosynthesis and calcification) and each site’s hydrological characteristics. Specifically, carbonate parameters were most affected by biological metabolisms at the SC site, and by environmental variables at the UAM site. Also, we demonstrate that macroalgal communities reduced ocean acidification conditions when ocean temperatures supported photosynthesis and thereby the absorption of dissolved inorganic carbon. However, once temperatures exceeded the optimum ranges for macroalgae, respiration within these communities exceeded photosynthesis and increased CO 2 concentrations, thereby exacerbating ocean acidification conditions. We conclude that the seawater carbonate chemistry is strongly influenced by the metabolisms of the dominant macroalgae within these different habitat types, which may, in turn, alter their buffering capacity against ocean acidification.

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Early Last Interglacial environmental changes recorded by speleothems from Katerloch (south‐east Austria) - Charlotte Honiat; Daniela Festi; Paul S. Wilcox; R. Lawrence Edwards; Hai Cheng; Christoph Spötl (Journal of Quaternary Science, 2022)
In the European Alps, the Last Interglacial (LIG, ~129–116 ka) has been primarily studied using pollen preserved in mires and lake sediments. These records document the vegetation succession across the LIG, but are poorly constrained chronologically. Here, we present a precisely dated stable isotope record for the early LIG (129.6 ± 0.4 to 125.0 ± 0.8 ka) based on two stalagmites from Katerloch, a cave located on the south‐eastern side of the Alps. The onset of the interglacial is marked by a sharp rise in the oxygen isotope values at 129.4 ± 0.4 ka, consistent within dating uncertainty with the timing of Termination II as recorded by other Alpine speleothems. Carbon isotope values show an equally prominent drop at Termination II and the establishment of a forest ecosystem. Although concentrations are low, pollen from these stalagmites provide insights into how the local vegetation changed across the first five millennia of the LIG. The spectra indicate a vegetation optimum recorded by the occurrence of warm‐demanding taxa typical of the Eemian mesocratic phase. By combining stable isotopes and pollen data, we propose an absolutely dated chronological framework for peri‐Alpine pollen successions from lacustrine sediments covering the first half of the LIG.

It’s the Little Things: The Role of Microscopic Life Stages in Maintaining Kelp Populations - Matthew S. Edwards (Frontiers in Marine Science, 2022)
Kelp forests are experiencing broad scale declines in abundance and shifts in latitudinal ranges in many areas of the world due to numerous environmental stressors, especially those associated with climate change. While the majority of studies on kelp ecology have focused exclusively on the macroscopic sporophyte life stage, a growing number of studies is showing quite convincingly that the microscopic zoospore and gametophyte life stages can be important to establishing spatial patterns in these marine forests, and in facilitating their recovery following deforestation. Unfortunately, their microscopic sizes have made them difficult to study in the field, leading to a ‘black box’ surrounding what we know about their ecologies. However, advances in experimental methodologies and a growing number of laboratories studying kelp microscopic life stages are revealing how they are affected by variability in environmental conditions, and are providing a clearer picture of how kelp forests might respond to a changing ocean climate. These studies have largely revealed that kelps can disperse over a wide range of distances, enhanced by the synchronous release and vertical transport of zoospores into shallower water, and by floating rafts of reproductive thalli. Settlement on the benthos is facilitated by both positive and negative chemotaxis, and by active selection of microhabitats that favor their growth and survival. Following settlement and subsequent germination, the haploid gametophytes can delay their development and form a bank of microscopic forms that persist during periods that are unfavorable for the large sporophyte populations, or they can develop and undergo sexual reproduction during which they respond to variability in environmental conditions. In particular, they are strongly affected by increases in irradiance (PAR, UVA + UVB) and temperature, decreases in nutrients and salinity, and by sedimentation and grazing. However, the manner in which they respond to these stressors varies among species and with their geographic distributions, which is integral to establishing biogeographic patterns in the large sporophyte populations. Given these factors are expected to change as the ocean climate changes, these species-specific responses have significant implications for future patterns of distribution and abundance of these iconic marine forests.

Fear at the top: killer whale predation drives white shark absence at South Africa’s largest aggregation site - AV Towner; RGA Watson; AA Kock; Y Papastamatiou; M Sturup; E Gennari; K Baker; T Booth; M Dicken; W Chivell; S Elwen; T Kaschke; et al. (African Journal of Marine Science, 2022)

Plasma Kallikrein Contributes to Intracerebral Hemorrhage and Hypertension in Stroke-Prone Spontaneously Hypertensive Rats - Jian Guan; Allen C. Clermont; Loc-Duyen Pham; Tuna Ustunkaya; Alexey S. Revenko; A. Robert MacLeod; Edward P. Feener; Fabrício Simão (Translational Stroke Research, 2022)

Resolving taxonomic confusion: establishing the genus Phytobacter on the list of clinically relevant Enterobacteriaceae - Theo H. M. Smits; Lavinia N. V. S. Arend; Sofia Cardew; Erika Tång-Hallbäck; Marcelo T. Mira; Edward R. B. Moore; Jorge L. M. Sampaio; Fabio Rezzonico; Marcelo Pillonetto (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Although many clinically significant strains belonging to the family Enterobacteriaceae fall into a restricted number of genera and species, there is still a substantial number of isolates that elude this classification and for which proper identification remains challenging. With the current improvements in the field of genomics, it is not only possible to generate high-quality data to accurately identify individual nosocomial isolates at the species level and understand their pathogenic potential but also to analyse retrospectively the genome sequence databases to identify past recurrences of a specific organism, particularly those originally published under an incorrect or outdated taxonomy. We propose a general use of this approach to classify further clinically relevant taxa, i.e., Phytobacter spp., that have so far gone unrecognised due to unsatisfactory identification procedures in clinical diagnostics. Here, we present a genomics and literature-based approach to establish the importance of the genus Phytobacter as a clinically relevant member of the Enterobacteriaceae family.

Importance of equitable cost sharing in the Convention on Biological Diversity's protected area agenda - Keila Stark; Vanessa Adams; Christopher J. Brown; Alienor Chauvenet; Katrina Davis; Edward T. Game; Benjamin S. Halpern; John Lynham; Bonnie Mappin; Kim Selkoe; James E. M. Watson; Hugh P. Possingham; et al. (Conservation Biology, 2022)

Low occurrence of multi‐antimicrobial and heavy metal resistance in Salmonella enterica from wild birds in the United States - Yezhi Fu; Nkuchia M. M'ikanatha; Chris A. Whitehouse; Heather Tate; Andrea Ottesen; Jeffrey M. Lorch; David S. Blehert; Brenda Berlowski‐Zier; Edward G. Dudley (Environmental Microbiology, 2022)
Summary Wild birds are common reservoirs of Salmonella enterica . Wild birds carrying resistant S . enterica may pose a risk to public health as they can spread the resistant bacteria across large spatial scales within a short time. Here, we whole‐genome sequenced 375 S . enterica strains from wild birds collected in 41 U.S. states during 1978–2019 to examine bacterial resistance to antibiotics and heavy metals. We found that Typhimurium was the dominant S . enterica serovar, accounting for 68.3% (256/375) of the bird isolates. Furthermore, the proportions of the isolates identified as multi‐antimicrobial resistant (multi‐AMR: resistant to at least three antimicrobial classes) or multi‐heavy metal resistant (multi‐HMR: resistant to at least three heavy metals) were both 1.87% (7/375). Interestingly, all the multi‐resistant S . enterica ( n = 12) were isolated from water birds or raptors; none of them was isolated from songbirds. Plasmid profiling demonstrated that 75% (9/12) of the multi‐resistant strains carried resistance plasmids. Our study indicates that wild birds do not serve as important reservoirs of multi‐resistant S . enterica strains. Nonetheless, continuous surveillance for bacterial resistance in wild birds is necessary because the multi‐resistant isolates identified in this study also showed close genetic relatedness with those from humans and domestic animals.

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

A National Status Report on United States Coral Reefs Based on 2012–2018 Data From National Oceanic and Atmospheric Administration’s National Coral Reef Monitoring Program - Erica K. Towle; E. Caroline Donovan; Heath Kelsey; Mary E. Allen; Hannah Barkley; Jeremiah Blondeau; Russell E. Brainard; Annie Carew; Courtney S. Couch; Maria K. Dillard; C. Mark Eakin; Kimberly Edwards; et al. (Frontiers in Marine Science, 2022)
National Oceanic and Atmospheric Administration’s Coral Reef Conservation Program supports the National Coral Reef Monitoring Program (NCRMP) in the United States Pacific, Atlantic, Caribbean, and Gulf of Mexico. NCRMP conducts standardized observations of biological, climatic, and socioeconomic indicators across American Samoa, Guam, the Main Hawaiian Islands, the Northwestern Hawaiian Islands, the Northern Mariana Islands, the Pacific Remote Islands, Florida, the Flower Garden Banks, Puerto Rico, and the United States Virgin Islands. NCRMP provides periodic, national-level assessments of the status of United States coral reef ecosystems and communities connected to them. In 2014, NCRMP partnered with the University of Maryland Center for Environmental Science on an unprecedented collaboration between federal and jurisdictional/state agencies, academia, and non-governmental organizations to synthesize NCRMP data into a reporting format designed to be accessible and relevant to the public and policy makers. The process involved multi-year data analyses of key benthic, fish, and climate indicators. In populated jurisdictions, socioeconomic data were integrated to assess public support for management actions, participation in pro-environmental behaviors, and awareness of threats to coral reefs. Jurisdictions were scored using a report-card scale (0–100%) by establishing references for each indicator using best-available historical data or expert opinion where historical data did not exist or were not statistically comparable. Despite overall ecosystem scores of Fair for all combined Atlantic (70%) and Pacific (74%) jurisdictions, the current trend is downward with a majority of United States coral reefs declining and vulnerable to further degradation. Remote, uninhabited reefs had an advantage with respect to reef fish population scores, i.e., Flower Garden Banks (85%) and Pacific Remote Islands (93%), when compared to populated location scores, i.e., Puerto Rico (63%) and Main Hawaiian Islands (66%). All coral reefs are highly impacted by climate change, and climate impacts were more pronounced than expected on remote reefs, i.e., the Northwestern Hawaiian Islands (58%). Presenting results in a report-card style facilitates communication to the public and policy makers, and provides a useful mechanism to garner support for management actions such as expanding protected areas; enforcing existing regulations; increasing climate change education; reducing land-based sources of pollution; and other actions to improve the trajectory of coral reef ecosystem conditions.

Persistently elevated complement alternative pathway biomarkers in COVID-19 correlate with hypoxemia and predict in-hospital mortality - Alexander Leatherdale; Sophie Stukas; Victor Lei; Henry E. West; Christopher J. Campbell; Ryan L. Hoiland; Jennifer Cooper; Cheryl L. Wellington; Mypinder S. Sekhon; Edward L. G. Pryzdial; Edward M. Conway (Medical Microbiology and Immunology, 2022)

Expanding the horizon of research into the pathogenesis of the white matter diseases: Proceedings of the 2021 Annual Workshop of the Albert Research Institute for White Matter and Cognition - Shawn N. Whitehead; Askiel Bruno; Jeffrey M. Burns; S. Thomas Carmichael; Anna Csiszar; Jodi D. Edwards; Fanny M. Elahi; Giuseppe Faraco; Douglas B. Gould; Deborah R. Gustafson; Vladimir Hachinski; Gary Rosenberg; et al. (GeroScience, 2022)

Stepping stones towards Antarctica: Switch to southern spawning grounds explains an abrupt range shift in krill - Angus Atkinson; Simeon L. Hill; Christian S. Reiss; Evgeny A. Pakhomov; Gregory Beaugrand; Geraint A. Tarling; Guang Yang; Deborah K. Steinberg; Katrin Schmidt; Martin Edwards; Emilce Rombolá; Frances A. Perry (Global Change Biology, 2022)
Poleward range shifts are a global‐scale response to warming, but these vary greatly among taxa and are hard to predict for individual species, localized regions or over shorter (years to decadal) timescales. Moving poleward might be easier in the Arctic than in the Southern Ocean, where evidence for range shifts is sparse and contradictory. Here, we compiled a database of larval Antarctic krill, Euphausia superba and, together with an adult database, it showed how their range shift is out of step with the pace of warming. During a 70‐year period of rapid warming (1920s–1990s), distribution centres of both larvae and adults in the SW Atlantic sector remained fixed, despite warming by 0.5–1.0°C and losing sea ice. This was followed by a hiatus in surface warming and ice loss, yet during this period the distributions of krill life stages shifted greatly, by ~1000 km, to the south‐west. Understanding the mechanism of such step changes is essential, since they herald system reorganizations that are hard to predict with current modelling approaches. We propose that the abrupt shift was driven by climatic controls acting on localized recruitment hotspots, superimposed on thermal niche conservatism. During the warming hiatus, the Southern Annular Mode index continued to become increasingly positive and, likely through reduced feeding success for larvae, this led to a precipitous decline in recruitment from the main reproduction hotspot along the southern Scotia Arc. This cut replenishment to the northern portion of the krill stock, as evidenced by declining density and swarm frequency. Concomitantly, a new, southern reproduction area developed after the 1990s, reinforcing the range shift despite the lack of surface warming. New spawning hotspots may provide the stepping stones needed for range shifts into polar regions, so planning of climate‐ready marine protected areas should include these key areas of future habitat.

Genome-wide analysis of deletions in maize population reveals abundant genetic diversity and functional impact - Xiao Zhang; Yonghui Zhu; Karl A. G. Kremling; M. Cinta Romay; Robert Bukowski; Qi Sun; Shibin Gao; Edward S. Buckler; Fei Lu (Theoretical and Applied Genetics, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Predicting phenotypes from genetic, environment, management, and historical data using CNNs - Jacob D. Washburn; Emre Cimen; Guillaume Ramstein; Timothy Reeves; Patrick O’Briant; Greg McLean; Mark Cooper; Graeme Hammer; Edward S. Buckler (Theoretical and Applied Genetics, 2021)

The Use of Hypnotics for Insomnia Disorder in Saudi Arabia: A Survey of Patients’ Experiences and Perceptions - Ali M. Dobia; Kath M. Ryan; Ahmed S. BaHammam; Mohammed H. Abutaleb; Rawaah Y. Alwadani; Alexander D. Edwards (Sleep and Vigilance, 2021)

Correction to: Smart controlled environment agriculture methods: a holistic review - S. Ragaveena; A. Shirly Edward; U. Surendran (Reviews in Environmental Science and Bio/Technology, 2021)

Smart controlled environment agriculture methods: a holistic review - S. Ragaveena; A. Shirly Edward; U. Surendran (Reviews in Environmental Science and Bio/Technology, 2021)

Ocean Turbulence and Mixing Near the Shelf Break South-East of Nova Scotia - Iossif Lozovatsky; Charlotte Wainwright; Edward Creegan; Harindra J. S. Fernando (Boundary-Layer Meteorology, 2021)

Effect of Subject-Specific, Spatially Reduced, and Idealized Boundary Conditions on the Predicted Hemodynamic Environment in the Murine Aorta - Kelly A. Smith; Samer S. Merchant; Edward W. Hsu; Lucas H. Timmins (Annals of Biomedical Engineering, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Evidence that geographic variation in genetic ancestry associates with uterine fibroids - Jacob M. Keaton; Elizabeth A. Jasper; Jacklyn N. Hellwege; Sarah H. Jones; Eric S. Torstenson; Todd L. Edwards; Digna R. Velez Edwards (Human Genetics, 2021)

Low-dose radiation therapy (LDRT) for COVID-19 and its deadlier variants - Rachna Kapoor; James S. Welsh; Vikas Dhawan; Seyed Alireza Javadinia; Edward J. Calabrese; Gaurav Dhawan (Archives of Toxicology, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Healthy Aging Requires a Healthy Home Care Workforce: the Occupational Safety and Health of Home Care Aides - M. M. Quinn; P. K. Markkanen; C. J. Galligan; S. R. Sama; J. E. Lindberg; M. F. Edwards (Current Environmental Health Reports, 2021)
Purpose of Review To identify important home care (HC) aide occupational safety and health (OSH) hazards and examine how addressing these can improve aide health and the delivery of HC services overall. Specifically, this review seeks to answer: Why is HC aide OSH important? What are the most significant OSH challenges? How can improving HC aide OSH also improve the safety and health of their clients? What implications do the findings have for future research? Recent Findings HC is one of the fastest growing US industries. Aides comprise its largest workforce and are increasingly needed to care for the rapidly aging population. There is an aide shortage due in part to instabilities in HC work organization and to serious job-specific hazards, resulting in aides losing work time. Recent social, economic, and technological factors are rapidly changing the nature of HC work, creating OSH hazards similar to those found in nursing homes. At the same time, aides are experiencing social and economic inequities that increase their vulnerability to OSH hazards. These hazards are also a burden on employers who are challenged to recruit, retain, and train aides. OSH injuries and illness interrupt the continuity of care delivery to clients. Many OSH hazards also put HC clients and families at risk. Summary A new framework and methodologies are needed to assess aide and client safety together in order to guide future HC research, policies, and practices. Government, industry, and labor commitment is needed to fund and coordinate a comprehensive, multidisciplinary research program.

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Coral reef resilience differs among islands within the Gulf of Mannar, southeast India, following successive coral bleaching events - K. Diraviya Raj; Greta S. Aeby; G. Mathews; Gareth J. Williams; Jamie M. Caldwell; R. L. Laju; M. Selva Bharath; P. Dinesh Kumar; A. Arasamuthu; N. Gladwin Gnana Asir; Lisa M. Wedding; Andrew J. Davies; et al. (Coral Reefs, 2021)

High Genetic Addiction Risk Score (GARS) in Chronically Prescribed Severe Chronic Opioid Probands Attending Multi-pain Clinics: an Open Clinical Pilot Trial - Mark Moran; Kenneth Blum; Jessica Valdez Ponce; Lisa Lott; Marjorie C. Gondré–Lewis; Sampada Badgaiyan; Raymond Brewer; B. William Downs; Philip Fynman; Alexander Weingarten; Jean Lud Cadet; David E. Smith; et al. (Molecular Neurobiology, 2021)
Millions of Americans experience pain daily. In 2017, opioid overdose claimed 64,000 lives increasing to 84,000 lives in 2020, resulting in a decrease in national life expectancy. Chronic opioid use results in dependency, drug tolerance, neuroadaptation, hyperalgesia, potential addictive behaviors, or Reward Deficiency Syndrome (RDS) caused by a hypodopaminergia. Evaluation of pain clinic patients with the Genetic Addiction Risk Score (GARS) test and the Addiction Severity Index (ASI- Media Version V) revealed that GARS scores equal to or greater than 4 and 7 alleles significantly predicted drug and alcohol severity, respectively. We utilized RT-PCR for SNP genotyping and multiplex PCR/capillary electrophoresis for fragment analysis of the role of eleven alleles in a ten-reward gene panel, reflecting the activity of brain reward circuitry in 121 chronic opioid users. The study consisted of 55 males and 66 females averaging ages 54 and 53 years of age, respectively. The patients included Caucasians, African Americans, Hispanics, and Asians. Inclusion criteria mandated that the Morphine Milligram Equivalent (MME) was 30–600 mg/day (males) and 20 to 180 mg/day (females) for treatment of chronic pain over 12 months. Ninety-six percent carried four or more risk alleles, and 73% carried seven or more risk alleles, suggesting a high predictive risk for opioid and alcohol dependence, respectively. These data indicate that chronic, legally prescribed opioid users attending a pain clinic possess high genetic risk for drug and alcohol addiction. Early identification of genetic risk, using the GARS test upon entry to treatment, may prevent iatrogenic induced opioid dependence.

Assessment of the efficacy of six field cleaning protocols for hydrocarbon quantification - Emily C. Pisarski; Edward F. Wirth; Paul L. Pennington; Ian Hartwell; Brian S. Shaddrix; David R. Whitall; Dennis A. Apeti; Gregory Baker (Environmental Science and Pollution Research, 2021)

Are visual working memory and episodic memory distinct processes? Insight from stroke patients by lesion-symptom mapping - Selma Lugtmeijer; Linda Geerligs; Frank Erik de Leeuw; Edward H. F. de Haan; Roy P. C. Kessels; Anouk R. Smits; Ben A. Schmand; Edward H. F. de Haan; Frank Erik de Leeuw; Gert jan Luijckx; H. Steven Scholte; Joke M. Spikman; et al. (Brain Structure and Function, 2021)
Working memory and episodic memory are two different processes, although the nature of their interrelationship is debated. As these processes are predominantly studied in isolation, it is unclear whether they crucially rely on different neural substrates. To obtain more insight in this, 81 adults with sub-acute ischemic stroke and 29 elderly controls were assessed on a visual working memory task, followed by a surprise subsequent memory test for the same stimuli. Multivariate, atlas- and track-based lesion-symptom mapping (LSM) analyses were performed to identify anatomical correlates of visual memory. Behavioral results gave moderate evidence for independence between discriminability in working memory and subsequent memory, and strong evidence for a correlation in response bias on the two tasks in stroke patients. LSM analyses suggested there might be independent regions associated with working memory and episodic memory. Lesions in the right arcuate fasciculus were more strongly associated with discriminability in working memory than in subsequent memory, while lesions in the frontal operculum in the right hemisphere were more strongly associated with criterion setting in subsequent memory. These findings support the view that some processes involved in working memory and episodic memory rely on separate mechanisms, while acknowledging that there might also be shared processes.

The Impact of Atmosphere–Ocean–Wave Coupling on the Near-Surface Wind Speed in Forecasts of Extratropical Cyclones - Emanuele S. Gentile; Suzanne L. Gray; Janet F. Barlow; Huw W. Lewis; John M. Edwards (Boundary-Layer Meteorology, 2021)
Accurate modelling of air–sea surface exchanges is crucial for reliable extreme surface wind-speed forecasts. While atmosphere-only weather forecast models represent ocean and wave effects through sea-state independent parametrizations, coupled multi-model systems capture sea-state dynamics by integrating feedbacks between the atmosphere, ocean and wave model components. Here, we investigate the sensitivity of extreme surface wind speeds to air–sea exchanges at the kilometre scale using coupled and uncoupled configurations of the Met Office’s UK Regional Coupled Environmental Prediction system. The case period includes the passage of extra-tropical cyclones Helen, Ali, and Bronagh, which brought maximum gusts of 36 m s $$^{-1}$$ - 1 over the UK. Compared with the atmosphere-only results, coupling to the ocean decreases the domain-average sea-surface temperature by up to 0.5 K. Inclusion of coupling to waves reduce the 98th percentile 10-m wind speed by up to 2 m s $$^{-1}$$ - 1 as young, growing wind waves reduce the wind speed by increasing the sea-surface aerodynamic roughness. Impacts on gusts are more modest, with local reductions of up to 1 m s $$^{-1}$$ - 1 , due to enhanced boundary-layer turbulence which partially offsets air–sea momentum transfer. Using a new drag parametrization based on the Coupled Ocean–Atmosphere Response Experiment 4.0 parametrization, with a cap on the neutral drag coefficient and reduction for wind speeds exceeding 27 m s $$^{-1}$$ - 1 , the atmosphere-only model achieves equivalent impacts on 10-m wind speeds and gusts as from coupling to waves. Overall, the new drag parametrization achieves the same 20% improvement in forecast 10-m wind-speed skill as coupling to waves, with the advantage of saving the computational cost of the ocean and wave models.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Revisiting the Colletotrichum species causing anthracnose of almond in Australia - D. D. de Silva; R. C. Mann; J. Kaur; P. N Ekanayake; T. I Sawbridge; S. McKay; P. W. J. Taylor; J. Edwards (Australasian Plant Pathology, 2021)

Macroecological patterns of forest structure and allometric scaling in mangrove forests - Andre S. Rovai; Robert R. Twilley; Edward Castañeda‐Moya; Stephen R. Midway; Daniel A. Friess; Carl C. Trettin; Jacob J. Bukoski; Atticus E.L. Stovall; Paulo R. Pagliosa; Alessandra L. Fonseca; Richard A. Mackenzie; Aslan Aslan; et al. (Global Ecology and Biogeography, 2021)
Aim Mangrove wetlands span broad geographical gradients, resulting in functionally diverse tree communities. We asked whether latitudinal variation, allometric scaling relationships and species composition influence mangrove forest structure and biomass allocation across biogeographical regions and distinct coastal morphologies. Location Global. Time period Present. Major taxa studied Mangrove ecosystems. Methods We built the largest field‐based dataset on mangrove forest structure and biomass to date ( c . 2,800 plots from 67 countries) to address macroecological questions pertaining to structural and functional diversity of mangroves spanning biogeographical and coastal morphology gradients. We used frequentist inference statistics and machine learning models to determine environmental drivers that control biomass allocation within and across mangrove communities globally. Results Allometric scaling relationships and forest structural complexity were consistent across biogeographical and coastal morphology gradients, suggesting that mangrove biomass is controlled by regional forcings rather than by latitude or species composition. For instance, nearly 40% of the global variation in biomass was explained by regional climate and hydroperiod, revealing nonlinear thresholds that control biomass accumulation across broad geographical gradients. Furthermore, we found that ecosystem‐level carbon stocks (average 401 ± 48 MgC/ha, covering biomass and the top 1 m of soil) varied little across diverse coastal morphologies, reflecting regional bottom‐up geomorphic controls that shape global patterns in mangrove biomass apportioning. Main conclusions Our findings reconcile views of wetland and terrestrial forest macroecology. Similarities in stand structural complexity and cross‐site size–density relationships across multiscale environmental gradients show that resource allocation in mangrove ecosystems is independent of tree size and invariant to species composition or latitude. Mangroves follow a universal fractal‐based scaling relationship that describes biomass allocation for several other terrestrial tree‐dominated communities. Understanding how mangroves adhere to these universal allometric rules can improve our ability to account for biomass apportioning and carbon stocks in response to broad geographical gradients.

Differences in microbial community response to nitrogen fertilization result in unique enzyme shifts between arbuscular and ectomycorrhizal‐dominated soils - Joseph E. Carrara; Christopher A. Walter; Zachary B. Freedman; Ashley N. Hostetler; Jennifer S. Hawkins; Ivan J. Fernandez; Edward R. Brzostek (Global Change Biology, 2021)
While the effect of nitrogen (N) deposition on belowground carbon (C) cycling varies, emerging evidence shows that forest soils dominated by trees that associate with ectomycorrhizal fungi (ECM) store more C than soils dominated by trees that associate with arbuscular mycorrhizae (AM) with increasing N deposition. We hypothesized that this is due to unique nutrient cycling responses to N between AM and ECM‐dominated soils. ECM trees primarily obtain N through fungal mining of soil organic matter subsidized by root‐C. As such, we expected the largest N‐induced responses of C and N cycling to occur in ECM rhizospheres and be driven by fungi. Conversely, as AM trees rely on bacterial scavengers in bulk soils to cycle N, we predicted the largest AM responses to be driven by shifts in bacteria and occur in bulk soils. To test this hypothesis, we measured microbial community composition, metatranscriptome profiles, and extracellular enzyme activity in bulk, rhizosphere, and organic horizon (OH) soils in AM and ECM‐dominated soils at Bear Brook Watershed in Maine, USA. After 27 years of N fertilization, fungal community composition shifted across ECM soils, but bacterial communities shifted across AM soils. These shifts were mirrored by enhanced C relative to N mining enzyme activities in both mycorrhizal types, but this occurred in different soil fractions. In ECM stands these shifts occurred in rhizosphere soils, but in AM stands they occurred in bulk soils. Additionally, ECM OH soils exhibited the opposite response with declines in C relative to N mining. As rhizosphere soils account for only a small portion of total soil volume relative to bulk soils, coupled with declines in C to N enzyme activity in ECM OH soils, we posit that this may partly explain why ECM soils store more C than AM soils as N inputs increase.

Agrochemical Health Risks Exposure and Its Determinants: Empirical Evidence among Cassava Farmers in Nigeria - Toyin S Olowogbon; Raphael O Babatunde; Edward Asiedu; Aaron M Yoder (Journal of Agromedicine, 2021)

Upland burning and grazing as strategies to offset climate-change effects on wetlands - Owen P. McKenna; David A. Renton; David M. Mushet; Edward S. DeKeyser (Wetlands Ecology and Management, 2021)
Wetland ecosystems perform a multitude of services valued by society and provide critical habitat for migratory birds and other wildlife. Despite their importance, wetlands have been lost to different local, regional, and global drivers. Remaining wetlands are extremely sensitive to changing temperature and precipitation regimes. Management of grassland areas in wetland catchments may be an effective strategy for counteracting potentially negative impacts of climate change on wetlands. Our objective was to estimate the effects of climate changes on wetland hydrology, and to explore strategies for increasing surface-water inputs to wetlands. We coupled a field study with process-based simulation modeling of wetland-water levels. We found that climate change could decrease the number of wetlands that hold ponded water during the waterfowl breeding season by 14% under a hot wet scenario or 29% under a hot dry scenario if no upland-management actions were taken. Upland burning reduced pond losses to 9% (hot wet) and 26% (hot dry). Upland grazing resulted in the smallest loss of ponded wetlands, 6% loss under the hot-and-wet scenario and 22% loss under the hot-and-dry scenario. Overall, water inputs could be increased by either burning or grazing of upland vegetation thereby reducing pond losses during the waterfowl breeding season. While field results suggest that both grazing and burning can reduce the vegetative structure that could lead to increases in runoff in grassland catchments, our model simulations indicated that additional actions may be needed for managers to minimize future meteorologically driven water losses.

Isonicotinoyl hydrazones of pyridoxine derivatives: synthesis and antimycobacterial activity - Nikita V. Shtyrlin; Rail M. Khaziev; Valery G. Shtyrlin; Edward M. Gilyazetdinov; Mariya N. Agafonova; Konstantin S. Usachev; Daut R. Islamov; Alexander E. Klimovitskii; Tatiana I. Vinogradova; Marine Z. Dogonadze; Natalia V. Zabolotnykh; Evgenii G. Sokolovich; et al. (Medicinal Chemistry Research, 2021)

Longitudinal uncoupling of the heart and arteries with aging in a community-dwelling population - Majd AlGhatrif; Chris H. Morrell; Lewis C. Becker; Paul D. Chantler; Samer S. Najjar; Luigi Ferrucci; Gary Gerstenblith; Edward G. Lakatta (GeroScience, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Ontogenetic scaling of the gastrointestinal tract of a marsupial foregut fermenter, the western grey kangaroo Macropus fuliginosus melanops - Adam J. Munn; Edward P. Snelling; David A. Taggart; Roger S. Seymour (Journal of Comparative Physiology B, 2021)

Are physiological and behavioural responses to stressors displayed concordantly by wild urban rodents? - Loren L. Fardell; Miguel A. Bedoya-Pérez; Christopher R. Dickman; Mathew S. Crowther; Chris R. Pavey; Edward J. Narayan (The Science of Nature, 2021)
Understanding wild animal responses to stressors underpins effective wildlife management. In order for responses to stressors to be correctly interpreted, it is critical that measurements are taken on wild animals using minimally invasive techniques. Studies investigating wild animal responses to stressors often measure either a single physiological or behavioural variable, but whether such responses are comparable and concordant remains uncertain. We investigated this question in a pilot study that measured responses of wild-caught urban brown and black rats ( Rattus norvegicus , Rattus rattus ) to fur-based olfactory cues from a predator, the domestic cat ( Felis catus ); a novel herbivore, the koala ( Phascolarctos cinereus ); and a familiar herbivore and competitor, the common brushtail possum ( Trichosurus vulpecula ). Physiological responses, measured by assaying faecal glucocorticoid metabolites, were compared to behavioural responses observed via video recordings. We found that physiological and behavioural responses to stressors were expressed concordantly. There was no sizeable physiological response observed, and the behavioural response when considered across the night was negligible. However, the behavioural response to the predator and competitor cues changed across the observation period, with activity increasing with increasing hours of exposure. Our results indicate that responses of wild rodents to cues are nuanced, with stress responses modulated by behaviour changes that vary over time according to the severity of the perceived threat as animals gather further information. If the physiological response alone had been assessed, this moderated response may not have been evident, and in terms of wildlife management, vital information would have been lost.

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

Scenarios for Global Aquaculture and Its Role in Human Nutrition - Jessica A. Gephart; Christopher D. Golden; Frank Asche; Ben Belton; Cecile Brugere; Halley E. Froehlich; Jillian P. Fry; Benjamin S. Halpern; Christina C. Hicks; Robert C. Jones; Dane H. Klinger; David C. Little; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Dietary intake, eating behavior and physical activity in individuals with and without obstructive sleep apnea - Caroline J. Beatty; Shane A. Landry; Joy Lee; Simon A. Joosten; Anthony Turton; Denise M. O’Driscoll; Ai-Ming Wong; Luke Thomson; Bradley A. Edwards; Garun S. Hamilton (Sleep and Biological Rhythms, 2021)

Potent antiproliferative active agents: novel bis Schiff bases and bis spiro β-lactams bearing isatin tethered with butylene and phenylene as spacer and DNA/BSA binding behavior as well as studying molecular docking - Mohammad Bashiri; Aliasghar Jarrahpour; S. Masoud Nabavizadeh; Somaye Karimian; Banafsheh Rastegari; Elahe Haddadi; Edward Turos (Medicinal Chemistry Research, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Differences in joint power distribution in high and low lactate threshold cyclists - Brian K. Leary; Heath M. Burton; Emre Vardarli; Anthony S. Wolfe; Charles K. Crawford; John D. Akins; Edward F. Coyle (European Journal of Applied Physiology, 2021)

Spatial analysis of urine zinc (Zn) concentration for women of reproductive age and school age children in Malawi - Felix P. Phiri; E. Louise Ander; R. Murray Lark; Edward J. M. Joy; Alexander A. Kalimbira; Parminder S. Suchdev; Jellita Gondwe; Elliott M. Hamilton; Michael J. Watts; Martin R. Broadley (Environmental Geochemistry and Health, 2021)
Zinc (Zn) is an essential micronutrient, and Zn deficiency remains a major global public health challenge. Recognised biomarkers of population Zn status include blood plasma or serum Zn concentration and proxy data such as dietary Zn intake and prevalence of stunting. Urine Zn concentration is rarely used to assess population Zn status. This study assessed the value of urine Zn concentration as a biomarker of population Zn status using a nationally representative sample of non-pregnant women of reproductive age (WRA) and school-aged children (SAC) in Malawi. Spot (casual) urine samples were collected from 741 WRA and 665 SAC. Urine Zn concentration was measured by inductively coupled plasma mass spectrometry with specific gravity adjustment for hydration status. Data were analysed using a linear mixed model with a spatially correlated random effect for between-cluster variation. The effect of time of sample collection (morning or afternoon), and gender (for SAC), on urine Zn concentration were examined. There was spatial dependence in urine Zn concentration between clusters among SAC but not WRA, which indicates that food system or environmental factors can influence urine Zn concentration. Mapping urine Zn concentration could potentially identify areas where the prevalence of Zn deficiency is greater and thus where further sampling or interventions might be targeted. There was no evidence for differences in urine Zn concentration between gender ( P = 0.69) or time of sample collection ( P = 0.85) in SAC. Urine Zn concentration was greater in afternoon samples for WRA ( P = 0.003). Relationships between urine Zn concentration, serum Zn concentration, dietary Zn intake, and potential food systems covariates warrant further study.

Macroalgal defense phenotype correlates with herbivore abundance - Scott S. Gabara; Benjamin P. Weitzman; Brenda H. Konar; Matthew S. Edwards (Marine Biology, 2020)

Trevor Alleyne Thorpe: His academic life and scientific legacy - Prakash P. Kumar; Stephen F. Chandler; Indra S. Harry; Chin-yi Lu; Claudio Stasolla; Edward C. Yeung (In Vitro Cellular & Developmental Biology - Plant, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Survey, identification and genetic diversity of Phytophthora capsici causing wilt of chilli (Capsicum annuum L.) in Bhutan - Ganja S. Rai; Edward C. Y. Liew; David. I. Guest (European Journal of Plant Pathology, 2020)

High Energy Side and Rear American Football Head Impacts Cause Obvious Performance Decrement on Video - Adam J. Bartsch; Daniel Hedin; Jay Alberts; Edward C. Benzel; Jason Cruickshank; Robert S. Gray; Kenneth Cameron; Megan N. Houston; Tyler Rooks; Gerald McGinty; Erick Kozlowski; Steven Rowson; et al. (Annals of Biomedical Engineering, 2020)

APPA (apocynin and paeonol) modulates pathological aspects of human neutrophil function, without supressing antimicrobial ability, and inhibits TNFα expression and signalling - A. L. Cross; J. Hawkes; H. L. Wright; R. J. Moots; S. W. Edwards (Inflammopharmacology, 2020)
Neutrophils are key players in the pathophysiological process underlying inflammatory conditions not only by release of tissue-damaging cytotoxic enzymes, reactive oxygen species (ROS) but also by secretion of important immunomodulatory chemokines and cytokines. Here, we report the effects of the novel agent APPA, undergoing formal clinical development for treatment of osteoarthritis, and its constituent components, apocynin (AP) and paeonol (PA) on a number of neutrophil functions, including effects on TNFα- expression and signalling. Neutrophils were treated with APPA (10–1000 µg/mL) prior to the measurement of cell functions, including ROS production, chemotaxis, apoptosis and surface receptor expression. Expression levels of several key genes and proteins were measured after incubation with APPA and the chromatin re-modelling agent, R848. APPA did not significantly affect phagocytosis, bacterial killing or expression of surface receptors, while chemotactic migration was affected only at the highest concentrations. However, APPA down-regulated neutrophil degranulation and ROS levels, and decreased the formation of neutrophil extracellular traps. APPA also decreased cytokine-stimulated gene expression, inhibiting both TNFα- and GM-CSF-induced cell signalling. APPA was as effective as infliximab in down-regulating chemokine and IL-6 expression following incubation with R848. Whilst APPA does not interfere with neutrophil host defence against infections, it does inhibit neutrophil degranulation, and cytokine-driven signalling pathways (e.g. autocrine signalling and NF-κB activation), processes that are associated with inflammation. These observations may explain the mechanisms by which APPA exerts anti-inflammatory effects and suggests a potential therapeutic role in inflammatory diseases in which neutrophils and TNFα signalling are important in pathology, such as rheumatoid arthritis.

The Human Gene Mutation Database (HGMD®): optimizing its use in a clinical diagnostic or research setting - Peter D. Stenson; Matthew Mort; Edward V. Ball; Molly Chapman; Katy Evans; Luisa Azevedo; Matthew Hayden; Sally Heywood; David S. Millar; Andrew D. Phillips; David N. Cooper (Human Genetics, 2020)
The Human Gene Mutation Database (HGMD ® ) constitutes a comprehensive collection of published germline mutations in nuclear genes that are thought to underlie, or are closely associated with human inherited disease. At the time of writing (June 2020), the database contains in excess of 289,000 different gene lesions identified in over 11,100 genes manually curated from 72,987 articles published in over 3100 peer-reviewed journals. There are primarily two main groups of users who utilise HGMD on a regular basis; research scientists and clinical diagnosticians. This review aims to highlight how to make the most out of HGMD data in each setting.

Evidence for craniofacial enhancer variation underlying nonsyndromic cleft lip and palate - Vershanna E. Morris; S. Shahrukh Hashmi; Lisha Zhu; Lorena Maili; Christian Urbina; Steven Blackwell; Matthew R. Greives; Edward P. Buchanan; John B. Mulliken; Susan H. Blanton; W. Jim Zheng; Jacqueline T. Hecht; et al. (Human Genetics, 2020)

Modelling climate change impacts on maize yields under low nitrogen input conditions in sub‐Saharan Africa - Gatien N. Falconnier; Marc Corbeels; Kenneth J. Boote; François Affholder; Myriam Adam; Dilys S. MacCarthy; Alex C. Ruane; Claas Nendel; Anthony M. Whitbread; Éric Justes; Lajpat R. Ahuja; Folorunso M. Akinseye; et al. (Global Change Biology, 2020)
Smallholder farmers in sub‐Saharan Africa (SSA) currently grow rainfed maize with limited inputs including fertilizer. Climate change may exacerbate current production constraints. Crop models can help quantify the potential impact of climate change on maize yields, but a comprehensive multimodel assessment of simulation accuracy and uncertainty in these low‐input systems is currently lacking. We evaluated the impact of varying [CO 2 ], temperature and rainfall conditions on maize yield, for different nitrogen (N) inputs (0, 80, 160 kg N/ha) for five environments in SSA, including cool subhumid Ethiopia, cool semi‐arid Rwanda, hot subhumid Ghana and hot semi‐arid Mali and Benin using an ensemble of 25 maize models. Models were calibrated with measured grain yield, plant biomass, plant N, leaf area index, harvest index and in‐season soil water content from 2‐year experiments in each country to assess their ability to simulate observed yield. Simulated responses to climate change factors were explored and compared between models. Calibrated models reproduced measured grain yield variations well with average relative root mean square error of 26%, although uncertainty in model prediction was substantial (CV = 28%). Model ensembles gave greater accuracy than any model taken at random. Nitrogen fertilization controlled the response to variations in [CO 2 ], temperature and rainfall. Without N fertilizer input, maize (a) benefited less from an increase in atmospheric [CO 2 ]; (b) was less affected by higher temperature or decreasing rainfall; and (c) was more affected by increased rainfall because N leaching was more critical. The model intercomparison revealed that simulation of daily soil N supply and N leaching plays a crucial role in simulating climate change impacts for low‐input systems. Climate change and N input interactions have strong implications for the design of robust adaptation approaches across SSA, because the impact of climate change in low input systems will be modified if farmers intensify maize production with balanced nutrient management.

Species-specific biomass drives macroalgal benthic primary production on temperate rocky reefs - Michael Spector; Matthew S. Edwards (Algae, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Eroding islands of Gulf of Mannar, Southeast India: a consequence of long-term impact of coral mining and climate change - N. Gladwin Gnana Asir; P. Dinesh Kumar; A. Arasamuthu; G. Mathews; K. Diraviya Raj; T. K. Ashok Kumar; Deepak S. Bilgi; J. K. Patterson Edward (Natural Hazards, 2020)

Cytotoxicity, anticancer, and antioxidant properties of mono and bis-naphthalimido β-lactam conjugates - Nassim Borazjani; Maryam Behzadi; Marzieh Dadkhah Aseman; Aliasghar Jarrahpour; Javad Ameri Rad; Sedigheh Kianpour; Aida Iraji; S. Masoud Nabavizadeh; Mohammad Mehdi Ghanbari; Gyula Batta; Edward Turos (Medicinal Chemistry Research, 2020)

Potential establishment and ecological effects of bighead and silver carp in a productive embayment of the Laurentian Great Lakes - Lori N. Ivan; Doran M. Mason; Hongyan Zhang; Edward S. Rutherford; Tim Hunter; Shaye Sable; Aaron T. Adamack; Kenneth Rose (Biological Invasions, 2020)
Bighead carp H . nobilis and silver carp Hypothalmichthys molitrix (collectively bigheaded carps, BHC) are invasive planktivorous fishes that threaten to enter the Laurentian Great Lakes and disrupt food webs. To assess the likelihood of BHC establishment and their likely effects on the food web of Saginaw Bay, Lake Huron, we developed a multi-species individual-based bioenergetics model that tracks individual bighead and silver carp, four key fish species, and seven prey biomass groups over 50 years. The model tracks the daily consumption, mortality and growth of all individuals and the biomass dynamics of interacting prey pools. We ran simulation scenarios to determine the likelihood of BHC establishment under initial introductions from 5 to 1 million yearling and older individuals, and assuming variable age-0 carp survival rates (high, intermediate, and low). We bounded the survival of age-0 BHC as recruitment continues to be one of the biggest unknowns. We also simulated the potential effects of an established population of 1 million bighead carp or silver carp assuming variation in age-0 survival. Results indicated that as few as 10 BHC could establish a population assuming high or intermediate age-0 survival, but at least 100,000 individuals were needed to establish a population assuming low age-0 survival. BHC had negative effects on plankton and planktivorous fish biomass, which increased with BHC density. However, piscivorous walleye Sander vitreus appeared to benefit from BHC establishment. The potential for BHC to establish and affect ecologically and economically important fish species in Saginaw Bay is a cause for concern.

Poly (ether) sulfone electrospun nanofibrous membranes embedded with graphene oxide quantum dots with antimicrobial activity - Charmaine S. Tshangana; Adolph A. Muleja; Edward N. Nxumalo; Sabelo D. Mhlanga (Environmental Science and Pollution Research, 2020)

Quaternary land bridges have not been universal conduits of gene flow - Emilie Cros; Balaji Chattopadhyay; Kritika M. Garg; Nathaniel S. R. Ng; Suzanne Tomassi; Suzan Benedick; David P. Edwards; Frank E. Rheindt (Molecular Ecology, 2020)
Quaternary climate oscillations are a well‐known driver of animal diversification, but their effects are most well studied in areas where glaciations lead to habitat fragmentation. In large areas of the planet, however, glaciations have had the opposite effect, but here their impacts are much less well understood. This is especially true in Southeast Asia, where cyclical changes in land distribution have generated enormous land expansions during glacial periods. In this study, we selected a panel of five songbird species complexes covering a range of ecological specificities to investigate the effects Quaternary land bridges have had on the connectivity of Southeast Asian forest biota. Specifically, we combined morphological and bioacoustic analysis with an arsenal of population genomic and modelling approaches applied to thousands of genome‐wide DNA markers across a total of more than 100 individuals. Our analyses show that species dependent on forest understorey exhibit deep differentiation between Borneo and western Sundaland, with no evidence of gene flow during the land bridges accompanying the last 1–2 ice ages. In contrast, dispersive canopy species and habitat generalists have experienced more recent gene flow. Our results argue that there remains much cryptic species‐level diversity to be discovered in Southeast Asia even in well‐known animal groups such as birds, especially in nondispersive forest understorey inhabitants. We also demonstrate that Quaternary land bridges have not been equally suitable conduits of gene flow for all species complexes and that life history is a major factor in predicting relative population divergence time across Quaternary climate fluctuations.

The influence of marine algae on iodine speciation in the coastal ocean - Mary W. Carrano; Kyoko Yarimizu; Jennifer L. Gonzales; Ricardo Cruz-López; Matthew S. Edwards; Teresa M. Tymon; Frithjof C. Küpper; Carl J. Carrano (Algae, 2020)

Impairments in Emotion Recognition and Risk-Taking Behavior After Isolated, Cerebellar Stroke - Nils S. van den Berg; Rients B. Huitema; Jacoba M. Spikman; Gert-Jan Luijckx; Edward H. F. de Haan (The Cerebellum, 2020)
An increasing amount of research has shown a cerebellar involvement in higher order cognitive functions, including emotional processing and decision-making. However, it has not been investigated whether impairments in facial emotion recognition, which could be a marker of impaired emotional experiences, are related to risky decision-making in these patients. Therefore, we aimed to investigate facial emotion recognition and risky decision-making in these patients as well as to investigate a relationship between these constructs. Thirteen patients with a discrete, isolated, cerebellar lesion as a consequence of a stroke were included in the study. Emotion recognition was assessed with the Facial Expressions of Emotions—Stimuli and Test (FEEST). Risk-taking behavior was assessed with the Action Selection Test (AST). Furthermore, 106 matched healthy controls performed the FEEST and 20 matched healthy controls performed the AST. Compared with healthy controls, patients were significantly worse in the recognition of emotional expressions and they took significantly more risks. In addition, a worse ability to recognize fearful facial expressions was strongly related to an increase in risky decisions in the AST. Therefore, we suggest that tests of emotion recognition should be incorporated into the neuropsychological assessment after cerebellar stroke to boost detection and treatment of these impairments in these patients.

7700-year persistence of an isolated, free-living coral assemblage in the Galápagos Islands: a model for coral refugia? - J. S. Feingold; B. Riegl; K. Hendrickson; L. T. Toth; H. Cheng; R. L. Edwards; R. B. Aronson (Coral Reefs, 2020)

Genus-level change in aggressiveness with continuous invasions: a phylogenetically-informed Bayesian quantile regression - Justin S. H. Wan; Edward C. Y. Liew (Biological Invasions, 2020)

Genetic structures across a biogeographical barrier reflect dispersal potential of four Southeast Asian mangrove plant species - Alison K. S. Wee; Annika M. E. Noreen; Junya Ono; Koji Takayama; Prakash P. Kumar; Hugh T. W. Tan; Mohd N. Saleh; Tadashi Kajita; Edward L. Webb (Journal of Biogeography, 2020)
Aim Biogeographical barriers restrict the movement of individuals, resulting in population divergence, genetic differentiation, endemism and speciation. Yet, some barriers demonstrate unequal effect across species depending on species dispersal, which manifests in varying genetic structure. We test the hypotheses that the genetic structure of four coastal mangrove species would reflect differences in dispersal potential across the Malay Peninsula, a major biogeographical barrier in the Indo‐West Pacific region. Location East and west coasts of the Malay Peninsula. Taxon Mangrove trees Avicennia alba , Sonneratia alba , Bruguiera gymnorhiza and Rhizophora mucronata. Methods For each species, we characterized genetic structure and gene flow using 7–12 species‐specific nuclear microsatellite markers. We tested for east–west genetic differentiation across the peninsula, a stepping‐stone migration pattern, and assessed the proportion of recent dispersal and direction of historical migration along the Malacca Strait. Results Significant east–west genetic differentiation across the peninsula was observed in A. alba , S. alba and B. gymnorhiza , and the effect was most pronounced for the two species with lower dispersal potential ( A. alba , S. alba ). In contrast, the two species with higher dispersal potential ( B. gymnorhiza and R. mucronata ) exhibited much higher proportion of recent inter‐population migration along the Malacca Strait. The signature of historical colonization from refugia in the Andaman Sea (north‐to‐south migration along the Malacca Strait) predominated for A. alba and S. alba. Historical south–north migration predominated for R. mucronata and B. gymnorhiza . Main conclusions This study implicated dispersal potential as a cause of varying mangrove species genetic structure across a biogeographical barrier. The Malay Peninsula functions as a filter to gene flow rather than a barrier. The genetic structure in mangrove species with a higher dispersal potential is more congruent with contemporary gene flow while that of species with a lower dispersal potential reflects historical processes. Our findings hint at the role of dispersal potential as a predictor of gene flow in mangroves.

Disturbance legacies increase and synchronize nutrient concentrations and bacterial productivity in coastal ecosystems - John S. Kominoski; Evelyn E. Gaiser; Edward Castañeda‐Moya; Stephen E. Davis; Shimelis B. Dessu; Paul Julian; Dong Yoon Lee; Luca Marazzi; Victor H. Rivera‐Monroy; Andres Sola; Ulrich Stingl; Sandro Stumpf; et al. (Ecology, 2020)
Long‐term ecological research can resolve effects of disturbance on ecosystem dynamics by capturing the scale of disturbance and interactions with environmental changes. To quantify how disturbances interact with long‐term directional changes (sea‐level rise, freshwater restoration), we studied 17 yr of monthly dissolved organic carbon (DOC), total nitrogen (TN), and phosphorus (TP) concentrations and bacterioplankton productivity across freshwater‐to‐marine estuary gradients exposed to multiple disturbance events (e.g., droughts, fire, hurricanes, and low‐temperature anomalies) and long‐term increases in water levels. By studying two neighboring drainages that differ in hydrologic connectivity, we additionally tested how disturbance legacies are shaped by hydrologic connectivity. We predicted that disturbance events would interact with long‐term increases in water levels in freshwater and marine ecosystems to increase spatiotemporal similarity (i.e., synchrony) of organic matter, nutrients, and microbial activities. Wetlands along the larger, deeper, and tidally influenced Shark River Slough (SRS) drainage had higher and more variable DOC, TN, and TP concentrations than wetlands along the smaller, shallower, tidally restricted Taylor River Slough/Panhandle (TS/Ph) drainage. Along SRS, DOC concentrations declined with proximity to coast, and increased in magnitude and variability following drought and flooding in 2015 and a hurricane in 2017. Along TS/Ph, DOC concentrations varied by site (higher in marine than freshwater wetlands) but not year. In both drainages, increases in TN from upstream freshwater marshes occurred following fire in 2008 and droughts in 2010 and 2015, whereas downstream increases in TP occurred with coastal storm surge from hurricanes in 2005 and 2017. Decreases in DOC:TN and DOC:TP were explained by increased TN and TP. Increases in bacterioplankton productivity occurred throughout both drainages following low‐temperature events (2010 and 2011) and a hurricane (2017). Long‐term TN and TP concentrations and bacterioplankton productivity were correlated ( r > 0.5) across a range of sampling distances (1–50 km), indicating spatiotemporal synchrony. DOC concentrations were not synchronized across space or time. Our study advances disturbance ecology theory by illustrating how disturbance events interact with long‐term environmental changes and hydrologic connectivity to determine the magnitude and extent of disturbance legacies. Understanding disturbance legacies will enhance prediction and enable more effective management of rapidly changing ecosystems.

The Rapid Regenerative Response of a Model Sea Anemone Species Exaiptasia pallida Is Characterised by Tissue Plasticity and Highly Coordinated Cell Communication - Chloé A. van der Burg; Ana Pavasovic; Edward K. Gilding; Elise S. Pelzer; Joachim M. Surm; Hayden L. Smith; Terence P. Walsh; Peter J. Prentis (Marine Biotechnology, 2020)

The role of industrial ecology in food and agriculture's adaptation to climate change - Alissa Kendall; Edward S. Spang (Journal of Industrial Ecology, 2020)
The food and agriculture sectors contribute significantly to climate change, but are also particularly vulnerable to its effects. Industrial ecology has robustly addressed these sectors’ contributions to climate change, but not their vulnerability to climate change. Climate change vulnerability must be addressed through development of climate change adaptation and resiliency strategies. However, there is a fundamental tension between the primary objectives of industrial ecology (efficiency, cyclic flows, and pollution prevention) and what is needed for climate change adaptation and resiliency. We develop here two potential ways through which the field can overcome (or work within) this tension and combine the tools and methods of industrial ecology with the science and process of climate change adaptation. The first layers industrial ecology tools on top of climate change adaptation strategies, allowing one to, for example, compare the environmental impacts of different adaptation strategies. The other embeds climate change adaptation and resiliency within industrial ecology tools, for example, by redefining the functional unit in life cycle assessment (LCA) to include functions of resiliency. In both, industrial ecology plays a somewhat narrow role, informing climate change adaptation and resilience decision‐making by providing quantitative indicators of environmental performance. This role for industrial ecology is important given the significant contributions and potential for mitigation of greenhouse gas emissions from food and agriculture. However, it suggests that industrial ecology's role in climate adaptation will be as an evaluator of adaptation strategies, rather than an originator.

Mature hematology in neonatal walruses supports diving alongside their mothers - Shawn R. Noren; Matthew S. Edwards (Marine Mammal Science, 2020)
An animal's physiology limits the environmental conditions where it can persist; quantifying the physiology of the walrus is timely since they are being impacted by alterations in sea ice. We examined postnatal changes in hematology, an important attribute that supports diving, by analyzing a longitudinal data set from aquaria walruses (five males and nine females) sampled from 0.04 to 12.0 years of age ( n = 795 samples). Red blood cell count (RBC), hemoglobin (Hb), hematocrit (Hct), mean corpuscular volume (MCV), mean cell hemoglobin (MCH), and mean corpuscular hemoglobin content (MCHC) did not change markedly after birth and appears to have not been influenced by sex. Estimated values at birth were RBC: 3.78 ± 0.12 × 10 6 mm −3 , Hb: 17.62 ± 0.82 g dl −1 , Hct: 45.21 ± 2.01%, MCV: 118.99 ± 3.99 fl, MCH: 47.10 ± 1.77 pg, and MCHC: 39.60 ± 0.70 g dl −1 . Compared to newborns, there were only subtle decreases in RBC, Hb, and MCHC, and a slight increase in MCV in the years following birth; Hct and MCH appear not to have changed. Unlike other pinnipeds, walruses swim within days of birth and have a prolonged 2‐year nursing interval. Mature hematology early in life supports breath‐holding, as young walruses must transit under sea ice with patchily distributed breathing holes.

The association of HFE gene H63D polymorphism with endurance athlete status and aerobic capacity: novel findings and a meta-analysis - Ekaterina A. Semenova; Eri Miyamoto-Mikami; Egor B. Akimov; Fatima Al-Khelaifi; Haruka Murakami; Hirofumi Zempo; Elena S. Kostryukova; Nikolay A. Kulemin; Andrey K. Larin; Oleg V. Borisov; Motohiko Miyachi; Daniil V. Popov; et al. (European Journal of Applied Physiology, 2020)
Purpose Iron is an important component of the oxygen-binding proteins and may be critical to optimal athletic performance. Previous studies have suggested that the G allele of C/G rare variant (rs1799945), which causes H63D amino acid replacement, in the HFE is associated with elevated iron indexes and may give some advantage in endurance-oriented sports. The aim of the present study was to investigate the association between the HFE H63D polymorphism and elite endurance athlete status in Japanese and Russian populations, aerobic capacity and to perform a meta-analysis using current findings and three previous studies. Methods The study involved 315 international-level endurance athletes (255 Russian and 60 Japanese) and 809 healthy controls (405 Russian and 404 Japanese). Genotyping was performed using micro-array analysis or by PCR. VO 2max in 46 male Russian endurance athletes was determined using gas analysis system. Results The frequency of the iron-increasing CG/GG genotypes was significantly higher in Russian (38.0 vs 24.9%; OR 1.85, P = 0.0003) and Japanese (13.3 vs 5.0%; OR 2.95, P = 0.011) endurance athletes compared to ethnically matched controls. The meta-analysis using five cohorts (two French, Japanese, Spanish, and Russian; 586 athletes and 1416 controls) showed significant prevalence of the CG/GG genotypes in endurance athletes compared to controls (OR 1.96, 95% CI 1.58–2.45; P = 1.7 × 10 –9 ). Furthermore, the HFE G allele was associated with high V̇O 2max in male athletes [CC: 61.8 (6.1), CG/GG: 66.3 (7.8) ml/min/kg; P = 0.036]. Conclusions We have shown that the HFE H63D polymorphism is strongly associated with elite endurance athlete status, regardless ethnicities and aerobic capacity in Russian athletes.

Decrease in 230 Th in the Amundsen Basin since 2007: far-field effect of increased scavenging on the shelf? - Ole Valk; Michiel M. Rutgers van der Loeff; Walter Geibert; Sandra Gdaniec; S. Bradley Moran; Kate Lepore; Robert Lawrence Edwards; Yanbin Lu; Viena Puigcorbé; Nuria Casacuberta; Ronja Paffrath; William Smethie; et al. (Ocean Science, 2020)
This study provides dissolved and particulate 230Th and 232Th results as well as particulate 234Th data collected during expeditions to the central Arctic Ocean (GEOTRACES, an international project to identify processes and quantify fluxes that control the distributions of trace elements; sections GN04 and GIPY11). Constructing a time series of dissolved 230Th from 1991 to 2015 enables the identification of processes that control the temporal development of 230Th distributions in the Amundsen Basin. After 2007, 230Th concentrations decreased significantly over the entire water column, particularly between 300 and 1500 m. This decrease is accompanied by a circulation change, evidenced by a concomitant increase in salinity. A potentially increased inflow of water of Atlantic origin with low dissolved 230Th concentrations leads to the observed depletion in dissolved 230Th in the central Arctic. Because atmospherically derived tracers (chlorofluorocarbon (CFC), sulfur hexafluoride (SF6)) do not reveal an increase in ventilation rate, it is suggested that these interior waters have undergone enhanced scavenging of Th during transit from Fram Strait and the Barents Sea to the central Amundsen Basin. The 230Th depletion propagates downward in the water column by settling particles and reversible scavenging.

Lipopolysaccharide and Morphine-3-Glucuronide-Induced Immune Signalling Increases the Expression of Polysialic Acid in PC12 Cells - Sameera Iqbal; Lindsay M. Parker; Arun V. Everest-Dass; Edward S. X. Moh; Nima Sayyadi; Mark R. Hutchinson; Nicolle H. Packer (Molecular Neurobiology, 2020)

Secondary forest fragments offer important carbon and biodiversity cobenefits - Fabio A. R. Matos; Luiz F. S. Magnago; Carlos Aquila Chan Miranda; Luis F. T. de Menezes; Markus Gastauer; Nathália V. H. Safar; Carlos E. G. R. Schaefer; Mônica P. da Silva; Marcelo Simonelli; Felicity A. Edwards; Sebastião V. Martins; João A. A. Meira‐Neto; et al. (Global Change Biology, 2020)
Tropical forests store large amounts of carbon and high biodiversity, but are being degraded at alarming rates. The emerging global Forest and Landscape Restoration (FLR) agenda seeks to limit global climate change by removing carbon dioxide from the atmosphere through the growth of trees. In doing so, it may also protect biodiversity as a free cobenefit, which is vital given the massive shortfall in funding for biodiversity conservation. We investigated whether natural forest regeneration on abandoned pastureland offers such cobenefits, focusing for the first time on the recovery of taxonomic diversity (TD), phylogenetic diversity (PD) and functional diversity (FD) of trees, including the recovery of threatened and endemic species richness, within isolated secondary forest (SF) fragments. We focused on the globally threatened Brazilian Atlantic Forest, where commitments have been made to restore 1 million hectares under FLR. Three decades after land abandonment, regenerating forests had recovered ~20% (72 Mg/ha) of the above‐ground carbon stocks of a primary forest (PF), with cattle pasture containing just 3% of stocks relative to PFs. Over this period, SF recovered ~76% of TD, 84% of PD and 96% of FD found within PFs. In addition, SFs had on average recovered 65% of threatened and ~30% of endemic species richness of primary Atlantic forest. Finally, we find positive relationships between carbon stock and tree diversity recovery. Our results emphasize that SF fragments offer cobenefits under FLR and other carbon‐based payments for ecosystem service schemes (e.g. carbon enhancements under REDD+). They also indicate that even isolated patches of SF could help to mitigate climate change and the biodiversity extinction crisis by recovering species of high conservation concern and improving landscape connectivity.

Nitric oxide mediates oxylipin production and grazing defense in diatoms - Matthew D. Johnson; Bethanie R. Edwards; David J. Beaudoin; Benjamin A. S. Van Mooy; Assaf Vardi (Environmental Microbiology, 2020)
Summary Diatom blooms are important features of productive marine ecosystems and are known to support higher trophic levels. However, when stressed or wounded, diatoms can produce oxylipin molecules known to inhibit the reproduction and development of copepods and decrease microzooplankton growth rates. Using oxylipin chemical treatments, lipidomic analysis and functional genomic approaches, we provide evidence that nitric oxide (NO) and oxylipin signalling pathways in diatoms respond to protist grazers, resulting in increased defence fitness and survival. Exposure of the diatom Phaeodactylum tricornutum to the dinoflagellate Oxyrrhis marina resulted in NO production by P . tricornutum and pronounced change in its dissolved oxylipin profile. Experimentally elevating levels of NO also resulted in increased oxylipin production, and lower overall grazing rates. Furthermore, O . marina preferentially grazed on P . tricornutum prey with lower levels of NO, suggesting that this molecule and its effect on oxylipin pathways play a key role in prey selection. Exposure of O . marina grazing on P . tricornutum to exogenous oxylipins also decreased grazing rates, which is consistent with a grazing deterrence role for these molecules. These results suggest that NO and oxylipin production help to structure diatom communities, in part by modulating interactions with microzooplankton predators.

Assessing a macroalgal foundation species: community variation with shifting algal assemblages - Jacob R. Metzger; Brenda Konar; Matthew S. Edwards (Marine Biology, 2019)

Changes in benthic community composition associated with the outbreak of the corallimorph, Rhodactis howesii, at Palmyra Atoll - Amanda L. Carter; Clinton B. Edwards; Michael D. Fox; Corinne G. Amir; Yoan Eynaud; Maggie D. Johnson; Levi S. Lewis; Stuart A. Sandin; Jennifer E. Smith (Coral Reefs, 2019)

Putative virulence factors of Plesiomonas shigelloides - Melissa S. Edwards; Richard William McLaughlin; Jia Li; XiaoLing Wan; Yingli Liu; HaiXia Xie; YuJiang Hao; JinSong Zheng (Antonie van Leeuwenhoek, 2019)

Mapping Tasmania's cultural landscapes: Using habitat suitability modelling of archaeological sites as a landscape history tool - Penelope J. Jones; Grant J. Williamson; David M. J. S. Bowman; Edward C. Lefroy (Journal of Biogeography, 2019)
Aim Understanding past distributions of people across the landscape is key to understanding how people used, affected and related to the natural environment. Here, we use habitat suitability modelling to represent the landscape distribution of Tasmanian Aboriginal archaeological sites and assess the implications for patterns of past human activity. Location Tasmania, Australia. Methods We developed a RandomForest ‘habitat suitability' model of site records in the Tasmanian Aboriginal Heritage Register. We applied a best‐effort bias correction, considered 31 predictor variables relating to climate, topography and resource proximity, and used a variable selection procedure to optimize the final model. Model uncertainty was assessed via bootstrapping and we ran an analogous MaxEnt model as a cross‐validation exercise. Results The results from the RandomForest and MaxEnt models are highly congruent. The strongest environmental predictors of site occurrence include distance to coast, elevation, soil clay content, topographic roughness and distance to inland water. The highest habitat suitability scores are distributed across a wide range of environments in central, northern and eastern Tasmania, including coastal areas, inland water body margins and forests and savannas in the drier parts of Tasmania. With the exception of coastal areas much of western Tasmania has low habitat suitability scores, consistent with theories of low‐density Holocene Tasmanian Aboriginal settlement in this region. Main conclusions Our modelling suggests Tasmanian Aboriginal people occupied a heterogeneity of habitats but targeted coastal areas around the whole island, and drier, less steep and/or open forest and savanna environments in the central lowlands . The western interior was identified as being rarely used by Aboriginal people in the Holocene, with the exception of isolated pockets of habitat; yet whether this is a true reflection of Aboriginal‐resourceuse demands increased archaeological surveys, particularly in the Tasmanian Wilderness World Heritage Area.

An approach to forecast grain crop yield using multi-layered, multi-farm data sets and machine learning - Patrick Filippi; Edward J. Jones; Niranjan S. Wimalathunge; Pallegedara D. S. N. Somarathna; Liana E. Pozza; Sabastine U. Ugbaje; Thomas G. Jephcott; Stacey E. Paterson; Brett M. Whelan; Thomas F. A. Bishop (Precision Agriculture, 2019)

Evidence of a high-density brown hyena population within an enclosed reserve: the role of fenced systems in conservation - S. Edwards; J. Noack; L. Heyns; D. Rodenwoldt (Mammal Research, 2019)

Integrated Risk Assessment for the Blue Economy - Emma E. Hodgson; Timothy E. Essington; Jameal F. Samhouri; Edward H. Allison; Nathan J. Bennett; Ann Bostrom; Alison C. Cullen; Stephen Kasperski; Phillip S. Levin; Melissa R. Poe (Frontiers in Marine Science, 2019)

A Computational Model of Neoadjuvant PD-1 Inhibition in Non-Small Cell Lung Cancer - Mohammad Jafarnejad; Chang Gong; Edward Gabrielson; Imke H. Bartelink; Paolo Vicini; Bing Wang; Rajesh Narwal; Lorin Roskos; Aleksander S. Popel (The AAPS Journal, 2019)

DNA of diverse adenoviruses detected in Cameroonian rodent and shrew species - Joseph Diffo; Valantine Ngum Ndze; Nkom Felix Ntumvi; Jean-Michel Takuo; Moctar M. M. Mouiche; Ubald Tamoufe; Julius Nwobegahay; Matthew LeBreton; Amethyst Gillis; Bradley S. Schneider; Joseph M. Fair; Corina Monagin; et al. (Archives of Virology, 2019)

Metabolic rhythms in flowing waters: An approach for classifying river productivity regimes - Philip Savoy; Alison P. Appling; James B. Heffernan; Edward G. Stets; Jordan S. Read; Judson W. Harvey; Emily S. Bernhardt (Limnology and Oceanography, 2019)
Although seasonal patterns of ecosystem productivity have been extensively described and analyzed with respect to their primary forcings in terrestrial and marine systems, comparatively little is known about these same processes in rivers. However, it is now possible to perform a large‐scale synthesis on the patterns and drivers of river productivity regimes because of the recent sensor advances allowing for near‐continuous estimates of river productivity. Here, we explore a dataset of 47 U.S. rivers to examine whether there are characteristic river productivity regimes. We use classification approaches to develop a typology of productivity regimes and then use these regimes to examine differences with respect to potential controls of productivity. We identified two distinct metabolic regimes, which we named Summer Peak and Spring Peak Rivers , within our dataset. These regimes meaningfully differed in both the timing and magnitude of productivity and were robust to different approaches to classification. We also found that several variables, including watershed area and characteristics of water temperature or discharge, were able to predict the class membership of these regimes with modest accuracy. Our results support the presence of characteristic metabolic regimes and suggests that these regimes may have common sets of environmental controls. We present classification as one approach to begin exploring the productivity regimes of rivers. The strength of our approach is that it fully leverages these newly available high‐frequency productivity estimates to create classes that can be used to draw inferences about how the controls of river productivity differ between or within systems.

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Observational Needs of Sea Surface Temperature - Anne G. O’Carroll; Edward M. Armstrong; Helen M. Beggs; Marouan Bouali; Kenneth S. Casey; Gary K. Corlett; Prasanjit Dash; Craig J. Donlon; Chelle L. Gentemann; Jacob L. Høyer; Alexander Ignatov; Kamila Kabobah; et al. (Frontiers in Marine Science, 2019)

Dopaminergic drug treatment remediates exaggerated cingulate prediction error responses in obsessive-compulsive disorder - Graham K. Murray; Franziska Knolle; Karen D. Ersche; Kevin J. Craig; Sanja Abbott; Shaila S. Shabbir; Naomi A. Fineberg; John Suckling; Barbara J. Sahakian; Edward T. Bullmore; Trevor W. Robbins (Psychopharmacology, 2019)

Caspase-8 restricts natural killer cell accumulation during MCMV Infection - Yanjun Feng; Lisa P. Daley-Bauer; Linda Roback; Marc Potempa; Lewis L. Lanier; Edward S. Mocarski (Medical Microbiology and Immunology, 2019)

Caspase-8-dependent control of NK- and T cell responses during cytomegalovirus infection - Yanjun Feng; Lisa P. Daley-Bauer; Edward S. Mocarski (Medical Microbiology and Immunology, 2019)

Simulations for the development of a ground motion model for induced seismicity in the Groningen gas field, The Netherlands - B. Edwards; B. Zurek; E. van Dedem; P. J. Stafford; S. Oates; J. van Elk; B. deMartin; J. J. Bommer (Bulletin of Earthquake Engineering, 2019)

Recombinant human lactoferrin induces apoptosis, disruption of F-actin structure and cell cycle arrest with selective cytotoxicity on human triple negative breast cancer cells - Blanca F. Iglesias-Figueroa; Tania S. Siqueiros-Cendón; Denisse A. Gutierrez; Renato J. Aguilera; Edward A. Espinoza-Sánchez; Sigifredo Arévalo-Gallegos; Armando Varela-Ramirez; Quintín Rascón-Cruz (Apoptosis, 2019)

Resolving the depth zonation paradox in reef‐building corals - T. Edward Roberts; Tom C. L. Bridge; M. Julian Caley; Joshua S. Madin; Andrew H. Baird (Ecology, 2019)
Changes in abundance across a natural environmental gradient provide important insights into a species’ realized ecological niche. In reef‐building corals, a species’ niche is often defined using its depth range. However, most reef‐building coral species occur over a broad depth range, a fact that is incompatible with the strong zonation found in coral assemblages across depth. We resolve this paradox by modeling the abundance distributions of 110 coral species across a 45 m depth gradient to show that most are in fact depth specialists and reveal that depth range alone is incapable of capturing a species’ depth use. We then highlight the significance of our results by demonstrating how depth range greatly overestimates the potential number of species with a refuge at depth from global warming. Our findings illustrate both the limitations of the simple metric of depth range and the ecological insights that can be gained by moving beyond it.

Lessons from seabird conservation in Alaskan longline fisheries - Edward F. Melvin; Kimberly S. Dietrich; Robert M. Suryan; Shannon M. Fitzgerald (Conservation Biology, 2019)
Although bycatch of seabirds and other long‐lived species is a critical conservation issue in world fisheries, case studies documenting significant reductions in the mortality of these low‐productivity species in a fishery are rare. We studied progress toward seabird conservation in the Alaskan longline fisheries, one of the largest and most diverse demersal fisheries. We generated annual seabird bycatch rates in 4 target fisheries and all fisheries combined from 23 years of fisheries observer data. We used 0‐inflated negative binomial models to evaluate variables influencing seabird bycatch per unit effort (BPUE) in 2 target fisheries. Following adoption of streamer lines, at first voluntarily and then mandatorily, seabird BPUE was reduced by 77–90%, preventing mortality of thousands of birds per year. Despite this, BPUE increased significantly in 2 of 4 target fisheries since streamer lines were adopted. Although night setting yielded significant reductions (74–97%) in seabird BPUE and significant increases (7–11%) in fish catch per unit effort over daytime setting, nighttime setting increased the BPUE of Northern Fulmar ( Fulmarus glacialis ) by 40% and nontarget fish species by 5–17%. Thus, best practices to prevent seabird mortalities in longline fisheries varied by species assemblage and fishery. Our results inform global efforts toward fisheries bycatch reduction by illustrating that successful conservation requires fishery‐specific solutions, strong industry support, constant vigilance in analysis and reporting observer data, and ongoing outreach to fleets, especially to vessels with anomalously high BPUE.

Combining supervised run interval training or moderate-intensity continuous training with the diabetes prevention program on clinical outcomes - Nicole M. Gilbertson; Joan A. Mandelson; Kathryn Hilovsky; Jeremy D. Akers; Trent A. Hargens; David L. Wenos; Elizabeth S. Edwards (European Journal of Applied Physiology, 2019)

Seagrass restoration in Gulf of Mannar, Tamil Nadu, Southeast India: a viable management tool - J. K. Patterson Edward; K. Diraviya Raj; G. Mathews; P. Dinesh Kumar; A. Arasamuthu; Nisha D’ Souza; Deepak S. Bilgi (Environmental Monitoring and Assessment, 2019)

Neurotoxicity of Micrurus lemniscatus lemniscatus (South American coralsnake) venom in vertebrate neuromuscular preparations in vitro and neutralization by antivenom - Rafael S. Floriano; Raphael Schezaro-Ramos; Nelson J. Silva; Fábio Bucaretchi; Edward G. Rowan; Stephen Hyslop (Archives of Toxicology, 2019)

Comparing the impacts of four ENSO events on giant kelp (Macrocystis pyrifera) in the northeast Pacific Ocean - Matthew S. Edwards (Algae, 2019)

Ten tips for developing interdisciplinary socio-ecological researchers - Rachel Kelly; Mary Mackay; Kirsty L. Nash; Christopher Cvitanovic; Edward H. Allison; Derek Armitage; Aletta Bonn; Steven J. Cooke; Stewart Frusher; Elizabeth A. Fulton; Benjamin S. Halpern; Priscila F. M. Lopes; et al. (Socio-Ecological Practice Research, 2019)

Seasonal variations in household food insecurity and dietary diversity and their association with maternal and child nutritional status in rural Ethiopia - Kedir T. Roba; Thomas P. O’Connor; Nora M. O’Brien; Chanyalew S. Aweke; Zenebe A. Kahsay; Nick Chisholm; Edward Lahiff (Food Security, 2019)

Development and validation of an exome-based SNP marker set for identification of the St, Jr and Jvs genomes of Thinopyrym intermedium in a wheat background - Andras Cseh; Caiyun Yang; Stella Hubbart-Edwards; Duncan Scholefield; Stephen S. Ashling; Amanda J. Burridge; Paul A. Wilkinson; Ian P. King; Julie King; Surbhi Grewal (Theoretical and Applied Genetics, 2019)

Differential influence of habitual third-person vision of a body part on mental rotation of images of hands and feet - Louisa M. Edwards; Ryan S. Causby; Halton Stewart; Tasha R. Stanton (Experimental Brain Research, 2019)

Observations and Numerical Simulation of the Effects of the 21 August 2017 North American Total Solar Eclipse on Surface Conditions and Atmospheric Boundary-Layer Evolution - Michael S. Buban; Temple R. Lee; Edward J. Dumas; C. Bruce Baker; Mark Heuer (Boundary-Layer Meteorology, 2019)

Modeling potential impacts of three benthic invasive species on the Lake Erie food web - Hongyan Zhang; Edward S. Rutherford; Doran M. Mason; Marion E. Wittmann; David M. Lodge; Xinhua Zhu; Timothy B. Johnson; Andrew Tucker (Biological Invasions, 2019)

Late Quaternary sea‐level change and evolution of Belfast Lough, Northern Ireland: new offshore evidence and implications for sea‐level reconstruction - Ruth M. K. Plets; S. Louise Callard; J. Andrew G. Cooper; Joseph T. Kelley; Daniel F. Belknap; Robin J. Edwards; Antony J. Long; Rory J. Quinn; Derek W. T. Jackson (Journal of Quaternary Science, 2019)
The interplay of eustatic and isostatic factors causes complex relative sea‐level (RSL) histories, particularly in paraglacial settings. In this context the past record of RSL is important in understanding ice‐sheet history, earth rheology and resulting glacio‐isostatic adjustment. Field data to develop sea‐level reconstructions are often limited to shallow depths and uncertainty exists as to the veracity of modelled sea‐level curves. We use seismic stratigraphy, 39 vibrocores and 26 radiocarbon dates to investigate the deglacial history of Belfast Lough, Northern Ireland, and reconstruct past RSL. A typical sequence of till, glacimarine and Holocene sediments is preserved. Two sea‐level lowstands (both max. −40 m) are recorded at c. 13.5 and 11.5k cal a bp . Each is followed by a rapid transgression and subsequent periods of RSL stability. The first transgression coincides temporally with a late stage of Meltwater Pulse 1a and the RSL stability occurred between c. 13.0 and c. 12.2k cal a bp (Younger Dryas). The second still/slowstand occurred between c. 10.3 and c. 11.5k cal a bp . Our data provide constraints on the direction and timing of RSL change during deglaciation. Application of the Depth of Closure concept adds an error term to sea‐level reconstructions based on seismic stratigraphic reconstructions.

Securing a Just Space for Small-Scale Fisheries in the Blue Economy - Philippa J. Cohen; Edward H. Allison; Neil L. Andrew; Joshua Cinner; Louisa S. Evans; Michael Fabinyi; Len R. Garces; Stephen J. Hall; Christina C. Hicks; Terry P. Hughes; Svein Jentoft; David J. Mills; et al. (Frontiers in Marine Science, 2019)

Advancing Research for the Management of Long-Lived Species: A Case Study on the Greenland Shark - Jena E. Edwards; Elizabeth Hiltz; Franziska Broell; Peter G. Bushnell; Steven E. Campana; Jørgen S. Christiansen; Brynn M. Devine; Jeffrey J. Gallant; Kevin J. Hedges; M. Aaron MacNeil; Bailey C. McMeans; Julius Nielsen; et al. (Frontiers in Marine Science, 2019)

Quantitation of Purines from Pigeon Guano and Implications for Cryptococcus neoformans Survival During Infection - Jessica L. Chitty; David J. Edwards; Avril A. B. Robertson; Mark S. Butler; John A. Duley; Matthew A. Cooper; James A. Fraser (Mycopathologia, 2019)

Future Directions in Conservation Research on Petrels and Shearwaters - Airam Rodríguez; José M. Arcos; Vincent Bretagnolle; Maria P. Dias; Nick D. Holmes; Maite Louzao; Jennifer Provencher; André F. Raine; Francisco Ramírez; Beneharo Rodríguez; Robert A. Ronconi; Rebecca S. Taylor; et al. (Frontiers in Marine Science, 2019)

Breaking the curse of dimensionality to identify causal variants in Breeding 4 - Guillaume P. Ramstein; Sarah E. Jensen; Edward S. Buckler (Theoretical and Applied Genetics, 2019)

Mitochondrial health and muscle plasticity after spinal cord injury - Ashraf S. Gorgey; Oksana Witt; Laura O’Brien; Christopher Cardozo; Qun Chen; Edward J. Lesnefsky; Zachary A. Graham (European Journal of Applied Physiology, 2019)

Identification of a metallothionein gene in honey bee Apis mellifera and its expression profile in response to Cd, Cu and Pb exposure - Jelena Purać; Tatjana V. Nikolić; Danijela Kojić; Anđelka S. Ćelić; Jovana J. Plavša; Duško P. Blagojević; Edward T. Petri (Molecular Ecology, 2019)
Metallothioneins are ubiquitous proteins important in metal homeostasis and detoxification. However, they have not previously been identified in honey bees or other Hymenoptera, where metallothioneins could be of ecophysiological and ecotoxicological significance. Better understanding of the molecular responses to stress induced by toxic metals could contribute to honey bee conservation. In addition, honey bee metallothionein could represent a biomarker for monitoring environmental quality. Here we identify and characterize a metallothionein gene in Apis mellifera ( AmMT ). AmMT is 1,680 bp long and encodes a 48 amino acids protein with 15 cysteines and no aromatic residues. A metal response element upstream of the start codon, coupled with numerous cis ‐regulatory elements indicate the functional context of AmMT. Molecular modelling predicts several transition metal binding sites, and comparative phylogenetic analysis revealed five putative metallothionein proteins in three other hymenoptera species. AmMT was characterized by cloning the full‐length coding sequence of the putative metallothionein. Recombinant AmMT was found to increase metal tolerance upon overexpression in Escherichia coli supplemented with Cd, Cu or Pb. Finally, in laboratory tests on honey bees, gene expression profiles showed a dose‐dependant relationship between Cd, Cu and Pb concentrations present in food and AmMT expression, while field experiments showed induction of AmMT in bees from an industrial site compared to those from an urban area. These studies suggest that AmMT has metal binding properties in agreement with a possible role in metal homeostasis. Further functional and structural characterization of metallothionein in honey bees and other Hymenoptera are necessary.

Corrigendum: Subregional variability in the response of New England vegetation to postglacial climate change - W. Wyatt Oswald; David R. Foster; Bryan N. Shuman; Elaine D. Doughty; Edward K. Faison; Brian R. Hall; Barbara C. S. Hansen; Matts Lindbladh; Adriana Marroquin; Sarah A. Truebe (Journal of Biogeography, 2019)

Spatial Subsidies and Mortality of an Estuarine Copepod Revealed Using a Box Model - Wim J. Kimmerer; Edward S. Gross; Anne M. Slaughter; John R. Durand (Estuaries and Coasts, 2019)

Australian cultures of Botryosphaeriaceae held in Queensland and Victoria plant pathology herbaria revisited - Yu Pei Tan; Roger G. Shivas; Thomas S. Marney; Jacqueline Edwards; John Dearnaley; Fahimeh Jami; Treena I. Burgess (Australasian Plant Pathology, 2019)

A Computational Cardiac Model for the Adaptation to Pulmonary Arterial Hypertension in the Rat - Reza Avazmohammadi; Emilio A. Mendiola; João S. Soares; David S. Li; Zhiqiang Chen; Samer Merchant; Edward W. Hsu; Peter Vanderslice; Richard A. F. Dixon; Michael S. Sacks (Annals of Biomedical Engineering, 2019)

Pharmacologic Treatment of Opioid Use Disorder: a Review of Pharmacotherapy, Adjuncts, and Toxicity - Michael S. Toce; Peter R. Chai; Michele M. Burns; Edward W. Boyer (Journal of Medical Toxicology, 2018)

Genome variations between rhizosphere and bulk soil ecotypes of a Pseudomonas koreensis population - Lucas Dantas Lopes; Michele de C. Pereira e Silva; Alexandra J. Weisberg; Edward W. Davis; Qing Yan; Camila de S. Varize; Chih‐Feng Wu; Jeff H. Chang; Joyce E. Loper; Fernando D. Andreote (Environmental Microbiology, 2018)
Summary Bulk soil and rhizosphere are soil compartments selecting different microbial communities. However, it is unknown whether this selection also can change the genome content of specific bacterial taxa, splitting a population in distinct ecotypes. To answer this question we compared the genome sequences of 53 isolates obtained from sugarcane rhizosphere (28) and bulk soil (25). These isolates were previously classified in the Pseudomonas koreensis subgroup of the P. fluorescens complex. Phylogenomics showed a trend of separation between bulk soil and rhizosphere isolates. Discriminant analysis of principal components (DAPC) identified differences in the accessory genome of rhizosphere and bulk soil sub‐populations. We found significant changes in gene frequencies distinguishing rhizosphere from bulk soil ecotypes, for example, enrichment of phosphatases and xylose utilization ( xut ) genes, respectively. Phenotypic assays and deletion of xutA gene indicated that accumulation of xut genes in the bulk soil sub‐population provided a higher growth capacity in a d ‐xylose medium, supporting the corresponding genomic differences. Despite the clear differences distinguishing the two ecotypes, all 53 isolates were classified in a single 16S rRNA gene OTU. Collectively, our results revealed that the gene pool and ecological behavior of a bacterial population can be different for ecotypes living in neighbouring soil habitats.

Bending the rules: exploitation of allochthonous resources by a top‐predator modifies size‐abundance scaling in stream food webs - Daniel M. Perkins; Isabelle Durance; Francois K. Edwards; Jonathan Grey; Alan G. Hildrew; Michelle Jackson; J. Iwan Jones; Rasmus B. Lauridsen; Katrin Layer‐Dobra; Murray S. A. Thompson; Guy Woodward (Ecology Letters, 2018)
Body mass–abundance ( M‐N ) allometries provide a key measure of community structure, and deviations from scaling predictions could reveal how cross‐ecosystem subsidies alter food webs. For 31 streams across the UK, we tested the hypothesis that linear log‐log M‐N scaling is shallower than that predicted by allometric scaling theory when top predators have access to allochthonous prey. These streams all contained a common and widespread top predator (brown trout) that regularly feeds on terrestrial prey and, as hypothesised, deviations from predicted scaling increased with its dominance of the fish assemblage. Our study identifies a key beneficiary of cross‐ecosystem subsidies at the top of stream food webs and elucidates how these inputs can reshape the size‐structure of these ‘open’ systems.

In memory of Thomas Turpin Bannister (1930–2018) - Edward Laws; Alan Weidemann; George Hoch; Horatio Bannister; Robert S. Knox; Govindjee (Photosynthesis Research, 2018)

Benign gynecologic conditions are associated with ovarian cancer risk in African-American women: a case–control study - Hyo K. Park; Joellen M. Schildkraut; Anthony J. Alberg; Elisa V. Bandera; Jill S. Barnholtz-Sloan; Melissa Bondy; Sydnee Crankshaw; Ellen Funkhouser; Patricia G. Moorman; Edward S. Peters; Paul Terry; Frances Wang; et al. (Cancer Causes & Control, 2018)

Ameliorating the adverse cardiorespiratory effects of chemical immobilization by inducing general anaesthesia in sheep and goats: implications for physiological studies of large wild mammals - Adian Izwan; Edward P. Snelling; Roger S. Seymour; Leith C. R. Meyer; Andrea Fuller; Anna Haw; Duncan Mitchell; Anthony P. Farrell; Mary-Ann Costello; Shane K. Maloney (Journal of Comparative Physiology B, 2018)

High‐turbidity events in Western Lake Erie during ice‐free cycles: Contributions of river‐loaded vs. resuspended sediments - Qianru Niu; Meng Xia; Stuart A. Ludsin; Philip Y. Chu; Doran M. Mason; Edward S. Rutherford (Limnology and Oceanography, 2018)
High‐turbidity events (HTEs) are common phenomena in shallow‐water environments that can alter ecological interactions. The relative contributions of river input (external loading) vs. resuspension (internal loading) to the occurrence, duration, and influenced areas of HTEs are not fully understood in most systems, owing to the lack of long‐term, source‐specified sediment maps. Using a Finite Volume Community Ocean Model‐based wave‐current forced sediment model, we investigated sediment dynamics in the shallow, river‐dominated Western Lake Erie during ice‐free cycles (April–November) of 2002–2012. Results indicated that wind waves predominated sediment dynamics in the offshore areas, with river discharges causing substantial inshore to offshore gradients. Owing to varying wind waves and river discharges, both the mean and extreme sediment dynamics had distinctive seasonal variations. The basin was turbid during spring and fall, with frequent (> 15%), broad (O [10 2 –10 3 km 2 ]), and more persistent (means of 3.2/4.4 d during spring/fall) HTEs caused mainly by resuspension events. During summer, the basin was clearer with occasional ( 2 km 2 ]), and short (mean of 1.5 d) HTEs near the mouths generated by pulsing river loadings. Although river loading rarely induced basin‐wide HTEs, they were important during floods, enlarging the high‐turbidity areas by 11.3%. Overall, by delineating the drivers of HTEs in Western Lake Erie, this study furthered the understanding of sediment dynamics in shallow ecosystems and provides a basis for investigating the ecological impact of sediments from different sources in river‐ and wave‐energetic systems.

Mapping of novel salt tolerance QTL in an Excalibur × Kukri doubled haploid wheat population - Muhammad A. Asif; Rhiannon K. Schilling; Joanne Tilbrook; Chris Brien; Kate Dowling; Huwaida Rabie; Laura Short; Christine Trittermann; Alexandre Garcia; Edward G. Barrett-Lennard; Bettina Berger; Diane E. Mather; et al. (Theoretical and Applied Genetics, 2018)
Key message Novel QTL for salinity tolerance traits have been detected using non-destructive and destructive phenotyping in bread wheat and were shown to be linked to improvements in yield in saline fields. Abstract Soil salinity is a major limitation to cereal production. Breeding new salt-tolerant cultivars has the potential to improve cereal crop yields. In this study, a doubled haploid bread wheat mapping population, derived from the bi-parental cross of Excalibur × Kukri, was grown in a glasshouse under control and salinity treatments and evaluated using high-throughput non-destructive imaging technology. Quantitative trait locus (QTL) analysis of this population detected multiple QTL under salt and control treatments. Of these, six QTL were detected in the salt treatment including one for maintenance of shoot growth under salinity ( QG (1 – 5) .asl - 7A ), one for leaf Na + exclusion ( QNa.asl - 7A ) and four for leaf K + accumulation ( QK.asl - 2B.1 , QK.asl - 2B.2 , QK.asl - 5A and QK:Na.asl - 6A ). The beneficial allele for QG (1 – 5) .asl - 7A (the maintenance of shoot growth under salinity) was present in six out of 44 mainly Australian bread and durum wheat cultivars. The effect of each QTL allele on grain yield was tested in a range of salinity concentrations at three field sites across 2 years. In six out of nine field trials with different levels of salinity stress, lines with alleles for Na + exclusion and/or K + maintenance at three QTL ( QNa.asl - 7A , QK.asl - 2B.2 and QK:Na.asl - 6A ) excluded more Na + or accumulated more K + compared to lines without these alleles. Importantly, the QK.asl - 2B.2 allele for higher K + accumulation was found to be associated with higher grain yield at all field sites. Several alleles at other QTL were associated with higher grain yields at selected field sites.

Community vulnerability and resilience in disaster risk reduction: an example from Phojal Nalla, Himachal Pradesh, India - Richard Michael Johnson; Esther Edwards; James S. Gardner; Alan P. Diduck (Regional Environmental Change, 2018)

Muscle health and performance in monozygotic twins with 30 years of discordant exercise habits - Katherine E. Bathgate; James R. Bagley; Edward Jo; Robert J. Talmadge; Irene S. Tobias; Lee E. Brown; Jared W. Coburn; Jose A. Arevalo; Nancy L. Segal; Andrew J. Galpin (European Journal of Applied Physiology, 2018)

Functional characterization of ligninolytic Klebsiella spp. strains associated with soil and freshwater - Amanda O. dos S. Melo-Nascimento; Claudia Treumann; Camila Neves; Edmilson Andrade; Ana Camila Andrade; Robert Edwards; Elizabeth Dinsdale; Thiago Bruce (Archives of Microbiology, 2018)

High‐resolution reconstruction of 8.2‐ka BP event documented in Père Noël cave, southern Belgium - M. Allan; N. Fagel; H. J. L. van der Lubbe; H. B. Vonhof; H. Cheng; R. Lawrence Edwards; S. Verheyden (Journal of Quaternary Science, 2018)
A distinct shift in δ 18 O, δ 13 C and trace element contents of the Père Noël (PN) stalagmite from southern Belgium revealed an abrupt climatic anomaly at 8.13 ± 0.03 ka BP (before present = before 1950 AD). This anomaly is characterized by a maximum drop in the δ 18 O (−1.4‰ compared the mean) between 8.13 and 8.10 ka BP (±0.03). This drop of δ 18 O coincides with a decrease in δ 13 C and trace element (Sr, Ba and Mg) concentrations suggesting drier conditions. Our precise chronology provides the timing of the outburst of proglacial lakes Agassiz and Ojibway that caused the δ 18 O, δ 13 C and trace elemental anomalies at 8.13–8.10 ± 0.03 ka BP, which corresponds to the 8.2‐ka BP event. The PN stalagmite bears δ 18 O values in fluid inclusions that covary with the δ 18 O values in calcite, suggesting that the speleothem calcite δ 18 O primarily reflects variations in the rainfall δ 18 O. Comparison of the PN record with different marine and terrestrial archives during the 8.2‐ka BP event shows a good agreement in timing and duration, suggesting that the PN speleothem can be regarded as a valuable proxy to better understand the 8.2‐ka BP event.

Subregional variability in the response of New England vegetation to postglacial climate change - W. Wyatt Oswald; David R. Foster; Bryan N. Shuman; Elaine D. Doughty; Edward K. Faison; Brian R. Hall; Barbara C. S. Hansen; Matts Lindbladh; Adriana Marroquin; Sarah A. Truebe (Journal of Biogeography, 2018)
Aim We analysed a dataset composed of multiple palaeoclimate and lake‐sediment pollen records from New England to explore how postglacial changes in the composition and spatial patterns of vegetation were controlled by regional‐scale climate change, a subregional environmental gradient, and landscape‐scale variations in soil characteristics. Location The 120,000‐km 2 study area includes parts of Vermont and New Hampshire in the north, where sites are 150–200 km from the Atlantic Ocean, and spans the coastline from southeastern New York to Cape Cod and the adjacent islands, including Block Island, the Elizabeth Islands, Nantucket, and Martha's Vineyard. Methods We analysed pollen records from 29 study sites, using multivariate cluster analysis to visualize changes in the composition and spatial patterns of vegetation during the last 14,000 years. The pollen data were compared with temperature and precipitation reconstructions. Results Boreal forest featuring Picea and Pinus banksiana was present across the region when conditions were cool and dry 14,000–12,000 calibrated 14 C years before present (ybp). Pinus strobus became regionally dominant as temperatures increased between 12,000 and 10,000 ybp. The composition of forests in inland and coastal areas diverged in response to further warming after 10,000 ybp, when Quercus and Pinus rigida expanded across southern New England, whereas conditions remained cool enough in inland areas to maintain Pinus strobus . Increasing precipitation allowed Tsuga canadensis , Fagus grandifolia , and Betula to replace Pinus strobus in inland areas during 9,000–8,000 ybp, and also led to the expansion of Carya across the coastal part of the region beginning at 7,000–6,000 ybp. Abrupt cooling at 5,500–5,000 ybp caused sharp declines in Tsuga in inland areas and Quercus at some coastal sites, and the populations of those taxa remained low until they recovered around 3,000 ybp in response to rising precipitation. Throughout most of the Holocene, sites underlain by sandy glacial deposits were occupied by Pinus rigida and Quercus . Main conclusions Postglacial changes in the composition and spatial pattern of New England forests were controlled by long‐term trends and abrupt shifts in temperature and precipitation, as well as by the environmental gradient between coastal and inland parts of the region. Substrate and soil moisture shaped landscape‐scale variations in forest composition.

A lateral-to-mesial organization of human ventral visual cortex at birth - P. Barttfeld; S. Abboud; H. Lagercrantz; U. Adén; N. Padilla; A. D. Edwards; L. Cohen; M. Sigman; S. Dehaene; G. Dehaene-Lambertz (Brain Structure and Function, 2018)

Anti-inflammatory Effects of Polyphenol Extracts from Ulva linza (Ulvophyceae, Chlorophyta) - Ju-Hyoung Kim; Shin Ae Kim; Matthew S. Edwards; In-Ah Lee (Toxicology and Environmental Health Sciences, 2018)

Thyroid hormone manipulation influences development of cardiovascular regulation in embryonic Pekin duck, Anas platyrhynchos domestica - Tushar S. Sirsat; Dane A. Crossley; Janna L. Crossley; Edward M. Dzialowski (Journal of Comparative Physiology B, 2018)

Motile Dendritic Cells Sense and Respond to Substrate Geometry - Amy C. Bendell; Nicholas Anderson; Daniel Blumenthal; Edward K. Williamson; Christopher S. Chen; Janis K. Burkhardt; Daniel A. Hammer (Annals of Biomedical Engineering, 2018)

Temporal variation in abundance of leaf litter beetles and ants in an Australian lowland tropical rainforest is driven by climate and litter fall - Peter S. Grimbacher; Will Edwards; Michael J. Liddell; Paul N. Nelson; Cassandra Nichols; Carl W. Wardhaugh; Nigel E. Stork (Biodiversity and Conservation, 2018)

The Servilia tomb: an architecturally and pictorially important Roman building - S. E. Jorge-Villar; I. Rodríguez Temiño; H. G. M. Edwards; A. Jiménez Hernández; J. I. Ruiz Cecilia; I. Miralles (Archaeological and Anthropological Sciences, 2018)

The DRD2 Taq1A A1 Allele May Magnify the Risk of Alzheimer’s in Aging African-Americans - Kenneth Blum; Rajendra D. Badgaiyan; Georgia M. Dunston; David Baron; Edward J. Modestino; Thomas McLaughlin; Bruce Steinberg; Mark S. Gold; Marjorie C. Gondré-Lewis (Molecular Neurobiology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Uranium as a possible criterion for the hydro-chemical alteration of betafite - Mohammad Hosseinpour Khanmiri; Svetlana Yu. Yanson; Edward V. Fomin; Anatoly V. Titov; Andrey V. Grebeniuk; Yury S. Polekhovsky; Roman V. Bogdanov (Physics and Chemistry of Minerals, 2018)

Interactions among plants, bacteria, and fungi reduce extracellular enzyme activities under long‐term N fertilization - Joseph E. Carrara; Christopher A. Walter; Jennifer S. Hawkins; William T. Peterjohn; Colin Averill; Edward R. Brzostek (Global Change Biology, 2018)
Atmospheric nitrogen (N) deposition has enhanced soil carbon (C) stocks in temperate forests. Most research has posited that these soil C gains are driven primarily by shifts in fungal community composition with elevated N leading to declines in lignin degrading Basidiomycetes . Recent research, however, suggests that plants and soil microbes are dynamically intertwined, whereby plants send C subsidies to rhizosphere microbes to enhance enzyme production and the mobilization of N. Thus, under elevated N, trees may reduce belowground C allocation leading to cascading impacts on the ability of microbes to degrade soil organic matter through a shift in microbial species and/or a change in plant–microbe interactions. The objective of this study was to determine the extent to which couplings among plant, fungal, and bacterial responses to N fertilization alter the activity of enzymes that are the primary agents of soil decomposition. We measured fungal and bacterial community composition, root–microbial interactions, and extracellular enzyme activity in the rhizosphere, bulk, and organic horizon of soils sampled from a long‐term (>25 years), whole‐watershed, N fertilization experiment at the Fernow Experimental Forest in West Virginia, USA. We observed significant declines in plant C investment to fine root biomass (24.7%), root morphology, and arbuscular mycorrhizal (AM) colonization (55.9%). Moreover, we found that declines in extracellular enzyme activity were significantly correlated with a shift in bacterial community composition, but not fungal community composition. This bacterial community shift was also correlated with reduced AM fungal colonization indicating that declines in plant investment belowground drive the response of bacterial community structure and function to N fertilization. Collectively, we find that enzyme activity responses to N fertilization are not solely driven by fungi, but instead reflect a whole ecosystem response, whereby declines in the strength of belowground C investment to gain N cascade through the soil environment.

Air–Sea/Land Interaction in the Coastal Zone - Andrey A. Grachev; Laura S. Leo; Harindra J. S. Fernando; Christopher W. Fairall; Edward Creegan; Byron W. Blomquist; Adam J. Christman; Christopher M. Hocut (Boundary-Layer Meteorology, 2018)

Unrecognized species diversity and new insights into colour pattern polymorphism within the widespread Malagasy snake Mimophis (Serpentes: Lamprophiidae) - Sara Ruane; Edward A. Myers; Kahmun Lo; Sara Yuen; Rachel S. Welt; Maya Juman; India Futterman; Ronald A. Nussbaum; Gregory Schneider; Frank T. Burbrink; Christopher J. Raxworthy (Systematics and Biodiversity, 2018)

Susceptibility of cereal species to Fusarium langsethiae under identical field conditions - N. Opoku; M. A. Back; S. G. Edwards (European Journal of Plant Pathology, 2018)

Environmental Stewardship: A Conceptual Review and Analytical Framework - Nathan J. Bennett; Tara S. Whitty; Elena Finkbeiner; Jeremy Pittman; Hannah Bassett; Stefan Gelcich; Edward H. Allison (Environmental Management, 2018)

A three-dimensional numerical study of river plume mixing processes in Otsuchi Bay, Japan - Kaushik Sasmal; Eiji Masunaga; Adrean Webb; Oliver B. Fringer; Edward S. Gross; Matthew D. Rayson; Hidekatsu Yamazaki (Journal of Oceanography, 2018)

Regional forcing explains local species diversity and turnover on tropical islands - Thomas Ibanez; Gunnar Keppel; Cláudia Baider; Chris Birkinshaw; Heike Culmsee; Susan Cordell; F. B. Vincent Florens; Janet Franklin; Christian P. Giardina; Thomas W. Gillespie; Melinda Laidlaw; Creighton M. Litton; et al. (Global Ecology and Biogeography, 2018)
Aim To determine the role of regional forcing on plot‐level species diversity and composition, and to quantify the relative importance of biogeographical and climatic factors in explaining woody plant diversity and composition at the local‐, island‐ and archipelago‐scale. Location Forty‐one tropical islands of the Indo‐Pacific region from Madagascar to Hawai‘i Island. Methods We analysed the diversity and composition of tropical woody plant communities located across 113 plots, 41 islands and 19 archipelagos. We used generalized linear mixed‐effects models and generalized dissimilarity models to determine the role of regional forcing at the island and archipelago scale and to assess the relative importance of biogeographical (area and isolation of islands or archipelagos, geographical distance between plots) and climatic factors in explaining differences in local diversity and composition (species turnover). Analyses were conducted at different geographical scales (local, island and archipelago) and taxonomic levels (species, genus and family). Results Variation in local (plot‐level) diversity (as species density, the number of species per 100 woody plants) was primarily explained by island and archipelago identity. Maximum species density was positively correlated with the area of an island (or archipelago) and negatively correlated with the isolation of an archipelago. Local climatic variability was also a significant predictor of species density, but less important than regional forcing. Climate variables explained Main conclusions Regional forcing was the key driver of local diversity and composition on islands. Island area and archipelago isolation are likely driving local diversity through their effects on the pool of island species. Geographical distance between plots is the main factor explaining species turnover, while at higher taxonomic levels, climatic factors and niche conservatism are the main drivers.

Extra-pair parentage and personality in a cooperatively breeding bird - Hannah A Edwards; Hannah L Dugdale; David S Richardson; Jan Komdeur; Terry Burke (Behavioral Ecology and Sociobiology, 2018)

Occupational exposure to perfluoroalkyl substances and serum levels of perfluorooctanesulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) in an aging population from upstate New York: a retrospective cohort study - Eva M. Tanner; Michael S. Bloom; Qian Wu; Kurunthachalam Kannan; Recai M. Yucel; Srishti Shrestha; Edward F. Fitzgerald (International Archives of Occupational and Environmental Health, 2018)

Army imposters: diversification of army ant-mimicking beetles with their Eciton hosts - S. Pérez-Espona; W. P. Goodall-Copestake; S. M. Berghoff; K. J. Edwards; N. R. Franks (Insectes Sociaux, 2018)

Profiling differential microRNA expression between in situ, infiltrative and lympho-vascular space invasive breast cancer: a pilot study - Patsy S. Soon; Pamela J. Provan; Edward Kim; Nirmala Pathmanathan; Dinny Graham; Christine L. Clarke; Rosemary L. Balleine (Clinical & Experimental Metastasis, 2018)

Identification of an anellovirus and genomoviruses in ixodid ticks - Kara Waits; Marten J. Edwards; Ilaria N. Cobb; Rafaela S. Fontenele; Arvind Varsani (Virus Genes, 2018)

How palynology could have been paepalology: the naming of a discipline - Kevin J. Edwards; Heather S. Pardoe (Palynology, 2018)

Recreational physical activity and survival in African-American women with ovarian cancer - Sarah E. Abbott; Fabian Camacho; Lauren C. Peres; Anthony J. Alberg; Elisa V. Bandera; Melissa Bondy; Michele L. Cote; Ellen Funkhouser; Patricia G. Moorman; Edward S. Peters; Bo Qin; Ann G. Schwartz; et al. (Cancer Causes & Control, 2018)

Relationship between SST gradients and upwelling off Peru and Chile: model/satellite data analysis - Jorge Vazquez-Cuervo; Hector S. Torres; Dimitris Menemenlis; Toshio Chin; Edward M. Armstrong (International Journal of Remote Sensing, 2017)

A Biocompatible Synthetic Lung Fluid Based on Human Respiratory Tract Lining Fluid Composition - Abhinav Kumar; Wachirun Terakosolphan; Mireille Hassoun; Kalliopi-Kelli Vandera; Astrid Novicky; Richard Harvey; Paul G. Royall; Elif Melis Bicer; Jonny Eriksson; Katarina Edwards; Dirk Valkenborg; Inge Nelissen; et al. (Pharmaceutical Research, 2017)

Speciation and potential long-term behaviour of chromium in urban sediment particulates - Patrick Byrne; Kevin G. Taylor; Karen A. Hudson-Edwards; Judith E. S. Barrett (Journal of Soils and Sediments, 2017)

Erratum to: A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)

Skeletal muscle mitochondrial mass is linked to lipid and metabolic profile in individuals with spinal cord injury - Laura C. O’Brien; Qun Chen; Jeannie Savas; Edward J. Lesnefsky; Ashraf S. Gorgey (European Journal of Applied Physiology, 2017)

Wastewater influences nitrogen dynamics in a coastal catchment during a prolonged drought - Denise A. Bruesewitz; Timothy J. Hoellein; Rae F. Mooney; Wayne S. Gardner; Edward J. Buskey (Limnology and Oceanography, 2017)
Ecosystem function measurements can enhance our understanding of nitrogen (N) delivery in coastal catchments across river and estuary ecosystems. Here, we contrast patterns of N cycling and export in two rivers, one heavily influenced by wastewater treatment plants (WWTP), in a coastal catchment of south Texas. We measured N export from both rivers to the estuary over 2 yr that encompass a severe drought, along with detailed mechanisms of N cycling in river, tidal river, and two estuary sites during prolonged drought. WWTP nutrient inputs stimulated uptake of N, but denitrification resulting in permanent N removal accounted for only a small proportion of total uptake. During drought periods, WWTP N was the primary source of exported N to the estuary, minimizing the influence of episodic storm‐derived nutrients from the WWTP‐influenced river to the estuary. In the site without WWTP influence, the river exported very little N during drought, so storm‐derived nutrient pulses were important for delivering N loads to the estuary. Overall, N is processed from river to estuary, but sustained WWTP‐N loads and periodic floods alter the timing of N delivery and N processing. Research that incorporates empirical measurements of N fluxes from river to estuary can inform management needs in the face of multiple anthropogenic stressors such as demand for freshwater and eutrophication.

Mutualistic interaction between dichloromethane‐ and chloromethane‐degrading bacteria in an anaerobic mixed culture - Gao Chen; Sara Kleindienst; Daniel R. Griffiths; E. Erin Mack; Edward S. Seger; Frank E. Löffler (Environmental Microbiology, 2017)
Summary The microbial mixed culture RM grows with dichloromethane (DCM) as the sole energy source generating acetate, methane, chloride and biomass as products. Chloromethane (CM) was not an intermediate during DCM utilization consistent with the observation that CM could not replace DCM as a growth substrate. Interestingly, cultures that received DCM and CM together degraded both compounds concomitantly. Transient hydrogen (H 2 ) formation reaching a maximum concentration of 205 ± 13 ppmv was observed in cultures growing with DCM, and the addition of exogenous H 2 at concentrations exceeding 3000 ppmv impeded DCM degradation. In contrast, CM degradation in culture RM had a strict requirement for H 2 . Following five consecutive transfers on CM and H 2 , Acetobacterium 16S rRNA gene sequences dominated the culture and the DCM‐degrader Candidatus Dichloromethanomonas elyunquensis was eliminated, consistent with the observation that the culture lost the ability to degrade DCM. These findings demonstrate that culture RM harbours different populations responsible for anaerobic DCM and CM metabolism, and further imply that the DCM and CM degradation pathways are mechanistically distinct. H 2 generated during DCM degradation is consumed by the hydrogenotrophic CM degrader, or may fuel other hydrogenotrophic processes, including organohalide respiration, methanogenesis and H 2 /CO 2 reductive acetogenesis.

Comparing tiers of a multi-tiered wetland assessment in the Prairie Pothole Region - Christina L. M. Hargiss; Edward S. DeKeyser; Jack E. Norland; Michael J. Ell (Wetlands Ecology and Management, 2017)

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)

A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)
Uterine fibroids are benign tumors of the uterus affecting up to 77% of women by menopause. They are the leading indication for hysterectomy, and account for $34 billion annually in the United States. Race/ethnicity and age are the strongest known risk factors. African American (AA) women have higher prevalence, earlier onset, and larger and more numerous fibroids than European American women. We conducted a multi-stage genome-wide association study (GWAS) of fibroid risk among AA women followed by in silico genetically predicted gene expression profiling of top hits. In Stage 1, cases and controls were confirmed by pelvic imaging, genotyped and imputed to 1000 Genomes. Stage 2 used self-reported fibroid and GWAS data from 23andMe, Inc. and the Black Women’s Health Study. Associations with fibroid risk were modeled using logistic regression adjusted for principal components, followed by meta-analysis of results. We observed a significant association among 3399 AA cases and 4764 AA controls at rs739187 (risk-allele frequency = 0.27) in CYTH4 (OR (95% confidence interval) = 1.23 (1.16–1.30), p value = 7.82 × 10 −9 ). Evaluation of the genetic association results with MetaXcan identified lower predicted gene expression of CYTH4 in thyroid tissue as significantly associated with fibroid risk ( p value = 5.86 × 10 −8 ). In this first multi-stage GWAS for fibroids among AA women, we identified a novel risk locus for fibroids within CYTH4 that impacts gene expression in thyroid and has potential biological relevance for fibroids.

Tubal ligation and ovarian cancer risk in African American women - Chrissy McNamara; Sarah E. Abbott; Elisa V. Bandera; Bo Qin; Lauren C. Peres; Fabian Camacho; Patricia G. Moorman; Anthony J. Alberg; Jill S. Barnholtz-Sloan; Melissa Bondy; Michele L. Cote; Ellen Funkhouser; et al. (Cancer Causes & Control, 2017)

The tooth, the whole tooth and nothing but the tooth: tooth shape and ontogenetic shift dynamics in the white shark Carcharodon carcharias - G. C. A. French; M. Stürup; S. Rizzuto; J. H. van Wyk; D. Edwards; R. W. Dolan; S. P. Wintner; A. V. Towner; W. O. H. Hughes (Journal of Fish Biology, 2017)
Results from this study of the white shark Carcharodon carcharias include measurements obtained using a novel photographic method that reveal significant differences between the sexes in the relationship between tooth cuspidity and shark total length, and a novel ontogenetic change in male tooth shape. Males exhibit broader upper first teeth and increased distal inclination of upper third teeth with increasing length, while females do not present a consistent morphological change. Substantial individual variation, with implications for pace of life syndrome, was present in males and tooth polymorphism was suggested in females. Sexual differences and individual variation may play major roles in ontogenetic changes in tooth morphology in C. carcharias , with potential implications for their foraging biology. Such individual and sexual differences should be included in studies of ontogenetic shift dynamics in other species and systems.

Effects of nalfurafine on the reinforcing, thermal antinociceptive, and respiratory-depressant effects of oxycodone: modeling an abuse-deterrent opioid analgesic in rats - E. Andrew Townsend; Jennifer E. Naylor; S. Stevens Negus; Shelley R. Edwards; Hina N. Qureshi; Hunter W. McLendon; Christopher R. McCurdy; Coco N. Kapanda; Jussara M. do Carmo; Fernanda S. da Silva; John E. Hall; Kenneth J. Sufka; et al. (Psychopharmacology, 2017)

Assessment of the Neuroprotective Effects of Arginine-Rich Protamine Peptides, Poly-Arginine Peptides (R12-Cyclic, R22) and Arginine–Tryptophan-Containing Peptides Following In Vitro Excitotoxicity and/or Permanent Middle Cerebral Artery Occlusion in Rats - Bruno P. Meloni; Diego Milani; Jane L. Cross; Vince W. Clark; Adam B. Edwards; Ryan S. Anderton; David J. Blacker; Neville W. Knuckey (NeuroMolecular Medicine, 2017)

Diversity and Inclusion in Conservation: A Proposal for a Marine Diversity Network - Nicola S. Smith; Isabelle M. Côté; Lourdes Martinez-Estevez; Edward J. Hind-Ozan; Angela L. Quiros; Nathan Johnson; Stephanie J. Green; Leslie Cornick; David Shiffman; Luis Malpica-Cruz; Allison Gleason Besch; Nikita Shiel-Rolle (Frontiers in Marine Science, 2017)

The Significant Surface-Water Connectivity of “Geographically Isolated Wetlands” - Aram J. K. Calhoun; David M. Mushet; Laurie C. Alexander; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Stephen C. Richter; Susan C. Walls (Wetlands, 2017)

The landscape of genetic diseases in Saudi Arabia based on the first 1000 diagnostic panels and exomes - Dorota Monies; Mohamed Abouelhoda; Moeenaldeen AlSayed; Zuhair Alhassnan; Maha Alotaibi; Husam Kayyali; Mohammed Al-Owain; Ayaz Shah; Zuhair Rahbeeni; Mohammad A. Al-Muhaizea; Hamad I. Alzaidan; Edward Cupler; et al. (Human Genetics, 2017)

Genomic analysis of chimeric human cytomegalovirus vaccine candidates derived from strains Towne and Toledo - Nicolás M. Suárez; Betty Lau; George M. Kemble; Ronzo Lee; Edward S. Mocarski; Gavin W. G. Wilkinson; Stuart P. Adler; Michael A. McVoy; Andrew J. Davison (Virus Genes, 2017)

Differences in meristems between monocots and dicots and susceptibility to attack by gall-inducing insects - Megan S. Silvia; Edward F. Connor (Arthropod-Plant Interactions, 2017)

Paleo-environmental reconstruction of Lopingian (upper Permian) sediments in the Galilee Basin, Queensland, Australia - L. J. Phillips; S. A. Edwards; V. Bianchi; J. S. Esterle (Australian Journal of Earth Sciences, 2017)

Cigarette smoking and the association with serous ovarian cancer in African American women: African American Cancer Epidemiology Study (AACES) - Linda E. Kelemen; Sarah Abbott; Bo Qin; Lauren Cole Peres; Patricia G. Moorman; Kristin Wallace; Elisa V. Bandera; Jill S. Barnholtz-Sloan; Melissa Bondy; Kathleen Cartmell; Michele L. Cote; Ellen Funkhouser; et al. (Cancer Causes & Control, 2017)

Greater temperature sensitivity of plant phenology at colder sites: implications for convergence across northern latitudes - Janet Prevéy; Mark Vellend; Nadja Rüger; Robert D. Hollister; Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Karin Clark; Elisabeth J. Cooper; Bo Elberling; Anna M. Fosaa; Gregory H. R. Henry; et al. (Global Change Biology, 2017)
Warmer temperatures are accelerating the phenology of organisms around the world. Temperature sensitivity of phenology might be greater in colder, higher latitude sites than in warmer regions, in part because small changes in temperature constitute greater relative changes in thermal balance at colder sites. To test this hypothesis, we examined up to 20 years of phenology data for 47 tundra plant species at 18 high‐latitude sites along a climatic gradient. Across all species, the timing of leaf emergence and flowering was more sensitive to a given increase in summer temperature at colder than warmer high‐latitude locations. A similar pattern was seen over time for the flowering phenology of a widespread species, Cassiope tetragona . These are among the first results highlighting differential phenological responses of plants across a climatic gradient and suggest the possibility of convergence in flowering times and therefore an increase in gene flow across latitudes as the climate warms.

Does Aquaculture Support the Needs of Nutritionally Vulnerable Nations? - Christopher D. Golden; Katherine L. Seto; Madan M. Dey; Oai L. Chen; Jessica A. Gephart; Samuel S. Myers; Matthew Smith; Bapu Vaitla; Edward H. Allison (Frontiers in Marine Science, 2017)

Erratum to: Changes in ecosystem engineers: the effects of kelp forest type on currents and benthic assemblages in Kachemak Bay, Alaska - Dominic Hondolero; Matthew S. Edwards (Marine Biology, 2017)

Lifetime number of ovulatory cycles and epithelial ovarian cancer risk in African American women - Lauren C. Peres; Patricia G. Moorman; Anthony J. Alberg; Elisa V. Bandera; Jill Barnholtz-Sloan; Melissa Bondy; Michele L. Cote; Ellen Funkhouser; Edward S. Peters; Ann G. Schwartz; Paul D. Terry; Sarah E. Abbott; et al. (Cancer Causes & Control, 2017)

Review of Lopingian (upper Permian) stratigraphy of the Galilee Basin, Queensland, Australia - L. J. Phillips; J. S. Esterle; S. A. Edwards (Australian Journal of Earth Sciences, 2017)

Changes in ecosystem engineers: the effects of kelp forest type on currents and benthic assemblages in Kachemak Bay, Alaska - Dominic Hondolero; Matthew S. Edwards (Marine Biology, 2017)

Structural imaging of mild traumatic brain injury may not be enough: overview of functional and metabolic imaging of mild traumatic brain injury - Samuel S. Shin; James W. Bales; C. Edward Dixon; Misun Hwang (Brain Imaging and Behavior, 2017)

Rotor Tracking Using Phase of Electrograms Recorded During Atrial Fibrillation - Caroline H. Roney; Chris D. Cantwell; Norman A. Qureshi; Rasheda A. Chowdhury; Emmanuel Dupont; Phang Boon Lim; Edward J. Vigmond; Jennifer H. Tweedy; Fu Siong Ng; Nicholas S. Peters (Annals of Biomedical Engineering, 2017)

Ensemble Decision Tree Models Using RUSBoost for Estimating Risk of Iron Failure in Drinking Water Distribution Systems - S. R. Mounce; K. Ellis; J. M. Edwards; V. L. Speight; N. Jakomis; J. B. Boxall (Water Resources Management, 2017)

Geochemistry of deep-sea sediments in two cores retrieved at the mouth of the Coatzacoalcos River delta, western Gulf of Mexico, Mexico - Mayla A. Ramos-Vázquez; John S. Armstrong-Altrin; Leticia Rosales-Hoz; María L. Machain-Castillo; Arturo Carranza-Edwards (Arabian Journal of Geosciences, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Characterisation of neuroprotective efficacy of modified poly-arginine-9 (R9) peptides using a neuronal glutamic acid excitotoxicity model - Adam B. Edwards; Ryan S. Anderton; Neville W. Knuckey; Bruno P. Meloni (Molecular and Cellular Biochemistry, 2017)

The Neuroprotective Peptide Poly-Arginine-12 (R12) Reduces Cell Surface Levels of NMDA NR2B Receptor Subunit in Cortical Neurons; Investigation into the Involvement of Endocytic Mechanisms - Gabriella MacDougall; Ryan S. Anderton; Adam B. Edwards; Neville W. Knuckey; Bruno P. Meloni (Journal of Molecular Neuroscience, 2017)

Hierarchical winner-take-all particle swarm optimization social network for neural model fitting - Brandon S. Coventry; Aravindakshan Parthasarathy; Alexandra L. Sommer; Edward L. Bartlett (Journal of Computational Neuroscience, 2017)

Application of human factors engineering (HFE) to the design of a naloxone auto-injector for the treatment of opioid emergencies - Robert B. Raffa; Robert Taylor; Joseph V. Pergolizzi; Srinivas Nalamachu; Eric S. Edwards; Evan T. Edwards (Drug Delivery and Translational Research, 2017)
The increased use of opioids for chronic treatment of pain and the resulting epidemic of opioid overdoses have created a major public health challenge. Parenteral naloxone has been used since the 1970’s to treat opioid overdose. Recently, a novel naloxone auto-injector device (EVZIO, kaleo, Inc., Richmond, VA) was approved by the Food and Drug Administration. In this article, we review the Human Factors Engineering (HFE) process used in the development and testing of this novel naloxone auto-injector currently used in nonmedical settings for the emergency treatment of known or suspected opioid overdose. HFE methods were employed throughout the product development process for the naloxone auto-injector including formative and summative studies in order to optimize the auto-injector’s user interface, mitigate use-related hazards and increase reliability during an opioid emergency use scenario. HFE was also used to optimize the product’s design and user interface in order to reduce or prevent user confusion and misuse. The naloxone auto-injector went through a rigorous HFE process that included perceptual, cognitive, and physical action analysis; formative usability evaluations; use error analysis and summative design validation studies. Applying HFE resulted in the development of a product that is safe, fast, easy and predictably reliable to deliver a potentially life-saving dose of naloxone during an opioid overdose emergency. The naloxone auto-injector may be considered as a universal precaution option for at-risk patients prescribed opioids or those who are at increased risk for an opioid overdose emergency.

Historical processes and contemporary ocean currents drive genetic structure in the seagrass T halassia hemprichii in the Indo‐Australian Archipelago - Udhi E. Hernawan; Kor‐jent van Dijk; Gary A. Kendrick; Ming Feng; Edward Biffin; Paul S. Lavery; Kathryn McMahon (Molecular Ecology, 2017)
Understanding spatial patterns of gene flow and genetic structure is essential for the conservation of marine ecosystems. Contemporary ocean currents and historical isolation due to Pleistocene sea level fluctuations have been predicted to influence the genetic structure in marine populations. In the Indo‐Australian Archipelago ( IAA ), the world's hotspot of marine biodiversity, seagrasses are a vital component but population genetic information is very limited. Here, we reconstructed the phylogeography of the seagrass Thalassia hemprichii in the IAA based on single nucleotide polymorphisms ( SNP s) and then characterized the genetic structure based on a panel of 16 microsatellite markers. We further examined the relative importance of historical isolation and contemporary ocean currents in driving the patterns of genetic structure. Results from SNP s revealed three population groups: eastern Indonesia, western Indonesia (Sunda Shelf) and Indian Ocean; while the microsatellites supported five population groups (eastern Indonesia, Sunda Shelf, Lesser Sunda, Western Australia and Indian Ocean). Both SNP s and microsatellites showed asymmetrical gene flow among population groups with a trend of southwestward migration from eastern Indonesia. Genetic diversity was generally higher in eastern Indonesia and decreased southwestward. The pattern of genetic structure and connectivity is attributed partly to the Pleistocene sea level fluctuations modified to a smaller level by contemporary ocean currents.

The city as a refuge for insect pollinators - Damon M. Hall; Gerardo R. Camilo; Rebecca K. Tonietto; Jeff Ollerton; Karin Ahrné; Mike Arduser; John S. Ascher; Katherine C. R. Baldock; Robert Fowler; Gordon Frankie; Dave Goulson; Bengt Gunnarsson; et al. (Conservation Biology, 2017)
Research on urban insect pollinators is changing views on the biological value and ecological importance of cities. The abundance and diversity of native bee species in urban landscapes that are absent in nearby rural lands evidence the biological value and ecological importance of cities and have implications for biodiversity conservation. Lagging behind this revised image of the city are urban conservation programs that historically have invested in education and outreach rather than programs designed to achieve high‐priority species conservation results. We synthesized research on urban bee species diversity and abundance to determine how urban conservation could be repositioned to better align with new views on the ecological importance of urban landscapes. Due to insect pollinators’ relatively small functional requirements—habitat range, life cycle, and nesting behavior—relative to larger mammals, we argue that pollinators put high‐priority and high‐impact urban conservation within reach. In a rapidly urbanizing world, transforming how environmental managers view the city can improve citizen engagement and contribute to the development of more sustainable urbanization.

Role of polysaccharides in food, digestion, and health - A. Lovegrove; C. H. Edwards; I. De Noni; H. Patel; S. N. El; T. Grassby; C. Zielke; M. Ulmius; L. Nilsson; P. J. Butterworth; P. R Ellis; P. R. Shewry (Critical Reviews in Food Science and Nutrition, 2017)

Erratum to: Time to flowering of temperate pulses in vivo and generation turnover in vivo–in vitro of narrow-leaf lupin accelerated by low red to far-red ratio and high intensity in the far-red region - Janine S. Croser; Maria Pazos-Navarro; Richard G. Bennett; Sabrina Tschirren; Kylie Edwards; William Erskine; Robert Creasy; Federico M. Ribalta (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Time to flowering of temperate pulses in vivo and generation turnover in vivo–in vitro of narrow-leaf lupin accelerated by low red to far-red ratio and high intensity in the far-red region - Janine S. Croser; Maria Pazos-Navarro; Richard G. Bennett; Sabrina Tschirren; Kylie Edwards; William Erskine; Robert Creasy; Federico M. Ribalta (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Shrinking of Vann Island, Gulf of Mannar, SE coast of India: assessing the impacts - M. Jayaprakash; K. Sivakumar; S. Muthusamy; R. R. Krishnamurthy; J. K. Edward Patterson (Natural Hazards, 2016)

Interaction between irbesartan, peroxisome proliferator-activated receptor (PPAR-γ), and adiponectin in the regulation of blood pressure and renal function in spontaneously hypertensive rats - S. Afzal; M. A. Sattar; Edward J. Johns; Mohammed H. Abdulla; Safia Akhtar; Fayyaz Hashmi; Nor Azizan Abdullah (Journal of Physiology and Biochemistry, 2016)

Analysis of mating system and genetic structure in the endangered, amphicarpic plant, Lewton’s polygala (Polygala lewtonii) - Joel F. Swift; Stacy A. Smith; Eric S. Menges; Burgund Bassüner; Christine E. Edwards (Conservation Genetics, 2016)

Alcohol dependence-induced regulation of the proliferation and survival of adult brain progenitors is associated with altered BDNF-TrkB signaling - Sucharita S. Somkuwar; McKenzie J. Fannon; Miranda C. Staples; Eva R. Zamora-Martinez; Alvaro I. Navarro; Airee Kim; Jacqueline A. Quigley; Scott Edwards; Chitra D. Mandyam (Brain Structure and Function, 2016)

Variability and anatomical specificity of the orbitofrontothalamic fibers of passage in the ventral capsule/ventral striatum (VC/VS): precision care for patient-specific tractography-guided targeting of deep brain stimulation (DBS) in obsessive compulsive disorder (OCD) - Nikolaos Makris; Yogesh Rathi; Palig Mouradian; Giorgio Bonmassar; George Papadimitriou; Wingkwai I. Ing; Edward H. Yeterian; Marek Kubicki; Emad N. Eskandar; Lawrence L. Wald; Qiuyun Fan; Aapo Nummenmaa; et al. (Brain Imaging and Behavior, 2016)

Review of Fusarium species isolated in association with mango malformation in Australia - E. C. Y. Liew; M. H. Laurence; C. A. Pearce; R. G. Shivas; G. I. Johnson; Y.P. Tan; J. Edwards; S. Perry; A.W. Cooke; B. A. Summerell (Australasian Plant Pathology, 2016)

Genome-wide association mapping of provitamin A carotenoid content in cassava - Williams Esuma; Liezel Herselman; Maryke Tine Labuschagne; Punna Ramu; Fei Lu; Yona Baguma; Edward S. Buckler; Robert Sezi Kawuki (Euphytica, 2016)

Primate genotyping via high resolution melt analysis: rapid and reliable identification of color vision status in wild lemurs - Rachel L. Jacobs; Amanda N. Spriggs; Tammie S. MacFie; Andrea L. Baden; Mitchell T. Irwin; Patricia C. Wright; Edward E. Louis; Richard R. Lawler; Nicholas I. Mundy; Brenda J. Bradley (Primates, 2016)

Prevalence of enteric bacterial parasites with respect to anthropogenic factors among commensal rhesus macaques in Dehradun, India - Brianne A. Beisner; Krishna N. Balasubramaniam; Kristine Fernandez; Allison Heagerty; Shannon K. Seil; Edward R. Atwill; Brij K. Gupta; P. C. Tyagi; Netrapal. P. S. Chauhan; Bishan S. Bonal; Priya. R. Sinha; Brenda McCowan (Primates, 2016)

Bruguiera hainesii, a critically endangered mangrove species, is a hybrid between B. cylindrica and B. gymnorhiza (Rhizophoraceae) - Junya Ono; Jean W. H. Yong; Koji Takayama; Mohd Nazre Bin Saleh; Alison K. S. Wee; Takeshi Asakawa; Orlex Baylen Yllano; Severino G. Salmo; Monica Suleiman; Nguyen Xuan Tung; Khin Khin Soe; Sankararamasubramanian Halasya Meenakshisundaram; et al. (Conservation Genetics, 2016)

Colletotrichum species in Australia - Roger G. Shivas; Yu Pei Tan; Jacqueline Edwards; Quang Dinh; Aaron Maxwell; Vera Andjic; José R. Liberato; Chris Anderson; Dean R. Beasley; Kaylene Bransgrove; Lindy M. Coates; Karren Cowan; et al. (Australasian Plant Pathology, 2016)

Species-specific responses of temperate macroalgae with different photosynthetic strategies to ocean acidification: a mesocosm study - Ju-Hyoung Kim; Eun Ju Kang; Matthew S. Edwards; Kitack Lee; Hae Jin Jeong; Kwang Young Kim (Algae, 2016)

Analysis of recombination QTLs, segregation distortion, and epistasis for fitness in maize multiple populations using ultra-high-density markers - Chunhui Li; Yongxiang Li; Yunsu Shi; Yanchun Song; Dengfeng Zhang; Edward S. Buckler; Zhiwu Zhang; Yu Li; Tianyu Wang (Theoretical and Applied Genetics, 2016)

Use of a coupled soil-root-leaf model to optimise phosphate fertiliser use efficiency in barley - J. Heppell; S. Payvandi; P. Talboys; K. C. Zygalakis; D. Langton; R. Sylvester-Bradley; A. C. Edwards; R. Walker; P. Withers; D. L. Jones; T. Roose (Plant and Soil, 2016)

Intramuscular MAPK signaling following high volume and high intensity resistance exercise protocols in trained men - Adam M. Gonzalez; Jay R. Hoffman; Jeremy R. Townsend; Adam R. Jajtner; Carleigh H. Boone; Kyle S. Beyer; Kayla M. Baker; Adam J. Wells; Gerald T. Mangine; Edward H. Robinson; David D. Church; Leonardo P. Oliveira; et al. (European Journal of Applied Physiology, 2016)

Fine-scale spatial variation in ice cover and surface temperature trends across the surface of the Laurentian Great Lakes - Lacey A. Mason; Catherine M. Riseng; Andrew D. Gronewold; Edward S. Rutherford; Jia Wang; Anne Clites; Sigrid D. P. Smith; Peter B. McIntyre (Climatic Change, 2016)

Contrasting trait responses to latitudinal climate variation in two lineages of an invasive grass - Thomas J. Mozdzer; Joshua S. Caplan; Rachel N. Hager; C. Edward Proffitt; Laura A. Meyerson (Biological Invasions, 2016)

Augmenting Surgery via Multi-scale Modeling and Translational Systems Biology in the Era of Precision Medicine: A Multidisciplinary Perspective - Ghassan S. Kassab; Gary An; Edward A. Sander; Michael I. Miga; Julius M. Guccione; Songbai Ji; Yoram Vodovotz (Annals of Biomedical Engineering, 2016)

Parametric Modeling of the Mouse Left Ventricular Myocardial Fiber Structure - Samer S. Merchant; Arnold David Gomez; James L. Morgan; Edward W. Hsu (Annals of Biomedical Engineering, 2016)

A Novel Application of Eddy Current Braking for Functional Strength Training During Gait - Edward P. Washabaugh; Edward S. Claflin; R. Brent Gillespie; Chandramouli Krishnan (Annals of Biomedical Engineering, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Daphnia magna’s sense of competition: intra-specific interactions (ISI) alter life history strategies and increase metals toxicity - Kurt A. Gust; Alan J. Kennedy; Nicolas L. Melby; Mitchell S. Wilbanks; Jennifer Laird; Barbara Meeks; Erik B. Muller; Roger M. Nisbet; Edward J. Perkins (Ecotoxicology, 2016)

Assessment of Top-Down and Bottom-Up Controls on the Collapse of Alewives (Alosa pseudoharengus) in Lake Huron - Yu-Chun Kao; Sara A. Adlerstein; Edward S. Rutherford (Ecosystems, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

A conceptual framework for analyzing deltas as coupled social–ecological systems: an example from the Amazon River Delta - Eduardo S. Brondizio; Nathan D. Vogt; Andressa V. Mansur; Edward J. Anthony; Sandra Costa; Scott Hetrick (Sustainability Science, 2016)

The 12-day thermoregulatory metamorphosis of Red-winged Blackbirds (Agelaius phoeniceus) - Sarah K. Goy Sirsat; Tushar S. Sirsat; Janna L. Crossley; Paul R. Sotherland; Edward M. Dzialowski (Journal of Comparative Physiology B, 2016)

A prospective study of oral contraceptive use and colorectal adenomas - Brittany M. Charlton; Edward Giovannucci; Charles S. Fuchs; Andrew T. Chan; Jung Eun Lee; Yin Cao; Stacey A. Missmer; Bernard A. Rosner; Susan E. Hankinson; Walter Willett; Kana Wu; Karin B. Michels (Cancer Causes & Control, 2016)

Analyzing Economic and Environmental Performance of Switchgrass Biofuel Supply Chains - T. Edward Yu; Burton C. English; Lixia He; James A. Larson; James Calcagno; Joshua S. Fu; Brad Wilson (BioEnergy Research, 2016)

Shrubline but not treeline advance matches climate velocity in montane ecosystems of south‐central Alaska - Roman J. Dial; T. Scott Smeltz; Patrick F. Sullivan; Christina L. Rinas; Katriina Timm; Jason E. Geck; S. Carl Tobin; Trevor S. Golden; Edward C. Berg (Global Change Biology, 2016)
Tall shrubs and trees are advancing into many tundra and wetland ecosystems but at a rate that often falls short of that predicted due to climate change. For forest, tall shrub, and tundra ecosystems in two pristine mountain ranges of Alaska, we apply a Bayesian, error‐propagated calculation of expected elevational rise (climate velocity), observed rise (biotic velocity), and their difference (biotic inertia). We show a sensitive dependence of climate velocity on lapse rate and derive biotic velocity as a rigid elevational shift. Ecosystem presence identified from recent and historic orthophotos ~50 years apart was regressed on elevation. Biotic velocity was estimated as the difference between critical point elevations of recent and historic logistic fits divided by time between imagery. For both mountain ranges, the 95% highest posterior density of climate velocity enclosed the posterior distributions of all biotic velocities. In the Kenai Mountains, mean tall shrub and climate velocities were both 2.8 m y −1 . In the better sampled Chugach Mountains, mean tundra retreat was 1.2 m y −1 and climate velocity 1.3 m y −1 . In each mountain range, the posterior mode of tall woody vegetation velocity (the complement of tundra) matched climate velocity better than either forest or tall shrub alone, suggesting competitive compensation can be important. Forest velocity was consistently low at 0.1–1.1 m y −1 , indicating treeline is advancing slowly. We hypothesize that the high biotic inertia of forest ecosystems in south‐central Alaska may be due to competition with tall shrubs and/or more complex climate controls on the elevational limits of trees than tall shrubs. Among tall shrubs, those that disperse farthest had lowest inertia. Finally, the rapid upward advance of woody vegetation may be contributing to regional declines in Dall's sheep (Ovis dalli), a poorly dispersing alpine specialist herbivore with substantial biotic inertia due to dispersal reluctance.

Air pollution influences on exhaled nitric oxide among people with type II diabetes - Cheng Peng; Heike Luttmann-Gibson; Antonella Zanobetti; Allison Cohen; Celine De Souza; Brent A. Coull; Edward S. Horton; Joel Schwartz; Petros Koutrakis; Diane R. Gold (Air Quality, Atmosphere & Health, 2016)

An integrated pan‐tropical biomass map using multiple reference datasets - Valerio Avitabile; Martin Herold; Gerard B. M. Heuvelink; Simon L. Lewis; Oliver L. Phillips; Gregory P. Asner; John Armston; Peter S. Ashton; Lindsay Banin; Nicolas Bayol; Nicholas J. Berry; Pascal Boeckx; et al. (Global Change Biology, 2016)
We combined two existing datasets of vegetation aboveground biomass ( AGB ) ( Proceedings of the National Academy of Sciences of the United States of America , 108 , 2011, 9899; Nature Climate Change , 2 , 2012, 182) into a pan‐tropical AGB map at 1‐km resolution using an independent reference dataset of field observations and locally calibrated high‐resolution biomass maps, harmonized and upscaled to 14 477 1‐km AGB estimates. Our data fusion approach uses bias removal and weighted linear averaging that incorporates and spatializes the biomass patterns indicated by the reference data. The method was applied independently in areas (strata) with homogeneous error patterns of the input (Saatchi and Baccini) maps, which were estimated from the reference data and additional covariates. Based on the fused map, we estimated AGB stock for the tropics (23.4 N–23.4 S) of 375 Pg dry mass, 9–18% lower than the Saatchi and Baccini estimates. The fused map also showed differing spatial patterns of AGB over large areas, with higher AGB density in the dense forest areas in the Congo basin, Eastern Amazon and South‐East Asia, and lower values in Central America and in most dry vegetation areas of Africa than either of the input maps. The validation exercise, based on 2118 estimates from the reference dataset not used in the fusion process, showed that the fused map had a RMSE 15–21% lower than that of the input maps and, most importantly, nearly unbiased estimates (mean bias 5 Mg dry mass ha −1 vs. 21 and 28 Mg ha −1 for the input maps). The fusion method can be applied at any scale including the policy‐relevant national level, where it can provide improved biomass estimates by integrating existing regional biomass maps as input maps and additional, country‐specific reference datasets.

Native and alien herbaceous plants in the Brazilian Cerrado are (co-)limited by different nutrients - Luciola S. Lannes; Mercedes M. C. Bustamante; Peter J. Edwards; Harry Olde Venterink (Plant and Soil, 2016)

Are Hypsodonty and Occlusal Enamel Complexity Evolutionarily Correlated in Ungulates? - Nicholas A. Famoso; Edward Byrd Davis; Robert S. Feranec; Samantha S. B. Hopkins; Samantha A. Price (Journal of Mammalian Evolution, 2016)

The impact of the introduction of fidaxomicin on the management of Clostridium difficile infection in seven NHS secondary care hospitals in England: a series of local service evaluations - S. D. Goldenberg; S. Brown; L. Edwards; D. Gnanarajah; P. Howard; D. Jenkins; D. Nayar; M. Pasztor; S. Oliver; T. Planche; J. A. T. Sandoe; P. Wade; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Evaluation of cystatin C as an early biomarker of cadmium nephrotoxicity in the rat - Walter C. Prozialeck; Aaron VanDreel; Christopher D. Ackerman; Ian Stock; Alexander Papaeliou; Christian Yasmine; Kristen Wilson; Peter C. Lamar; Victoria L. Sears; Joshua Z. Gasiorowski; Karyn M. DiNovo; Vishal S. Vaidya; et al. (BioMetals, 2016)

Does Increased Road Dust Due to Energy Development Impact Wetlands in the Bakken Region? - Jessica Creuzer; Christina L. M. Hargiss; Jack E. Norland; Thomas DeSutter; Francis X. Casey; Edward S. DeKeyser; Mike Ell (Water, Air, & Soil Pollution, 2016)

First record of coralline lethal orange disease (CLOD) in the Indian Ocean - G. S. Aeby; K. Diraviya Raj; G. Mathews; M. Selva Bharath; J. K. Patterson Edward (Coral Reefs, 2015)

Initial evaluations of a Gulf of Mexico/Caribbean ocean forecast system in the context of the Deepwater Horizon disaster - Edward D. Zaron; Patrick J. Fitzpatrick; Scott L. Cross; John M. Harding; Frank L. Bub; Jerry D. Wiggert; Dong S. Ko; Yee Lau; Katharine Woodard; Christopher N. K. Mooers (Frontiers of Earth Science, 2015)

Decadal warming causes a consistent and persistent shift from heterotrophic to autotrophic respiration in contrasting permafrost ecosystems - Caitlin E. Hicks Pries; Richard S. P. van Logtestijn; Edward A. G. Schuur; Susan M. Natali; Johannes H. C. Cornelissen; Rien Aerts; Ellen Dorrepaal (Global Change Biology, 2015)
Soil carbon in permafrost ecosystems has the potential to become a major positive feedback to climate change if permafrost thaw increases heterotrophic decomposition. However, warming can also stimulate autotrophic production leading to increased ecosystem carbon storage—a negative climate change feedback. Few studies partitioning ecosystem respiration examine decadal warming effects or compare responses among ecosystems. Here, we first examined how 11 years of warming during different seasons affected autotrophic and heterotrophic respiration in a bryophyte‐dominated peatland in Abisko, Sweden. We used natural abundance radiocarbon to partition ecosystem respiration into autotrophic respiration, associated with production, and heterotrophic decomposition. Summertime warming decreased the age of carbon respired by the ecosystem due to increased proportional contributions from autotrophic and young soil respiration and decreased proportional contributions from old soil. Summertime warming's large effect was due to not only warmer air temperatures during the growing season, but also to warmer deep soils year‐round. Second, we compared ecosystem respiration responses between two contrasting ecosystems, the Abisko peatland and a tussock‐dominated tundra in Healy, Alaska. Each ecosystem had two different timescales of warming (

Retrospective stable isotope analysis reveals ecosystem responses to river regulation over the last century - Thomas F. Turner; Trevor J. Krabbenhoft; Michael L. Collyer; Corey A. Krabbenhoft; Melanie S. Edwards; Zachary D. Sharp (Ecology, 2015)
Disruption of natural flow regimes, nutrient pollution, and other consequences of human population growth and development have impacted most major rivers of the world. Alarming losses of aquatic biodiversity coincide with human‐caused river alteration, but effects of biotic homogenization on aquatic ecosystem processes are not as well documented. This is because unaltered systems for comparison are scarce, and some ecosystem‐wide effects may take decades to manifest. We evaluated aquatic ecosystem responses to extensive river‐floodplain engineering and nutrient addition in the Rio Grande of southwestern North America as revealed by changes in trophic structure of, and resource availability to, the fish community. Stable Isotope Analysis (SIA) was conducted on museum‐preserved fishes collected over a 70‐year period of intensive river management and exponential human population growth. Trophic complexity and resource heterogeneity for fish consumers (measured as “isotopic niche breadth”) decreased following sediment deprivation and channelization, and these effects persist into the present. Increased nutrient inputs led to δ 15 N enrichment in the entire fish community at all affected sites, and a shift to autochthonous sources of carbon at the most proximal site downstream of wastewater release, probably via bottom‐up transfer. Overall, retrospective SIA of apex consumers suggests radical change and functional impairment of a floodplain river ecosystem already marked by significant biodiversity loss.

Organic geochemical characteristics of the Upper Cretaceous–Early Paleogene source rock and correlation with some Egyptian mummy bitumen and oil from the southern Gulf of Suez, Egypt - W. Sh. El Diasty; A. R. Mostafa; S. Y. El Beialy; H. A. El Adl; K. J. Edwards (Arabian Journal of Geosciences, 2015)

Fostering effective international collaboration for marine science in small island states - Edward J. Hind; Steven M. Alexander; Stephanie J. Green; Jacob P. Kritzer; Michael J. Sweet; Ayana Elizabeth Johnson; Fabian P. Amargós; Nicola S. Smith; Angelie M. Peterson (Frontiers in Marine Science, 2015)

Television watching and colorectal cancer survival in men - Yin Cao; Jeffrey A. Meyerhardt; Andrew T. Chan; Kana Wu; Charles S. Fuchs; Edward L. Giovannucci (Cancer Causes & Control, 2015)

Would protecting tropical forest fragments provide carbon and biodiversity cobenefits under REDD +? - Luiz Fernando S. Magnago; Ainhoa Magrach; William F. Laurance; Sebastião V. Martins; João Augusto A. Meira‐Neto; Marcelo Simonelli; David P. Edwards (Global Change Biology, 2015)
Tropical forests store vast amounts of carbon and are the most biodiverse terrestrial habitats, yet they are being converted and degraded at alarming rates. Given global shortfalls in the budgets required to prevent carbon and biodiversity loss, we need to seek solutions that simultaneously address both issues. Of particular interest are carbon‐based payments under the Reducing Emissions from Deforestation and Forest Degradation ( REDD +) mechanism to also conserve biodiversity at no additional cost. One potential is for REDD + to protect forest fragments, especially within biomes where contiguous forest cover has diminished dramatically, but we require empirical tests of the strength of any carbon and biodiversity cobenefits in such fragmented systems. Using the globally threatened Atlantic Forest landscape, we measured above‐ground carbon stocks within forest fragments spanning 13 to 23 442 ha in area and with different degrees of isolation. We related these stocks to tree community structure and to the richness and abundance of endemic and IUCN Red‐listed species. We found that increasing fragment size has a positive relationship with above‐ground carbon stock and with abundance of IUCN Red‐listed species and tree community structure. We also found negative relationships between distance from large forest block and tree community structure, endemic species richness and abundance, and IUCN Red‐listed species abundance. These resulted in positive congruence between carbon stocks and Red‐listed species, and the abundance and richness of endemic species, demonstrating vital cobenefits. As such, protecting forest fragments in hotspots of biodiversity, particularly larger fragments and those closest to sources, offers important carbon and biodiversity cobenefits. More generally, our results suggest that macroscale models of cobenefits under REDD + have likely overlooked key benefits at small scales, indicating the necessity to apply models that include finer‐grained assessments in fragmented landscapes rather than using averaged coarse‐grained cells.

A High‐Resolution Approach to Mapping Energy Flows through Water Infrastructure Systems - Edward S. Spang; Frank J. Loge (Journal of Industrial Ecology, 2015)
Summary Using data from the water service area of the East Bay Municipal Utility District in Northern California, we develop and discuss a method for assessing, at a high resolution, the energy intensity of water treated and delivered to customers of a major metropolitan water district. This method extends previous efforts by integrating hourly data from supervisory control and data acquisition systems with calculations based on the actual structure of the engineered infrastructure to produce a detailed understanding of energy use in space and time within the territory of a large‐scale urban water provider. We found significant variations in the energy intensity of delivered potable water resulting from seasonal and topographic effects. This method enhances our understanding of the energy inputs for potable water systems and can be applied to the entire delivery and postuse water life cycle. A nuanced understanding of water's energy intensity in an urban setting enables more intelligent, targeted efforts to jointly conserve water and energy resources that take seasonal, distance, and elevation effects into account.

Seasonal Water Column NH4 + Cycling Along a Semi-arid Sub-tropical River–Estuary Continuum: Responses to Episodic Events and Drought Conditions - Denise A. Bruesewitz; Wayne S. Gardner; Rae F. Mooney; Edward J. Buskey (Ecosystems, 2015)

Adolescent dietary vitamin D and sun exposure in relation to benign breast disease - Caroline E. Boeke; Rulla M. Tamimi; Catherine S. Berkey; Graham A. Colditz; Edward Giovannucci; Susan Malspeis; Walter C. Willett; A. Lindsay Frazier (Cancer Causes & Control, 2015)

Proceedings of the second international molecular pathological epidemiology (MPE) meeting - Shuji Ogino; Peter T. Campbell; Reiko Nishihara; Amanda I. Phipps; Andrew H. Beck; Mark E. Sherman; Andrew T. Chan; Melissa A. Troester; Adam J. Bass; Kathryn C. Fitzgerald; Rafael A. Irizarry; Karl T. Kelsey; et al. (Cancer Causes & Control, 2015)

The Effect of Cerium Oxide Nanoparticle Valence State on Reactive Oxygen Species and Toxicity - Katherine M. Dunnick; Rajalekshmi Pillai; Kelly L. Pisane; Aleksandr B. Stefaniak; Edward M. Sabolsky; Stephen S. Leonard (Biological Trace Element Research, 2015)

Immunoglobulin VH gene diversity and somatic hypermutation during SIV infection of rhesus macaques - Kejun Guo; Kalani Halemano; Kimberly Schmitt; Miki Katuwal; Yaqiong Wang; Michael S. Harper; Karl J. Heilman; Takeo Kuwata; Edward B. Stephens; Mario L. Santiago (Immunogenetics, 2015)

Geographically Isolated Wetlands: Rethinking a Misnomer - David M. Mushet; Aram J. K. Calhoun; Laurie C. Alexander; Matthew J. Cohen; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Susan C. Walls (Wetlands, 2015)

High-resolution skim genotyping by sequencing reveals the distribution of crossovers and gene conversions in Cicer arietinum and Brassica napus - Philipp E. Bayer; Pradeep Ruperao; Annaliese S. Mason; Jiri Stiller; Chon-Kit Kenneth Chan; Satomi Hayashi; Yan Long; Jinling Meng; Tim Sutton; Paul Visendi; Rajeev K. Varshney; Jacqueline Batley; et al. (Theoretical and Applied Genetics, 2015)

Human cytomegalovirus: taking the strain - Gavin W. G. Wilkinson; Andrew J. Davison; Peter Tomasec; Ceri A. Fielding; Rebecca Aicheler; Isa Murrell; Sepher Seirafian; Edward C. Y. Wang; Michael Weekes; Paul J. Lehner; Gavin S. Wilkie; Richard J. Stanton (Medical Microbiology and Immunology, 2015)

Manipulation of apoptosis and necroptosis signaling by herpesviruses - Hongyan Guo; William J. Kaiser; Edward S. Mocarski (Medical Microbiology and Immunology, 2015)

Stanley Plotkin: the bright spark of cytomegalovirus vaccines - Edward S. Mocarski (Medical Microbiology and Immunology, 2015)

Genomic regulation of senescence and innate immunity signaling in the retinal pigment epithelium - Edward Chaum; Christina S. Winborn; Sujoy Bhattacharya (Mammalian Genome, 2015)

Decadal trends of atmospheric methane in East Asia from 1991 to 2013 - Hak-Sung Kim; Yong S. Chung; Pieter P. Tans; Edward J. Dlugokencky (Air Quality, Atmosphere & Health, 2015)

New QTL alleles for quality-related traits in spring wheat revealed by RIL population derived from supernumerary × non-supernumerary spikelet genotypes - Morgan Echeverry-Solarte; Ajay Kumar; Shahryar Kianian; Senay Simsek; Mohammed S. Alamri; Eder E. Mantovani; Phillip E. McClean; Edward L. Deckard; Elias Elias; Blaine Schatz; Steven S. Xu; Mohamed Mergoum (Theoretical and Applied Genetics, 2015)

Arabinose and protocatechuate catabolism genes are important for growth of Rhizobium leguminosarum biovar viciae in the pea rhizosphere - Paula Garcia-Fraile; Jonathan C. Seaman; Ramakrishnan Karunakaran; Anne Edwards; Philip S. Poole; J. Allan Downie (Plant and Soil, 2015)

Cell-Penetrating Antimicrobial Peptides – Prospectives for Targeting Intracellular Infections - Jesper S. Bahnsen; Henrik Franzyk; Edward J. Sayers; Arwyn T. Jones; Hanne M. Nielsen (Pharmaceutical Research, 2015)

From Red Tides to Green and Brown Tides: Bloom Dynamics in a Restricted Subtropical Lagoon Under Shifting Climatic Conditions - Edward J. Phlips; Susan Badylak; Margaret A. Lasi; Robert Chamberlain; Whitney C. Green; Lauren M. Hall; Jane A. Hart; Jean C. Lockwood; Janice D. Miller; Lori J. Morris; Joel S. Steward (Estuaries and Coasts, 2015)

Climate change implications in the northern coastal temperate rainforest of North America - Colin S. Shanley; Sanjay Pyare; Michael I. Goldstein; Paul B. Alaback; David M. Albert; Colin M. Beier; Todd J. Brinkman; Rick T. Edwards; Eran Hood; Andy MacKinnon; Megan V. McPhee; Trista M. Patterson; et al. (Climatic Change, 2015)

Neck muscle afferents influence oromotor and cardiorespiratory brainstem neural circuits - I. J. Edwards; V. K. Lall; J. F. Paton; Y. Yanagawa; G. Szabo; S. A. Deuchars; J. Deuchars (Brain Structure and Function, 2015)

A continental‐scale analysis of feral cat diet in Australia - Tim S. Doherty; Robert A. Davis; Eddie J. B. van Etten; Dave Algar; Neil Collier; Chris R. Dickman; Glenn Edwards; Pip Masters; Russell Palmer; Sue Robinson (Journal of Biogeography, 2015)
Aim Reducing the impacts of feral cats ( Felis catus ) is a priority for conservation managers across the globe, and success in achieving this aim requires a detailed understanding of the species’ ecology across a broad spectrum of climatic and environmental conditions. We reviewed the diet of the feral cat across Australia and on Australian territorial islands, seeking to identify biogeographical patterns in dietary composition and diversity, and use the results to consider how feral cats may best be managed. Location Australia and its territorial islands. Methods Using 49 published and unpublished data sets, we modelled trophic diversity and the consumption of eight food groups against latitude, longitude, mean temperature, precipitation, environmental productivity and climate‐habitat regions. Results We recorded 400 vertebrate species that feral cats feed on or kill in Australia, including 28 IUCN Red List species. We found evidence of continental‐scale prey‐switching from rabbits to small mammals, previously recorded only at the local scale. The consumption of arthropods, reptiles, rabbits, rodents and medium‐sized native mammals varied with different combinations of latitude, longitude, mean annual precipitation, temperature and environmental productivity. The frequency of rodents and dasyurids in cats’ diets increased as rabbit consumption decreased. Main conclusions The feral cat is an opportunistic, generalist carnivore that consumes a diverse suite of vertebrate prey across Australia. It uses a facultative feeding strategy, feeding mainly on rabbits when they are available, but switching to other food groups when they are not. Control programmes aimed at culling rabbits could potentially decrease the availability of a preferred food source for cats and then lead to greater predation pressure on native mammals. The interplay between cat diet and prey species diversity at a continental scale is complex, and thus cat management is likely to be necessary and most effective at the local landscape level.

Rhizosphere processes are quantitatively important components of terrestrial carbon and nutrient cycles - Adrien C. Finzi; Rose Z. Abramoff; Kimberly S. Spiller; Edward R. Brzostek; Bridget A. Darby; Mark A. Kramer; Richard P. Phillips (Global Change Biology, 2015)
While there is an emerging view that roots and their associated microbes actively alter resource availability and soil organic matter ( SOM ) decomposition, the ecosystem consequences of such rhizosphere effects have rarely been quantified. Using a meta‐analysis, we show that multiple indices of microbially mediated C and nitrogen (N) cycling, including SOM decomposition, are significantly enhanced in the rhizospheres of diverse vegetation types. Then, using a numerical model that combines rhizosphere effect sizes with fine root morphology and depth distributions, we show that root‐accelerated mineralization and priming can account for up to one‐third of the total C and N mineralized in temperate forest soils. Finally, using a stoichiometrically constrained microbial decomposition model, we show that these effects can be induced by relatively modest fluxes of root‐derived C, on the order of 4% and 6% of gross and net primary production, respectively. Collectively, our results indicate that rhizosphere processes are a widespread, quantitatively important driver of SOM decomposition and nutrient release at the ecosystem scale, with potential consequences for global C stocks and vegetation feedbacks to climate.

Textural and geochemical characteristics of marine sediments in the SW Gulf of Mexico: implications for source and seasonal change - Leticia Rosales-Hoz; Arturo Carranza-Edwards; Raymundo G. Martinez-Serrano; Miguel Angel Alatorre; John S. Armstrong-Altrin (Environmental Monitoring and Assessment, 2015)

Minimizing the biodiversity impact of Neotropical oil palm development - James J. Gilroy; Graham W. Prescott; Johann S. Cardenas; Pamela González del Pliego Castañeda; Andrés Sánchez; Luis E. Rojas‐Murcia; Claudia A. Medina Uribe; Torbjørn Haugaasen; David P. Edwards (Global Change Biology, 2015)
Oil palm agriculture is rapidly expanding in the Neotropics, at the expense of a range of natural and seminatural habitats. A key question is how this expansion should be managed to reduce negative impacts on biodiversity. Focusing on the Llanos of Colombia, a mixed grassland–forest system identified as a priority zone for future oil palm development, we survey communities of ants, dung beetles, birds and herpetofauna occurring in oil palm plantations and the other principal form of agriculture in the region – improved cattle pasture – together with those of surrounding natural forests. We show that oil palm plantations have similar or higher species richness across all four taxonomic groups than improved pasture. For dung beetles, species richness in oil palm was equal to that of forest, whereas the other three taxa had highest species richness in forests. Hierarchical modelling of species occupancy probabilities indicated that oil palm plantations supported a higher proportion of species characteristic of forests than did cattle pastures. Across the bird community, occupancy probabilities within oil palm were positively influenced by increasing forest cover in a surrounding 250 m radius, whereas surrounding forest cover did not strongly influence the occurrence of other taxonomic groups in oil palm. Overall, our results suggest that the conversion of existing improved pastures to oil palm has limited negative impacts on biodiversity. As such, existing cattle pastures of the Colombian Llanos could offer a key opportunity to meet governmental targets for oil palm development without incurring significant biodiversity costs. Our results also highlight the value of preserving remnant forests within these agricultural landscapes, protecting high biodiversity and exporting avian ‘spill‐over’ effects into oil palm plantations.

Anterior–posterior dissociation of the default mode network in dogs - Sreenath P. Kyathanahally; Hao Jia; Oleg M. Pustovyy; Paul Waggoner; Ronald Beyers; John Schumacher; Jay Barrett; Edward E. Morrison; Nouha Salibi; Thomas S. Denney; Vitaly J. Vodyanoy; Gopikrishna Deshpande (Brain Structure and Function, 2015)

Worldwide phylogeography of the invasive ctenophore Mnemiopsis leidyi (Ctenophora) based on nuclear and mitochondrial DNA data - K. M. Bayha; M. H. Chang; C. L. Mariani; J. L. Richardson; D. L. Edwards; T. S. DeBoer; C. Moseley; E. Aksoy; M. B. Decker; P. M. Gaffney; G. R. Harbison; J. H. McDonald; et al. (Biological Invasions, 2015)

Use of structured expert judgment to forecast invasions by bighead and silver carp in Lake Erie - Marion E. Wittmann; Roger M. Cooke; John D. Rothlisberger; Edward S. Rutherford; Hongyan Zhang; Doran M. Mason; David M. Lodge (Conservation Biology, 2015)
Identifying which nonindigenous species will become invasive and forecasting the damage they will cause is difficult and presents a significant problem for natural resource management. Often, the data or resources necessary for ecological risk assessment are incomplete or absent, leaving environmental decision makers ill equipped to effectively manage valuable natural resources. Structured expert judgment (SEJ) is a mathematical and performance‐based method of eliciting, weighting, and aggregating expert judgments. In contrast to other methods of eliciting and aggregating expert judgments (where, for example, equal weights may be assigned to experts), SEJ weights each expert on the basis of his or her statistical accuracy and informativeness through performance measurement on a set of calibration variables. We used SEJ to forecast impacts of nonindigenous Asian carp ( Hypophthalmichthys spp.) in Lake Erie, where it is believed not to be established. Experts quantified Asian carp biomass, production, and consumption and their impact on 4 fish species if Asian carp were to become established. According to experts, in Lake Erie Asian carp have the potential to achieve biomass levels that are similar to the sum of biomasses for several fishes that are harvested commercially or recreationally. However, the impact of Asian carp on the biomass of these fishes was estimated by experts to be small, relative to long term average biomasses, with little uncertainty. Impacts of Asian carp in tributaries and on recreational activities, water quality, or other species were not addressed. SEJ can be used to quantify key uncertainties of invasion biology and also provide a decision‐support tool when the necessary information for natural resource management and policy is not available. El Uso de Juicio Experto Estructurado para Predecir Invasiones de Carpas Asiáticas en el Lago Erie

Beak and feather disease viruses circulating in Cape parrots (Poicepahlus robustus) in South Africa - Guy L. Regnard; Rutledge S. Boyes; Rowan O. Martin; Inga I. Hitzeroth; Edward P. Rybicki (Archives of Virology, 2015)

Beak and feather disease virus: correlation between viral load and clinical signs in wild Cape parrots (Poicepahlus robustus) in South Africa - Guy L. Regnard; Rutledge S. Boyes; Rowan O. Martin; Inga I. Hitzeroth; Edward P. Rybicki (Archives of Virology, 2015)

The Virtual Toxicology Service: Wearable Head-Mounted Devices for Medical Toxicology - Peter R. Chai; Roger Y. Wu; Megan L. Ranney; Paul S. Porter; Kavita M. Babu; Edward W. Boyer (Journal of Medical Toxicology, 2014)

Admixture mapping identifies a locus at 15q21.2–22.3 associated with keloid formation in African Americans - Digna R. Velez Edwards; Krystal S. Tsosie; Scott M. Williams; Todd L. Edwards; Shirley B. Russell (Human Genetics, 2014)

A high-throughput SNP array in the amphidiploid species Brassica napus shows diversity in resistance genes - Jessica Dalton-Morgan; Alice Hayward; Salman Alamery; Reece Tollenaere; Annaliese S. Mason; Emma Campbell; Dhwani Patel; Michał T. Lorenc; Bin Yi; Yan Long; Jinling Meng; Rosy Raman; et al. (Functional & Integrative Genomics, 2014)

Recovery of precision grasping after motor cortex lesion does not require forced use of the impaired hand in macaca mulatta - Warren G. Darling; Robert J. Morecraft; Diane L. Rotella; Marc A. Pizzimenti; Jizhi Ge; Kimberly S. Stilwell-Morecraft; Hongyu Zhang; Hesham Soliman; Dave Seecharan; Ian Edwards; David McNeal; Randolph J. Nudo; et al. (Experimental Brain Research, 2014)

Apparent environmental synergism drives the dynamics of Amazonian forest fragments - William F. Laurance; Ana S. Andrade; Ainhoa Magrach; José L. C. Camargo; Mason Campbell; Philip M. Fearnside; Will Edwards; Jefferson J. Valsko; Thomas E. Lovejoy; Susan G. Laurance (Ecology, 2014)
Many contemporary ecosystems are likely to be affected by multiple environmental drivers, complicating efforts to predict future changes in those ecosystems. We studied long‐term changes (1980–2012) in forest dynamics and liana (woody vine) abundance and biomass in fragmented and intact forests of the central Amazon. We did so by contrasting trends in 33 permanent 1‐ha plots near forest edges (plot center 2 or regional climate drivers that influence forest dynamics. Hence, the dynamics of Amazonian forest fragments cannot be understood simply as a consequence of forest fragmentation. Rather, the changes we observed appear to arise from an interaction of fragmentation with one or more global‐ or regional‐scale drivers affecting forest dynamics. Both sets of phenomena are evidently increasing forest dynamics and liana abundances in fragmented forests, changes that could reduce carbon storage and alter many aspects of forest ecology.

Functional analysis reveals angiogenic potential of human mesenchymal stem cells from Wharton’s jelly in dermal regeneration - Sandra S. Edwards; Gabriela Zavala; Catalina P. Prieto; Matías Elliott; Samuel Martínez; Jose T. Egaña; María R. Bono; Verónica Palma (Angiogenesis, 2014)

Effects of climate change on the physiology of giant kelp, Macrocystis pyrifera, and grazing by purple urchin, Strongylocentrotus purpuratus - Matthew B. Brown; Matthew S. Edwards; Kwang Young Kim (Algae, 2014)

Cimetidine, acetaminophen, and 1,7-dimethylxanthine, as indicators of wastewater pollution in marine sediments from Masan Bay, Korea - Minkyu Choi; Edward T. Furlong; Stephen L. Werner; Anthony S. Pait; In-Seok Lee; Hee-Gu Choi (Ocean Science Journal, 2014)

The Impact of Radiation on the GABLS3 Large-Eddy Simulation through the Night and during the Morning Transition - J. M. Edwards; S. Basu; F. C. Bosveld; A. A. M. Holtslag (Boundary-Layer Meteorology, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Non‐native acylated homoserine lactones reveal that LuxIR quorum sensing promotes symbiont stability - Sarah V. Studer; Julia A. Schwartzman; Jessica S. Ho; Grant D. Geske; Helen E. Blackwell; Edward G. Ruby (Environmental Microbiology, 2014)
Summary Quorum sensing, a group behaviour coordinated by a diffusible pheromone signal and a cognate receptor, is typical of bacteria that form symbioses with plants and animals. LuxIR ‐type N ‐acyl L‐homoserine ( AHL ) quorum sensing is common in Gram‐negative Proteobacteria , and many members of this group have additional quorum‐sensing networks. The bioluminescent symbiont V ibrio fischeri encodes two AHL signal synthases: AinS and LuxI . AinS ‐dependent quorum sensing converges with LuxI ‐dependent quorum sensing at the LuxR regulatory element. Both AinS ‐ and LuxI ‐mediated signalling are required for efficient and persistent colonization of the squid host, E uprymna scolopes . The basis of the mutualism is symbiont bioluminescence, which is regulated by both LuxI ‐ and AinS ‐dependent quorum sensing, and is essential for maintaining a colonization of the host. Here, we used chemical and genetic approaches to probe the dynamics of LuxI ‐ and AinS ‐mediated regulation of bioluminescence during symbiosis. We demonstrate that both native AHLs and non‐native AHL analogues can be used to non‐invasively and specifically modulate induction of symbiotic bioluminescence via LuxI ‐dependent quorum sensing. Our data suggest that the first day of colonization, during which symbiont bioluminescence is induced by LuxIR , is a critical period that determines the stability of the V . fischeri population once symbiosis is established.

A human rights approach to an international code of conduct for genomic and clinical data sharing - Bartha M. Knoppers; Jennifer R. Harris; Isabelle Budin-Ljøsne; Edward S. Dove (Human Genetics, 2014)

Enhancement of the accuracy of single-epoch GPS positioning for long baselines by local ionospheric modelling - M. Assiadi; S. J. Edwards; P. J. Clarke (GPS Solutions, 2014)

Special issue—organic pig production in Europe—animal health, welfare and production challenges - S. A. Edwards; A. Prunier; M. Bonde; E. A. Stockdale (Organic Agriculture, 2014)

Long‐term changes in liana abundance and forest dynamics in undisturbed Amazonian forests - William F. Laurance; Ana S. Andrade; Ainhoa Magrach; José L. C. Camargo; Jefferson J. Valsko; Mason Campbell; Philip M. Fearnside; Will Edwards; Thomas E. Lovejoy; Susan G. Laurance (Ecology, 2014)
Lianas (climbing woody vines) are important structural parasites of tropical trees and may be increasing in abundance in response to global‐change drivers. We assessed long‐term (∼14‐year) changes in liana abundance and forest dynamics within 36 1‐ha permanent plots spanning ∼600 km 2 of undisturbed rainforest in central Amazonia. Within each plot, we counted each liana stem (≥2 cm diameter) and measured its diameter at 1.3 m height, and then used these data to estimate liana aboveground biomass. An initial liana survey was completed in 1997–1999 and then repeated in 2012, using identical methods. Liana abundance in the plots increased by an average of 1.00% ± 0.88% per year, leading to a highly significant ( t = 6.58, df = 35, P t = 1.46, df = 35, P = 0.15; paired t tests). Liana size distributions shifted significantly (χ 2 = 191, df = 8, P We used long‐term data on rainfall and forest dynamics from our study site to test hypotheses about potential drivers of change in liana communities. Lianas generally increase with rainfall seasonality, but we found no significant trends over time (1997–2012) in five rainfall parameters (total annual rainfall, dry‐season rainfall, wet‐season rainfall, number of very dry months, CV of monthly rainfall). However, rates of tree mortality and recruitment have increased significantly over time in our plots, and general linear mixed‐effect models suggested that lianas were more abundant at sites with higher tree mortality and flatter topography. Rising concentrations of atmospheric CO 2 , which may stimulate liana growth, might also have promoted liana increases. Our findings clearly support the view that lianas are increasing in abundance in old‐growth tropical forests, possibly in response to accelerating forest dynamics and rising CO 2 concentrations. The aboveground biomass of trees was lowest in plots with abundant lianas, suggesting that lianas could reduce forest carbon storage and potentially alter forest dynamics if they continue to proliferate.

Species-specific bioluminescence facilitates speciation in the deep sea - Matthew P. Davis; Nancy I. Holcroft; Edward O. Wiley; John S. Sparks; W. Leo Smith (Marine Biology, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Population-based surveillance for cervical cancer precursors in three central cancer registries, United States 2009 - Elaine W. Flagg; S. Deblina Datta; Mona Saraiya; Elizabeth R. Unger; Edward Peters; Lauren Cole; Vivien W. Chen; Thomas Tucker; Mary Jane Byrne; Glenn Copeland; Won Silva; Meg Watson; et al. (Cancer Causes & Control, 2014)

Tidal migration and retention of estuarine zooplankton investigated using a particle‐tracking model - Wim J. Kimmerer; Edward S. Gross; Michael L. MacWilliams (Limnology and Oceanography, 2014)
We used hydrodynamic and particle‐tracking models to investigate vertical movement of plankton and resulting retention in the San Francisco Estuary. The hydrodynamic model was UnTRIM, a three‐dimensional, unstructured grid model, which had been calibrated to historical conditions in this estuary for 1994–1997, a period of widely varying hydrology. Intensive field studies of hydrodynamics and vertical movements of organisms during 1994–1996 provided input data for the models. The particle‐tracking model was run with 14 alternative behaviors for three 45 d periods of contrasting hydrology. The behaviors included passive behavior, several simple tidal migration patterns, and several sinking speeds. Vertical positions of migrating and sinking particles resembled those seen in the field studies for copepods and epibenthos, respectively. Passive particles were advected from the estuary at rates that depended on freshwater flow. All of the non‐passive behaviors caused retention of the particles in the low‐salinity region of the estuary under some flow conditions. Tidal migration was very effective at maintaining position, but model results and a re‐examination of the field data suggested that migration speed should increase with increasing freshwater flow. Continuous sinking was also effective at retention, particularly in deep areas of low tidal velocity. We conclude that the vertical distributions observed in the field studies were a result of active patterns of movement, that these patterns can result in retention, and that retention in a bathymetrically complex estuary can be understood only in the context of the full time‐varying three‐dimensional flow field.

Oceanic currents, not land masses, maintain the genetic structure of the mangrove Rhizophora mucronata Lam. (Rhizophoraceae) in Southeast Asia - Alison K. S. Wee; Koji Takayama; Takeshi Asakawa; Bijoy Thompson; Onrizal; Sarawood Sungkaew; Nguyen Xuan Tung; M. Nazre; Khin Khin Soe; Hugh T. W. Tan; Yasuyuki Watano; Shigeyuki Baba; et al. (Journal of Biogeography, 2014)
Aim Mangroves are intertidal plants with sea‐dispersed propagules, hence their population structure can offer valuable insights into the biogeographical processes driving population subdivision in coastal species. In this study, we used molecular markers and ocean circulation simulations to examine the effects of ocean currents and land masses on the genetic structure of the major mangrove species Rhizophora mucronata . Location Southeast Asia. Methods We assessed the genetic structure of 13 R. mucronata populations from continental Southeast Asia and Sumatra using 10 microsatellite loci. We first examined the relative effects of geographical distance and land mass (the Malay Peninsula) in shaping the genetic structure of R. mucronata in Southeast Asia. We then characterized the genetic structure of R. mucronata and compared it to the simulated ocean circulation patterns within our study region. Results Despite the low genetic diversity, significant genetic structuring was detected across R. mucronata populations. Contrary to observations on other mangrove species, genetic differentiation in R. mucronata was not found across the coasts of the Malay Peninsula, nor was it correlated with geographical distance. Instead, the most distinct genetic discontinuity was found at the boundary between the Andaman Sea and the Malacca Strait, and this can be explained by the prevailing ocean currents in this region. Main conclusions Our study presents novel evidence that the genetic structure of R. mucronata is maintained by ocean current‐facilitated propagule dispersal.

Computational Identification and Comparative Analysis of miRNAs in Wheat Group 7 Chromosomes - Pingchuan Deng; Xiaojun Nie; Le Wang; Licao Cui; Peixun Liu; Wei Tong; Siddanagouda S. Biradar; David Edwards; Paul Berkman; Hana Šimková; Jaroslav Doležel; Mincheng Luo; et al. (Plant Molecular Biology Reporter, 2014)

Cold habituation does not improve manual dexterity during rest and exercise in 5 °C - Matthew D. Muller; Yongsuk Seo; Chul-Ho Kim; Edward J. Ryan; Brandon S. Pollock; Keith J. Burns; Ellen L. Glickman (International Journal of Biometeorology, 2014)

Persistence of 2,4-D and its Effects on Benthic Macroinvertebrates Following Spring Treatment of Eurasian Watermilfoil, Myriophyllum spicatum L. in Two Lakes in Southeastern Wisconsin, USA - E. A. Harrahy; D. S. Edwards; C. J. Hedman (Bulletin of Environmental Contamination and Toxicology, 2014)

A multi‐genome analysis approach enables tracking of the invasion of a single R ussian wheat aphid ( D iuraphis noxia ) clone throughout the N ew W orld - B. Zhang; O. Edwards; L. Kang; S. Fuller (Molecular Ecology, 2014)
This study investigated the population genetics, demographic history and pathway of invasion of the Russian wheat aphid ( RWA ) from its native range in Central Asia, the Middle East and Europe to South Africa and the Americas. We screened microsatellite markers, mitochondrial DNA and endosymbiont genes in 504 RWA clones from nineteen populations worldwide. Following pathway analyses of microsatellite and endosymbiont data, we postulate that Turkey and Syria were the most likely sources of invasion to Kenya and South Africa, respectively. Furthermore, we found that one clone transferred between South Africa and the Americas was most likely responsible for the New World invasion. Finally, endosymbiont DNA was found to be a high‐resolution population genetic marker, extremely useful for studies of invasion over a relatively short evolutionary history time frame. This study has provided valuable insights into the factors that may have facilitated the recent global invasion by this damaging pest.

Normal eyeblink classical conditioning in patients with fixed dystonia - Sabine Janssen; Lidwien C. Veugen; Britt S. Hoffland; Panagiotis Kassavetis; Diana E. van Rooijen; Dick F. Stegeman; Mark J. Edwards; Jacobus J. van Hilten; Bart P. van de Warrenburg (Experimental Brain Research, 2014)

Water, sediment, and nutrient runoff from urban lawns established on disturbed subsoil or topsoil and managed with inorganic or organic fertilizers - Zhiqiang Cheng; Edward L. McCoy; Parwinder S. Grewal (Urban Ecosystems, 2014)

Phosgene Exposure: A Case of Accidental Industrial Exposure - Lewis S. Hardison; Edward Wright; Anthony F. Pizon (Journal of Medical Toxicology, 2014)

The global contribution of forage fish to marine fisheries and ecosystems - Ellen K Pikitch; Konstantine J Rountos; Timothy E Essington; Christine Santora; Daniel Pauly; Reg Watson; Ussif R Sumaila; P Dee Boersma; Ian L Boyd; David O Conover; Philippe Cury; Selina S Heppell; et al. (Fish and Fisheries, 2014)
Forage fish play a pivotal role in marine ecosystems and economies worldwide by sustaining many predators and fisheries directly and indirectly. We estimate global forage fish contributions to marine ecosystems through a synthesis of 72 published E copath models from around the world. Three distinct contributions of forage fish were examined: (i) the ecological support service of forage fish to predators in marine ecosystems, (ii) the total catch and value of forage fisheries and (iii) the support service of forage fish to the catch and value of other commercially targeted predators. Forage fish use and value varied and exhibited patterns across latitudes and ecosystem types. Forage fish supported many kinds of predators, including fish, seabirds, marine mammals and squid. Overall, forage fish contribute a total of about $16.9 billion USD to global fisheries values annually, i.e. 20% of the global ex‐vessel catch values of all marine fisheries combined. While the global catch value of forage fisheries was $5.6 billion, fisheries supported by forage fish were more than twice as valuable ($11.3 billion). These estimates provide important information for evaluating the trade‐offs of various uses of forage fish across ecosystem types, latitudes and globally. We did not estimate a monetary value for supportive contributions of forage fish to recreational fisheries or to uses unrelated to fisheries, and thus the estimates of economic value reported herein understate the global value of forage fishes.

Non-invasive Cerebellar Stimulation—a Consensus Paper - G. Grimaldi; G. P. Argyropoulos; A. Boehringer; P. Celnik; M. J. Edwards; R. Ferrucci; J. M. Galea; S. J. Groiss; K. Hiraoka; P. Kassavetis; E. Lesage; M. Manto; et al. (The Cerebellum, 2014)

Biological interactions maintain the boundaries between kelp forests and urchin barrens in the Aleutian Archipelago - Brenda Konar; Matthew S. Edwards; James A. Estes (Hydrobiologia, 2014)

The challenges of conducting environmental research on privately owned land - Christina L. M. Hargiss; Edward S. DeKeyser (Environmental Monitoring and Assessment, 2014)

Potential Impacts and Management Implications of Climate Change on Tampa Bay Estuary Critical Coastal Habitats - Edward T. Sherwood; Holly S. Greening (Environmental Management, 2014)

Natural antisense transcripts of UL123 packaged in human cytomegalovirus virions - Cui-Qing Yang; Ling-Feng Miao; Xing Pan; Cong-Cong Wu; Simon Rayner; Edward S. Mocarski; Han-Qing Ye; Min-Hua Luo (Archives of Virology, 2014)

Land‐sharing versus land‐sparing logging: reconciling timber extraction with biodiversity conservation - David P. Edwards; James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; David J. R. Andrews; Mia A. Derhé; Teegan D. S. Docherty; Wayne W. Hsu; Simon L. Mitchell; Takahiro Ota; Leah J. Williams; et al. (Global Change Biology, 2014)
Selective logging is a major driver of rainforest degradation across the tropics. Two competing logging strategies are proposed to meet timber demands with the least impact on biodiversity: land sharing, which combines timber extraction with biodiversity protection across the concession; and land sparing, in which higher intensity logging is combined with the protection of intact primary forest reserves. We evaluate these strategies by comparing the abundances and species richness of birds, dung beetles and ants in Borneo, using a protocol that allows us to control for both timber yield and net profit across strategies. Within each taxonomic group, more species had higher abundances with land‐sparing than land‐sharing logging, and this translated into significantly higher species richness within land‐sparing concessions. Our results are similar when focusing only on species found in primary forest and restricted in range to Sundaland, and they are independent of the scale of sampling. For each taxonomic group, land‐sparing logging was the most promising strategy for maximizing the biological value of logging operations.

Mining conifers’ mega-genome using rapid and efficient multiplexed high-throughput genotyping-by-sequencing (GBS) SNP discovery platform - Charles Chen; Sharon E. Mitchell; Robert J. Elshire; Edward S. Buckler; Yousry A. El-Kassaby (Tree Genetics & Genomes, 2013)

Discordant results between biochemical and molecular transthyretin assays: lessons learned from a unique testing algorithm at the Mayo Clinic - HONEY V. REDDI; BRITTANY C. THOMAS; KURT S. WILLKOMM; MATTHEW J. FERBER; KANDELARIA M. RUMILLA; KIMIYO M. RAYMOND; JOHN F. O’BRIEN; W. EDWARD HIGHSMITH (Journal of Genetics, 2013)

Development of 11 polymorphic microsatellite markers for Xylocarpus granatum (Meliaceae) using next-generation sequencing technology - Yuki Tomizawa; Yoshimi Shinmura; Alison K. S. Wee; Koji Takayama; Takeshi Asakawa; Orlex Baylen Yllano; Severino Garengo Salmo; Erwin Riyanto Ardli; Nguyen Xuan Tung; Norhaslinda Binti Malekal; Onrizal; Sankararamasubramanian Halasya Meenakshisundaram; et al. (Conservation Genetics Resources, 2013)

Human proximity and habitat fragmentation are key drivers of the rangewide bonobo distribution - Jena R. Hickey; Janet Nackoney; Nathan P. Nibbelink; Stephen Blake; Aime Bonyenge; Sally Coxe; Jef Dupain; Maurice Emetshu; Takeshi Furuichi; Falk Grossmann; Patrick Guislain; John Hart; et al. (Biodiversity and Conservation, 2013)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Parkinson disease loci in the mid-western Amish - M. F. Davis; A. C. Cummings; L. N. D’Aoust; L. Jiang; D. R. Velez Edwards; R. Laux; L. Reinhart-Mercer; D. Fuzzell; W. K. Scott; M. A. Pericak-Vance; S. L. Lee; J. L. Haines (Human Genetics, 2013)

Estuarine ecosystem function response to flood and drought in a shallow, semiarid estuary: Nitrogen cycling and ecosystem metabolism - Denise A. Bruesewitz; Wayne S. Gardner; Rae F. Mooney; Lindsey Pollard; Edward J. Buskey (Limnology and Oceanography, 2013)
We quantified sediment‐water interface and water column nitrogen (N) transformation rates seasonally over the course of a year that incorporated a major storm event and a period of prolonged riverine base flow in Copano Bay, Texas, a shallow, productive estuary in the western Gulf of Mexico. We calculated daily rates of gross primary production (GPP), community respiration (CR), and net ecosystem production (NEP) in Copano Bay to examine carbon (C) cycling over the course of the year. These metrics of estuarine ecosystem function indicated that the estuary switched from a net sink for N during floods to a net source of N during droughts while sustaining high rates of primary production throughout the year. The estuary became a net sink for N as a result of increased denitrification rates following a storm event. Both GPP and CR increased immediately following a flood event, and the system was driven to net heterotrophy. Copano Bay became a net source of N during periods of prolonged base flow via increased N fixation rates. Internal N cycling became increasingly important during periods of base flow, including increased rates of dissimilatory nitrate reduction to ammonium. This internal N cycling sustained production during periods of drought, when GPP ≈ CR. Both CR and NEP were linked to nutrient export from the inflowing rivers. N and C cycles were tightly linked but became decoupled briefly as a result of inputs of nutrients and organic matter during the period after a major storm event.

Acetochlor Persistence in Surface and Subsurface Soil Samples - Rubem S. Oliveira; William C. Koskinen; Carrie D. Graff; James L. Anderson; David J. Mulla; Edward A. Nater; Diego G. Alonso (Water, Air, & Soil Pollution, 2013)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Holarctic phylogeography of the testate amoeba H yalosphenia papilio (Amoebozoa: Arcellinida) reveals extensive genetic diversity explained more by environment than dispersal limitation - Thierry J. Heger; Edward A. D. Mitchell; Brian S. Leander (Molecular Ecology, 2013)
Although free‐living protists play essential roles in aquatic and soil ecology, little is known about their diversity and phylogeography, especially in terrestrial ecosystems. We used mitochondrial cytochrome c oxidase subunit 1 (COI) gene sequences to investigate the genetic diversity and phylogeography of the testate amoeba morphospecies Hyalosphenia papilio in 42 Sphagnum (moss) ‐ dominated peatlands in North America, Europe and Asia. Based on ≥1% sequence divergence threshold, our results from single‐cell PCRs of 301 individuals revealed 12 different genetic lineages and both the general mixed Yule‐coalescent (GMYC) model and the automatic barcode gap discovery (ABGD) methods largely support the hypothesis that these 12 H. papilio lineages correspond to evolutionary independent units (i.e. cryptic species). Our data also showed a high degree of genetic heterogeneity within different geographical regions. Furthermore, we used variation partitioning based on partial redundancy analyses ( pRDA ) to evaluate the contributions of climate and dispersal limitations on the distribution patterns of the different genetic lineages. The largest fraction of the variation in genetic lineage distribution was attributed to purely climatic factors (21%), followed by the joint effect of spatial and bioclimatic factors (13%), and a purely spatial effect (3%). Therefore, these data suggest that the distribution patterns of H. papilio genetic lineages in the Northern Hemisphere are more influenced by climatic conditions than by dispersal limitations.

Reliable, verifiable and efficient monitoring of biodiversity via metabarcoding - Yinqiu Ji; Louise Ashton; Scott M. Pedley; David P. Edwards; Yong Tang; Akihiro Nakamura; Roger Kitching; Paul M. Dolman; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; Wayne W. Hsu; et al. (Ecology Letters, 2013)
To manage and conserve biodiversity, one must know what is being lost, where, and why, as well as which remedies are likely to be most effective. Metabarcoding technology can characterise the species compositions of mass samples of eukaryotes or of environmental DNA . Here, we validate metabarcoding by testing it against three high‐quality standard data sets that were collected in Malaysia (tropical), China (subtropical) and the United Kingdom (temperate) and that comprised 55,813 arthropod and bird specimens identified to species level with the expenditure of 2,505 person‐hours of taxonomic expertise. The metabarcode and standard data sets exhibit statistically correlated alpha‐ and beta‐diversities, and the two data sets produce similar policy conclusions for two conservation applications: restoration ecology and systematic conservation planning. Compared with standard biodiversity data sets, metabarcoded samples are taxonomically more comprehensive, many times quicker to produce, less reliant on taxonomic expertise and auditable by third parties, which is essential for dispute resolution.

Trophic Flexibility and the Persistence of Understory Birds in Intensively Logged Rainforest - DAVID P. EDWARDS; PAUL WOODCOCK; ROB J. NEWTON; FELICITY A. EDWARDS; DAVID J. R. ANDREWS; TEEGAN D. S. DOCHERTY; SIMON L. MITCHELL; TAKAHIRO OTA; SUZAN BENEDICK; SIMON H. BOTTRELL; KEITH C. HAMER (Conservation Biology, 2013)
Effects of logging on species composition in tropical rainforests are well known but may fail to reveal key changes in species interactions. We used nitrogen stable‐isotope analysis of 73 species of understory birds to quantify trophic responses to repeated intensive logging of rainforest in northern Borneo and to test 4 hypotheses: logging has significant effects on trophic positions and trophic‐niche widths of species, and the persistence of species in degraded forest is related to their trophic positions and trophic‐niche widths in primary forest. Species fed from higher up the food chain and had narrower trophic‐niche widths in degraded forest. Species with narrow trophic‐niche widths in primary forest were less likely to persist after logging, a result that indicates a higher vulnerability of dietary specialists to local extinction following habitat disturbance. Persistence of species in degraded forest was not related to a species’ trophic position. These results indicate changes in trophic organization that were not apparent from changes in species composition and highlight the importance of focusing on trophic flexibility over the prevailing emphasis on membership of static feeding guilds. Our results thus support the notion that alterations to trophic organization and interactions within tropical forests may be a pervasive and functionally important hidden effect of forest degradation. Flexibilidad Trófica y la Persistencia de Aves de Sotobosque en un Bosque Lluvioso Talado Intensivamente

Performance of a Multi-disciplinary Emergency Department Observation Protocol for Acetaminophen Overdose - Gillian A. Beauchamp; Kimberly W. Hart; Christopher J. Lindsell; Michael S. Lyons; Edward J. Otten; Carol L. Smith; Michael J. Ward; Stewart W. Wright (Journal of Medical Toxicology, 2013)

Genetic and experimental evidence for a mixed‐age, mixed‐origin bank of kelp microscopic stages in southern California - Laura T. Carney; Andrew J. Bohonak; Matthew S. Edwards; Filipe Alberto (Ecology, 2013)
Laboratory studies have demonstrated that the microscopic stages of kelps can rapidly resume development from a delayed state. Like terrestrial seeds or aquatic resting eggs, banks of delayed kelp stages may supplement population recovery after periods of stress, playing an important role for kelp populations that experience adult sporophyte absences due to seasonal or interannual disturbances. We found that removing the microscopic stages from natural rock substratum could prevent the appearance of juvenile kelp sporophytes for three months and the establishment of a diverse kelp assemblage for over four months within a southern California kelp forest. Juveniles were observed within one month in plots where microscopic stages were left intact, which may confer an advantage for the resulting sporophytes as they attain larger sizes before later recruiting neighbors. Microsatellite diversity was high (expected heterozygosity H E ≈ 0.9) for juveniles and adults within our sites. Using a microsatellite‐based parentage analysis for the dominant kelp, Macrocystis pyrifera , we estimated that a portion of the new M. pyrifera sporophyte recruits had originated from their parents at least seven months after their parents had disappeared. Similar delay durations have been demonstrated in recent laboratory studies. Additionally, our results suggest that zoospore dispersal distances >50 m may be supported by including additional microsatellite loci in the analysis. We propose a mixed‐age and, potentially, a mixed‐origin bank of M. pyrifera gametophytes promotes maximal genetic diversity in recovering populations and reduces population genetic subdivision and self‐fertilization rates for intact populations by promoting the survival of zoospores dispersed >10 m and during inhospitable environmental conditions.

Putative Agmatinase Inhibitor for Hypoxic-Ischemic New Born Brain Damage - John E. Piletz; Stephanie Klenotich; Ken S. Lee; Qian Long Zhu; Edward Valente; Michael A. Collins; Vyvyca Jones; Soeb Nam Lee; Feng Yangzheng (Neurotoxicity Research, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Identification of serum analytes and metabolites associated with aerobic capacity - Michael S. Lustgarten; Lori Lyn Price; Tanya Logvinenko; Christos Hatzis; Nandan Padukone; Nicholas V. Reo; Edward M. Phillips; Dylan Kirn; John Mills; Roger A. Fielding (European Journal of Applied Physiology, 2013)

Development of Fusarium langsethiae in commercial cereal production - N. Opoku; M. Back; S. G. Edwards (European Journal of Plant Pathology, 2013)

Prospective cohort studies of bowel movement frequency and laxative use and colorectal cancer incidence in US women and men - Xuehong Zhang; Kana Wu; Eunyoung Cho; Jing Ma; Andrew T. Chan; Xiang Gao; Walter C. Willett; Charles S. Fuchs; Edward L. Giovannucci (Cancer Causes & Control, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Prediagnostic plasma vitamin B6 (pyridoxal 5′-phosphate) and survival in patients with colorectal cancer - Youjin Je; Jung Eun Lee; Jing Ma; Xuehong Zhang; Eunyoung Cho; Bernard Rosner; Jacob Selhub; Charles S. Fuchs; Jeffrey Meyerhardt; Edward Giovannucci (Cancer Causes & Control, 2013)

Fungal palaeodiversity revealed using high‐throughput metabarcoding of ancient DNA from arctic permafrost - Eva Bellemain; Marie L. Davey; Håvard Kauserud; Laura S. Epp; Sanne Boessenkool; Eric Coissac; Jozsef Geml; Mary Edwards; Eske Willerslev; Galina Gussarova; Pierre Taberlet; Christian Brochmann (Environmental Microbiology, 2013)
Summary The taxonomic and ecological diversity of ancient fungal communities was assessed by combining next generation sequencing and metabarcoding of DNA preserved in permafrost. Twenty‐six sediment samples dated 16 000–32 000 radiocarbon years old from two localities in S iberia were analysed for fungal ITS . We detected 75 fungal OTU s from 21 orders representing three phyla, although rarefaction analyses suggested that the full diversity was not recovered despite generating an average of 6677 ± 3811 (mean ± SD ) sequences per sample and that preservation bias likely has considerable effect on the recovered DNA . Most OTU s (75.4%) represented ascomycetes. Due to insufficient sequencing depth, DNA degradation and putative preservation biases in our samples, the recovered taxa probably do not represent the complete historic fungal community, and it is difficult to determine whether the fungal communities varied geographically or experienced a composition shift within the period of 16 000–32 000 bp . However, annotation of OTU s to functional ecological groups provided a wealth of information on the historic communities. About one‐third of the OTUs are presumed plant‐associates (pathogens, saprotrophs and endophytes) typical of graminoid‐ and forb‐rich habitats. We also detected putative insect pathogens, coprophiles and keratinophiles likely associated with ancient insect and herbivore faunas. The detection of putative insect pathogens, mycoparasites, aquatic fungi and endophytes broadens our previous knowledge of the diversity of fungi present in Beringian palaeoecosystems. A large group of putatively psychrophilic/psychrotolerant fungi was also detected, most likely representing a modern, metabolically active fungal community.

Interspecific effects of 4A-DNT (4-amino-2,6-dinitrotoluene) and RDX (1,3,5-trinitro-1,3,5-triazine) in Japanese quail, Northern bobwhite, and Zebra finch - Michael J. Quinn; Terry L. Hanna; Alicia A. Shiflett; Craig A. McFarland; Michelle E. Cook; Mark S. Johnson; Kurt A. Gust; Edward J. Perkins (Ecotoxicology, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

The nature and formation of cristobalite at the Soufrière Hills volcano, Montserrat: implications for the petrology and stability of silicic lava domes - Claire J. Horwell; Ben J. Williamson; Edward W. Llewellin; David E. Damby; Jennifer S. Le Blond (Bulletin of Volcanology, 2013)

Interannual variation in effective number of breeders and estimation of effective population size in long‐lived iteroparous lake sturgeon ( Acipenser fulvescens ) - Thuy Yen Duong; Kim T. Scribner; Patrick S. Forsythe; James A. Crossman; Edward A. Baker (Molecular Ecology, 2013)
Quantifying interannual variation in effective adult breeding number ( N b ) and relationships between N b , effective population size ( N e ), adult census size ( N ) and population demographic characteristics are important to predict genetic changes in populations of conservation concern. Such relationships are rarely available for long‐lived iteroparous species like lake sturgeon ( Acipenser fulvescens ). We estimated annual N b and generational N e using genotypes from 12 microsatellite loci for lake sturgeon adults ( n = 796) captured during ten spawning seasons and offspring ( n = 3925) collected during larval dispersal in a closed population over 8 years. Inbreeding and variance N b estimated using mean and variance in individual reproductive success derived from genetically identified parentage and using linkage disequilibrium ( LD ) were similar within and among years (interannual range of N b across estimators: 41–205). Variance in reproductive success and unequal sex ratios reduced N b relative to N on average 36.8% and 16.3%, respectively. Interannual variation in N b /N ratios (0.27–0.86) resulted from stable N and low standardized variance in reproductive success due to high proportions of adults breeding and the species' polygamous mating system, despite a 40‐fold difference in annual larval production across years (437–16 417). Results indicated environmental conditions and features of the species' reproductive ecology interact to affect demographic parameters and N b /N . Estimates of N e based on three single‐sample estimators, including LD , approximate Bayesian computation and sibship assignment, were similar to annual estimates of N b . Findings have important implications concerning applications of genetic monitoring in conservation planning for lake sturgeon and other species with similar life histories and mating systems.

Building the niche through time: using 13,000 years of data to predict the effects of climate change on three tree species in Europe - L. Maiorano; R. Cheddadi; N. E. Zimmermann; L. Pellissier; B. Petitpierre; J. Pottier; H. Laborde; B. I. Hurdu; P. B. Pearman; A. Psomas; J. S. Singarayer; O. Broennimann; et al. (Global Ecology and Biogeography, 2013)
Aim Species distribution models (SDMs) based on current species ranges underestimate the potential distribution when projected in time and/or space. A multi‐temporal model calibration approach has been suggested as an alternative, and we evaluate this using 13,000 years of data. Location Europe. Methods We used fossil‐based records of presence for Picea abies , Abies alba and Fagus sylvatica and six climatic variables for the period 13,000 to 1000 yr bp . To measure the contribution of each 1000‐year time step to the total niche of each species (the niche measured by pooling all the data), we employed a principal components analysis (PCA) calibrated with data over the entire range of possible climates. Then we projected both the total niche and the partial niches from single time frames into the PCA space, and tested if the partial niches were more similar to the total niche than random. Using an ensemble forecasting approach, we calibrated SDMs for each time frame and for the pooled database. We projected each model to current climate and evaluated the results against current pollen data. We also projected all models into the future. Results Niche similarity between the partial and the total‐SDMs was almost always statistically significant and increased through time. SDMs calibrated from single time frames gave different results when projected to current climate, providing evidence of a change in the species realized niches through time. Moreover, they predicted limited climate suitability when compared with the total‐SDMs. The same results were obtained when projected to future climates. Main conclusions The realized climatic niche of species differed for current and future climates when SDMs were calibrated considering different past climates. Building the niche as an ensemble through time represents a way forward to a better understanding of a species' range and its ecology in a changing climate.

Estimating global arthropod species richness: refining probabilistic models using probability bounds analysis - Andrew J. Hamilton; Vojtech Novotný; Edward K. Waters; Yves Basset; Kurt K. Benke; Peter S. Grimbacher; Scott E. Miller; G. Allan Samuelson; George D. Weiblen; Jian D. L. Yen; Nigel E. Stork (Oecologia, 2013)

Fine map of the Gct1 spontaneous ovarian granulosa cell tumor locus - Kerri N. Smith; Sarah J. Halfyard; Edward S. Yaskowiak; Kathryn L. Shultz; Wesley G. Beamer; Ann M. Dorward (Mammalian Genome, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Trait-dependent declines of species following conversion of rain forest to oil palm plantations - Michael J. M. Senior; Keith C. Hamer; Simon Bottrell; David P. Edwards; Tom M. Fayle; Jennifer M. Lucey; Peter J. Mayhew; Robert Newton; Kelvin S.-H. Peh; Frederick H. Sheldon; Christopher Stewart; Alison R. Styring; et al. (Biodiversity and Conservation, 2013)

Isolation and characterization of 14 microsatellite markers for Rhizophora mucronata (Rhizophoraceae) and their potential use in range-wide population studies - Yoshimi Shinmura; Alison K. S. Wee; Koji Takayama; Sankararamasubramanian Halasya Meenakshisundaram; Takeshi Asakawa; Onrizal; Bayu Adjie; Erwin Riyanto Ardli; Sarawood Sungkaew; Norhaslinda Binti Malekal; Nguyen Xuan Tung; Severino G. Salmo III; et al. (Conservation Genetics Resources, 2012)

Modelling streamflow trends for a watershed with limited data: case of the Litani basin, Lebanon - Hamzeh H. Ramadan; R. Edward Beighley; Amruthur S. Ramamurthy (Hydrological Sciences Journal, 2012)

Application of large-scale sequencing to marker discovery in plants - Robert J Henry; Mark Edwards; Daniel L E Waters; Gopala Krishnan S; Peter Bundock; Timothy R Sexton; Ardashir K Masouleh; Catherine J Nock; Julie Pattemore (Journal of Biosciences, 2012)

Multiple environmental stressors elicit complex interactive effects in the western fence lizard (Sceloporus occidentalis) - Craig A. McFarland; Larry G. Talent; Michael J. Quinn; Matthew A. Bazar; Mitchell S. Wilbanks; Mandana Nisanian; Robert M. Gogal; Mark S. Johnson; Edward J. Perkins; Kurt A. Gust (Ecotoxicology, 2012)

Regular dental visits are associated with earlier stage at diagnosis for oral and pharyngeal cancer - Scott M. Langevin; Dominique S. Michaud; Melissa Eliot; Edward S. Peters; Michael D. McClean; Karl T. Kelsey (Cancer Causes & Control, 2012)

Mathematical Simulation of Membrane Protein Clustering for Efficient Signal Transduction - Krishnan Radhakrishnan; Ádám Halász; Meghan M. McCabe; Jeremy S. Edwards; Bridget S. Wilson (Annals of Biomedical Engineering, 2012)

Microbial cell budgets of an A rctic glacier surface quantified using flow cytometry - T. D. L. Irvine‐Fynn; A. Edwards; S. Newton; H. Langford; S. M. Rassner; J. Telling; A. M. Anesio; A. J. Hodson (Environmental Microbiology, 2012)
Summary Uncertainty surrounds estimates of microbial cell and organic detritus fluxes from glacier surfaces. Here, we present the first enumeration of biological particles draining from a supraglacial catchment, on M idtre L ovénbreen ( S valbard) over 36 days. A stream cell flux of 1.08 × 10 7 cells m −2 h −1 was found, with strong inverse, non‐linear associations between water discharge and biological particle concentrations. Over the study period, a significant decrease in cell‐like particles exhibiting 530 nm autofluorescence was noted. The observed total fluvial export of ∼ 7.5 × 10 14 cells equates to 15.1–72.7 g C , and a large proportion of these cells were small ( 7 cells m −2 h −1 . Analysis of surface ice cores revealed cell concentrations comparable to previous studies (6 × 10 4 cells ml −1 ) but, critically, showed no variation with depth in the uppermost 1 m. The physical retention and growth of particulates at glacier surfaces has two implications: to contribute to ice mass thinning through feedbacks altering surface albedo, and to potentially seed recently deglaciated terrain with cells, genes and labile organic matter. This highlights the merit of further study into glacier surface hydraulics and biological processes.

The Gauss–Listing geopotential value W 0 and its rate from altimetric mean sea level and GRACE - N. Dayoub; S. J. Edwards; P. Moore (Journal of Geodesy, 2012)

Development and characterization of 15 polymorphic microsatellite loci in Sonneratia alba (Lythraceae) using next-generation sequencing - Yoshimi Shinmura; Alison K. S. Wee; Koji Takayama; Takeshi Asakawa; Orlex Baylen Yllano; Severino G. Salmo; Erwin Riyanto Ardli; Nguyen Xuan Tung; Norhaslinda Binti Malekal; Onrizal; Sankararamasubramanian Halasya Meenakshisundaram; Sarawood Sungkaew; et al. (Conservation Genetics Resources, 2012)

Classifying area-restricted search (ARS) using a partial sum approach - Andrew S. Knell; Edward A. Codling (Theoretical Ecology, 2012)

Effects of vicariant barriers, habitat stability, population isolation and environmental features on species divergence in the south‐western Australian coastal reptile community - D. L. EDWARDS; J. S. KEOGH; L. L. KNOWLES (Molecular Ecology, 2012)
Identifying explicit hypotheses regarding the factors determining genetic structuring within species can be difficult, especially in species distributed in historically dynamic regions. To contend with these challenges, we use a framework that combines species distribution models, environmental data and multi‐locus genetic data to generate and explore phylogeographic hypotheses for reptile species occupying the coastal sand‐dune and sand‐plain habitats of the south‐western Australian biodiversity hotspot, a community which has both a high diversity of endemics and has varied dramatically in spatial extent over time. We use hierarchical amova , summary statistic and distance‐based analyses to explicitly test specific phylogeographic hypotheses. Namely, we test if biogeographic vicariance across barriers, habitat stability, population isolation along a linear habitat or fragmentation across different environments can explain genetic divergence within five co‐distributed squamate reptile species. Our results show that patterns of genetic variation reflect complex and species‐specific interactions related to the spatial distribution of habitats present currently and during repeated glacial minima, as opposed to being associated with historical factors such as habitat stability between glacial and inter‐glacial periods or vicariant barriers. We suggest that the large impact of habitat characteristics over time (i.e. relative levels of habitat connectivity, climatic gradients and spatial heterogeneity of soil types) reflects the ecological restrictions of the sand‐dune and sand‐plain reptile communities and may explain the lack of concordance across taxa. The study demonstrates the general utility of the approach for assemblage‐level, as well as single species, phylogeographic study, including its usefulness for exploring biologically informed hypotheses about what factors have influenced patterns of genetic variation.

The effect of experimental warming and precipitation change on proteolytic enzyme activity: positive feedbacks to nitrogen availability are not universal - Edward R. Brzostek; John M. Blair; Jeffrey S. Dukes; Serita D. Frey; Sarah E. Hobbie; Jerry M. Melillo; Robert J. Mitchell; Elise Pendall; Peter B. Reich; Gaius R. Shaver; Artur Stefanski; Mark G. Tjoelker; et al. (Global Change Biology, 2012)
Nitrogen regulates the E arth's climate system by constraining the terrestrial sink for atmospheric CO 2 . Proteolytic enzymes are a principal driver of the within‐system cycle of soil nitrogen, yet there is little to no understanding of their response to climate change. Here, we use a single methodology to investigate potential proteolytic enzyme activity in soils from 16 global change experiments. We show that regardless of geographical location or experimental manipulation (i.e., temperature, precipitation, or both), all sites plotted along a single line relating the response ratio of potential proteolytic activity to soil moisture deficit, the difference between precipitation and evapotranspiration. In particular, warming and reductions in precipitation stimulated potential proteolytic activity in mesic sites – temperate and boreal forests, arctic tundra – whereas these manipulations suppressed potential activity in dry grasslands. This study provides a foundation for a simple representation of the impacts of climate change on a central component of the nitrogen cycle.

Incorporating invasive weeds into a plant indicator method (LakeSPI) to assess lake ecological condition - M. D. de Winton; J. S. Clayton; T. Edwards (Hydrobiologia, 2012)

Evolutionary genetics of the human Rh blood group system - George H. Perry; Yali Xue; Richard S. Smith; Wynn K. Meyer; Minal Çalışkan; Omar Yanez-Cuna; Arthur S. Lee; María Gutiérrez-Arcelus; Carole Ober; Edward J. Hollox; Chris Tyler-Smith; Charles Lee (Human Genetics, 2012)

Muscle power failure in mobility-limited older adults: preserved single fiber function despite lower whole muscle size, quality and rate of neuromuscular activation - Kieran F. Reid; Gheorghe Doros; David J. Clark; Carolynn Patten; Robert J. Carabello; Gregory J. Cloutier; Edward M. Phillips; Lisa S. Krivickas; Walter R. Frontera; Roger A. Fielding (European Journal of Applied Physiology, 2012)

A dietary pattern that is associated with C-peptide and risk of colorectal cancer in women - Teresa T. Fung; Frank B. Hu; Matthias Schulze; Michael Pollak; Tianying Wu; Charles S. Fuchs; Edward Giovannucci (Cancer Causes & Control, 2012)

Metabolic syndrome in mice induced by expressing a transcriptional activator in adipose tissue - Liwen Zhang; Yuchen Zhou; Amber Ying Zhu; Xiang-qing Li; Steven S. Mundt; Ling Gao; JeanMarie Lisnock; Melba Hernandez; Magdalena Alonso-Galicia; Martin S. Springer; Edward A. O’Neill; Bruce L. Daugherty; et al. (Transgenic Research, 2012)

Phosphite utilization by the marine picocyanobacterium Prochlorococcus MIT9301 - Asunción Martínez; Marcia S. Osburne; Adrian K. Sharma; Edward F. DeLong; Sallie W. Chisholm (Environmental Microbiology, 2012)
Summary Primary productivity in the ocean's oligotrophic regions is often limited by phosphorus (P) availability. In low phosphate environments, the prevalence of many genes involved in P acquisition is elevated, suggesting that the ability to effectively access diverse P sources is advantageous for organisms inhabiting these regions. Prochlorococcus, the numerically dominant primary producer in the oligotrophic ocean, encodes high‐affinity P transporters, P regulatory proteins and enzymes for organic phosphate utilization, but its ability to use reduced P compounds has not been previously demonstrated. Because Prochlorococcus strain MIT9301 encodes genes similar to phnY and phnZ , which constitute a novel marine bacterial 2‐aminoethylphosphonate (2‐AEPn) utilization pathway, it has been suggested that this organism might use 2‐AEPn as an alternative P source. We show here that although MIT9301 was unable to use 2‐AEPn as a sole P source under standard culture conditions, it was able to use phosphite. Phosphite utilization by MIT9301 appears to be mediated by an NAD‐dependent phosphite dehydrogenase encoded by ptxD . We show that phosphite utilization genes are present in diverse marine microbes and that their abundance is higher in low‐P waters. These results strongly suggest that phosphite represents a previously unrecognized component of the marine P cycle.

(2-Methoxyethoxy)acetic acid: a urinary biomarker of exposure for jet fuel JP-8 - Clayton B’Hymer; Patricia Mathias; Edward Krieg; Kenneth L. Cheever; Christine A. Toennis; John C. Clark; James S. Kesner; Roger L. Gibson; Mary Ann Butler (International Archives of Occupational and Environmental Health, 2012)

Russian wheat aphids ( Diuraphis noxia ) in China: native range expansion or recent introduction? - B. ZHANG; O. R. EDWARDS; L. KANG; S. J. FULLER (Molecular Ecology, 2012)
In this study, we explore the population genetics of the Russian wheat aphid (RWA) ( Diuraphis noxia ), one of the world’s most invasive agricultural pests, in north‐western China. We have analysed the data of 10 microsatellite loci and mitochondrial sequences from 27 populations sampled over 2 years in China. The results confirm that the RWAs are holocyclic in China with high genetic diversity indicating widespread sexual reproduction. Distinct differences in microsatellite genetic diversity and distribution revealed clear geographic isolation between RWA populations in northern and southern Xinjiang, China, with gene flow interrupted across extensive desert regions. Despite frequent grain transportation from north to south in this region, little evidence for RWA translocation as a result of human agricultural activities was found. Consequently, frequent gene flow among northern populations most likely resulted from natural dispersal, potentially facilitated by wind currents. We also found evidence for the long‐term existence and expansion of RWAs in China, despite local opinion that it is an exotic species only present in China since 1975. Our estimated date of RWA expansion throughout China coincides with the debut of wheat domestication and cultivation practices in western Asia in the Holocene. We conclude that western China represents the limit of the far eastern native range of this species. This study is the most comprehensive molecular genetic investigation of the RWA in its native range undertaken to date and provides valuable insights into the history of the association of this aphid with domesticated cereals and wild grasses.

Plasma folate, methylenetetrahydrofolate reductase (MTHFR), and colorectal cancer risk in three large nested case–control studies - Jung Eun Lee; Esther K. Wei; Charles S. Fuchs; David J. Hunter; I-Min Lee; Jacob Selhub; Meir J. Stampfer; Walter C. Willett; Jing Ma; Edward Giovannucci (Cancer Causes & Control, 2012)

Conditions for the occurence of unphysical negative values of the anelastic SH plane wave energy-based transmission coefficient - Edward S. Krebes; S. Moradi (Studia Geophysica et Geodaetica, 2012)

Monitoring the effects of Rodolia cardinalis on Icerya purchasi populations on the Galapagos Islands - Carolina Calderón Alvarez; Charlotte E. Causton; Mark S. Hoddle; Christina D. Hoddle; Roy van Driesche; Edward J. Stanek (BioControl, 2012)

New environmental metabarcodes for analysing soil DNA: potential for studying past and present ecosystems - LAURA S. EPP; SANNE BOESSENKOOL; EVA P. BELLEMAIN; JAMES HAILE; ALFONSO ESPOSITO; TIAYYBA RIAZ; CHRISTER ERSÉUS; VLADIMIR I. GUSAROV; MARY E. EDWARDS; ARILD JOHNSEN; HANS K. STENØIEN; KRISTIAN HASSEL; et al. (Molecular Ecology, 2012)
Metabarcoding approaches use total and typically degraded DNA from environmental samples to analyse biotic assemblages and can potentially be carried out for any kinds of organisms in an ecosystem. These analyses rely on specific markers, here called metabarcodes, which should be optimized for taxonomic resolution, minimal bias in amplification of the target organism group and short sequence length. Using bioinformatic tools, we developed metabarcodes for several groups of organisms: fungi, bryophytes, enchytraeids, beetles and birds. The ability of these metabarcodes to amplify the target groups was systematically evaluated by (i) in silico PCRs using all standard sequences in the EMBL public database as templates, (ii) in vitro PCRs of DNA extracts from surface soil samples from a site in Varanger, northern Norway and (iii) in vitro PCRs of DNA extracts from permanently frozen sediment samples of late‐Pleistocene age (∼16 000–50 000 years bp ) from two Siberian sites, Duvanny Yar and Main River. Comparison of the results from the in silico PCR with those obtained in vitro showed that the in silico approach offered a reliable estimate of the suitability of a marker. All target groups were detected in the environmental DNA, but we found large variation in the level of detection among the groups and between modern and ancient samples. Success rates for the Pleistocene samples were highest for fungal DNA, whereas bryophyte, beetle and bird sequences could also be retrieved, but to a much lesser degree. The metabarcoding approach has considerable potential for biodiversity screening of modern samples and also as a palaeoecological tool.

Blocking human contaminant DNA during PCR allows amplification of rare mammal species from sedimentary ancient DNA - SANNE BOESSENKOOL; LAURA S. EPP; JAMES HAILE; EVA BELLEMAIN; MARY EDWARDS; ERIC COISSAC; ESKE WILLERSLEV; CHRISTIAN BROCHMANN (Molecular Ecology, 2012)
Analyses of degraded DNA are typically hampered by contamination, especially when employing universal primers such as commonly used in environmental DNA studies. In addition to false‐positive results, the amplification of contaminant DNA may cause false‐negative results because of competition, or bias, during the PCR. In this study, we test the utility of human‐specific blocking primers in mammal diversity analyses of ancient permafrost samples from Siberia. Using quantitative PCR (qPCR) on human and mammoth DNA, we first optimized the design and concentration of blocking primer in the PCR. Subsequently, 454 pyrosequencing of ancient permafrost samples amplified with and without the addition of blocking primer revealed that DNA sequences from a diversity of mammalian representatives of the Beringian megafauna were retrieved only when the blocking primer was added to the PCR. Notably, we observe the first retrieval of woolly rhinoceros ( Coelodonta antiquitatis ) DNA from ancient permafrost cores. In contrast, reactions without blocking primer resulted in complete dominance by human DNA sequences. These results demonstrate that in ancient environmental analyses, the PCR can be biased towards the amplification of contaminant sequences to such an extent that retrieval of the endogenous DNA is severely restricted. The application of blocking primers is a promising tool to avoid this bias and can greatly enhance the quantity and the diversity of the endogenous DNA sequences that are amplified.

Volcanic Eruptions in the Deep Sea - Kenneth Rubin; S. Adam Soule; William Chadwick; Daniel Fornari; David Clague; Robert Embley; Edward Baker; Michael Perfit; David Caress; Robert Dziak (Oceanography, 2012)

Seasonal variation in the effects of food availability on gametogenesis in the purple urchin (Strongylocentrotus purpuratus) - Christina A. Dodge; Matthew S. Edwards (Marine Biology, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

The rate of permafrost carbon release under aerobic and anaerobic conditions and its potential effects on climate - Hanna Lee; Edward A. G. Schuur; Kanika S. Inglett; Martin Lavoie; Jeffrey P. Chanton (Global Change Biology, 2012)
Recent observations suggest that permafrost thaw may create two completely different soil environments: aerobic in relatively well‐drained uplands and anaerobic in poorly drained wetlands. The soil oxygen availability will dictate the rate of permafrost carbon release as carbon dioxide ( CO 2 ) and as methane ( CH 4 ), and the overall effects of these emitted greenhouse gases on climate. The objective of this study was to quantify CO 2 and CH 4 release over a 500‐day period from permafrost soil under aerobic and anaerobic conditions in the laboratory and to compare the potential effects of these emissions on future climate by estimating their relative climate forcing. We used permafrost soils collected from A laska and S iberia with varying organic matter characteristics and simultaneously incubated them under aerobic and anaerobic conditions to determine rates of CO 2 and CH 4 production. Over 500 days of soil incubation at 15 °C, we observed that carbon released under aerobic conditions was 3.9–10.0 times greater than anaerobic conditions. When scaled by greenhouse warming potential to account for differences between CO 2 and CH 4 , relative climate forcing ranged between 1.5 and 7.1. Carbon release in organic soils was nearly 20 times greater than mineral soils on a per gram soil basis, but when compared on a per gram carbon basis, deep permafrost mineral soils showed carbon release rates similar to organic soils for some soil types. This suggests that permafrost carbon may be very labile, but that there are significant differences across soil types depending on the processes that controlled initial permafrost carbon accumulation within a particular landscape. Overall, our study showed that, independent of soil type, permafrost carbon in a relatively aerobic upland ecosystems may have a greater effect on climate when compared with a similar amount of permafrost carbon thawing in an anaerobic environment, despite the release of CH 4 that occurs in anaerobic conditions.

Migratory flyway and geographical distance are barriers to the gene flow of influenza virus among North American birds - Tommy Tsan‐Yuk Lam; Hon S. Ip; Elodie Ghedin; David E. Wentworth; Rebecca A. Halpin; Timothy B. Stockwell; David J. Spiro; Robert J. Dusek; James B. Bortner; Jenny Hoskins; Bradley D. Bales; Dan R. Yparraguirre; et al. (Ecology Letters, 2012)
Ecology Letters (2011) 14 : 24–33 Abstract Despite the importance of migratory birds in the ecology and evolution of avian influenza virus (AIV), there is a lack of information on the patterns of AIV spread at the intra‐continental scale. We applied a variety of statistical phylogeographic techniques to a plethora of viral genome sequence data to determine the strength, pattern and determinants of gene flow in AIV sampled from wild birds in North America. These analyses revealed a clear isolation‐by‐distance of AIV among sampling localities. In addition, we show that phylogeographic models incorporating information on the avian flyway of sampling proved a better fit to the observed sequence data than those specifying homogeneous or random rates of gene flow among localities. In sum, these data strongly suggest that the intra‐continental spread of AIV by migratory birds is subject to major ecological barriers, including spatial distance and avian flyway.

Dabigatran: Review of Pharmacology and Management of Bleeding Complications of This Novel Oral Anticoagulant - Michael Ganetsky; Kavita M. Babu; Steven D. Salhanick; Robert S. Brown; Edward W. Boyer (Journal of Medical Toxicology, 2011)

Web 2.0 collaborations address uncertainty in climate reconstructions of the past millennium - David Morrill Anderson; Bruce A. Bauer; Charles R. Buckner; Edward Gille; Wendy S. Gross; Michael Hartman; Carrie Morrill; Anju M. Shah; Eugene R. Wahl (Earth Science Informatics, 2011)

A prospective study of intakes of zinc and heme iron and colorectal cancer risk in men and women - Xuehong Zhang; Edward L. Giovannucci; Stephanie A. Smith-Warner; Kana Wu; Charles S. Fuchs; Michael Pollak; Walter C. Willett; Jing Ma (Cancer Causes & Control, 2011)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

New Choices and Challenges for Regulated Private Forests: The “Alternate Plan” Option - Roje S. Gootee; Keith A. Blatner; Matthew S. Carroll; David M. Baumgartner; Edward P. Weber (Journal of Forestry, 2011)
The state of Washington has developed a policy instrument that substantially amends traditional “top-down” private forest regulation. Called the “Alternate Plan” option, it gives landowners unusual new flexibility in designing forest management projects for their property. Projects may depart from any of the state's established Forest Practices Rules, if the property owner can satisfactorily show that a customized proposal would provide equivalent environmental protection. The state provides a prompt review and decision and then supervises project implementation and monitors compliance with the approved project specifications. We interviewed 109 stakeholders involved in the design, use, and implementation of this innovative program. From this data we evaluate the functional advantages and challenges inherent in this new regulatory approach, suggest modifications to improve its effectiveness, and discuss policymaking implications.

Equitable regulation of private forests - Roje S. Gootee; Keith A. Blatner; David M. Baumgartner; Matthew S. Carroll; Edward P. Weber (Small-scale Forestry, 2011)

Ancient Chinese medicine and mechanistic evidence of acupuncture physiology - Edward S. Yang; Pei-Wen Li; Bernd Nilius; Geng Li (Pflügers Archiv - European Journal of Physiology, 2011)

Physiology and cell biology of acupuncture observed in calcium signaling activated by acoustic shear wave - Geng Li; Jie-Ming Liang; Pei-Wen Li; Xiaoqiang Yao; Peter Zhong Pei; Wei Li; Qi-Hua He; Xifei Yang; Queenie C. C. Chan; Paul Y. S. Cheung; Qi Yuan Ma; Siu Kam Lam; et al. (Pflügers Archiv - European Journal of Physiology, 2011)

BMP4 loss-of-function mutations in developmental eye disorders including SHORT syndrome - Linda M. Reis; Rebecca C. Tyler; Kala F. Schilter; Omar Abdul-Rahman; Jeffrey W. Innis; Beth A. Kozel; Adele S. Schneider; Tanya M. Bardakjian; Edward J. Lose; Donna M. Martin; Ulrich Broeckel; Elena V. Semina (Human Genetics, 2011)

Bioaccumulation of copper and zinc by the giant kelp Macrocystis pyrifera - La Kenya Evans; Matthew S. Edwards (Algae, 2011)

Construction of green fluorescent protein based bacterial biosensor for heavy metal remediation - C. Edward Raja; G. S. Selvam (International Journal of Environmental Science and Technology, 2011)

Relative larval loss among females during dispersal of Lake Sturgeon (Acipenser fulvescens) - Thuy Yen Duong; Kim T. Scribner; James A. Crossman; Patrick S. Forsythe; Edward A. Baker; Jeannette Kanefsky; Jared J. Homola; Christin Davis (Environmental Biology of Fishes, 2011)

Distribution of Fusarium mycotoxins in UK wheat mill fractions - S.G. Edwards; E.T. Dickin; S. MacDonald; D. Buttler; C.M. Hazel; S. Patel; K.A. Scudamore (Food Additives & Contaminants: Part A, 2011)

The Mid‐Brunhes Event and West Antarctic ice sheet stability - P. B. Holden; N. R. Edwards; E. W. Wolff; P. J. Valdes; J. S. Singarayer (Journal of Quaternary Science, 2011)
The complex cyclical nature of Pleistocene climate, driven by the evolving orbital configuration of the Earth, is well known but not well understood. A major climatic transition took place at the Mid‐Brunhes Event (MBE), ca. 430 ka ago after which the amplitude of the ca.100 ka climate oscillations increased, with substantially warmer interglacials, including periods warmer than present. Recent modelling has indicated that while the timing of these warmer‐than‐present transient (WPT) events is consistent with southern warming due to a deglaciation‐forced slowdown of the Atlantic Meridional Overturning Circulation, the magnitude of warming requires a local amplification, for which a candidate is the feedback of significant West Antarctic Ice Sheet (WAIS) retreat. We here extend this argument, based on the absence of WPTs in the early ice core record (450–800 ka ago), to hypothesize that the MBE could be a manifestation of decreased WAIS stability, triggered by ongoing subglacial erosion. Copyright © 2011 John Wiley & Sons, Ltd.

Fluorine-free mixed amphiphilic polymers based on PDMS and PEG side chains for fouling release applications - Harihara S. Sundaram; Youngjin Cho; Michael D. Dimitriou; Craig J. Weinman; John A. Finlay; Gemma Cone; Maureen E. Callow; James A. Callow; Edward J. Kramer; Christopher K. Ober (Biofouling, 2011)

JNJ-39220675, a novel selective histamine H3 receptor antagonist, reduces the abuse-related effects of alcohol in rats - Ruggero Galici; Amir H. Rezvani; Leah Aluisio; Brian Lord; Edward D. Levin; Ian Fraser; Jamin Boggs; Natalie Welty; James R. Shoblock; S. Timothy Motley; Michael A. Letavic; Nicholas I. Carruthers; et al. (Psychopharmacology, 2011)

Large herbivores may alter vegetation structure of semi-arid savannas through soil nutrient mediation - Cornelis van der Waal; Ada Kool; Seline S. Meijer; Edward Kohi; Ignas M. A. Heitkönig; Willem F. de Boer; Frank van Langevelde; Rina C. Grant; Mike J. S. Peel; Rob Slotow; Henrik J. de Knegt; Herbert H. T. Prins; et al. (Oecologia, 2011)

An Integrated Approach to Gene Discovery and Marker Development in Atlantic Cod (Gadus morhua) - Sharen Bowman; Sophie Hubert; Brent Higgins; Cynthia Stone; Jennifer Kimball; Tudor Borza; Jillian Tarrant Bussey; Gary Simpson; Catherine Kozera; Bruce A. Curtis; Jennifer R. Hall; Tiago S. Hori; et al. (Marine Biotechnology, 2011)

Cancer survival among Latinos and the Hispanic Paradox - Paulo S. Pinheiro; Melanie Williams; Eric A. Miller; Stephanie Easterday; Sheniz Moonie; Edward J. Trapido (Cancer Causes & Control, 2011)

Cerebellar brain inhibition is decreased in active and surround muscles at the onset of voluntary movement - Panagiotis Kassavetis; Britt S. Hoffland; Tabish A. Saifee; Kailash P. Bhatia; Bart P. van de Warrenburg; John C. Rothwell; Mark J. Edwards (Experimental Brain Research, 2011)

Neuronavigation Increases the Physiologic and Behavioral Effects of Low-Frequency rTMS of Primary Motor Cortex in Healthy Subjects - S. Bashir; D. Edwards; A. Pascual-Leone (Brain Topography, 2011)

Computational Model of the Human Elbow and Forearm: Application to Complex Varus Instability - Edward M. Spratley; Jennifer S. Wayne (Annals of Biomedical Engineering, 2011)

Reduction of fear-potentiated startle by benzodiazepines in C57BL/6J mice - Kiersten S. Smith; Edward G. Meloni; Karyn M. Myers; Ashlee Van’t Veer; William A. Carlezon; Uwe Rudolph (Psychopharmacology, 2011)

Reducing seabird strikes with trawl cables in the pollock catcher-processor fleet in the eastern Bering Sea - Edward F. Melvin; Kimberly S. Dietrich; Shannon Fitzgerald; Tamre Cardoso (Polar Biology, 2011)

Localization of AQP5 during development of the mouse submandibular salivary gland - Helga S. Larsen; Marit H. Aure; Sarah B. Peters; Melinda Larsen; Edward B. Messelt; Hilde Kanli Galtung (Journal of Molecular Histology, 2011)

MGMT promoter methylation, loss of expression and prognosis in 855 colorectal cancers - Kaori Shima; Teppei Morikawa; Yoshifumi Baba; Katsuhiko Nosho; Maiko Suzuki; Mai Yamauchi; Marika Hayashi; Edward Giovannucci; Charles S. Fuchs; Shuji Ogino (Cancer Causes & Control, 2011)

Coordinated approaches to quantify long‐term ecosystem dynamics in response to global change - YIQI LUO; JERRY MELILLO; SHULI NIU; CLAUS BEIER; JAMES S. CLARK; AIMÉE T. CLASSEN; ERIC DAVIDSON; JEFFREY S. DUKES; R. DAVE EVANS; CHRISTOPHER B. FIELD; CLAUDIA I. CZIMCZIK; MICHAEL KELLER; et al. (Global Change Biology, 2011)
Many serious ecosystem consequences of climate change will take decades or even centuries to emerge. Long‐term ecological responses to global change are strongly regulated by slow processes, such as changes in species composition, carbon dynamics in soil and by long‐lived plants, and accumulation of nutrient capitals. Understanding and predicting these processes require experiments on decadal time scales. But decadal experiments by themselves may not be adequate because many of the slow processes have characteristic time scales much longer than experiments can be maintained. This article promotes a coordinated approach that combines long‐term, large‐scale global change experiments with process studies and modeling. Long‐term global change manipulative experiments, especially in high‐priority ecosystems such as tropical forests and high‐latitude regions, are essential to maximize information gain concerning future states of the earth system. The long‐term experiments should be conducted in tandem with complementary process studies, such as those using model ecosystems, species replacements, laboratory incubations, isotope tracers, and greenhouse facilities. Models are essential to assimilate data from long‐term experiments and process studies together with information from long‐term observations, surveys, and space‐for‐time studies along environmental and biological gradients. Future research programs with coordinated long‐term experiments, process studies, and modeling have the potential to be the most effective strategy to gain the best information on long‐term ecosystem dynamics in response to global change.

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

Factors associated with Type I and Type II endometrial cancer - Ashley S. Felix; Joel L. Weissfeld; Roslyn A. Stone; Robert Bowser; Mamatha Chivukula; Robert P. Edwards; Faina Linkov (Cancer Causes & Control, 2010)

A proposal to change existing virus species names to non-Latinized binomials - Marc H. V. Van Regenmortel; Donald S. Burke; Charles H. Calisher; Ralf G. Dietzgen; Claude M. Fauquet; Said A. Ghabrial; Peter B. Jahrling; Karl M. Johnson; Michael R. Holbrook; Marian C. Horzinek; Günther M. Keil; Jens H. Kuhn; et al. (Archives of Virology, 2010)

Toward the roles of store-operated Ca2+ entry in skeletal muscle - Bradley S. Launikonis; Robyn M. Murphy; Joshua N. Edwards (Pflügers Archiv - European Journal of Physiology, 2010)

Mucosal control of the intestinal microbial community - Sylvia Brugman; Edward E. S. Nieuwenhuis (Journal of Molecular Medicine, 2010)

Cancer Patients and Their Companion Animals: Results from a 309-Patient Survey on Pet-Related Concerns and Anxieties During Chemotherapy - Brenda R. Larson; Sherry Looker; Dianne M. Herrera; Edward T. Creagan; Suzanne R. Hayman; Judith S. Kaur; Aminah Jatoi (Journal of Cancer Education, 2010)

Assessing regional impacts and adaptation strategies for climate change: the Washington Climate Change Impacts Assessment - Edward L. Miles; Marketa M. Elsner; Jeremy S. Littell; Lara Whitely Binder; Dennis P. Lettenmaier (Climatic Change, 2010)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Natural transformation of Vibrio fischeri requires tfoX and tfoY - Amber Pollack‐Berti; Michael S. Wollenberg; Edward G. Ruby (Environmental Microbiology, 2010)
Summary Recent evidence has indicated that natural genetic transformation occurs in Vibrio cholerae, and that it requires both induction by chitin oligosaccharides, like chitohexaose, and expression of a putative regulatory gene designated tfoX . Using sequence and phylogenetic analyses we have found two tfoX paralogues in all sequenced genomes of the genus Vibrio . Like V. cholerae , when grown in chitohexaose, cells of V. fischeri are able to take up and incorporate exogenous DNA. Chitohexaose‐independent transformation by V. fischeri was observed when tfoX was present in multicopy. The second tfoX paralogue, designated tfoY, is also required for efficient transformation in V. fischeri , but is not functionally identical to tfoX . Natural transformation of V. fischeri facilitates rapid transfer of mutations across strains, and provides a highly useful tool for experimental genetic manipulation in this species. The presence of chitin‐induced competence in several vibrios highlights the potential for a conserved mechanism of genetic exchange across this family of environmentally important marine bacteria.

Separation of grassland litter and ecosite influences on seasonal soil moisture and plant growth dynamics - Eliza S. Deutsch; Edward W. Bork; Walter D. Willms (Plant Ecology, 2010)

Symbiosis research, technology, and education: Proceedings of the 6th International Symbiosis Society Congress held in Madison Wisconsin, USA, August 2009 - Heidi Goodrich-Blair; Jean-Michel Ané; James D. Bever; Seth R. Bordenstein; Monika Bright; John M. Chaston; Keith Clay; Cameron R. Currie; Angela E. Douglas; Nicole Gerardo; Maria J. Harrison; Ruth E. Ley; et al. (Symbiosis, 2010)

Choosing What to Believe About Forests: Differences Between Professional and Non-Professional Evaluative Criteria - Roje S. Gootee; Keith A. Blatner; David M. Baumgartner; Matthew S. Carroll; Edward P. Weber (Small-scale Forestry, 2010)

Coenzyme Q10 Reduces β-Amyloid Plaque in an APP/PS1 Transgenic Mouse Model of Alzheimer’s Disease - Xifei Yang; George Dai; Geng Li; Edward S. Yang (Journal of Molecular Neuroscience, 2010)

World phylogeography and male-mediated gene flow in the sandbar shark, Carcharhinus plumbeus - DAVID S. PORTNOY; JAN R. MCDOWELL; EDWARD J. HEIST; JOHN A. MUSICK; JOHN E. GRAVES (Molecular Ecology, 2010)

Derivation and characterisation of the human embryonic stem cell line, OxF1 - Frances Anne Brook; Sally A. Cowley; Edward P. Evans; Karen Turner; William S. James; Helen J. Mardon (In Vitro Cellular & Developmental Biology - Animal, 2010)

Electrophysiological properties of isthmic neurons in frogs revealed by in vitro and in vivo studies - Matthew S. Caudill; Adam T. Eggebrecht; Edward R. Gruberg; Ralf Wessel (Journal of Comparative Physiology A, 2010)

Local people value environmental services provided by forested parks - Navjot S. Sodhi; Tien Ming Lee; Cagan H. Sekercioglu; Edward L. Webb; Dewi M. Prawiradilaga; David J. Lohman; Naomi E. Pierce; Arvin C. Diesmos; Madhu Rao; Paul R. Ehrlich (Biodiversity and Conservation, 2010)

Population synchrony of a native fish across three Laurentian Great Lakes: evaluating the effects of dispersal and climate - David B. Bunnell; Jean V. Adams; Owen T. Gorman; Charles P. Madenjian; Stephen C. Riley; Edward F. Roseman; Jeffrey S. Schaeffer (Oecologia, 2010)

Molecular identification of Na + –H + exchanger isoforms (NHE2) in the gills of the euryhaline teleost Fundulus heteroclitus - S. L. Edwards; J. C. Weakley; A. W. Diamanduros; J. B. Claiborne (Journal of Fish Biology, 2010)
In the current study, reverse‐transcription polymerase chain reaction (RT‐PCR) and rapid amplification of cDNA ends (RACE) PCR were used to clone full‐length putative Na + –H + exchanger isoforms (NHE2a) cDNA from the gills of Fundulus heteroclitus. The 2480 bp cDNA includes a coding region for a protein that shows a 57% amino acid homology to rabbit NHE2. These sequences allowed data mining of available fish genome data, which revealed at least three NHE2 subtypes in some teleost species.

Payments for Ecosystem Services as a Framework for Community‐Based Conservation in Northern Tanzania - FRED NELSON; CHARLES FOLEY; LARA S. FOLEY; ABRAHAM LEPOSO; EDWARD LOURE; DAVID PETERSON; MIKE PETERSON; THAD PETERSON; HASSAN SACHEDINA; ANDREW WILLIAMS (Conservation Biology, 2010)
Payments for ecosystem services (PES) are an increasingly promoted approach to conservation. These approaches seek to develop financial mechanisms that create economic incentives for the maintenance of ecosystems and associated biodiversity by rewarding those who are responsible for provision of ecological services. There are, however, few cases in which such schemes have been used as a strategy for conserving wildlife in developing countries and very few operational examples of such schemes of any sort in sub‐Saharan Africa. In savannah ecosystems, large mammal populations generally depend on seasonal use of extensive areas and are widely declining as a result of habitat loss, overexploitation, and policies that limit local benefits from wildlife. Community‐based conservation strategies seek to create local incentives for conserving wildlife, but often have limited impact as a result of persistent institutional barriers that limit local rights and economic benefits. In northern Tanzania, a consortium of tourism operators is attempting to address these challenges through an agreement with a village that possesses part of a key wildlife dispersal area outside Tarangire National Park. The operators pay the community to enforce voluntary restrictions on agricultural cultivation and permanent settlement in a defined area of land. The initiative represents a potentially cost‐effective framework for community‐based conservation in an ecologically important area and is helping to reconcile historically conflicting local and national interests relative to land tenure, pastoralist livelihoods, and conservation. Wider adaptation of payments for ecosystem services approaches to settings where sustaining wildlife populations depends on local stewardship may help address current challenges facing conservation outside state‐protected areas in savannah ecosystems in sub‐Saharan Africa and other parts of the world.

Comparing plasma and faecal measures of steroid hormones in Adelie penguins Pygoscelis adeliae - Calum Edward Ninnes; J. R. Waas; N. Ling; S. Nakagawa; J. C. Banks; D. G. Bell; A. Bright; P. W. Carey; J. Chandler; Q. J. Hudson; J. R. Ingram; K. Lyall; et al. (Journal of Comparative Physiology B, 2010)

Megadroughts in North America: placing IPCC projections of hydroclimatic change in a long‐term palaeoclimate context - Edward R. Cook; Richard Seager; Richard R. Heim; Russell S. Vose; Celine Herweijer; Connie Woodhouse (Journal of Quaternary Science, 2010)
IPCC Assessment Report 4 model projections suggest that the subtropical dry zones of the world will both dry and expand poleward in the future due to greenhouse warming. The US Southwest is particularly vulnerable in this regard and model projections indicate a progressive drying there out to the end of the 21st century. At the same time, the USA has been in a state of drought over much of the West for about 10 years now. While severe, this turn of the century drought has not yet clearly exceeded the severity of two exceptional droughts in the 20th century. So while the coincidence between the turn of the century drought and projected drying in the Southwest is cause for concern, it is premature to claim that the model projections are correct. At the same time, great new insights into past drought variability over North America have been made through the development of the North American Drought Atlas from tree rings. Analyses of this drought atlas have revealed past megadroughts of unprecedented duration in the West, largely in the Medieval period about 1000 years ago. A vastly improved Living Blended Drought Atlas (LBDA) for North America now under development reveals these megadroughts in far greater detail. The LBDA indicates the occurrence of the same Medieval megadroughts in the West and similar‐scale megadroughts in the agriculturally and commercially important Mississippi Valley. Possible causes of these megadroughts and their implications for the future are discussed. Copyright © 2009 John Wiley & Sons, Ltd.

Genetic map construction and QTL mapping of resistance to blackleg (Leptosphaeria maculans) disease in Australian canola (Brassica napus L.) cultivars - S. Kaur; N. O. I. Cogan; G. Ye; R. C. Baillie; M. L. Hand; A. E. Ling; A. K. Mcgearey; J. Kaur; C. J. Hopkins; M. Todorovic; H. Mountford; D. Edwards; et al. (Theoretical and Applied Genetics, 2009)

Mitochondrial genome sequence of Unionicola foili (Acari: Unionicolidae): a unique gene order with implications for phylogenetic inference - Brian R. Ernsting; Dale D. Edwards; Katie J. Aldred; Jeffrey S. Fites; Caroline R. Neff (Experimental and Applied Acarology, 2009)

New record of fungus Mycoleptodiscus terrestris from New Zealand - Deborah E. Hofstra; Tracey Edwards; John S. Clayton; Judy F. Shearer (New Zealand Journal of Botany, 2009)
During a survey of submersed aquatic macrophytes and their associated fungi from lakes and waterways in New Zealand's North Island, an isolate of Mycoleptodiscus terrestris (Gerd.) Ostaz. was confirmed on the basis of colony characteristics, sporodochia, and conidial morphology. This is a new record of M. terrestris in New Zealand and a new host species, the introduced aquatic macrophyte, Ceratophyllum demersum L.

Dynamic marine protected areas can improve the resilience of coral reef systems - Edward T. Game; Michael Bode; Eve McDonald‐Madden; Hedley S. Grantham; Hugh P. Possingham (Ecology Letters, 2009)
Ecology Letters (2009) 12: 1336–1346 Abstract Marine Protected Areas are usually static, permanently closed areas. There are, however, both social and ecological reasons to adopt dynamic closures, where reserves move through time. Using a general theoretical framework, we investigate whether dynamic closures can improve the mean biomass of herbivorous fishes on reef systems, thereby enhancing resilience to undesirable phase‐shifts. At current levels of reservation (10–30%), moving protection between all reefs in a system is unlikely to improve herbivore biomass, but can lead to a more even distribution of biomass. However, if protected areas are rotated among an appropriate subset of the entire reef system (e.g. rotating 10 protected areas between only 20 reefs in a 100 reef system), dynamic closures always lead to increased mean herbivore biomass. The management strategy that will achieve the highest mean herbivore biomass depends on both the trajectories and rates of population recovery and decline. Given the current large‐scale threats to coral reefs, the ability of dynamic marine protected areas to achieve conservation goals deserves more attention.

Acid soil indicators in forest soils of the Cherry River Watershed, West Virginia - C. Farr; J. Skousen; P. Edwards; S. Connolly; J. Sencindiver (Environmental Monitoring and Assessment, 2009)

Genotypes of Brassica rapa respond differently to plant-induced variation in air CO2 concentration in growth chambers with standard and enhanced venting - Christine E. Edwards; Monia S. H. Haselhorst; Autumn M. McKnite; Brent E. Ewers; David G. Williams; Cynthia Weinig (Theoretical and Applied Genetics, 2009)

Rapid effects of hypoxia on H+ homeostasis in articular chondrocytes - John S. Gibson; David McCartney; Joanna Sumpter; Thomas P. A. Fairfax; Peter I. Milner; Hannah L. Edwards; Robert J. Wilkins (Pflügers Archiv - European Journal of Physiology, 2009)

Linking stream and landscape trajectories in the southern Appalachians - Edward P. Gardiner; Andrew B. Sutherland; Rebecca J. Bixby; Mark C. Scott; Judy L. Meyer; Gene S. Helfman; E. Fred Benfield; Cathy M. Pringle; Paul V. Bolstad; David N. Wear (Environmental Monitoring and Assessment, 2009)

Adaptive response of equine intestinal Na+/glucose co-transporter (SGLT1) to an increase in dietary soluble carbohydrate - Jane Dyer; Miran Al-Rammahi; Louise Waterfall; Kieron S. H. Salmon; Ray J. Geor; Ludovic Bouré; G. Barrie Edwards; Christopher J. Proudman; Soraya P. Shirazi-Beechey (Pflügers Archiv - European Journal of Physiology, 2009)

Manual and oculomotor performance develop contemporaneously but independently during continuous tracking - Eric D. Vidoni; Jason S. McCarley; Jodi D. Edwards; Lara A. Boyd (Experimental Brain Research, 2009)

Monitoring Benthic AIgal Communides:A Comparison of Targeted and Coefficient Sampling Methods - Matthew S. Edwards; Martin T. Tinker (Algae, 2009)

Vulnerability of national economies to the impacts of climate change on fisheries - Edward H. Allison; Allison L. Perry; Marie‐Caroline Badjeck; W. Neil Adger; Katrina Brown; Declan Conway; Ashley S. Halls; Graham M. Pilling; John D. Reynolds; Neil L. Andrew; Nicholas K. Dulvy (Fish and Fisheries, 2009)
Anthropogenic global warming has significantly influenced physical and biological processes at global and regional scales. The observed and anticipated changes in global climate present significant opportunities and challenges for societies and economies. We compare the vulnerability of 132 national economies to potential climate change impacts on their capture fisheries using an indicator‐based approach. Countries in Central and Western Africa (e.g. Malawi, Guinea, Senegal, and Uganda), Peru and Colombia in north‐western South America, and four tropical Asian countries (Bangladesh, Cambodia, Pakistan, and Yemen) were identified as most vulnerable. This vulnerability was due to the combined effect of predicted warming, the relative importance of fisheries to national economies and diets, and limited societal capacity to adapt to potential impacts and opportunities. Many vulnerable countries were also among the world’s least developed countries whose inhabitants are among the world’s poorest and twice as reliant on fish, which provides 27% of dietary protein compared to 13% in less vulnerable countries. These countries also produce 20% of the world’s fish exports and are in greatest need of adaptation planning to maintain or enhance the contribution that fisheries can make to poverty reduction. Although the precise impacts and direction of climate‐driven change for particular fish stocks and fisheries are uncertain, our analysis suggests they are likely to lead to either increased economic hardship or missed opportunities for development in countries that depend upon fisheries but lack the capacity to adapt.

Fecal Sterol and Bile Acid Biomarkers: Runoff Concentrations in Animal Waste-Amended Pastures - Punam Tyagi; Dwayne R. Edwards; Mark S. Coyne (Water, Air, & Soil Pollution, 2009)

Estimating watershed area for playas in the Southern High Plains, USA - Amy J. Ekanayake; Jo -Szu Tsai; Linda J. S. Allen; Loren M. Smith; James G. Surles; Edward J. Allen (Wetlands, 2009)

Plasmid profile and curing analysis of Pseudomonas aeruginosa as metal resistant - C. Edward Raja; G. S. Selvam (International Journal of Environmental Science and Technology, 2009)

Is the Response of Estuarine Nekton to Freshwater Flow in the San Francisco Estuary Explained by Variation in Habitat Volume? - Wim J. Kimmerer; Edward S. Gross; Michael L. MacWilliams (Estuaries and Coasts, 2009)

Enhanced Resistance to Control Potato Tuberworm by Combining Engineered Resistance, Avidin, and Natural Resistance Derived from, Solanum Chacoense - Susannah G. Cooper; David S. Douches; Kelly Zarka; Edward J. Grafius (American Journal of Potato Research, 2009)

Photoperiod insensitive Ppd-A1a mutations in tetraploid wheat (Triticum durum Desf.) - Edward P. Wilhelm; Adrian S. Turner; David A. Laurie (Theoretical and Applied Genetics, 2009)

Using patterns of genetic structure based on microsatellite loci to test hypotheses of current hybridization, ancient hybridization and incomplete lineage sorting in Conradina (Lamiaceae) - C. E. EDWARDS; D. E. SOLTIS; P. S. SOLTIS (Molecular Ecology, 2008)
Hybridization and/or incomplete sorting of ancestral polymorphism are commonly implicated to explain discordant phylogenetic analyses of closely related species complexes. One genus in which these phenomena have been suggested to have played major roles based on phylogenetic data is Conradina , a genus of mints (Lamiaceae) endemic to the southeastern USA containing several endangered species. The goals of this study were to use microsatellite data to better understand patterns of genetic structure in Conradina, to test hypotheses of recent or ancient hybridization and incomplete lineage sorting, and to clarify species boundaries. Individuals from 55 populations representing all Conradina species were genotyped using 10 microsatellite loci. Analyses of the patterns of genetic structure in Conradina revealed a clear differentiation of populations following recognized species boundaries, indicating that species have diverged from one another genetically and interspecific hybridization has not occurred recently. Neither ancient hybridization nor incomplete lineage sorting is supported as the sole cause of species nonmonophyly, suggesting that both may have contributed to patterns found in phylogenetic trees; however, analyses of other types of data may be more appropriate to distinguish between these two hypotheses. Because all described species appear to be valid entities, the current listing status of most endangered species of Conradina is appropriate; however, populations of Conradina canescens are genetically differentiated into three groups, each of which may merit species status, and several recently discovered populations of Conradina in Dunn's Creek State Park in Florida are highly differentiated genetically and also appear to represent a new species.

A region of barley chromosome 6H harbors multiple major genes associated with net type net blotch resistance - M. Abu Qamar; Z. H. Liu; J. D. Faris; S. Chao; M. C. Edwards; Z. Lai; J. D. Franckowiak; T. L. Friesen (Theoretical and Applied Genetics, 2008)

Association of the TCF7L2 polymorphism with colorectal cancer and adenoma risk - Aditi Hazra; Charles S. Fuchs; Andrew T. Chan; Edward L. Giovannucci; David J. Hunter (Cancer Causes & Control, 2008)

A review of the relationship between tooth loss, periodontal disease, and cancer - Mara S. Meyer; Kaumudi Joshipura; Edward Giovannucci; Dominique S. Michaud (Cancer Causes & Control, 2008)

Syringeal anatomy and allometry in murres (Alcidae: Uria) - Edward H. Miller; Sampath S. Seneviratne; Ian L. Jones; Gregory J. Robertson; Sabina I. Wilhelm (Journal of Ornithology, 2008)

Antiproliferative compounds of Artabotrys madagascariensis from the Madagascar rainforest - Brian T. Murphy; Shugeng Cao; Peggy J. Brodie; James S. Miller; Fidy Ratovoson; Chris Birkinshaw; Etienne Rakotobe; Vincent E. Rasamison; Karen Tendyke; Edward M. Suh; David G. I. Kingston (Natural Product Research, 2008)

Preparation of Active Proteins, Vaccines and Pharmaceuticals as Fine Powders using Supercritical or Near-Critical Fluids - Stephen P. Cape; Joseph A. Villa; Edward T. S. Huang; Tzung-Horng Yang; John F. Carpenter; Robert E. Sievers (Pharmaceutical Research, 2008)

Hormonal profile of diabetic men and the potential link to prostate cancer - Jocelyn S. Kasper; Yan Liu; Michael N. Pollak; Nader Rifai; Edward Giovannucci (Cancer Causes & Control, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

TCR-MHC docking orientation: natural selection, or thymic selection? - Edward J. Collins; David S. Riddle (Immunologic Research, 2008)

Carbapenems versus other beta-lactams in treating severe infections in intensive care: a systematic review of randomised controlled trials - S. J. Edwards; M. J. Clarke; S. Wordsworth; C. E. Emmas (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Upgrades to the Boundary-Layer Scheme in the Met Office Numerical Weather Prediction Model - A. R. Brown; R. J. Beare; J. M. Edwards; A. P. Lock; S. J. Keogh; S. F. Milton; D. N. Walters (Boundary-Layer Meteorology, 2008)

Zoning of phosphorus in igneous olivine - Margaret S. Milman-Barris; John R. Beckett; Michael B. Baker; Amy E. Hofmann; Zachary Morgan; Meghan R. Crowley; Daniel Vielzeuf; Edward Stolper (Contributions to Mineralogy and Petrology, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Effect of timing of fungicide application on the development of Fusarium head blight and the accumulation of deoxynivalenol (DON) in winter wheat grain - S. Pirgozliev; R. Ray; S. Edwards; M. Hare; P. Jenkinson (Cereal Research Communications, 2008)

Standpunkte, Praktiken und Kenntnisstand zur Ferkelkastration in Europa (PIGCAS) – Projektziele und erste Ergebnisse - Eberhard von Borell; M. Oliver; B. Fredriksen; S. Edwards; M. Bonneau (Journal of Consumer Protection and Food Safety, 2008)

Changes in abundance and spatial distribution of geese molting near Teshekpuk Lake, Alaska: interspecific competition or ecological change? - Paul L. Flint; Edward J. Mallek; Rodney J. King; Joel A. Schmutz; Karen S. Bollinger; Dirk V. Derksen (Polar Biology, 2008)

The plant availability of auto-cast platinum group elements - P. S. Hooda; A. Miller; A. C. Edwards (Environmental Geochemistry and Health, 2008)

Outdoor Air PCB Concentrations in Three Communities Along the Upper Hudson River, New York - Patrick M. Palmer; Erin E. Belanger; Lloyd R. Wilson; Syni-An A. Hwang; Rajinder S. Narang; Marta I. Gomez; Michael R. Cayo; Lorie A. Durocher; Edward F. Fitzgerald (Archives of Environmental Contamination and Toxicology, 2008)

Liver lesions in demersal fishes near a large ocean outfall on the San Pedro Shelf, California - Edward Basmadjian; Edwin M. Perkins; Charles R. Phillips; Daniel J. Heilprin; Susan D. Watts; Douglas R. Diener; Mark S. Myers; Kelly A. Koerner; Michael J. Mengel; George Robertson; Jeffrey L. Armstrong; Andrew L. Lissner; et al. (Environmental Monitoring and Assessment, 2008)

Aureoles of Pb(II)-enriched feldspar around monazite in paragneiss and anatectic pods of the Napier Complex, Enderby Land, East Antarctica: the roles of dissolution-reprecipitation and diffusion - Edward S. Grew; Martin G. Yates; Christopher J. L. Wilson (Contributions to Mineralogy and Petrology, 2008)

Coenzyme Q10 Attenuates β-Amyloid Pathology in the Aged Transgenic Mice with Alzheimer Presenilin 1 Mutation - Xifei Yang; Ying Yang; Geng Li; Jianzhi Wang; Edward S Yang (Journal of Molecular Neuroscience, 2008)

Nutrient Addition Prompts Rapid Destabilization of Organic Matter in an Arctic Tundra Ecosystem - Nicole S. Nowinski; Susan E. Trumbore; Edward A. G. Schuur; Michelle C. Mack; Gaius R. Shaver (Ecosystems, 2008)

Contrasting success in the restoration of plant and phytophagous beetle assemblages of species-rich mesotrophic grasslands - B. A. Woodcock; A. R. Edwards; C. S. Lawson; D. B. Westbury; A. J. Brook; S. J. Harris; V. K. Brown; S. R. Mortimer (Oecologia, 2008)

The California Hotspots Project: identifying regions of rapid diversification of mammals - EDWARD BYRD DAVIS; MICHELLE S. KOO; CHRIS CONROY; JAMES L. PATTON; CRAIG MORITZ (Molecular Ecology, 2008)
The high rate of anthropogenic impact on natural systems mandates protection of the evolutionary processes that generate and sustain biological diversity. Environmental drivers of diversification include spatial heterogeneity of abiotic and biotic agents of divergent selection, features that suppress gene flow, and climatic or geological processes that open new niche space. To explore how well such proxies perform as surrogates for conservation planning, we need first to map areas with rapid diversification —‘evolutionary hotspots’. Here we combine estimates of range size and divergence time to map spatial patterns of neo‐endemism for mammals of California, a global biodiversity hotspot. Neo‐endemism is explored at two scales: (i) endemic species, weighted by the inverse of range size and mtDNA sequence divergence from sisters; and (ii) as a surrogate for spatial patterns of phenotypic divergence, endemic subspecies, again using inverse‐weighting of range size. The species‐level analysis revealed foci of narrowly endemic, young taxa in the central Sierra Nevada, northern and central coast, and Tehachapi and Peninsular Ranges. The subspecies endemism‐richness analysis supported the last four areas as hotspots for diversification, but also highlighted additional coastal areas (Monterey to north of San Francisco Bay) and the Inyo Valley to the east. We suggest these hotspots reflect the major processes shaping mammal neo‐endemism: steep environmental gradients, biotic admixture areas, and areas with recent geological/climate change. Anthropogenic changes to both environment and land use will have direct impacts on regions of rapid divergence. However, despite widespread changes to land cover in California, the majority of the hotspots identified here occur in areas with relatively intact ecological landscapes. The geographical scope of conserving evolutionary process is beyond the scale of any single agency or nongovernmental organization. Choosing which land to closely protect and/or purchase will always require close coordination between agencies.

Atlantic reef fish biogeography and evolution - S. R. Floeter; L. A. Rocha; D. R. Robertson; J. C. Joyeux; W. F. Smith‐Vaniz; P. Wirtz; A. J. Edwards; J. P. Barreiros; C. E. L. Ferreira; J. L. Gasparini; A. Brito; J. M. Falcón; et al. (Journal of Biogeography, 2008)
Aim To understand why and when areas of endemism (provinces) of the tropical Atlantic Ocean were formed, how they relate to each other, and what processes have contributed to faunal enrichment. Location Atlantic Ocean. Methods The distributions of 2605 species of reef fishes were compiled for 25 areas of the Atlantic and southern Africa. Maximum‐parsimony and distance analyses were employed to investigate biogeographical relationships among those areas. A collection of 26 phylogenies of various Atlantic reef fish taxa was used to assess patterns of origin and diversification relative to evolutionary scenarios based on spatio‐temporal sequences of species splitting produced by geological and palaeoceanographic events. We present data on faunal (species and genera) richness, endemism patterns, diversity buildup (i.e. speciation processes), and evaluate the operation of the main biogeographical barriers and/or filters. Results Phylogenetic (proportion of sister species) and distributional (number of shared species) patterns are generally concordant with recognized biogeographical provinces in the Atlantic. The highly uneven distribution of species in certain genera appears to be related to their origin, with highest species richness in areas with the greatest phylogenetic depth. Diversity buildup in Atlantic reef fishes involved (1) diversification within each province, (2) isolation as a result of biogeographical barriers, and (3) stochastic accretion by means of dispersal between provinces. The timing of divergence events is not concordant among taxonomic groups. The three soft (non‐terrestrial) inter‐regional barriers (mid‐Atlantic, Amazon, and Benguela) clearly act as ‘filters’ by restricting dispersal but at the same time allowing occasional crossings that apparently lead to the establishment of new populations and species. Fluctuations in the effectiveness of the filters, combined with ecological differences among provinces, apparently provide a mechanism for much of the recent diversification of reef fishes in the Atlantic. Main conclusions Our data set indicates that both historical events (e.g. Tethys closure) and relatively recent dispersal (with or without further speciation) have had a strong influence on Atlantic tropical marine biodiversity and have contributed to the biogeographical patterns we observe today; however, examples of the latter process outnumber those of the former.

Use of Sterol and Bile Acid Biomarkers to Identify Domesticated Animal Sources of Fecal Pollution - Punam Tyagi; Dwayne R. Edwards; Mark S. Coyne (Water, Air, & Soil Pollution, 2007)

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

External mechanical compression reduces regional arterial stiffness - Kevin S. Heffernan; David G. Edwards; Lindy Rossow; Sae Young Jae; Bo Fernhall (European Journal of Applied Physiology, 2007)

Effects of Helicobacter hepaticus on the proteome of HEp-2 cells - Arinze S. Okoli; Edward M. Fox; Mark J. Raftery; George L. Mendz (Antonie van Leeuwenhoek, 2007)

Foraging behavior by Daphnia in stoichiometric gradients of food quality - Greg S. Schatz; Edward McCauley (Oecologia, 2007)

Effects of atmospheric dynamics and ocean resolution on bi-stability of the thermohaline circulation examined using the Grid ENabled Integrated Earth system modelling (GENIE) framework - T. M. Lenton; R. Marsh; A. R. Price; D. J. Lunt; Y. Aksenov; J. D. Annan; T. Cooper-Chadwick; S. J. Cox; N. R. Edwards; S. Goswami; J. C. Hargreaves; P. P. Harris; et al. (Climate Dynamics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Exploration of Ellsworth Subglacial Lake: a concept paper on the development, organisation and execution of an experiment to explore, measure and sample the environment of a West Antarctic subglacial lake - M.J. Siegert; A. Behar; M. Bentley; D. Blake; S. Bowden; P. Christoffersen; C. Cockell; H. Corr; D. C. Cullen; H. Edwards; A. Ellery; C. Ellis-Evans; et al. (Reviews in Environmental Science and Bio/Technology, 2007)

A note on the top-down and bottom-up gradient functions over a forested site - Weiguo Wang; Kenneth J. Davis; Chuixiang Yi; Edward G. Patton; Martha P. Butler; Daniel M. Ricciuto; Peter S. Bakwin (Boundary-Layer Meteorology, 2007)

Invasive aphids attack native Hawaiian plants - Russell H. Messing; Michelle N. Tremblay; Edward B. Mondor; Robert G. Foottit; Keith S. Pike (Biological Invasions, 2007)

Effects of ocean temperature on the southern range limits of two understory kelps, Pterygophora californica and Eisenia arborea, at multiple life-stages - Paul G. Matson; Matthew S. Edwards (Marine Biology, 2007)

Herpes simplex virus type 1 shows multiple interactions with sulfonated compounds at binding, penetration, and cell-to-cell passage - José Santiago Aguilar; Katherine S. Held; Edward K. Wagner (Virus Genes, 2007)

In vitro rooting of microshoots of Cotinus coggygria Mill, a woody ornamental plant - Peter S. R. Metivier; Edward C. Yeung; Kamlesh R. Patel; Trevor A. Thorpe (In Vitro Cellular & Developmental Biology - Plant, 2007)

AAPS-FDA Workshop White Paper: Microdialysis Principles, Application and Regulatory Perspectives - Chandra S. Chaurasia; Markus Müller; Edward D. Bashaw; Eva Benfeldt; Jan Bolinder; Ross Bullock; Peter M. Bungay; Elizabeth C. M. DeLange; Hartmut Derendorf; William F. Elmquist; Margareta Hammarlund-Udenaes; Christian Joukhadar; et al. (Pharmaceutical Research, 2007)

GPS sidereal filtering: coordinate- and carrier-phase-level strategies - A. E. Ragheb; P. J. Clarke; S. J. Edwards (Journal of Geodesy, 2007)

Post‐glacial changes in spatial patterns of vegetation across southern New England - W. Wyatt Oswald; Edward K. Faison; David R. Foster; Elaine D. Doughty; Brian R. Hall; Barbara C. S. Hansen (Journal of Biogeography, 2007)
Aim We analysed lake‐sediment pollen records from eight sites in southern New England to address: (1) regional variation in ecological responses to post‐glacial climatic changes, (2) landscape‐scale vegetational heterogeneity at different times in the past, and (3) environmental and ecological controls on spatial patterns of vegetation. Location The eight study sites are located in southern New England in the states of Massachusetts and Connecticut. The sites span a climatic and vegetational gradient from the lowland areas of eastern Massachusetts and Connecticut to the uplands of north‐central and western Massachusetts. Tsuga canadensis and Fagus grandifolia are abundant in the upland area, while Quercus , Carya and Pinus species have higher abundances in the lowlands. Methods We collected sediment cores from three lakes in eastern and north‐central Massachusetts (Berry East, Blood and Little Royalston Ponds). Pollen records from those sites were compared with previously published pollen data from five other sites. Multivariate data analysis (non‐metric multi‐dimensional scaling) was used to compare the pollen spectra of these sites through time. Results Our analyses revealed a sequence of vegetational responses to climate changes occurring across southern New England during the past 14,000 calibrated radiocarbon years before present (cal yr bp ). Pollen assemblages at all sites were dominated by Picea and Pinus banksiana between 14,000 and 11,500 cal yr bp ; by Pinus strobus from 11,500 to 10,500 cal yr bp ; and by P. strobus and Tsuga between 10,500 and 9500 cal yr bp . At 9500–8000 cal yr bp , however, vegetation composition began to differentiate between lowland and upland sites. Lowland sites had higher percentages of Quercus pollen, whereas Tsuga abundance was higher at the upland sites. This spatial heterogeneity strengthened between 8000 and 5500 cal yr bp , when Fagus became abundant in the uplands and Quercus pollen percentages increased further in the lowland records. The differentiation of upland and lowland vegetation zones remained strong during the mid‐Holocene Tsuga decline (5500–3500 cal yr bp ), but the pattern weakened during the late‐Holocene (3500–300 cal yr bp ) and European‐settlement intervals. Within‐group similarity declined in response to the uneven late‐Holocene expansion of Castanea , while between‐group similarity increased due to homogenization of the regional vegetation by forest clearance and ongoing disturbances. Main conclusions The regional gradient of vegetation composition across southern New England was first established between 9500 and 8000 cal yr bp . The spatial heterogeneity of the vegetation may have arisen at that time in response to the development or strengthening of the regional climatic gradient. Alternatively, the differentiation of upland and lowland vegetation types may have occurred as the climate ameliorated and an increasing number of species arrived in the region, arranging themselves in progressively more complex vegetation patterns across relatively stationary environmental gradients. The emergence of a regional vegetational gradient in southern New England may be a manifestation of the increasing number of species and more finely divided resource gradient.

Characterization and multi-generational stability of the growth hormone transgene (EO-1α) responsible for enhanced growth rates in Atlantic Salmon - Edward S. Yaskowiak; Margaret A. Shears; Alka Agarwal-Mawal; Garth L. Fletcher (Transgenic Research, 2007)

AAPS-FDA workshop white paper: Microdialysis principles, application, and regulatory perspectives report from the Joint AAPS-FDA Workshop, November 4–5, 2005, Nashville, TN - Chandra S. Chaurasia; Markus Müller; Edward D. Bashaw; Eva Benfeldt; Jan Bolinder; Ross Bullock; Peter M. Bungay; Elizabeth C. M. DeLange; Hartmut Derendorf; William F. Elmquist; Margareta Hammarlund-Udenaes; Christian Joukhadar; et al. (The AAPS Journal, 2007)

Spatio-temporal patterns in county-level incidence and reporting of Lyme disease in the northeastern United States, 1990–2000 - Lance A. Waller; Brett J. Goodwin; Mark L. Wilson; Richard S. Ostfeld; Stacie L. Marshall; Edward B. Hayes (Environmental and Ecological Statistics, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

Phylogeny of Bonatea (Orchidaceae: Habenariinae) based on molecular and morphological data - M. E. Ponsie; A. Mitchell; T. J. Edwards; S. D. Johnson (Plant Systematics and Evolution, 2007)

Redressing cultural erosion and ecological decline in a far North Queensland aboriginal community (Australia): the Aurukun ethnobiology database project - S. E. Edwards; M. Heinrich (Environment, Development and Sustainability, 2006)

A prospective study of fish, marine fatty acids, and bladder cancer risk among men and women (United States) - Crystal N. Holick; Edward L. Giovannucci; Meir J. Stampfer; Dominique S. Michaud (Cancer Causes & Control, 2006)

An eddy covariance mesonet to measure the effect of forest age on land–atmosphere exchange - MICHAEL L. GOULDEN; GREGORY C. WINSTON; ANDREW M. S. McMILLAN; MARCY E. LITVAK; EDWARD L. READ; ADRIAN V. ROCHA; J. ROB ELLIOT (Global Change Biology, 2006)
We deployed a mesonet of year‐round eddy covariance towers in boreal forest stands that last burned in ∼1850, ∼1930, 1964, 1981, 1989, 1998, and 2003 to understand how CO 2 exchange and evapotranspiration change during secondary succession. We used MODIS imagery to establish that the tower sites were representative of the patterns of secondary succession in the region, and Landsat images to show that the individual stands have changed over the last 22 years in ways that match the spatially derived trends. The eddy covariance towers were well matched, with similar equipment and programs, which maximized site‐to‐site precision and allowed us to operate the network in an efficient manner. The six oldest sites were fully operational for ∼90% of the growing season and ∼70% of the dormant season from 2001 or 2002 to 2004, with most of the missing data caused by low battery charge or bad signals from the sonic anemometers. The rates of midday growing‐season CO 2 uptake recovered to preburn levels within 4 years of fire. The seasonality of land–atmosphere exchange and growing‐season length changed markedly with stand age. The foliage in the younger stands (1989, 1998, and 2003 burns) was almost entirely deciduous, which resulted in comparatively short growing seasons that lasted ∼65 days. In contrast, the older stands (1850, 1930, 1964, and 1981) were mostly evergreen, which resulted in comparatively long growing seasons that lasted ∼130 days. The eddy covariance mesonet approach we describe could be used within the context of other ecological experimental designs such as controlled manipulations and gradient comparisons.

Temperature‐independent diel variation in soil respiration observed from a temperate deciduous forest - Q. LIU; N. T. EDWARDS; W. M. POST; L. GU; J. LEDFORD; S. LENHART (Global Change Biology, 2006)
The response of soil respiration ( R s ) to temperature depends largely on the temporal and spatial scales of interest and how other environmental factors interact with this response. They are often represented by empirical exponential equations in many ecosystem analyses because of the difficulties in separating covarying environmental responses and in observing below ground processes. The objective of this study was to quantify a soil temperature‐independent component in R s by examining the diel variation of an R s time series measured in a temperate deciduous forest located at Oak Ridge, TN, USA between March and December 2003. By fitting 2 hourly, continuous automatic chamber measurements of CO 2 efflux at the soil surface to a Q 10 function to obtain the temperature‐dependent respiration ( R t ) and plotting the diel cycles of R t , R s , and their difference ( R i ), we found that an obvious temperature‐independent component exists in R s during the growing season. The diel cycle of this component has a distinct day/night pattern and agrees well with diel variations in photosynthetically active radiation (PAR) and air temperature. Elevated canopy CO 2 concentration resulted in similar patterns in the diel cycle of the temperature‐independent component but with different daily average rates in different stages of growing season. We speculate that photosynthesis of the stand is one of the main contributors to this temperature‐independent respiration component although more experiments are needed to draw a firm conclusion. We also found that despite its relatively small magnitude compared with the temperature‐dependent component, the diel variation in the temperature‐independent component can lead to significantly different estimates of the temperature sensitivity of soil respiration in the study forest. As a result, the common practice of using fitted temperature‐dependent function from night‐time measurements to extrapolate soil respiration during the daytime may underestimate daytime soil respiration.

Effect of animal browse protection and fertilizer application on the establishment of planted Nuttall oak seedlings - Troy S. Taylor; Edward F. Loewenstein; Arthur H. Chappelka (New Forests, 2006)

Spatial strategies in real and virtual environments - Tamas Makany; Itiel E. Dror; Edward S. Redhead (Cognitive Processing, 2006)

Temporal and spatial appearance of wall polysaccharides during cellularization of barley (Hordeum vulgare) endosperm - Sarah M. Wilson; Rachel A. Burton; Monika S. Doblin; Bruce A. Stone; Edward J. Newbigin; Geoffrey B. Fincher; Antony Bacic (Planta, 2006)

Effects of neuromuscular electrical stimulation parameters on specific tension - Ashraf S. Gorgey; Edward Mahoney; Tracee Kendall; Gary A. Dudley (European Journal of Applied Physiology, 2006)

Characterization and multi-generational stability of the growth hormone transgene (EO-1α) responsible for enhanced growth rates in Atlantic Salmon - Edward S. Yaskowiak; Margaret A. Shears; Alka Agarwal-Mawal; Garth L. Fletcher (Transgenic Research, 2006)

Pharmacodynamics of Antiretroviral Agents in HIV-1 Infected Patients: Using Viral Dynamic Models that Incorporate Drug Susceptibility and Adherence - Hulin Wu; Yangxin Huang; Edward P. Acosta; Jeong -Gun Park; Song Yu; Susan L. Rosenkranz; Daniel R. Kuritzkes; Joseph J. Eron; Alan S. Perelson; John G. Gerber (Journal of Pharmacokinetics and Pharmacodynamics, 2006)

Movement patterns of the limpet Cellana grata (Gould) observed over a continuous period through a changing tidal regime - Mark S. Davies; M. Edwards; Gray A. Williams (Marine Biology, 2006)

Smooth muscle trans-membrane sarcoglycan complex in partial bladder outlet obstruction - Edward J. Macarak; Jake Schulz; Stephen A. Zderic; Yoshikazu Sado; Yoshifumi Ninomiya; Erzsebet Polyak; Samuel Chacko; Pamela S. Howard (Histochemistry and Cell Biology, 2006)

Cryptic Processes in the Sea: A Review of Delayed Development in theMicroscopic Life Stages of Marine Macroalgae - Laura T. Carney; Matthew S. Edwards (Algae, 2006)

Phosphorus Translocation by Red Deer on a Subalpine Grassland in the Central European Alps - Martin Schütz; Anita C. Risch; Gérald Achermann; Conny Thiel-Egenter; Deborah S. Page-Dumroese; Martin F. Jurgensen; Peter J. Edwards (Ecosystems, 2006)

Millennial timescale carbon cycle and climate change in an efficient Earth system model - T. M. Lenton; M. S. Williamson; N. R. Edwards; R. Marsh; A. R. Price; A. J. Ridgwell; J. G. Shepherd; S. J. Cox (Climate Dynamics, 2006)

Interactions between Widely Spaced Young Poplars (Populus spp.) and the Understorey Environment - G. B. Douglas; A. S. Walcroft; S. E. Hurst; J. F. Potter; A. G. Foote; L. E. Fung; W. R. N. Edwards; C. van den Dijssel (Agroforestry Systems, 2006)

Revision of the Mouse Lemurs (Microcebus) of Eastern Madagascar - Edward E. Louis; Melissa S. Coles; Rambinintsoa Andriantompohavana; Julie A. Sommer; Shannon E. Engberg; John R. Zaonarivelo; Mireya I. Mayor; Rick A. Brenneman (International Journal of Primatology, 2006)

Nickel hyperaccumulation by Streptanthus polygaloides protects against the folivore Plutella xylostella (Lepidoptera: Plutellidae) - Edward M. Jhee; Robert S. Boyd; Micky D. Eubanks; Micheal A. Davis (Plant Ecology, 2006)

Two-locus genome-wide linkage scan for prostate cancer susceptibility genes with an interaction effect - Bao-Li Chang; Ethan M. Lange; Latchezar Dimitrov; Christopher J. Valis; Elizabeth M. Gillanders; Leslie A. Lange; Kathleen E. Wiley; Sarah D. Isaacs; Fredrik Wiklund; Agnes Baffoe-Bonnie; Carl D Langefeld; S. Lilly Zheng; et al. (Human Genetics, 2006)

Oracle-based optimization applied to climate model calibration - Cesar Beltran; N. R. Edwards; A. B. Haurie; J.-P. Vial; D. S. Zachary (Environmental Modeling & Assessment, 2006)

Effectiveness of Metal–Metal and Metal–Organic Compound Combinations Against Plutella xylostella: Implications for Plant Elemental Defense - Edward M. Jhee; Robert S. Boyd; Micky D. Eubanks (Journal of Chemical Ecology, 2006)

Interactions between Widely Spaced Young Poplars (Populus spp.) and Introduced Pasture Mixtures - G. B. Douglas; A. S. Walcroft; S. E. Hurst; J. F. Potter; A. G. Foote; L. E. Fung; W. R. N. Edwards; C. van den Dijssel (Agroforestry Systems, 2006)

Phosphodiesterase inhibition by sildenafil citrate attenuates a maze learning impairment in rats induced by nitric oxide synthase inhibition - Bryan D. Devan; Jonna L. Bowker; Kara B. Duffy; Ila S. Bharati; Mariana Jimenez; Demetrio Sierra-Mercado; Christopher M. Nelson; Edward L. Spangler; Donald K. Ingram (Psychopharmacology, 2006)

First record of anthracnose of spinach caused by Colletotrichum dematium in Australia - W. S. Washington; G. Irvine; R. Aldaoud; S. DeAlwis; J. Edwards; I. G. Pascoe (Australasian Plant Pathology, 2006)

Intake of Fruits and Vegetables, Carotenoids, Folate, and Vitamins A, C, E and Risk of Bladder Cancer Among Women (United States) - Crystal N. Holick; Immaculata De Vivo; Diane Feskanich; Edward Giovannucci; Meir Stampfer; Dominique S. Michaud (Cancer Causes & Control, 2005)

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

Altered genotypic and phenotypic frequencies of aphid populations under enriched CO 2 and O 3 atmospheres - Edward B. Mondor; Michelle N. Tremblay; Caroline S. Awmack; Richard L. Lindroth (Global Change Biology, 2005)
Environmental change is anticipated to negatively affect both plant and animal populations. As abiotic factors rapidly change habitat suitability, projections range from altered genetic diversity to wide‐spread species loss. Here, we assess the degree to which changes in atmospheric composition associated with environmental change will influence not only the abundance, but also the genotypic/phenotypic diversity, of herbivore populations. Using free‐air CO 2 and O 3 enrichment (FACE) technology, we assess numerical responses of pea aphids ( Acyrthosiphon pisum ) exhibiting a pink–green genetic polymorphism and an environmentally determined wing polyphenism on broad bean plants ( Vicia faba ) under enriched CO 2 and/or O 3 atmospheres, over multiple generations. We show that these two greenhouse gases alter not only aphid population sizes, but also genotypic and phenotypic frequencies. As the green genotype was positively influenced by elevated CO 2 levels, but the pink genotype was not, genotypic frequencies (pink morph : green morph) ranged from 1 : 1 to 9 : 1. These two genotypes also displayed marked differences in phenotypic frequencies. The pink genotype exhibited higher levels of wing induction under all atmospheric treatments, however, this polyphenism was negatively influenced by elevated O 3 levels. Resultantly, frequencies of winged phenotypes (pink morph : green morph) varied from 10 : 1 to 332 : 1. Thus, atmospheric conditions associated with environmental change may alter not just overall population sizes, but also genotypic and phenotypic frequencies of herbivore populations, thereby influencing community and ecosystem functioning.

Impairment of specific episodic memory processes by sub-psychotic doses of ketamine: the effects of levels of processing at encoding and of the subsequent retrieval task - Garry D. Honey; Rebekah A. E. Honey; Sam R. Sharar; Danielle C. Turner; Edith Pomarol-Clotet; Dharshan Kumaran; Jon S. Simons; Xiangen Hu; Michael D. Rugg; Edward T. Bullmore; Paul C. Fletcher (Psychopharmacology, 2005)

Cell Proliferation of Cultured Human Cancer Cells are Affected by the Elevated Tumor Pressures that Exist In Vivo - Gene R. DiResta; Saminathan S. Nathan; Mark W. Manoso; Jorge Casas-Ganem; Chris Wyatt; Tadaheko Kubo; Patrick J. Boland; Edward A. Athanasian; Jonathan Miodownik; Richard Gorlick; John H. Healey (Annals of Biomedical Engineering, 2005)

Development of baroreflex and endocrine responses to hypotensive stress in newborn foals and lambs - S. J. O’Connor; D. S. Gardner; J. C. Ousey; N. Holdstock; P. Rossdale; C. M. B. Edwards; A. L. Fowden; D. A. Giussani (Pflügers Archiv - European Journal of Physiology, 2005)

Sleep quality deteriorates over a binge–abstinence cycle in chronic smoked cocaine users - Edward F. Pace-Schott; Robert Stickgold; Amir Muzur; Pia E. Wigren; Amie S. Ward; Carl L. Hart; Denise Clarke; Alexandra Morgan; J. Allan Hobson (Psychopharmacology, 2005)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Delayed recovery of giant kelp near its southern range limit in the North Pacific following El Niño - M. S. Edwards; G. Hernández-Carmona (Marine Biology, 2005)

Construction of a Festuca pratensis BAC library for map-based cloning in Festulolium substitution lines - Iain S. Donnison; Donal M. O’Sullivan; Ann Thomas; Peter Canter; Beverley Moore; Ian Armstead; Howard Thomas; Keith J. Edwards; Ian P. King (Theoretical and Applied Genetics, 2005)

Conservation genetics and Pacific fisheries bycatch: Mitochondrial differentiation and population assignment in black-footed albatrosses (Phoebastria nigripes) - H. E. Walsh; S. V. Edwards (Conservation Genetics, 2005)

6-Alkylsalicylic Acids and 6-Alkylresorcylic Acids from Ants in the Genus Crematogaster from Brunei - T. H. JONES; S. R. BRUNNER; A. A. EDWARDS; D. W. DAVIDSON; R. R. SNELLING (Journal of Chemical Ecology, 2005)

NMI-1182, a gastro-protective cyclo-oxygenase-inhibiting nitric oxide donor - James L. Ellis; Michael E. Augustyniak; Edward D. Cochran; Richard A. Earl; David S. Garvey; Laura J. Gordon; David R. Janero; Subhash P. Khanapure; L. Gordon Letts; Terry L. Melim; Madhavi G. Murty; David J. Schwalb; et al. (Inflammopharmacology, 2005)

A new locus for nonsyndromic deafness DFNB49 maps to chromosome 5q12.3-q14.1 - Khushnooda Ramzan; Rehan S. Shaikh; Jamil Ahmad; Shaheen N. Khan; Saima Riazuddin; Zubair M. Ahmed; Thomas B. Friedman; Edward R. Wilcox; Sheikh Riazuddin (Human Genetics, 2005)

Bistability of the thermohaline circulation identified through comprehensive 2-parameter sweeps of an efficient climate model - R. Marsh; A. Yool; T. M. Lenton; M. Y. Gulamali; N. R. Edwards; J. G. Shepherd; M. Krznaric; S. Newhouse; S. J. Cox (Climate Dynamics, 2004)

Relationship between the incidences of ear and spikelet infection of Fusarium ear blight in wheat - X.-m. Xu; D.W. Parry; S.G. Edwards; B.M. Cooke; F.M. Doohan; A. Maanen; J.M. Brennan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; L. Hornok; et al. (European Journal of Plant Pathology, 2004)

Characterization of the dog Agouti gene and a nonagoutimutation in German Shepherd Dogs - Julie A. Kerns; J. Newton; Tom G. Berryere; Edward M. Rubin; Jan-Fang Cheng; Sheila M. Schmutz; Gregory S. Barsh (Mammalian Genome, 2004)

Quaternary ecological and geomorphic changes associated with rainfall events in presently semi‐arid northeastern Brazil - Augusto S. Auler; Xianfeng Wang; R. Lawrence Edwards; Hai Cheng; Patrícia S. Cristalli; Peter L. Smart; David A. Richards (Journal of Quaternary Science, 2004)
Several geomorphic features and palaeobiotic remains in now semi‐arid northeastern Brazil indicate major palaeoenvironmental changes during past periods of increased rainfall. 230 Th mass spectrometric ages of speleothems and travertines have allowed the determination of the timing and duration of wetter than present conditions. The data demonstrate that wet events have occurred throughout much of the Pleistocene, present dry conditions having been established at the end of the Younger Dryas. A markedly different fauna comprising megafaunal elements not adapted to the present low arboreal scrubland caatinga vegetation existed in the area. Palaeobotanical remains embedded in travertine indicate forested vegetation at these wetter intervals, suggesting that the caatinga was then replaced or mixed with a semi‐deciduous forest. Due to the abundance of travertine sites containing fossil botanical remains in northeastern Brazil, it is believed that forest expansion occurred over large areas of the now semi‐arid zone, showing that the long hypothesised forested links between biodiversity‐rich Amazon and Atlantic rainforests may indeed have existed during these moister phases. Copyright © 2004 John Wiley & Sons, Ltd.

Divergent pheromone‐mediated insect behaviour under global atmospheric change - Edward B. Mondor; Michelle N. Tremblay; Caroline S. Awmack; Richard L. Lindroth (Global Change Biology, 2004)
While the effects of global atmospheric changes on vegetation and resulting insect populations(‘bottom‐up interactions’) are being increasingly studied, how these gases modify interactions among insects and their natural enemies (‘top‐down interactions’) is less clear. As natural enemy efficacy is governed largely by behavioural mechanisms, altered prey finding and prey defence may change insect population dynamics. Here we show that pheromone‐mediated escape behaviours, and hence the vulnerability of insects to natural enemies, are divergent under atmospheric conditions associated with global climate change. Chaitophorus stevensis , a common aphid on trembling aspen trees, Populus tremuloides , have diminished escape responses in enriched carbon dioxide (CO 2 ) environments, while those in enriched ozone (O 3 ) have augmented escape responses, to alarm pheromone. These results suggest that divergent pheromone‐mediated behaviours could alter predator–prey interactions in future environments.

Mapping Ds insertions in barley using a sequence-based approach - L. D. Cooper; L. Marquez-Cedillo; J. Singh; A. K. Sturbaum; S. Zhang; V. Edwards; K. Johnson; A. Kleinhofs; S. Rangel; V. Carollo; P. Bregitzer; P. G. Lemaux; et al. (Molecular Genetics and Genomics, 2004)

Dissolved solids do not induce diapause in the calanoid copepod Aglaodiaptomus leptopus - Steve S. Di Lonardo; Edward J. Maly (Aquatic Ecology, 2004)

Implications of Anthropogenic Landscape Change on Inter-Population Movements of the Desert Tortoise (Gopherus agassizii) - Taylor Edwards; Cecil R. Schwalbe; Don E. Swann; Caren S. Goldberg (Conservation Genetics, 2004)

West Nile virus: pending crisis for greater sage‐grouse - David E. Naugle; Cameron L. Aldridge; Brett L. Walker; Todd E. Cornish; Brendan J. Moynahan; Matt J. Holloran; Kimberly Brown; Gregory D. Johnson; Edward T. Schmidtmann; Richard T. Mayer; Cecilia Y. Kato; Marc R. Matchett; et al. (Ecology Letters, 2004)
Scientists have feared that emerging infectious diseases could complicate efforts to conserve rare and endangered species, but quantifying impacts has proven difficult until now. We report unexpected impacts of West Nile virus (WNv) on radio‐marked greater sage‐grouse ( Centrocercus urophasianus ), a species that has declined 45–80% and is endangered in Canada and under current consideration for federal listing in the US. We show that WNv reduced late‐summer survival an average of 25% in four radio‐marked populations in the western US and Canada. Serum from 112 sage‐grouse collected after the outbreak show that none had antibodies, suggesting that they lack resistance. The spread of WNv represents a significant new stressor on sage‐grouse and probably other at‐risk species. While managing habitat might lessen its impact on sage‐grouse populations, WNv has left wildlife and public health officials scrambling to address surface water and vector control issues in western North America.

Hybridization Between Canada Lynx and Bobcats: Genetic Results and Management Implications - Michael K. Schwartz; Kristine L. Pilgrim; Kevin S. McKelvey; Edward L. Lindquist; James J. Claar; Steve Loch; Leonard F. Ruggiero (Conservation Genetics, 2004)

Perchlorate‐reducing microorganisms isolated from contaminated sites - Alison S. Waller; Evan E. Cox; Elizabeth A. Edwards (Environmental Microbiology, 2004)
Summary An extensive microcosm survey of perchlorate‐contaminated sites was undertaken to assess the ability of indigenous microorganisms to degrade perchlorate. Samples from 12 contaminated sites and from one pristine location were analysed. Perchlorate was degraded to below detection limit in all electron donor‐amended microcosms. Perchlorate‐reducing microorganisms (PRMs) were numerous at most of these sites. Sixteen distinct PRMs were isolated that were phylogenetically related to either Dechloromonas in the Beta Proteobacteria (9/16 isolates) or to Azospirillum in the Alpha Proteobacteria (7/16 isolates). The majority of previously isolated PRMs are in the Beta Proteobacteria related to Dechloromonas or Dechlorosoma . This study indicates that PRMs of the genus Azospirillum may be more prevalent at contaminated sites than the current record of isolates suggests. Cell yields, electron donor to perchlorate ratios and maximum specific growth rates were similar among the isolates and similar to the few previously published values. However, the Monod half‐saturation constants for perchlorate for the two Azospirillum isolates characterized were lower than those measured for other genera, suggesting that they may be more effective at low concentrations of perchlorate. These results extend the current understanding of PRMs from diverse environments and provide added confidence that microbial perchlorate reduction is ubiquitous, even at highly contaminated sites, and can be harnessed effectively for bioremediation.

Sources and predictors of resolvable indel polymorphism assessed using rice as a model - J. D. Edwards; V. M. Lee; S. R. McCouch (Molecular Genetics and Genomics, 2004)

Pharmacokinetic and Pharmacodynamic Issues in the Treatment of Parasitic Infections - G. Edwards; S. Krishna (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Highly variable SSR markers in Douglas-fir: Mendelian inheritance and map locations - G. T. Slavov; G. T. Howe; I. Yakovlev; K. J. Edwards; K. V. Krutovskii; G. A. Tuskan; J. E. Carlson; S. H. Strauss; W. T. Adams (Theoretical and Applied Genetics, 2004)

A microsatellite marker based framework linkage map of Vitis vinifera L. - S. Riaz; G. S. Dangl; K. J. Edwards; C. P. Meredith (Theoretical and Applied Genetics, 2004)

Tiba inhibition of in vitro organogenesis in excised tobacco leaf explants - Harbinder S. Dhaliwal; Edward C. Yeung; Trevor A. Thorpe (In Vitro Cellular & Developmental Biology - Plant, 2004)

Qualification of analytical instruments for use in the pharmaceutical industry: A scientific approach - Surendra K. Bansal; Thomas Layloff; Ernest D. Bush; Marta Hamilton; Edward A. Hankinson; John S. Landy; Stephen Lowes; Moheb M. Nasr; Paul A. St. Jean; Vinod P. Shah (AAPS PharmSciTech, 2004)

Qualification of analytical instruments for use in the pharmaceutical industry: A scientific approach - Surendra K. Bansal; Thomas Layloff; Ernest D. Bush; Marta Hamilton; Edward A. Hankinson; John S. Landy; Stephen Lowes; Moheb M. Nasr; Paul A. St. Jean; Vinod P. Shah (AAPS PharmSciTech, 2004)

Estimating scale-dependency in disturbance impacts: El Nios and giant kelp forests in the northeast Pacific - Matthew S. Edwards (Oecologia, 2004)

Properties of human motor units after prolonged activity at a constant firing rate - K. V. B. Johnson; S. C. Edwards; C. Van Tongeren; P. Bawa (Experimental Brain Research, 2004)

EXPLANT-CELL CULTURE OF PRIMARY MAMMARY TUMORS FROM MMTV-c-Myc TRANSGENIC MICE - XU FANG PEI; MARCIA S. NOBLE; MARIA ANTONIETTA DAVOLI; EDWARD ROSFJORD; MADDALENA T. TILLI; PRISCILLA A. FURTH; ROBERT RUSSELL; MICHAEL D. JOHNSON; ROBERT B. DICKSON (In Vitro Cellular & Developmental Biology - Animal, 2004)

GROWTH, IMMORTALIZATION, AND DIFFERENTIATION POTENTIAL OF NORMAL ADULT HUMAN PROXIMAL TUBULE CELLS - DAVID E. OROSZ; PHILIP G. WOOST; ROBERT J. KOLB; MARGARET B. FINESILVER; WENWU JIN; PHYLLIS S. FRISA; CHEE-KEONG CHOO; CHUNG-FAI YAU; KWOK-WAH CHAN; MARTIN I. RESNICK; JANICE G. DOUGLAS; JOHN C. EDWARDS; et al. (In Vitro Cellular & Developmental Biology - Animal, 2004)

Preparing for Climatic Change: The Water, Salmon, and Forests of the Pacific Northwest - Philip W. Mote; Edward A. Parson; Alan F. Hamlet; William S. Keeton; Dennis Lettenmaier; Nathan Mantua; Edward L. Miles; David W. Peterson; David L. Peterson; Richard Slaughter; Amy K. Snover (Climatic Change, 2003)

Family history and colorectal cancer: predictors of risk - M.L. Slattery; T.R. Levin; K. Ma; D. Goldgar; R. Holubkov; S. Edwards (Cancer Causes & Control, 2003)

Tuna schools/aggregations in surface longline data 1993–98 - David S. Kirby; Edward R. Abraham; Michael J. Uddstrom; Hudson Dean (New Zealand Journal of Marine and Freshwater Research, 2003)
Exploratory data analysis of a high‐resolution (hook‐by‐hook), 6‐year time series (1993–98) of observed longline catch data for tunas was used to investigate fine‐scale spatial patterns along individual sets that may be indicative of social behaviour (i.e., schooling) and/or the response of individual fish to favourable extrinsic conditions (i.e., aggregation). Methods of spatial data analysis (i.e., nearest neighbour analysis) that have previously been applied in various other sciences (e.g., forestry and astronomy) were used. Results indicate strong clustering of individual tunas at characteristic scales within the set. Mean Nearest Neighbour Distances (NNDs) were between 100 and 200 m, compared with NNDs of 200–700 m predicted by a heterogeneous Poisson process on the same spatial domain. The results suggest that these adult tunas were either schooling or aggregating at the time of capture; this may therefore be related either to social behaviour or to sub‐mesoscale oceanographic features. An aggregation index was derived from the NNDs, giving a classification method that may be used for similar data and the development of empirical models attempting to relate patterns in fish catch distributions to environmental variables. The success of such models will ultimately depend on elucidating the ecological processes reflected in oceanographic features at biologically meaningful spatial scales.

Characterization of expressed pigmented core light harvesting complex (LH 1) in a reaction center deficient mutant of Blastochloris viridis - Agnes E. Ostafin; Nina S. Ponomarenko; Julia A. Popova; Martin Jäger; Edward J. Bylina; James R. Norris (Photosynthesis Research, 2003)

Haplotype diversity in the interleukin-4 gene is not associated with HIV-1 transmission and AIDS progression - William S. Modi; Thomas R. O'Brien; David Vlahov; Susan Buchbinder; Edward Gomperts; John Phair; Stephen J. O'Brien; Cheryl Winkler (Immunogenetics, 2003)

Effects of ultraviolet radiation on toad early life stages - Edward E. Little; Robin D. Calfee; David L. Fabacher; Cynthia Carey; Vicki S. Blazer; Elizabeth M. Middleton (Environmental Science and Pollution Research, 2003)

Matrix synthesis by bladder smooth muscle cells is modulated by stretch frequency - Douglas E. Coplen; Edward J. Macarak; Pamela S. Howard (In Vitro Cellular & Developmental Biology - Animal, 2003)

Selecting in situ conservation sites for grape genetic resources in the USA - Diane S. Pavek; Warren F. Lamboy; Edward J. Garvey (Genetic Resources and Crop Evolution, 2003)

Understanding Climatic Impacts, Vulnerabilities, and Adaptation in the United States: Building a Capacity for Assessment - Edward A. Parson; Robert W. Corell; Eric J. Barron; Virginia Burkett; Anthony Janetos; Linda Joyce; Thomas R. Karl; Michael C. MacCracken; Jerry Melillo; M. Granger Morgan; David S. Schimel; Thomas Wilbanks (Climatic Change, 2003)

Nitrous oxide emission from agricultural drainage waters - David S. Reay; Keith A. Smith; Anthony C. Edwards (Global Change Biology, 2003)
Uncertainty about the amounts of the greenhouse gas nitrous oxide (N 2 O), which arise from N leaching from agricultural soils, predominantly as nitrate (NO 3 – ), is large. To date, the bulk of studies of N 2 O in aquatic systems have relied upon measurement of dissolved N 2 O concentrations at wide spatial intervals (of the order of km) down a stream, river or estuary. When we combined a fine‐scale (m) assessment of N 2 O concentrations in agricultural drainage water with novel measurement of net N 2 O emission from the same drainage system, we found that dissolved N 2 O in agricultural drainage water was very rapidly lost to the atmosphere, while dissolved NO 3 – in the same water was conserved. Consequently, the N 2 O emission factor (as a proportion of the nitrate‐N present, the IPCC's ‘EF 5 ’) fell by a factor of more than 5 within only 100 m. Direct measurement of N 2 O emission from the drainage water confirmed the disappearance of N 2 O as being due to emission from water to the atmosphere, rather than in situ consumption by denitrification. Our findings indicate that making widely spaced measurements of dissolved N 2 O concentration and/or emissions from the water surface will not take account of this much more dynamic behaviour over short distances. Realistic assessment of the ‘indirect’ agricultural emissions of N 2 O from leached N will necessitate much more intensive sampling of the whole drainage system, from ditch to stream to river to estuary, accompanied by measurements of in‐stream production. The quantities of N 2 O actually released in the ditches gave values for EF 5‐g (the IPCC's emission factor for N 2 O from surface drainage and groundwaters) of between 0.02 and 0.03%, compared with the IPCC value of 1.5%. For the latter to be realistic, the quantity of N 2 O required to be formed after the initial entry of water into the drainage system would need to exceed the initial load by the order of 50‐fold.

MATRIX SYNTHESIS BY BLADDER SMOOTH MUSCLE CELLS IS MODULATED BY STRETCH FREQUENCY - DOUGLAS E. COPLEN; EDWARD J. MACARAK; PAMELA S. HOWARD (In Vitro Cellular & Developmental Biology - Animal, 2003)

Four new species of Roupala (Proteaceae) - K. S. Edwards; G. T. Prance (Brittonia, 2003)

Diatom—chemistry relationships in Yellowstone Lake (Wyoming) sediments: Implications for climatic and aquatic processes research - Sebastian J. Interlandi; Susan S. Kilham; Edward C. Theriot (Limnology and Oceanography, 2003)
We analyzed sediment elemental composition (C, N, P, and Si) and planktonic diatom fossils from the top 32 cm of a short core (55 cm) from Yellowstone Lake (Wyoming), tracking deposition from about 1650 to 1998. Associations between fossil communities and sediment chemistry were measured by rank‐order correlation to gauge decadal scale relationships between lake chemistry and phytoplankton community composition. Strong associations were found between the abundance of individual diatom species and the chemical composition of sediments, suggesting that sediment chemistry can directly track the elemental composition of seston. Among three fossil measures (relative frustule abundance, relative biovolume, and absolute biovolume), associations between sediment chemistry and relative biovolume were strongest. We then compared measures and trends in sediment elemental composition to in‐lake seston chemistry to assess transport processes that alter sediment composition relative to source material. On the basis of elemental stoichiometry, sediments were enriched in P and depleted in C and N compared with seston. Trends of increasing C and N accumulation along with decreasing Si accumulation were consistent with patterns of increasing productivity, increasing lake N levels, and decreasing dominance of diatoms, respectively. A sharp increase in sediment C:N ratio, with a decrease in diatom absolute biovolume and absolute C and N levels, was associated with a prolonged drought in the 1930s. These trends suggest alteration of ecosystem properties by a combination of climatic variation and increasing N availability, adding complexity to larger goals of climatic reconstruction by diatom—nutrient chemistry—climate transfer functions in large lakes of the region.

Genetic mapping of grapevine (Vitis vinifera L.) applied to the detection of QTLs for seedlessness and berry weight - A. Doligez; A. Bouquet; Y. Danglot; F. Lahogue; S. Riaz; C. Meredith; K. Edwards; P. This (Theoretical and Applied Genetics, 2002)

The Homogeneous Finite-Difference Formulation of the P-SV-Wave Equation of Motion - Raphael S. Slawinski; Edward S. Krebes (Studia Geophysica et Geodaetica, 2002)

Characterization of the flanking regions of Zea mays microsatellites reveals a large number of useful sequence polymorphisms - R. Mogg; J. Batley; S. Hanley; D. Edwards; H. O'Sullivan; K. Edwards (Theoretical and Applied Genetics, 2002)

The family Tymoviridae - G. P. Martelli; S. Sabanadzovic; N. Abou-Ghanem Sabanadzovic; M. C. Edwards; T. Dreher (Archives of Virology, 2002)

The Importance of Temperature in Assessing Iron Pipe Corrosion in Water Distribution Systems - Laurie S. McNeill; Marc Edwards (Environmental Monitoring and Assessment, 2002)

Region Specific Modeling of Cardiac Muscle: Comparison of Simulated and Experimental Potentials - Adam L. Muzikant; Edward W. Hsu; Patrick D. Wolf; Craig S. Henriquez (Annals of Biomedical Engineering, 2002)

Nonsyndromic recessive deafness DFNB18 and Usher syndrome type IC are allelic mutations of USHIC - Zubair M. Ahmed; Tenesha N. Smith; Saima Riazuddin; Tomoko Makishima; Manju Ghosh; Sirosh Bokhari; Puthezhath S. Menon; Dilip Deshmukh; Andrew J. Griffith; Sheikh Riazuddin; Thomas B. Friedman; Edward R. Wilcox (Human Genetics, 2002)

A high degree of genetic diversity is revealed in Isatis spp. (dyer's woad) by amplified fragment length polymorphism (AFLP) - K. Gilbert; S. Garton; M. Karam; G. Arnold; A. Karp; K. Edwards; D. Cooke; J. Barker (Theoretical and Applied Genetics, 2002)

The stratigraphic evolution of the Indus Fan and the history of sedimentation in the Arabian Sea - Peter Clift; Christoph Gaedicke; Rosemary Edwards; Jae Il Lee; Peter Hildebrand; Shahid Amjad; Robert S. White; Hans-Ulrich Schlüter (Marine Geophysical Research, 2002)

Metabolic modelling of microbes: the flux‐balance approach - Jeremy S. Edwards; Markus Covert; Bernhard Palsson (Environmental Microbiology, 2002)

Estimating recharge at Yucca Mountain, Nevada, USA: comparison of methods - Alan L. Flint; Lorraine E. Flint; Edward M. Kwicklis; June T. Fabryka-Martin; Gudmundur S. Bodvarsson (Hydrogeology Journal, 2002)

Plant frequency, stem and root characteristics, and CO2 uptake for Opuntia acanthocarpa: elevational correlates in the northwestern Sonoran Desert - Park S. Nobel; Edward G. Bobich (Oecologia, 2002)

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VI. The pioneer arthropod community of Motmot - John S. Edwards; Ian W. B. Thornton (Journal of Biogeography, 2001)

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)
Location, aims Long Island's biota was destroyed by volcanic eruption in c. 1645, and Motmot, an emergent island in its caldera lake, was re‐created in 1968, providing a nested pair of natural colonization sequences. In 1999 we surveyed the plants and vertebrates of Long and the entire biota of Motmot for comparison with previous surveys of Long (1932, 1972, birds only) and Motmot (1969–88). Results The known flora of Long is 305 vascular plants (thirty‐two pteridophytes, 273 spermatophytes), including thirty‐one Ficus species, the sixteen fruiting all having pollinating wasps, and there were eleven species of effective fig dispersers. There were two frog species, a crocodile, a monitor, seven skinks, four geckos, a boid snake, fifty species non‐migrant land birds, seven bats, two rats, a cuscus (probably introduced) and feral pigs, dogs, cats and chickens. Most of Motmot's surface was barren or sparsely vegetated ash, cinder and lava fields. There were seven pteridophyte and thirty‐eight spermatophyte species, including eight Ficus , and the cumulative known flora comprises eleven pteridophytes and fifty‐one spermatophytes, mainly zoochorous and anemochorous, with sedges, grasses and herbs predominating. All Ficus individuals but one were small; three plants of two species bore syconia but had not been pollinated and had not set seed. Motmot's known invertebrate fauna comprises thirty‐five species, mainly predators and scavengers; two spider and one ant species dominating. An insectivorous bat and eight land bird species (three breeding) were the only vertebrates. Main conclusions Long's biota comprised mainly widely distributed species with broad ecological tolerances, well‐adapted for colonizing species‐poor islands. The mid‐level caldera plateau, as in 1932, was covered in fairly open forest of similar‐sized trees with a few much larger individuals and little or no understorey. Primary rain forest tree species from the region were under‐represented or absent but secondary forest species were common. There were few regional endemic Ficus species. The avifauna comprised species with good dispersal ability, lacked endemic subspecies and probably for at least the past seven decades has been held at a quasi‐equilibrium of fifty species, fourteen below the theoretical number. More than half the fifty‐four resident land birds known from Long (and three of the seven bats) are high class tramps in the sense of Diamond; only two birds are high‐S species. Turnover has been low and none of the bird super tramps has been replaced. The non‐avian fauna comprised mostly high‐category tramptype species with relatively broad habitat requirements and extensive geographical ranges. Non‐volant vertebrates comprised a number of highly vagile species associated with humans. Several groups, especially snakes and amphibians, were depauperate compared with the fauna of other islands in the area. Long's biota is evidently held at an arrested stage of development by some physical factor, possibly the extremely porous substratum and relatively dry climate. The allochthonous input of lake insects to Motmot evidently provides the major energy source for its animal communities, with a very minor contribution from organic flotsam. Reflecting Motmot's very isolated situation, plant colonization has been slow, but when more fig individuals mature and fig–wasp populations become established fruit production should attract frugivores and start a positive feedback process which will accelerate the growth of Motmot's community. Long's colonization shows similarities with that of Krakatau (Sunda Strait, Indonesia) after the 1883 eruption, and species shared by the two include a high proportion of pioneer species. Motmot's triple isolation (sea, land and fresh‐water barriers) means that its colonization differs markedly from those on two marine emergent islands of the region, Tuluman (Admiralty Group) and Anak Krakatau.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VI. The pioneer arthropod community of Motmot - John S. Edwards; Ian W. B. Thornton (Journal of Biogeography, 2001)
Aim To evaluate the arthropod community of Motmot in relation to primary colonization of young volcanic surfaces. Location Motmot, an island in Lake Wisdom which occupies the caldera of Long Island, Papua New Guinea. Methods Arthropod sampling by means of pitfall, water and tube traps, fallout collectors, and hand collecting. Results At least thirty‐five species of arthropod were collected in 6 days between 23 June and 3 July 1999. Lycosid spiders and ants dominated in all areas. The predator‐scavenger arthropod population is largely or entirely dependent on allochthonous input of aquatic insects from the surrounding lake. Main conclusions Major changes in the arthropod fauna since the pioneer surveys of Ball and his colleagues in the 1970s are the loss of a strand flotsam community as the island has eroded to form a predominantly cliffed coastline. Ant and spider diversity has increased. The current colonists include a number of widespread ‘tramp' species sensu Diamond.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)

The effect of endurance training on resting heart rate variability in sedentary adult males - Edward L. Melanson; Patty S. Freedson (European Journal of Applied Physiology, 2001)

A prospective study on intake of animal products and risk of prostate cancer - Dominique S. Michaud; Katarina Augustsson; Eric B. Rimm; Meir J. Stampfer; Walter C. Willett; Edward Giovannucci (Cancer Causes & Control, 2001)

Unprecedented bleaching-induced mortality in Porites spp. at Rangiroa Atoll, French Polynesia - Mumby P.; Chisholm J.; Edwards A.; Clark C.; Roark E.; Andrefouet S.; Jaubert J. (Marine Biology, 2001)

Novel Chemistry of Abdominal Defensive Glands of Nymphalid Butterfly Agraulis vanillae - Gary N. Ross; Henry M. Fales; Helen A. Lloyd; Tappey Jones; Edward A. Sokoloski; Kimberly Marshall-Batty; Murray S. Blum (Journal of Chemical Ecology, 2001)

Agonistic behavior in naïve juvenile lobsters depleted of serotonin by 5,7-dihydroxytryptamine - Sarah B. Doernberg; Stuart I. Cromarty; Ralf Heinrich; Barbara S. Beltz; Edward A. Kravitz (Journal of Comparative Physiology A, 2001)

Validation of Rapid Velocity Encoded Cine Imaging of a Dynamically Complex Flow Field Using Turbo Block Regional Interpolation Scheme for k Space - Eduardo Kortright; Mark Doyle; Andreas S. Anayiotos; Edward G. Walsh; Anthon R. Fuisz; Gerald M. Pohost (Annals of Biomedical Engineering, 2001)

Tissue distribution and functional expression of the human voltage-gated sodium channel β3 subunit - Edward B. Stevens; Peter J. Cox; Bhaval S. Shah; Alistair K. Dixon; Peter J. Richardson; Robert D. Pinnock; Kevin Lee (Pflügers Archiv - European Journal of Physiology, 2001)

Simple sequence repeat (SSR) markers survey of the cassava (Manihot esculenta Crantz) genome: towards an SSR-based molecular genetic map of cassava - R. E. C. Mba; P. Stephenson; K. Edwards; S. Melzer; J. Nkumbira; U. Gullberg; K. Apel; M. Gale; J. Tohme; M. Fregene (Theoretical and Applied Genetics, 2001)

AN IN VITRO MODEL FOR MURINE URETERIC EPITHELIAL CELLS - P. LaMont Bryant; Lola M. Reid; Edward S. Diala; Barbara D. Abbott; Angela R. Buckalew (In Vitro Cellular & Developmental Biology - Animal, 2001)

Microsatellites for Barren Brome ( Anisantha sterilis ) - J. M. Green; K. J. Edwards; S. L. Usher; J. H. A. Barker; E. J. P. Marshall; R. J. Froud‐Williams; A. Karp (Molecular Ecology, 2000)

Intact negative patterning in rats with fornix or combined perirhinal and postrhinal cortex lesions - Timothy J. Bussey; Rebecca Dias; Edward S. Redhead; John M. Pearce; Janice L. Muir; John P. Aggleton (Experimental Brain Research, 2000)

Assessing the Effects of Natural and Anthropogenic Stressors in the Potomac Estuary: Implications for Long-Term Monitoring - Henry A. Walker; James S. Latimer; Edward H. Dettmann (Environmental Monitoring and Assessment, 2000)

AERIAL VIDEOGRAMMETRY FROM A TETHERED AIRSHIP TO ASSESS MANATEE LIFE‐STAGE STRUCTURE - Richard O. Flamm; Edward C. G. Owen; Caryn F. W. Owen; Randall S. Wells; Doug Nowacek (Marine Mammal Science, 2000)
A bstract Aerial videogrammetry from an airship tethered to a boat was used to assess the life‐stage structure of manatees in the Blue Waters area of the Homosassa River on the west coast of central Florida. Individual frames of videos were loaded onto a computer and lengths of manatees measured using graphics software. All images of manatees were measured independently by three observers. Measurements were transformed to total manatee lengths by calculating the ratio between the measurements of a reference object of known length and the measurement of the manatee. Length estimates were highly variable but were unbiased with respect to observer. Results of an analysis of variance suggested that the hypothesis that lengths differed among days and among observers should not be rejected. Life‐stage structures were represented in three schemes. One scheme‐which included four life stages: dependent calves, juveniles, animals in tramsition between juvenile and adult, and adults‐was included to provide the most information without sacrificing confidence in the life‐stage distribution. Overall, the video system was effective at capturing images of manatees for life‐stage characterization and, with improvements in image resolution, could become a valuable tool for photo‐identification in sight‐resight experiments.

Development and incorporation of microsatellite markers into the linkage map of sugar beet (Beta vulgaris spp.) - S. J. Rae; C. Aldam; I. Dominguez; M. Hoebrechts; S. R. Barnes; K. J. Edwards (Theoretical and Applied Genetics, 2000)

2-Methoxyestradiol: an Endogenous Antiangiogenic and Antiproliferative Drug Candidate - Victor S. Pribluda; Edward R. Gubish; Edward R. Gubish; Theresa M. LaVallee; Anthony Treston; Glenn M. Swartz; Shawn J. Green (Cancer and Metastasis Reviews, 2000)

Identification of theta-class glutathione S-transferase in liver cytosol of the marmoset monkey - Thomas G. Schulz; Frederike A. Wiebel; Ricarda Thier; Diether Neubert; Donald S. Davis; Robert J. Edwards (Archives of Toxicology, 2000)

Geochemistry and tectonic significance of peridotites from the South Sandwich arc-basin system, South Atlantic - J. A. Pearce; P. F. Barker; S. J. Edwards; I. J. Parkinson; P. T. Leat (Contributions to Mineralogy and Petrology, 2000)

Pollen‐based biomes for Beringia 18,000, 6000 and 0 14 C yr bp † - M. E. Edwards; P. M. Anderson; L. B. Brubaker; T. A. Ager; A. A. Andreev; N. H. Bigelow; L. C. Cwynar; W. R. Eisner; S. P. Harrison; F.‐S. Hu; D. Jolly; A. V. Lozhkin; et al. (Journal of Biogeography, 2000)
The objective biomization method developed by Prentice et al . (1996) for Europe was extended using modern pollen samples from Beringia and then applied to fossil pollen data to reconstruct palaeovegetation patterns at 6000 and 18,000 14 C yr bp . The predicted modern distribution of tundra, taiga and cool conifer forests in Alaska and north‐western Canada generally corresponds well to actual vegetation patterns, although sites in regions characterized today by a mosaic of forest and tundra vegetation tend to be preferentially assigned to tundra. Siberian larch forests are delimited less well, probably due to the extreme under‐representation of Larix in pollen spectra. The biome distribution across Beringia at 6000 14 C yr bp was broadly similar to today, with little change in the northern forest limit, except for a possible northward advance in the Mackenzie delta region. The western forest limit in Alaska was probably east of its modern position. At 18,000 14 C yr bp the whole of Beringia was covered by tundra. However, the importance of the various plant functional types varied from site to site, supporting the idea that the vegetation cover was a mosaic of different tundra types.

Central and peripheral tissue distribution of diclofenac after subcutaneous injection in the rat - R. F. Grace; S. R. Edwards; L. E. Mather; Y. Lin; I. Power (Inflammopharmacology, 2000)

Evaluation of 24-color Multifluor-Fluorescence In-situ Hybridization (M-FISH) Karyotyping by Comparison with Reverse Chromosome Painting of the Human Breast Cancer Cell Line T-47D - Yong-Jie Lu; Joanna S. Morris; Paul A. W. Edwards; Janet Shipley (Chromosome Research, 2000)

The structure and function of orchid pollinaria - S. D. Johnson; T. J. Edwards (Plant Systematics and Evolution, 2000)

Occurrence of C3 and C4 photosynthesis in cotyledons and leaves of Salsola species (Chenopodiaceae) - Vladimir I. Pyankov; Elena V. Voznesenskaya; Alexander N. Kuz'min; Maurice S. B. Ku; Eric Ganko; Vincent R. Franceschi; Clanton C. Black; Gerald E. Edwards (Photosynthesis Research, 2000)

Activity in deep intermediate layer collicular neurons during interrupted saccades - Edward L. Keller; Neeraj J. Gandhi; S. Vijay Sekaran (Experimental Brain Research, 2000)

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

Gene trap insertional mutagenesis in mice: New vectors and germ Line mutations in two novel genes - Edward G. Neilan; Gregory S. Barsh (Transgenic Research, 1999)

Photosynthetic acclimation of maize to growth under elevated levels of carbon dioxide - João P. Maroco; Gerald E. Edwards; Maurice S. B. Ku (Planta, 1999)

Malate metabolism by NADP-malic enzyme in plant defense - Paula Casati; María F. Drincovich; Gerald E. Edwards; Carlos S. Andreo (Photosynthesis Research, 1999)

Combination benefit of PEGylated soluble tumor necrosis factor receptor type I (PEG sTNF-RI) and dexamethasone or indomethacin in adjuvant arthritic rats - A. M. Bendele; J. McComb; T. Gould; J. Frazier; E. S. Chlipala; J. Seely; G. Kieft; J. Wolf; C. K. Edwards, III (Inflammation Research, 1999)

A microsatellite marker associated with a QTL for grain protein content on chromosome arm 2DL of bread wheat - M. Prasad; R. K. Varshney; A. Kumar; H. S. Balyan; P. C. Sharma; K. J. Edwards; H-Singh; H. S. Dhaliwal; J. K. Roy; P. K. Gupta (Theoretical and Applied Genetics, 1999)

Identification of a microsatellite on chromosomes 6B and a STS on 7D of bread wheat showing an association with preharvest sprouting tolerance - J. K. Roy; M. Prasad; R. K. Varshney; H. S. Balyan; T. K. Blake; H. S. Dhaliwal; H-Singh; K. J. Edwards; P. K. Gupta (Theoretical and Applied Genetics, 1999)

Identification of stretch-responsive genes in pulmonary artery smooth muscle cells by a two arbitrary primer-based mRNA differential display approach - Brahim Chaqour; Pamela S. Howard; Edward J. Macarak (Molecular and Cellular Biochemistry, 1999)

Identification and characterization of microsatellite loci in ash ( Fraxinus excelsior L.) and their conservation in the olive family (Oleaceae) - F. Lefort; S. Brachet; N. Frascaria‐Lacoste; K. J. Edwards; G. C. Douglas (Molecular Ecology, 1999)

Abundance and polymorphism of microsatellite markers in the tea tree (Melaleuca alternifolia, Myrtaceae) - M. Rossetto; A. McLauchlan; F. C. L. Harriss; R. J. Henry; P. R. Baverstock; L. S. Lee; T. L. Maguire; K. J. Edwards (Theoretical and Applied Genetics, 1999)

Responses of phytoplankton to varied resource availability in large lakes of the Greater Yellowstone Ecosystem - Sebastian J. Interlandi; Susan S. Kilham; Edward C. Theriot (Limnology and Oceanography, 1999)
We assessed phytoplankton dynamics in three lakes in the Greater Yellowstone Ecosystem to better understand the connections between changing environmental conditions and aquatic communities. This work primarily describes the connections between resource availability and phytoplankton seasonal succession in these lakes. We hypothesized that algal species efficient at utilizing a given resource (including N, P, Si, and light) would be correlated with low relative concentrations of those resources. The lakes generally exhibited moderate resource limitation, which is characteristic of lakes in subalpine and subarctic regions. Although in proximity, the lakes all exhibited different resource relationships: Lewis Lake was most P limited, Jackson Lake was most N limited, and Yellowstone Lake exhibited a moderate degree of N limitation along with periodic Si limitation. Mixing depths and light penetration were also variable among lakes. In 1996, spring diatom biomass was dominated by Stephanodiscus minutulus , Asterionella formosa , Aulacoseira subarctica , and Synedra sp. Relative abundances and dominance varied among the lakes. A. formosa and Synedra sp. abundances were positively correlated with total N:total P (TN:TP) levels in an analysis of data from all three lakes. A. subarctica was negatively correlated with TN:TP and all light:nutrient ratios. Species exhibiting late season maxima included Cyclotella bodanica , Fragilaria crotonensis , and Stephanodiscus niagarae . C. bodanica abundances corresponded to high‐light/low‐N situations, whereas S. niagarae maxima were found in high‐TN:TP/low‐light conditions. F. crotonensis abundances were most strongly positively correlated with total Si:TP and TN:TP. Environmental correlations were generally in good agreement with the measured physiological requirements of these species. Additionally, local population maxima of major species of diatoms never coincided.

Using in situ substratum sterilization and fluorescence microscopy in studies of microscopic stages of marine macroalgae - Matthew S. Edwards (Hydrobiologia, 1999)

An example of intron junctional sliding in the gene families encoding squalene monooxygenase homologues in Arabidopsis thaliana and Brassica napus* - Ulrike A. Schäfer; Darwin W. Reed; David G. Hunter; Kening Yao; Alan M. Weninger; Edward W.T. Tsang; Martin J.T. Reaney; Samuel L. MacKenzie; Patrick S. Covello (Plant Molecular Biology, 1999)

Enhanced neointimal growth in cultured rabbit aorta following in vivo balloon angioplasty - William E. Dale; Peter S. Batra; Edward H. Blaine (In Vitro Cellular & Developmental Biology - Animal, 1998)

CO2 and O2 dependence of PS II activity in C4 plants having genetically produced deficiencies in the C3 or C4 cycle - João P. Maroco; Maurice S. B. Ku; Robert T. Furbank; Peter J. Lea; Richard C. Leegood; Gerald E. Edwards (Photosynthesis Research, 1998)

Numerical analysis of the hydrogeologic controls in a layered coastal aquifer system, Oahu, Hawaii, USA - Delwyn S. Oki; William R. Souza; Edward L. Bolke; Glenn R. Bauer (Hydrogeology Journal, 1998)

Gut length, food transit time and diving habit in phocid seals - Per-Erik Mårtensson; Erling S. Nordøy; Edward B. Messelt; Arnoldus Schytte Blix (Polar Biology, 1998)

Screening endoscopy and risk of colorectal cancer in United States men - Charles S. Fuchs; Edward L. Giovannucci; Graham A. Colditz; Anne M. Kavanagh (Cancer Causes & Control, 1998)

A Bayesian neural network method for adverse drug reaction signal generation - A. Bate; M. Lindquist; I. R. Edwards; S. Olsson; R. Orre; A. Lansner; R. M. De Freitas (European Journal of Clinical Pharmacology, 1998)

Gravity and light control of the developmental polarity of regenerating protoplasts isolated from prothallial cells of the fern Ceratopteris richardii - E. S. Edwards; S. J. Roux (Plant Cell Reports, 1998)

Characterising food‐webs in two New Zealand streams - N. G. Jaarsma; S. M. de Boer; C. R. Townsend; R. M. Thompson; E. D. Edwards (New Zealand Journal of Marine and Freshwater Research, 1998)
The food‐web communities of two stony tributaries of the Taieri River in New Zealand were documented. We placed heavy emphasis on algal and macroinvertebrate taxonomy, identifying most taxa to species or morpho‐species level. Food‐web attributes were derived from symmetrical matrices using an Excel macro. The values of the food‐web attributes are generally consistent with generalities that have previously been reported in food‐web studies, although some hypothesisied relationships between connectance and food‐web size did not hold. The patterns detected were robust to the inclusion or exclusion of species that were identified in gut contents but not in field samples. The attributes strongly reflected the trophic status of the streams. Dempsters Creek was classified as autotrophic (based on high primary production and a high ratio of production to respiration) and displayed a larger food‐web size and longer food‐chains than those seen in Healy Creek, which was classified as hetero‐trophic (lower primary production and production to respiration ratio). The importance of dynamic environmental attributes such as production and disturbance in structuring food‐webs is emphasised in this study.

Correlation between Waardenburg syndrome phenotype and genotype in a population of individuals with identified PAX3 mutations - Anita L. DeStefano; L. Adrienne Cupples; Kathleen S. Arnos; J. H. Jr. Asher; Clinton T. Baldwin; Susan Blanton; Melisa L. Carey; Elias O. da Silva; T. B. Friedman; Jacquie Greenberg; Anil K. Lalwani; Aubrey Milunsky; et al. (Human Genetics, 1998)

Single-dose dextropropoxyphene in post-operative pain: a quantitative systematic review - S. L. Collins; J. E. Edwards; R. A. Moore; H. J. McQuay (European Journal of Clinical Pharmacology, 1998)

Kornerupine parageneses in whiteschists and other magnesian rocks: is kornerupine + talc a high-pressure assemblage equivalent to tourmaline + orthoamphibole? - Edward S. Grew; Nikolai N. Pertsev; Stanislav Vrána; Martin G. Yates; Charles K. Shearer; Michael Wiedenbeck (Contributions to Mineralogy and Petrology, 1998)

Modeling Flushing and Mixing in a Deep Estuary - John Eric Edinger; Edward M. Buchak; Venkat S. Kollubru (Water, Air, & Soil Pollution, 1998)

Multiple parameters for the comprehensive evaluation of the susceptibility of Escherichia coli to the silver ion - Guojing Zhao; S. Edward Stevens (BioMetals, 1998)

Changes in biological production of the cyanobacterium, Nostoc sp. strain MAC, under subinhibitory concentrations of tannic acid and related compounds - Guojing Zhao; Jacqueline Watson; Cynthia Crowder; S. Edward Stevens (Journal of Applied Phycology, 1998)

A New Natural Resources Degree for a New Century - Edward C. Jensen; Paul S. Doescher; Bo Shelby (Journal of Forestry, 1998)
Oregon State University is offering a new interdisciplinary undergraduate degree in natural resources. The degree, which emphasizes the skills and knowledge that students need to manage natural resources, crosses traditional disciplinary boundaries and value systems. The rationale behind the new program is described, as well as the degree requirements and challenges associated with the new degree, including employability, advising depth of content, and the special concerns of students, professors, and administrators.

Non-Hodgkin's lymphoma and family history of malignant tumors in a case-control study (United States) - Kangmin Zhu; Robert S. Levine; Yuan Gu; Edward A. Brann; Irene Hall; Lee S. Caplan; Marianna K. Baum (Cancer Causes & Control, 1998)

Withdrawal reactions with selective serotonin re-uptake inhibitors as reported to the WHO system - M. M. S. Stahl; M. Lindquist; M. Pettersson; I. R. Edwards; J. H. Sanderson; N. F. A. Taylor; A. P. Fletcher; J. S. Schou (European Journal of Clinical Pharmacology, 1997)

Mapping to Chromosomes 1 and 12 of mouse homologs of human protein tyrosine phosphatase, receptor-type, related genes encoding pancreatic beta cell autoantigens - Edward H. Leiter; Hideki Tsumura; David V. Serreze; Harold D. Chapman; Daniel U. Rabin; Michael S. Lan; Abner L. Notkins (Mammalian Genome, 1997)

Parity and other reproductive factors and risk of adenomatous polyps of the distal colorectum (United States) - Elizabeth A. Platz; Maria Elena Martinez; Francine Grodstein; Charles S. Fuchs; Graham A. Colditz; Meir J. Stampfer; Edward Giovannucci (Cancer Causes & Control, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Self-learning fuzzy control of atracurium-induced neuromuscular block during surgery - D. G. Mason; J. J. Ross; N. D. Edwards; D. A. Linkens; C. S. Reilly (Medical & Biological Engineering & Computing, 1997)

Effects of inflammation on cell proliferation in the myenteric plexus of the guinea-pig ileum - John S. Bradley Jr.; Edward J. Parr; Keith A. Sharkey (Cell and Tissue Research, 1997)

Establishment of serial persistent infections with bovine viral diarrhoea virus in cattle and sheep and changes in epitope expression related to host species - D. Paton; M. Gunn; J. Sands; F. Yappl; T. Drew; S. Vilcek; S. Edwards (Archives of Virology, 1997)

Mechanism of induction of heme oxygenase by metalloporphyrins in primary chick embryo liver cells: Evidence against a stress-mediated response - Edward E. Cable; Otto S. Gildemeister; Joyce A. Pepe; Richard W. Lambrecht; Herbert L. Bonkovsky (Molecular and Cellular Biochemistry, 1997)

To blink or not to blink: inhibition and facilitation of reflex blinks - Alice S. Powers; Edward J. Schicatano; Michele A. Basso; Craig Evinger (Experimental Brain Research, 1997)

Relation between delayed impairment of cerebral energy metabolism and infarction following transient focal hypoxia-ischaemia in the developing brain - R. M. Blumberg; E. B. Cady; J. S. Wigglesworth; J. E. McKenzie; A. D. Edwards (Experimental Brain Research, 1997)

The role of glutathione in L -2-chloropropionic acid induced cerebellar granule cell necrosis in the rat - I. Wyatt; Andrew Gyte; Michael G. Simpson; Peter S. Widdowson; Edward A. Lock (Archives of Toxicology, 1996)

Elevated serum silicon levels in women with silicone gel breast implants - Suzanne S. Teuber; Robert L. Saunders; Georges M. Halpern; Robert F. Brucker; Victor Conte; Brian D. Goldman; Edward E. Winger; W. Graham Wood; M. Eric Gershwin (Biological Trace Element Research, 1995)

A new genetically isolated population of theSaccharomyces sensu stricto complex from Brazil - Gennadi I. Naumov; Elena S. Naumova; Alen N. Hagler; Leda C. Mendona-Hagler; Edward J. Louis (Antonie van Leeuwenhoek, 1995)

High level production of potyvirus-like particles in insect cells infected with recombinant baculovirus - S. J. Edwards; M. B. Hayden; R. C. Hamilton; J. A. Haynes; I. T. Nisbet; M. N. Jagadish (Archives of Virology, 1994)

Border disease virus: delineation by monoclonal antibodies - D. J. Paton; J. J. Sands; S. Edwards (Archives of Virology, 1994)

Expression and characterisation of equine herpesvirus 1 glycoprotein H using a recombinant baculovirus - E. M. McGowan; M. B. Hayden; S. J. Edwards; D. Pye; D. N. Love; J. M. Whalley (Archives of Virology, 1994)

Structural and compositional analyses of the phycobilisomes of Synechococcus sp. PCC 7002. Analyses of the wild-type strain and a phycocyanin-less mutant constructed by interposon mutagenesis - Donald A. Bryant; Robert de Lorimier; Gerard Guglielmi; S. Edward Stevens (Archives of Microbiology, 1990)

Structure and mutation of a gene encoding a Mr 33000 phycocyanin-associated linker polypeptide - Robert de Lorimier; Gerard Guglielmi; Donald A. Bryant; S. Edward Stevens (Archives of Microbiology, 1990)

Deacetylation and further metabolism of the mercapturic acid of hexachloro-1,3-butadiene by rat kidney cytosol in vitro - Iona S. Pratt; Edward A. Lock (Archives of Toxicology, 1988)

The application of monoclonal antibody panels to characterize pestivirus isolates from ruminants in Great Britain - S. Edwards; J. J. Sands; J. W. Harkness (Archives of Virology, 1988)

Long-term effects of lactational zinc deficiency on bone mineral composition in rats fed a commercially modified Luecke diet - Curtiss D. Hunt; Edward S. Halas; Marilou J. Eberhardt (Biological Trace Element Research, 1988)

Genotoxic properties of municipal wastewaters in Ohio - John R. Meier; William F. Blazak; Edward S. Riccio; Barbara E. Stewart; Dolloff F. Bishop; Lyman W. Condie (Archives of Environmental Contamination and Toxicology, 1987)

The respiratory chain of the facultative thermophile, Bacillus coagulans - A. S. Ball; C. Edwards (Archives of Microbiology, 1986)

Development and use of a remote-controlled mitral valve - Jay S. Meisner; Srdjan Nikolić; Takako Tamura; Koichi Tamura; Robert W. M. Frater; Edward L. Yellin (Annals of Biomedical Engineering, 1986)

The expression of human glycerol-3-phosphate dehydrogenase in human/rodent somatic-cell hybrids - Yvonne Edwards; S. Lynn McMillan; Cay Kielty; Marie-Anne Shaw (Biochemical Genetics, 1985)

Bloodless evaluation of blood oxygenators - Sanjiv S. Shah; Edward F. Leonard (Annals of Biomedical Engineering, 1983)

Actin acetylation in Drosophila tissue culture cells - Edward M. Berger; Gerard Cox; Lee Weber; John S. Kenney (Biochemical Genetics, 1981)

A determination and estimation of trend in Maine’s fresh potato shipments - Alan S. Kezis; Edward F. Johnston; Peter Baldwin (American Journal of Potato Research, 1980)

Preferred packaging and storage location in relation to quality problems encountered by Northeast fresh potato consumers - Alan S. Kezis; Edward F. Johnston; Robert Faunce (American Journal of Potato Research, 1979)

Potassium hydroxide for peeling potatoes - P. Muneta; Wu-Wei Shen; S. Jennings; D. Everson; L. Edwards (American Journal of Potato Research, 1977)

Accidental persistent infection of cell lines by Newcastle disease virus, showing three unusual features ? Defective neuraminidase, temperature sensitivity and intranuclear inclusions - G. Fraser; Helen H. Edwards; M. S. McNulty; J. M. S. Ruben (Archives of Virology, 1976)

An intravascular test device for thromboresistant materials: Analysis and preliminary experimental evaluation - Eric F. Grabowski; Anne R. Derby; Robert M. Koffsky; Robert S. Litwak; Edward F. Leonard (Annals of Biomedical Engineering, 1975)

A morphologic study of FL cells infected with para-influenza 3 virus - S. M. Cohen; S. Bullivant; G. A. Edwards (Archives of Virology, 1962)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)

Drying potatoes for feed in a direct-fired, rotary drier. Economic feasibility of the process - Paul W. Edwards; A. Hoersch; C. S. Redfield; Roderick K. Eskew (American Journal of Potato Research, 1952)

Aphid control on potatoes - Edward S. Sylvester; John G. McLean (American Journal of Potato Research, 1949)